Adolescent with painful vesicular otitis and vertigo. - Conversano, Ester; Cozzi, Giorgio; Poropat, Federico; Di Mascio, Alberto; Salis, Simona; Grasso, Domenico Leonardo; Barbi, Egidio (Arch Dis Child Educ Pract Ed, 2019)

Antibodies reacting to mimotopes of Simian virus 40 large T antigen, the viral oncoprotein, in sera from children. - Mazzoni, Elisa; Frontini, Francesca; Rotondo, John Charles; Zanotta, Nunzia; Fioravanti, Arianna; Minelli, Francesca; Torreggiani, Elena; Campisciano, Giuseppina; Marcuzzi, Annalisa; Guerra, Giovanni; Tommasini, Alberto; Touzé, Antoine; et al. (J Cell Physiol, 2019)
Recent data indicate that the Simian virus 40 (SV40) infection appears to be transmitted in humans independently from early SV40-contaminated antipolio vaccines. Serum antibodies against SV40 large T antigen (Tag) were analyzed in children/adolescents and young adults. To investigate antibodies reacting to SV40 Tag antigens, serum samples ( n = 812) from children and young adults were analyzed by indirect ELISAs using specific SV40 Tag mimotopes. Mimotopes were synthetic peptides corresponding to SV40 Tag epitopes. In sera ( n = 412) from healthy children up to 17 years old, IgG antibodies against SV40 Tag mimotopes reached an overall prevalence of 15%. IgM antibodies against SV40 Tag were detected in sera of children 6-8 months old confirming and extending the knowledge that SV40 seroconversion occurs early in life. In children/adolescents affected by different diseases ( n = 180) SV40 Tag had a prevalence of 18%, being the difference no significant compared to healthy subjects ( n = 220; 16%) of the same age. Our immunological data indicate that SV40 circulates in children and young adults, both in healthy conditions and affected by distinct diseases. The IgM detection in sera from healthy children suggests that the SV40 infection/seroconversion occurs early in life (>6 months). Our immunological data support the hypothesis that SV40, or a closely related still unknown polyomavirus, infects humans. The SV40 seroprevalence is lower than common polyomaviruses, such as BKPyV and JCPyV, and other new human polyomaviruses. In addition, our immunological surveillance indicates a lack of association between different diseases, considered herein, and SV40.

Changing Epidemiology of Liver Involvement in Children With Celiac Disease. - Benelli, Elisa; Naviglio, Samuele; De Leo, Luigina; Stera, Giacomo; Giangreco, Manuela; Ronfani, Luca; Villanacci, Vincenzo; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Available data indicate that liver involvement is present in a significant proportion of children with celiac disease (CD) at the diagnosis (elevated transaminases 15%-57%, autoimmune liver disease 1%-2%). We sought to evaluate prevalence, clinical course, and risk factors for liver involvement in a large cohort of children with CD. METHODS: Children (age 0-18 years) diagnosed with CD from March 2010 to April 2016 were enrolled. Liver involvement was considered to be present when alanine transaminase (ALT) levels were >40 U/L (hypertransaminasemia [HTS]). Patients with HTS were re-evaluated after at least 12 months of a gluten-free diet. RESULTS: CD was diagnosed in 806 patients during the study period; of these, ALT levels were available for 700 patients (86.9%), and were elevated in 27 (3.9%, HTS group); median ALT and aspartate transaminase levels in the HTS group were 57 U/L (interquartile range 49-80 U/L) and 67 U/L (interquartile range 53-85 U/L), respectively. Younger age, malabsorption symptoms, and low hemoglobin or ferritin were significantly more common in the HTS group at univariate analysis. At multivariate analysis, only age ≤4.27 years correlated with risk of liver involvement (odds ratio 3.73; 95% confidence interval: 1.61-8.66). When retested on a gluten-free diet, all but 3 patients normalized ALT levels; of these, 1 was diagnosed with sclerosing cholangitis. CONCLUSIONS: Liver involvement in celiac children is now less frequent than previously reported, possibly due to changing CD epidemiology. Younger age is the only risk factor. Associated autoimmune liver disease is rare.

An evaluation of the Movement ABC-2 Test for use in Italy: A comparison of data from Italy and the UK. - Zoia, Stefania; Biancotto, Marina; Guicciardi, Marco; Lecis, Romina; Lucidi, Fabio; Pelamatti, Giovanna M; Carrozzi, Marco; Skabar, Aldo; Sugden, David A; Barnett, Anna L; Henderson, Sheila E (Res Dev Disabil, 2019)
BACKGROUND: The standardized test within the Movement Assessment Battery for Children-2nd edition (MABC-2) is used worldwide to assess motor problems in children. Ideally, any country using a test developed in another country should produce national norms to ensure that it functions effectively in the new context. AIM: The first objective of this study was to explore the differences in motor performance between Italian and British children. The second was to examine the structural validity of the test for the Italian sample. METHOD: A total of 718 Italian (IT) and 765 British (UK) children, aged 3-10 years, were individually tested on the age-appropriate items of the MABC-2 Test. RESULTS: Developmental trends emerged on every task and differences between IT and UK children were obtained on 11 of 27 task comparisons. Interactions between age and country indicated that differences were not consistently in favor of one culture. Confirmatory factor analysis generally supported the proposed structure of the MABC-2 Test. CONCLUSION: Although the differences between the IT and the UK children were relatively few, those that did emerge emphasize the need for population specific norms and suggest that cultural diversity in motor experiences should be considered when evaluating motor abilities in children.

Four-miRNA Signature to Identify Asbestos-Related Lung Malignancies. - Santarelli, Lory; Gaetani, Simona; Monaco, Federica; Bracci, Massimo; Valentino, Matteo; Amati, Monica; Rubini, Corrado; Sabbatini, Armando; Pasquini, Ernesto; Zanotta, Nunzia; Comar, Manola; Neuzil, Jiri; et al. (Cancer Epidemiol Biomarkers Prev, 2019)
BACKGROUND: Altered miRNA expression is an early event upon exposure to occupational/environmental carcinogens; thus, identification of a novel asbestos-related profile of miRNAs able to distinguish asbestos-induced cancer from cancer with different etiology can be useful for diagnosis. We therefore performed a study to identify miRNAs associated with asbestos-induced malignancies. METHODS: Four groups of patients were included in the study, including patients with asbestos-related (NSCLC) and asbestos-unrelated non-small cell lung cancer (NSCLC) or with malignant pleural mesothelioma (MPM), and disease-free subjects (CTRL). The selected miRNAs were evaluated in asbestos-exposed population. RESULTS: Four serum miRNAs, that is miR-126, miR-205, miR-222, and miR-520g, were found to be implicated in asbestos-related malignant diseases. Notably, increased expression of miR-126 and miR-222 were found in asbestos-exposed subjects, and both miRNAs are involved in major pathways linked to cancer development. Epigenetic changes and cancer-stroma cross-talk could induce repression of miR-126 to facilitate tumor formation, angiogenesis, and invasion. CONCLUSIONS: This study indicates that miRNAs are potentially involved in asbestos-related malignancies, and their expression outlines mechanism(s) whereby miRNAs may be involved in an asbestos-induced pathogenesis. IMPACT: The discovery of a miRNA panel for asbestos-related malignancies would impact on occupational compensation and may be utilized for screening asbestos-exposed populations.

Global, regional, and national burden of traumatic brain injury and spinal cord injury, 1990-2016: a systematic analysis for the Global Burden of Disease Study 2016. (Lancet Neurol, 2019)
BACKGROUND: Traumatic brain injury (TBI) and spinal cord injury (SCI) are increasingly recognised as global health priorities in view of the preventability of most injuries and the complex and expensive medical care they necessitate. We aimed to measure the incidence, prevalence, and years of life lived with disability (YLDs) for TBI and SCI from all causes of injury in every country, to describe how these measures have changed between 1990 and 2016, and to estimate the proportion of TBI and SCI cases caused by different types of injury. METHODS: We used results from the Global Burden of Diseases, Injuries, and Risk Factors (GBD) Study 2016 to measure the global, regional, and national burden of TBI and SCI by age and sex. We measured the incidence and prevalence of all causes of injury requiring medical care in inpatient and outpatient records, literature studies, and survey data. By use of clinical record data, we estimated the proportion of each cause of injury that required medical care that would result in TBI or SCI being considered as the nature of injury. We used literature studies to establish standardised mortality ratios and applied differential equations to convert incidence to prevalence of long-term disability. Finally, we applied GBD disability weights to calculate YLDs. We used a Bayesian meta-regression tool for epidemiological modelling, used cause-specific mortality rates for non-fatal estimation, and adjusted our results for disability experienced with comorbid conditions. We also analysed results on the basis of the Socio-demographic Index, a compound measure of income per capita, education, and fertility. FINDINGS: In 2016, there were 27·08 million (95% uncertainty interval [UI] 24·30-30·30 million) new cases of TBI and 0·93 million (0·78-1·16 million) new cases of SCI, with age-standardised incidence rates of 369 (331-412) per 100 000 population for TBI and 13 (11-16) per 100 000 for SCI. In 2016, the number of prevalent cases of TBI was 55·50 million (53·40-57·62 million) and of SCI was 27·04 million (24·98-30·15 million). From 1990 to 2016, the age-standardised prevalence of TBI increased by 8·4% (95% UI 7·7 to 9·2), whereas that of SCI did not change significantly (-0·2% [-2·1 to 2·7]). Age-standardised incidence rates increased by 3·6% (1·8 to 5·5) for TBI, but did not change significantly for SCI (-3·6% [-7·4 to 4·0]). TBI caused 8·1 million (95% UI 6·0-10·4 million) YLDs and SCI caused 9·5 million (6·7-12·4 million) YLDs in 2016, corresponding to age-standardised rates of 111 (82-141) per 100 000 for TBI and 130 (90-170) per 100 000 for SCI. Falls and road injuries were the leading causes of new cases of TBI and SCI in most regions. INTERPRETATION: TBI and SCI constitute a considerable portion of the global injury burden and are caused primarily by falls and road injuries. The increase in incidence of TBI over time might continue in view of increases in population density, population ageing, and increasing use of motor vehicles, motorcycles, and bicycles. The number of individuals living with SCI is expected to increase in view of population growth, which is concerning because of the specialised care that people with SCI can require. Our study was limited by data sparsity in some regions, and it will be important to invest greater resources in collection of data for TBI and SCI to improve the accuracy of future assessments. FUNDING: Bill & Melinda Gates Foundation.

Idiopathic neutropenia of infancy: Data from the Italian Neutropenia Registry. - Farruggia, Piero; Fioredda, Francesca; Puccio, Giuseppe; Onofrillo, Daniela; Russo, Giovanna; Barone, Angelica; Bonanomi, Sonia; Boscarol, Gianluca; Finocchi, Andrea; Ghilardi, Roberta; Giordano, Paola; Ladogana, Saverio; et al. (Am J Hematol, 2019)
Autoimmune neutropenia of infancy (AIN) is characterized by low risk of severe infection, tendency to spontaneously resolve and typically onset at ≤4-5 years of age; it is due to auto-antibodies whose detection is often difficult. In case of negativity of 4 antineutrophils autoantibody tests, after having excluded ethnic, postinfection, drug induced, or congenital neutropenia, according to the Italian guidelines the patients will be defined as affected by "idiopathic neutropenia" (IN). We describe the characteristics of 85 IN patients enrolled in the Italian neutropenia registry: they were compared with 336 children affected by AIN. The 2 groups were clinically very similar and the main differences were detection age (later in IN), length of disease (longer in IN) and, among recovered patients, age of spontaneous recovery: the median age at resolution was 2.13 years in AINs and 3.03 years in INs (P = .00002). At bivariate analysis among AIN patients earlier detection age (P = .00013), male sex (P = .000748), absence of leucopenia (P = .0045), and absence of monocytosis (P = .0419) were significantly associated with earlier recovery; in the IN group only detection age (P = .013) and absence of monocytosis (P = .0333) were significant. At multivariate analysis detection age and absence of monocytosis were independently significant (P = 6.7e-05 and 4.4e-03, respectively) in the AIN group, whereas in the IN group only detection age stayed significant (P = .013).

Loss-of-function mutations in cause a new form of inherited thrombocytopenia. - Marconi, Caterina; Di Buduo, Christian A; LeVine, Kellie; Barozzi, Serena; Faleschini, Michela; Bozzi, Valeria; Palombo, Flavia; McKinstry, Spencer; Lassandro, Giuseppe; Giordano, Paola; Noris, Patrizia; Balduini, Carlo L; et al. (Blood, 2019)
Inherited thrombocytopenias (ITs) are a heterogeneous group of disorders characterized by low platelet count that may result in bleeding tendency. Despite progress being made in defining the genetic causes of ITs, nearly 50% of patients with familial thrombocytopenia are affected with forms of unknown origin. Here, through exome sequencing of 2 siblings with autosomal-recessive thrombocytopenia, we identified biallelic loss-of-function variants in This gene encodes for a receptor-like PTP, PTPRJ (or CD148), which is expressed abundantly in platelets and megakaryocytes. Consistent with the predicted effects of the variants, both probands have an almost complete loss of PTPRJ at the messenger RNA and protein levels. To investigate the pathogenic role of PTPRJ deficiency in hematopoiesis in vivo, we carried out CRISPR/Cas9-mediated ablation of (the ortholog of human ) in zebrafish, which induced a significantly decreased number of CD41 thrombocytes in vivo. Moreover, megakaryocytes of our patients showed impaired maturation and profound defects in SDF1-driven migration and formation of proplatelets in vitro. Silencing of in a human megakaryocytic cell line reproduced the functional defects observed in patients' megakaryocytes. The disorder caused by mutations presented as a nonsyndromic thrombocytopenia characterized by spontaneous bleeding, small-sized platelets, and impaired platelet responses to the GPVI agonists collagen and convulxin. These platelet functional defects could be attributed to reduced activation of Src family kinases. Taken together, our data identify a new form of IT and highlight a hitherto unknown fundamental role for PTPRJ in platelet biogenesis.

Management of endometrial, ovarian and cervical cancer in the elderly: current approach to a challenging condition. - Vitale, Salvatore Giovanni; Capriglione, Stella; Zito, Gabriella; Lopez, Salvatore; Gulino, Ferdinando Antonio; Di Guardo, Federica; Vitagliano, Amerigo; Noventa, Marco; La Rosa, Valentina Lucia; Sapia, Fabrizio; Valenti, Gaetano; Rapisarda, Agnese Maria Chiara; et al. (Arch Gynecol Obstet, 2019)
PURPOSE: Gynaecological cancer management in older people represents a current challenge. Therefore, in the present paper, we aimed to gather all the evidence reported in the literature concerning gynecological cancers in the elderly, illustrating the state of art and the future perspectives. METHODS: We searched MEDLINE (PubMed), EMBASE, Cochrane Central Register of Controlled Trials, IBECS, BIOSIS, Web of Science, SCOPUS and Grey literature (Google Scholar; British Library) from January 1952 to May 2017, using the terms "ovarian cancer", "endometrial cancer", "cervical cancer", "gynecological cancers" combined with 'elderly', 'cancer', 'clinical trial' and 'geriatric assessment'. RESULTS: The search identified 81 citations, of which 65 were potentially relevant after initial evaluation and met the criteria for inclusion and were analyzed. We divided all included studies into three different issue: "Endometrial cancer", "Ovarian cancer" and "Cervical cancer". CONCLUSIONS: The present literature review shows that, in spite of the higher burden of comorbidities, elderly patients can also benefit from standard treatment to manage their gynecological cancers. It is important to overcome the common habit of undertreating the elderly patients because they are more fragile and with a lower life expectancy than their younger counterpart. Further trials with elderly women are warranted.

MYH9-Related Thrombocytopenia: Four Novel Variants Affecting the Tail Domain of the Non-Muscle Myosin Heavy Chain IIA Associated with a Mild Clinical Evolution of the Disorder. - Zaninetti, Carlo; De Rocco, Daniela; Giangregorio, Tania; Bozzi, Valeria; Demeter, Judit; Leoni, Pietro; Noris, Patrizia; Ryhänen, Samppa; Barozzi, Serena; Pecci, Alessandro; Savoia, Anna (Hamostaseologie, 2019)
-related disease (-RD) is an autosomal-dominant thrombocytopenia caused by mutations in the gene for non-muscle myosin heavy chain IIA (NMMHC-IIA). Patients present congenital macrothrombocytopenia and inclusions of NMMHC-IIA in leukocytes, and have a variable risk of developing kidney damage, sensorineural deafness, presenile cataracts and/or liver enzymes abnormalities. The spectrum of mutations found in -RD patients is limited and the incidence and severity of the non-congenital features are predicted by the causative variant. In particular, different alterations of the C-terminal tail domain of NMMHC-IIA associate with remarkably different disease evolution. We report four novel mutations affecting the tail domain of NMMHC-IIA and responsible for -RD in four families. Two variants cause amino acid substitutions in the coiled-coil region of NMMHC-IIA, while the other two are a splicing variant and a single nucleotide deletion both resulting in frameshift alterations of the short non-helical tailpiece. Characterization of phenotypes of affected individuals shows that all of these novel variants are associated with a mild clinical evolution of the disease.

Next-generation sequencing identified SPATC1L as a possible candidate gene for both early-onset and age-related hearing loss. - Morgan, Anna; Vuckovic, Dragana; Krishnamoorthy, Navaneethakrishnan; Rubinato, Elisa; Ambrosetti, Umberto; Castorina, Pierangela; Franzè, Annamaria; Vozzi, Diego; La Bianca, Martina; Cappellani, Stefania; Di Stazio, Mariateresa; Gasparini, Paolo; et al. (Eur J Hum Genet, 2019)
Hereditary hearing loss (HHL) and age-related hearing loss (ARHL) are two major sensory diseases affecting millions of people worldwide. Despite many efforts, additional HHL-genes and ARHL genetic risk factors still need to be identified. To fill this gap a large genomic screening based on next-generation sequencing technologies was performed. Whole exome sequencing in a 3-generation Italian HHL family and targeted re-sequencing in 464 ARHL patients were performed. We detected three variants in SPATC1L: a nonsense allele in an HHL family and a frameshift insertion and a missense variation in two unrelated ARHL patients. In silico molecular modelling of all variants suggested a significant impact on the structural stability of the protein itself, likely leading to deleterious effects and resulting in truncated isoforms. After demonstrating Spatc1l expression in mice inner ear, in vitro functional experiments were performed confirming the results of the molecular modelling studies. Finally, a candidate-gene population-based statistical study in cohorts from Caucasus and Central Asia revealed a statistically significant association of SPATC1L with normal hearing function at low and medium hearing frequencies. Overall, the amount of different genetic data presented here (variants with early-onset and late-onset hearing loss in addition to genetic association with normal hearing function), together with relevant functional evidence, likely suggest a role of SPATC1L in hearing function and loss.

Prevalence and phenotype of the c.1529C>T SPG7 variant in adult-onset cerebellar ataxia in Italy. - Mancini, C; Giorgio, E; Rubegni, A; Pradotto, L; Bagnoli, S; Rubino, E; Prontera, P; Cavalieri, S; Di Gregorio, E; Ferrero, M; Pozzi, E; Riberi, E; et al. (Eur J Neurol, 2019)
BACKGROUND AND PURPOSE: Hereditary ataxias are heterogeneous groups of neurodegenerative disorders, characterized by cerebellar syndromes associated with dysarthria, oculomotor and corticospinal signs, neuropathy and cognitive impairment. Recent reports have suggested mutations in the SPG7 gene, causing the most common form of autosomal recessive spastic paraplegia (MIM#607259), as a main cause of ataxias. The majority of described patients were homozygotes or compound heterozygotes for the c.1529C>T (p.Ala510Val) change. We screened a cohort of 895 Italian patients with ataxia for p.Ala510Val in order to define the prevalence and genotype-phenotype correlation of this variant. METHODS: We set up a rapid assay for c.1529C>T using restriction enzyme analysis after polymerase chain reaction amplification. We confirmed the diagnosis with Sanger sequencing. RESULTS: We identified eight homozygotes and 13 compound heterozygotes, including two novel variants affecting splicing. Mutated patients showed a pure cerebellar ataxia at onset, evolving in mild spastic ataxia (alternatively) associated with dysarthria (~80% of patients), urinary urgency (~30%) and pyramidal signs (~70%). Comparing homozygotes and compound heterozygotes, we noted a difference in age at onset and Scale for the Assessment and Rating of Ataxia score between the two groups, supporting an earlier and more severe phenotype in compound heterozygotes versus homozygotes. CONCLUSIONS: The SPG7 c.1529C>T (p.Ala510Val) mutants accounted for 2.3% of cerebellar ataxia cases in Italy, suggesting that this variant should be considered as a priority test in the presence of late-onset pure ataxia. Moreover, the heterozygous/homozygous genotype appeared to predict the onset of clinical manifestation and disease progression.

Retrospective study showed that palpitations with tachycardia on admission to a paediatric emergency department were related to cardiac arrhythmias. - Bobbo, Marco; Amoroso, Stefano; Tamaro, Gianluca; Gesuete, Valentina; D'agata Mottolese, Biancamaria; Barbi, Egidio; Ventura, Alessandro (Acta Paediatr, 2019)
AIM: This retrospective study reviewed the prevalence and long-term prognosis of children aged 0-18 with palpitations who were admitted to the emergency department (ED) of an Italian paediatric hospital. METHODS: We examined all admissions to the ED of the IRCCS Burlo Garofolo between January 2009 and December 2015 by selecting triage diagnoses of palpitations. The hospital discharge cards were reviewed to assess vital parameters, physical examinations, diagnostic tests, cardiology consultations and final diagnoses. RESULTS: Of the 142 803 patients who attended our ED for any reason, 96 (0.07%) complained of palpitations. Despite this low prevalence, it was noteworthy that 13.5% had a real underlying arrhythmic cause and needed medical assistance. Over half (52.1%) were women and the mean age was 12.7 years. At the long-term follow-up, at a mean of 47 ± 23 months, 53.8% of patients with a cardiac arrhythmia had received medical therapy and 46.1% had undergone trans-catheter ablation for supraventricular tachycardia. A heart rate above 146 beats per minute or palpitations for more than an hour was statistically related to a cardiac arrhythmia. CONCLUSION: Palpitations were an infrequent cause of admission to our ED, but 13.5% who displayed them had an underlying cardiac arrhythmia.

ACTN1 mutations lead to a benign form of platelet macrocytosis not always associated with thrombocytopenia. - Faleschini, Michela; Melazzini, Federica; Marconi, Caterina; Giangregorio, Tania; Pippucci, Tommaso; Cigalini, Elena; Pecci, Alessandro; Bottega, Roberta; Ramenghi, Ugo; Siitonen, Timo; Seri, Marco; Pastore, Annalisa; et al. (Br J Haematol, 2018)
The inherited thrombocytopenias (IT) are a heterogeneous group of diseases resulting from mutations in more than 30 different genes. Among them, ACTN1-related thrombocytopenia (ACTN1-RT; Online Mendelian Inheritance in Man: 615193) is one of the most recently identified forms. It has been described as a mild autosomal dominant macrothrombocytopenia caused by mutations in ACTN1, a gene encoding for one of the two non-muscle isoforms of α-actinin. We recently identified seven new unrelated families with ACTN1-RT caused by different mutations. Two of them are novel missense variants (p.Trp128Cys and p.Pro233Leu), whose pathogenic role has been confirmed by in vitro studies. Together with the 10 families we have previously described, our cohort of ACTN1-RT now consists of 49 individuals carrying ACTN1 mutations. This is the largest case series ever collected and enabled a critical evaluation of the clinical aspects of the disease. We concluded that ACTN1-RT is the fourth most frequent form of IT worldwide and it is characterized by platelet macrocytosis in all affected subjects and mild thrombocytopenia in less than 80% of cases. The risk of bleeding, either spontaneous or upon haemostatic challenge, is negligible and there are no other associated defects, either congenital or acquired. Therefore, ACTN1-RT is a benign form of IT, whose diagnosis provides affected individuals and their families with a good prognosis.

Acute small bowel obstruction in a child with a strict raw vegan diet. - Amoroso, Stefano; Scarpa, Maria-Grazia; Poropat, Federico; Giorgi, Rita; Murru, Flora Maria; Barbi, Egidio (Arch Dis Child, 2018)

Adenomyomatosis of the Gallbladder as a Cause of Recurrent Abdominal Pain. - Agrusti, Anna; Gregori, Massimo; Salviato, Tiziana; Codrich, Daniela; Barbi, Egidio (J Pediatr, 2018)
Keywords: Abdominal Pain; Adenomyoma; Adolescent; Biopsy, Needle; Cholecystectomy; Diagnosis, Differential; Female; Gallbladder; Gallbladder Neoplasms; Humans; Immunohistochemistry; Recurrence; Risk Assessment; Severity of Illness Index; Ultrasonography, Doppler

Afebrile seizures in infants: Never forget magnesium! - Minute, Marta; Ventura, Giovanna; Giorgi, Rita; Faletra, Flavio; Costa, Paola; Cozzi, Giorgio (J Paediatr Child Health, 2018)

Alcohol use and burden for 195 countries and territories, 1990-2016: a systematic analysis for the Global Burden of Disease Study 2016. (Lancet, 2018)
BACKGROUND: Alcohol use is a leading risk factor for death and disability, but its overall association with health remains complex given the possible protective effects of moderate alcohol consumption on some conditions. With our comprehensive approach to health accounting within the Global Burden of Diseases, Injuries, and Risk Factors Study 2016, we generated improved estimates of alcohol use and alcohol-attributable deaths and disability-adjusted life-years (DALYs) for 195 locations from 1990 to 2016, for both sexes and for 5-year age groups between the ages of 15 years and 95 years and older. METHODS: Using 694 data sources of individual and population-level alcohol consumption, along with 592 prospective and retrospective studies on the risk of alcohol use, we produced estimates of the prevalence of current drinking, abstention, the distribution of alcohol consumption among current drinkers in standard drinks daily (defined as 10 g of pure ethyl alcohol), and alcohol-attributable deaths and DALYs. We made several methodological improvements compared with previous estimates: first, we adjusted alcohol sales estimates to take into account tourist and unrecorded consumption; second, we did a new meta-analysis of relative risks for 23 health outcomes associated with alcohol use; and third, we developed a new method to quantify the level of alcohol consumption that minimises the overall risk to individual health. FINDINGS: Globally, alcohol use was the seventh leading risk factor for both deaths and DALYs in 2016, accounting for 2·2% (95% uncertainty interval [UI] 1·5-3·0) of age-standardised female deaths and 6·8% (5·8-8·0) of age-standardised male deaths. Among the population aged 15-49 years, alcohol use was the leading risk factor globally in 2016, with 3·8% (95% UI 3·2-4·3) of female deaths and 12·2% (10·8-13·6) of male deaths attributable to alcohol use. For the population aged 15-49 years, female attributable DALYs were 2·3% (95% UI 2·0-2·6) and male attributable DALYs were 8·9% (7·8-9·9). The three leading causes of attributable deaths in this age group were tuberculosis (1·4% [95% UI 1·0-1·7] of total deaths), road injuries (1·2% [0·7-1·9]), and self-harm (1·1% [0·6-1·5]). For populations aged 50 years and older, cancers accounted for a large proportion of total alcohol-attributable deaths in 2016, constituting 27·1% (95% UI 21·2-33·3) of total alcohol-attributable female deaths and 18·9% (15·3-22·6) of male deaths. The level of alcohol consumption that minimised harm across health outcomes was zero (95% UI 0·0-0·8) standard drinks per week. INTERPRETATION: Alcohol use is a leading risk factor for global disease burden and causes substantial health loss. We found that the risk of all-cause mortality, and of cancers specifically, rises with increasing levels of consumption, and the level of consumption that minimises health loss is zero. These results suggest that alcohol control policies might need to be revised worldwide, refocusing on efforts to lower overall population-level consumption. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Alcohol Drinking; Cause of Death; Commerce; Female; Global Burden of Disease; Global Health; Humans; Male; Middle Aged; Observational Studies as Topic; Population Surveillance; Prevalence; Prospective Studies; Quality-Adjusted Life Years; Retrospective Studies; Risk Assessment; Risk Factors; Sex Distribution; Young Adult

Are aortic coarctation and rheumatoid arthritis different models of aortic stiffness? Data from an echocardiographic study. - Faganello, Giorgio; Cioffi, Giovanni; Rossini, Maurizio; Ognibeni, Federica; Giollo, Alessandro; Fisicaro, Maurizio; Russo, Giulia; Di Nora, Concetta; Doimo, Sara; Tarantini, Luigi; Mazzone, Carmine; Cherubini, Antonella; et al. (Cardiovasc Ultrasound, 2018)
BACKGROUND: Patients who underwent a successful repair of the aortic coarctation (CoA) show high risk for cardiovascular (CV) events. Mechanical and structural abnormalities in the ascending aorta (Ao) might have a role in the prognosis of CoA patients. We analyzed the elastic properties of Ao measured as aortic stiffness index (AoSI) in CoA patients in the long-term period and we compared AoSI with a cohort of 38 patients with rheumatoid arthritis (RA) and 38 non-RA matched controls. METHODS: Data from 19 CoA patients were analyzed 28 ± 13 years after surgery. Abnormally high AoSI was diagnosed if AoSI > 6.07% (95th percentile of the AoSI detected in our reference healthy population). AoSI was assessed at the level of the aortic root by two-dimensional guided M-mode evaluation. RESULTS: CoA patients showed more than two-fold higher AoSI compared to RA and controls (9.8 ± 12.6 vs 4.8 ± 2.5% and 3.1 ± 2.0%, respectively; all p < 0.05 and in 5 of 19 patients with CoA (26%) AoSI was exceptionally high. The 5 patients with abnormally high AoSI were older with higher BP, LV mass and prevalence of LV diastolic dysfunction. Multiple linear regression analysis revealed that AoSI was independently related to the presence of LV hypertrophy and higher LV relative wall thickness. CONCLUSIONS: CoA patients have higher AoSI levels than RA patients and non-RA matched controls. AoSI levels are abnormally high in a small sub-group of CoA patients who show a very high-risk clinical profile for adverse CV events.
Keywords: Aorta; Aortic Coarctation; Arthritis, Rheumatoid; Humans; Prognosis; Vascular Stiffness

Bariatric surgery drives major rearrangements of the intestinal microbiota including the biofilm composition. - Campisciano, Giuseppina; Cason, Carolina; Palmisano, Silvia; Giuricin, Michela; Rizzardi, Alessia; Croce, Lory Saveria; De Manzini, Nicolo; Comar, Manola (Front Biosci (Elite Ed), 2018)
The intestinal microbiota disequilibrium has been associated with obesity, while the role of the gut mucosal biofilms in this pathology is still unknown. We analysed the changes in the intestinal microbiota of obese patients after bariatric surgery with the aim of disclosing the rearrangement of the biofilm configuration. Although the bariatric surgery drives major rearrangements of the gut microbiota, obese patients maintain the enterotype before and after surgery, as shown by normal weight patients, with an increase of and . The enterotype guarantees the strong ability to form a biofilm which allows a more efficient digestion of polysaccharides than planktonic communities and leads to the production of acetate which is a key player to inhibit enteropathogens. Additionally, the laparoscopic gastric bypass induces an increase of , a facultative anaerobic bacterium involved in intestinal and inflammatory disorders. Bariatric surgery influences the microbial composition of gut biofilm. Further studies are needed to elucidate the impact of this variation on recovery after surgery and on weight loss.
Keywords: Biofilms; Case-Control Studies; Gastric Bypass; Gastrointestinal Microbiome; Humans; Intestinal Mucosa; Obesity; Prospective Studies

Benign hereditary chorea and deletions outside NKX2-1: What's the role of MBIP? - Invernizzi, Federica; Zorzi, Giovanna; Legati, Andrea; Coppola, Giovanni; d'Adamo, Pio; Nardocci, Nardo; Garavaglia, Barbara; Ghezzi, Daniele (Eur J Med Genet, 2018)
Heterozygous point mutations or deletions of the NKX2-1 gene cause benign hereditary chorea (BHC) or a various combinations of primary hypothyroidism, respiratory distress and neurological disorders. Deletions proximal to, but not encompassing, NKX2-1 have been described in few subjects with brain-lung-thyroid syndrome. We report on a three-generation Italian family, with 6 subjects presenting BHC and harboring a genomic deletion adjacent to NKX2-1 and including the gene MBIP, recently proposed to be relevant for the pathogenesis of brain-lung-thyroid syndrome. We observed a clear reduction of NKX2-1 transcript levels in fibroblasts from our patients compared to controls; this finding suggests that MBIP deletion affects NKX2-1 expression, mimicking haploinsufficiency caused by classical NKX2-1 related mutations.
Keywords: Cells, Cultured; Chorea; Haploinsufficiency; Humans; Intracellular Signaling Peptides and Proteins; Pedigree; Sequence Deletion; Thyroid Nuclear Factor 1

Cervical-length measurement in mid-gestation to predict spontaneous preterm birth in asymptomatic triplet pregnancy. - Fichera, A; Pagani, G; Stagnati, V; Cascella, S; Faiola, S; Gaini, C; Lanna, M; Pasquini, L; Raffaelli, R; Stampalija, T; Tommasini, A; Prefumo, F (Ultrasound Obstet Gynecol, 2018)
OBJECTIVE: To assess the predictive value of sonographic cervical-length (CL) measurement in mid-gestation for spontaneous preterm birth (PTB) in asymptomatic triplet pregnancy. METHODS: This was a retrospective study of asymptomatic triplet pregnancies followed at five Italian tertiary referral centers, between 2002 and 2015. CL was measured transvaginally between 18 and 24 weeks' gestation. Pregnancies with medically indicated PTB were excluded. Demographic and pregnancy characteristics of pregnancies complicated by PTB were analyzed and the distributions of CL measurements in these patients were calculated. Logistic regression analysis was performed to assess the association between CL and PTB, adjusted for confounders. Performance of CL measurement in prediction of PTB < 28, < 30 and < 32 weeks of gestation was assessed. RESULTS: A total of 120 triplet pregnancies were included in the final analysis. Median CL was 35 (interquartile range (IQR), 29-40) mm measured at a median gestational age of 20 + 2 (IQR, 20 + 0 to 23 + 4) weeks. Overall, 23 (19.2%), 17 (14.2%) and eight (6.7%) patients had a CL < 25, < 20 and < 15 mm, respectively. Spontaneous PTB < 32 weeks occurred in 41 (34.2%) cases, < 30 weeks in 23 (19.2%) and < 28 weeks in 12 (10%) cases. CL < 15 mm was significantly more frequent in the group of patients who delivered < 28 (P = 0.03) and < 30 (P = 0.01) weeks' gestation, compared with those who delivered after 28 and after 30 weeks, respectively, while CL < 20 mm was more common in triplet pregnancies with delivery < 32 weeks compared with those delivered ≥ 32 weeks (P = 0.03). Logistic regression analysis was possible only for PTB < 32 weeks due to the small number of cases that delivered < 30 and < 28 weeks. After adjustment for confounders, CL was not significantly associated with PTB < 32 weeks (adjusted odds ratio, 0.97; 95% CI, 0.94-1.01). CL measurement had an area under the receiver-operating characteristics curve of 0.41 (95% CI, 0.20-0.62), 0.41 (95% CI, 0.26-0.56) and 0.42 (95% CI, 0.31-0.54) for the prediction of spontaneous PTB < 28, < 30 and < 32 weeks, respectively. CONCLUSION: CL assessed in mid-gestation is a poor predictor of PTB < 28, < 30 and < 32 weeks' gestation in asymptomatic triplet pregnancy. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cervical Length Measurement; Female; Gestational Age; Humans; Infant, Newborn; Logistic Models; Predictive Value of Tests; Pregnancy; Pregnancy, Triplet; Premature Birth; Retrospective Studies

A Child with Diminished Linear Growth and Waddling Gait. - Tamaro, Gianluca; Pederiva, Federica; Dibello, Daniela; Gregori, Massimo; Carbone, Marco; Pantaleoni, Francesca; Dentici, Maria Lisa; Niceta, Marcello; Barbi, Egidio (J Pediatr, 2018)
Keywords: Abnormalities, Multiple; Child; Dwarfism; Female; Gait; Humans; Osteochondrodysplasias; Radiography

Complete Remission of a Refractory Acute Myeloid Leukemia with Myelodysplastic- and Monosomy 7-Related Changes after a Combined Conditioning Regimen of Plerixafor, Cytarabine and Melphalan in a 4-Year-Old Boy: A Case Report and Review of Literature. - Grasso, Antonio G; Granzotto, Marilena; Zanon, Davide; Maestro, Alessandra; Loiacono, Stefano; Maximova, Natalia (Cancers (Basel), 2018)
Acute myeloid leukemia with myelodysplastic changes and monosomy 7 is a rare form of pediatric leukemia associated with very poor disease-free survival. The refractoriness of the disease is due to the protection offered by the bone marrow niche, making leukemic stem cells impervious to whatever chemotherapy or myeloablative regimen is chosen. Using a mobilizing agent for haematopoietic stem cells, Plerixafor, could sensitise leukemic cells to the myeloablative therapy. This approach was not previously used in a pediatric population, and in adult populations, was used in combination with busulphan with no difference in overall survival. We describe the case of a 4-year-old boy affected by refractory acute myeloid leukemia with myelodysplastic changes and monosomy 7. The child had never achieved a remission. We proposed a combined time-scheduled scheme of therapy with plerixafor and melphalan. Combining pharmacokinetics of plerixafor with pharmacokinetics and rapid and elevated myeloablative potential of melphalan in high dosage (200 mg/m²), we succeeded in mobilizing more than 85% of stem blasts immediately before infusion of Melphalan. The count of residual blasts after 8 h from melphalan infusion was only 1.3 cells/μL. The child achieved an engraftment at day +32 with full donor chimerism. Sixteen months after haematopoietic stem cell transplantation (HSCT), he is well and in complete remission. Our case suggests that the use of plerixafor before a conditioning therapy with melphalan could induce remission in acute myeloid leukemia refractory to the usual conditioning therapy in pediatric patients. This work adds strength to the body of knowledge regarding the "personalized" conditioning regimen for high-risk leukemic patients.

Cx26 partial loss causes accelerated presbycusis by redox imbalance and dysregulation of Nfr2 pathway. - Fetoni, Anna Rita; Zorzi, Veronica; Paciello, Fabiola; Ziraldo, Gaia; Peres, Chiara; Raspa, Marcello; Scavizzi, Ferdinando; Salvatore, Anna Maria; Crispino, Giulia; Tognola, Gabriella; Gentile, Giulia; Spampinato, Antonio Gianmaria; et al. (Redox Biol, 2018)
Mutations in GJB2, the gene that encodes connexin 26 (Cx26), are the most common cause of sensorineural hearing impairment. The truncating variant 35delG, which determines a complete loss of Cx26 protein function, is the prevalent GJB2 mutation in several populations. Here, we generated and analyzed Gjb2 mice as a model of heterozygous human carriers of 35delG. Compared to control mice, auditory brainstem responses (ABRs) and distortion product otoacoustic emissions (DPOAEs) worsened over time more rapidly in Gjb2 mice, indicating they were affected by accelerated age-related hearing loss (ARHL), or presbycusis. We linked causally the auditory phenotype of Gjb2 mice to apoptosis and oxidative damage in the cochlear duct, reduced release of glutathione from connexin hemichannels, decreased nutrient delivery to the sensory epithelium via cochlear gap junctions and deregulated expression of genes that are under transcriptional control of the nuclear factor erythroid 2-related factor 2 (Nrf2), a pivotal regulator of tolerance to redox stress. Moreover, a statistically significant genome-wide association with two genes (PRKCE and TGFB1) related to the Nrf2 pathway (p-value < 4 × 10) was detected in a very large cohort of 4091 individuals, originating from Europe, Caucasus and Central Asia, with hearing phenotype (including 1076 presbycusis patients and 1290 healthy matched controls). We conclude that (i) elements of the Nrf2 pathway are essential for hearing maintenance and (ii) their dysfunction may play an important role in the etiopathogenesis of human presbycusis.
Keywords: Animals; Apoptosis; Connexin 26; Female; Gene Deletion; Male; Mice; Mice, Inbred C57BL; NF-E2-Related Factor 2; Oxidation-Reduction; Presbycusis; Signal Transduction

De novo unbalanced translocations have a complex history/aetiology. - Bonaglia, Maria Clara; Kurtas, Nehir Edibe; Errichiello, Edoardo; Bertuzzo, Sara; Beri, Silvana; Mehrjouy, Mana M; Provenzano, Aldesia; Vergani, Debora; Pecile, Vanna; Novara, Francesca; Reho, Paolo; Di Giacomo, Marilena Carmela; et al. (Hum Genet, 2018)
We investigated 52 cases of de novo unbalanced translocations, consisting in a terminally deleted or inverted-duplicated deleted (inv-dup del) 46th chromosome to which the distal portion of another chromosome or its opposite end was transposed. Array CGH, whole-genome sequencing, qPCR, FISH, and trio genotyping were applied. A biparental origin of the deletion and duplication was detected in 6 cases, whereas in 46, both imbalances have the same parental origin. Moreover, the duplicated region was of maternal origin in more than half of the cases, with 25% of them showing two maternal and one paternal haplotype. In all these cases, maternal age was increased. These findings indicate that the primary driver for the occurrence of the de novo unbalanced translocations is a maternal meiotic non-disjunction, followed by partial trisomy rescue of the supernumerary chromosome present in the trisomic zygote. In contrast, asymmetric breakage of a dicentric chromosome, originated either at the meiosis or postzygotically, in which the two resulting chromosomes, one being deleted and the other one inv-dup del, are repaired by telomere capture, appears at the basis of all inv-dup del translocations. Notably, this mechanism also fits with the origin of some simple translocations in which the duplicated region was of paternal origin. In all cases, the signature at the translocation junctions was that of non-homologous end joining (NHEJ) rather than non-allelic homologous recombination (NAHR). Our data imply that there is no risk of recurrence in the following pregnancies for any of the de novo unbalanced translocations we discuss here.
Keywords: DNA End-Joining Repair; Female; Humans; Male; Meiosis; Recombinational DNA Repair; Translocation, Genetic

Efficacy and Safety of Adalimumab in Pediatric Ulcerative Colitis: A Real-life Experience from the SIGENP-IBD Registry. - Aloi, Marina; Bramuzzo, Matteo; Arrigo, Serena; Romano, Claudio; D'Arcangelo, Giulia; Lacorte, Doriana; Gatti, Simona; Illiceto, Maria T; Zucconi, Francesca; Dilillo, Dario; Zuin, Giovanna; Knafelz, Daniela; et al. (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: The aim of this study was to evaluate the effectiveness and safety of adalimumab (ADA) in children with ulcerative colitis (UC) previously treated with infliximab (IFX). METHODS: Retrospective study including children with UC from a national registry who received ADA therapy. The primary endpoint was the rate of corticosteroid-free remission at week 52. Secondary outcomes were the rate of sustained clinical remission, primary nonresponse, and loss of response at weeks 12, 30, and 52 and rate of mucosal healing and side effects at week 52. RESULTS: Thirty-two children received ADA (median age 10 ± 4 years). Median disease duration before ADA therapy was 27 months. All patients received previous IFX (43% intolerant, 50% nonresponders [37.5% primary, 42.5% secondary nonresponders], 6.7% positive anti-IFX antibodies). Fifty-two weeks after ADA initiation, 13 patients (41%) were in corticosteroid-free remission. Mucosal healing occurred in 9 patients (28%) at 52 weeks. The cumulative probability of a clinical relapse-free course was 69%, 59%, and 53% at 12, 30, and 52 weeks, respectively. Ten patients (31%) had a primary failure and 5 (15%) a loss of response to ADA. No significant differences in efficacy were reported between not-responders and intolerant to IFX (P = 1.0). Overall, 19 patient (59%) maintained ADA during 52-week follow-up. Seven patients (22%) experienced an adverse event, no serious side effects were observed and none resulted in ADA discontinuation. CONCLUSIONS: Based on our data, ADA seems to be effective in children with UC, allowing to recover a significant percentage of patients intolerant or not-responding to IFX. The safety profile was good.

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.
Keywords: ADAMTS Proteins; African Continental Ancestry Group; Animals; Connexin 43; Electrocardiography; European Continental Ancestry Group; Exome; Female; Gene Expression; Gene Expression Profiling; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Mice; Middle Aged; Myocardium; Open Reading Frames; Polymorphism, Single Nucleotide; Whole Exome Sequencing

Ferruginous bodies resolved by synchrotron XRF in a dog with peritoneal malignant mesothelioma. - Pascotto, Ernesto; Gianoncelli, Alessandra; Calligaro, Carla; Marcuzzo, Thomas; Melato, Mauro; Rizzardi, Clara; Pascolo, Lorella (Environ Sci Pollut Res Int, 2018)
Mesothelioma is a malignant tumor mainly correlated to occupational asbestos exposure. Rare reports describe its occurrence also in animals, mainly linked to asbestos in the environment. Asbestos exposure is demonstrated by the appearance of characteristic histological hallmarks: asbestos containing ferruginous bodies that are iron-based structures forming around fibers and also other dust particles. Here we present a clinical case of a suspect of mesothelioma in the peritoneum of a dog with parallel histological observation of ferruginous bodies. To possibly correlate the dog tumor to environmental exposure, we performed X-ray fluorescence (XRF) analyses at two different synchrotrons to resolve the ferruginous bodies' composition. While the histological examination diagnoses a tubulo-papillary mesothelioma, the XRF analyses show that ferruginous bodies contain Si particles, resembling formations of exogenous origin; however, the morphology is unlikely that of asbestos fibers. We speculate that the peritoneal mesothelioma of this dog could be related to environmental exposure to non-asbestos material.
Keywords: Animals; Asbestos; Dogs; Environmental Exposure; Immunohistochemistry; Iron; Lung; Lung Neoplasms; Male; Mesothelioma; Peritoneal Neoplasms; Silicon; Spectrometry, X-Ray Emission; Synchrotrons

Flares After Withdrawal of Biologic Therapies in Juvenile Idiopathic Arthritis: Clinical and Laboratory Correlates of Remission Duration. - Simonini, Gabriele; Ferrara, Giovanna; Pontikaki, Irene; Scoccimarro, Erika; Giani, Teresa; Taddio, Andrea; Meroni, Pier Luigi; Cimaz, Rolando (Arthritis Care Res (Hoboken), 2018)
OBJECTIVE: To assess the time in remission after discontinuing biologic therapy in patients with juvenile idiopathic arthritis (JIA). METHODS: We enrolled 135 patients followed in 3 tertiary-care centers. The primary outcome was to assess, once remission was achieved, the time in remission up to the first flare after discontinuing treatment. Mann-Whitney U test, Wilcoxon's signed rank test for paired samples, chi-square tests, and Fisher's exact test were used to compare data. Pearson's and Spearman's correlation tests were used to determine correlation coefficients for different variables. To identify predictors of outcome, Cox regression model and Kaplan-Meier curves were constructed, each one at the mean of entered covariates. RESULTS: The majority of enrolled patients flared after stopping treatment with biologics (102 of 135, 75.6%) after a median followup time in remission off therapy of 6 months (range 3-109 months). A higher probability of maintaining remission after discontinuing treatment was present in systemic-onset disease compared to the rest of the JIA patients (Mantel-Cox χ = 8.31, P < 0.004). In analysis limited to children with JIA with polyarticular and oligoarticular disease, patients who received biologics >2 years after achieving remission had a higher probability of maintaining such remission off therapy (mean ± SD 18.64 ± 3.3 months versus 11.51 ± 2.7 months [P < 0.009]; Mantel-Cox χ = 9.06, P < 0.002). No other clinical variable was significantly associated with a long-lasting remission. CONCLUSION: Children with oligoarticular and polyarticular JIA who stop treatment before 2 years from remission have a higher chance of relapsing after biologic withdrawal.

Fractional CO laser for genitourinary syndrome of menopause in breast cancer survivors: clinical, immunological, and microbiological aspects. - Becorpi, Angelamaria; Campisciano, Giuseppina; Zanotta, Nunzia; Tredici, Zelinda; Guaschino, Secondo; Petraglia, Felice; Pieralli, Annalisa; Sisti, Giovanni; De Seta, Francesco; Comar, Manola (Lasers Med Sci, 2018)
The composition of vaginal microbiome in menopause and cancer survivor women changes dramatically leading to genitourinary syndrome of menopause (GSM) in up to 70% of patients. Recent reports suggest that laser therapy may be valuable as a not hormonal therapeutic modality. The aim of the present study was to evaluate the effects of fractional CO laser treatment on the vaginal secretory pathway of a large panel of immune mediators, usually implicated in tissue remodeling and inflammation, and on microbiome composition in postmenopausal breast cancer survivors. The Ion Torrent PGM platform and the Luminex Bio-Plex platform were used for microbiome and immune factor analysis. The significant reduction of clinical symptoms and the non-significant changes in vaginal microbiome support the efficacy and safety of laser treatment. Moreover, the high remodeling status in vaginal epithelium is demonstrated by the significant changes in inflammatory and modulatory cytokine patterns. Laser therapy can be used for the treatment of GSM symptoms and does not show any adverse effects. However, further studies will be needed to clarify its long-term efficacy and other effects.
Keywords: Breast Neoplasms; Cancer Survivors; Cytokines; Dyspareunia; Female; Humans; Lasers, Gas; Menopause; Microbiota; Middle Aged; Prospective Studies; Syndrome; Vagina; Vaginal Diseases

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genetic profile of patients with early onset inflammatory bowel disease. - Girardelli, Martina; Basaldella, Federica; Paolera, Sara Della; Vuch, Josef; Tommasini, Alberto; Martelossi, Stefano; Crovella, Sergio; Bianco, Anna Monica (Gene, 2018)
Inflammatory Bowel disease (IBD) is a widespread pathological condition with clinical heterogeneity and with different levels of severity. Although IBD usually occurs in young adults, onset in childhood and infancy are described in patients within the 10th and second year of age. By genome-wide association studies and meta-analysis, several genetic loci have been identified associated with an increased risk of developing IBD in Western populations with variants that may alter the normal mucosal immunity in the gastrointestinal tract. The clinical complexity and the heterogeneity of the IBD phenotype probably reflect the presence of genetic heterogeneity where different genes or combinations of them may be involved, together with environmental factors. We hypothesized that patients with early onset IBD could have either more severe genetic variants in genes associated with IBD or multiple variants in different genes. Under the multifactorial diseases is crucial to consider the small contribution of a single variant in all not only to other small variations in the same gene but also in different genes belonging to the same pathway. We performed direct gene sequencing looking for 94 variations in NOD2, ATG16L1, IL23R, IL10R, IL10 and XIAP genes previously shown as correlated with IBD both in multifactorial and in Mendelian models. All variants identified are known in literature as being associated with IBD except for three variants in the genes NOD2, IL10 and IL10RB that even though present in online databases have never been involved in association studies on IBD patients. Moreover, we coupled genetic variants identification with an accurate "in silico" analysis to verify their predictive impact on the protein structure and function. The in-silico prediction of these variants results as benign therefore even if they exhibit a very low frequency in control population being benign, they cannot be considered pathogenic as monogenic disease but fall within the multifactorial range. The variants identified in our study partially reflect the association data described in the literature but there are no significant differences with the onset of disease (VEO vs EO-IBD).
Keywords: Age of Onset; Autophagy-Related Proteins; Child; Child, Preschool; Computer Simulation; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Infant; Inflammatory Bowel Diseases; Interleukin-10; Male; Nod2 Signaling Adaptor Protein; Polymorphism, Single Nucleotide; Receptors, Interleukin; Receptors, Interleukin-10; Sequence Analysis, DNA; X-Linked Inhibitor of Apoptosis Protein

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide association meta-analysis highlights light-induced signaling as a driver for refractive error. - Tedja, Milly S; Wojciechowski, Robert; Hysi, Pirro G; Eriksson, Nicholas; Furlotte, Nicholas A; Verhoeven, Virginie J M; Iglesias, Adriana I; Meester-Smoor, Magda A; Tompson, Stuart W; Fan, Qiao; Khawaja, Anthony P; Cheng, Ching-Yu; et al. (Nat Genet, 2018)
Refractive errors, including myopia, are the most frequent eye disorders worldwide and an increasingly common cause of blindness. This genome-wide association meta-analysis in 160,420 participants and replication in 95,505 participants increased the number of established independent signals from 37 to 161 and showed high genetic correlation between Europeans and Asians (>0.78). Expression experiments and comprehensive in silico analyses identified retinal cell physiology and light processing as prominent mechanisms, and also identified functional contributions to refractive-error development in all cell types of the neurosensory retina, retinal pigment epithelium, vascular endothelium and extracellular matrix. Newly identified genes implicate novel mechanisms such as rod-and-cone bipolar synaptic neurotransmission, anterior-segment morphology and angiogenesis. Thirty-one loci resided in or near regions transcribing small RNAs, thus suggesting a role for post-transcriptional regulation. Our results support the notion that refractive errors are caused by a light-dependent retina-to-sclera signaling cascade and delineate potential pathobiological molecular drivers.

Genome-wide association meta-analysis of individuals of European ancestry identifies new loci explaining a substantial fraction of hair color variation and heritability. - Hysi, Pirro G; Valdes, Ana M; Liu, Fan; Furlotte, Nicholas A; Evans, David M; Bataille, Veronique; Visconti, Alessia; Hemani, Gibran; McMahon, George; Ring, Susan M; Smith, George Davey; Duffy, David L; et al. (Nat Genet, 2018)
Hair color is one of the most recognizable visual traits in European populations and is under strong genetic control. Here we report the results of a genome-wide association study meta-analysis of almost 300,000 participants of European descent. We identified 123 autosomal and one X-chromosome loci significantly associated with hair color; all but 13 are novel. Collectively, single-nucleotide polymorphisms associated with hair color within these loci explain 34.6% of red hair, 24.8% of blond hair, and 26.1% of black hair heritability in the study populations. These results confirm the polygenic nature of complex phenotypes and improve our understanding of melanin pigment metabolism in humans.

A genome-wide association study identifies an association between variants in EFCAB4B gene and periodontal disease in an Italian isolated population. - Bevilacqua, Lorenzo; Navarra, Chiara O; Pirastu, Nicola; Lenarda, Roberto Di; Gasparini, Paolo; Robino, Antonietta (J Periodontal Res, 2018)
BACKGROUND AND OBJECTIVE: Periodontitis in one of the most prevalent dental diseases. Despite numerous studies have investigated its aetiopathogenetic factors, few works have focused on its genetic predisposition and most of them took into account only candidate genes. Therefore, we conducted a Genome Wide Association Study in an Italian isolated population aimed at uncovering genetic variants that predispose to this disorder. METHODS: Diagnosis of chronic periodontitis was made following the criteria of the American Academy of Periodontology. Patients with chronic periodontitis were grouped into different categories: slight, severe, localized and generalized. A control group composed by people without signs of periodontitis or gingivitis was defined. DNA was genotyped using 370k Illumina chips. Linear mixed model regression was used to test the association between each single nucleotide polymorphism (SNP) (independent variable) and the periodontitis status (dependent variable), controlling for confounders sex, age and smoking. The genomic kinship matrix was also used as random effect. RESULTS: Four SNPs on the gene EFCAB4B resulted significantly associated to localized periodontitis (P < 5 × 10 ), with the best hit on the rs242016 SNP (P = 1.5 × 10 ). CONCLUSION: We have identified a novel significant association between the EFCAB4B gene and localized periodontitis. These results open a new perspective in the understanding of genetic factors contributing to this common disorder.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Calcium-Binding Proteins; Chronic Periodontitis; DNA; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Young Adult

A genome-wide association study of corneal astigmatism: The CREAM Consortium. - Shah, Rupal L; Li, Qing; Zhao, Wanting; Tedja, Milly S; Tideman, J Willem L; Khawaja, Anthony P; Fan, Qiao; Yazar, Seyhan; Williams, Katie M; Verhoeven, Virginie J M; Xie, Jing; Wang, Ya Xing; et al. (Mol Vis, 2018)
Purpose: To identify genes and genetic markers associated with corneal astigmatism. Methods: A meta-analysis of genome-wide association studies (GWASs) of corneal astigmatism undertaken for 14 European ancestry (n=22,250) and 8 Asian ancestry (n=9,120) cohorts was performed by the Consortium for Refractive Error and Myopia. Cases were defined as having >0.75 diopters of corneal astigmatism. Subsequent gene-based and gene-set analyses of the meta-analyzed results of European ancestry cohorts were performed using VEGAS2 and MAGMA software. Additionally, estimates of single nucleotide polymorphism (SNP)-based heritability for corneal and refractive astigmatism and the spherical equivalent were calculated for Europeans using LD score regression. Results: The meta-analysis of all cohorts identified a genome-wide significant locus near the platelet-derived growth factor receptor alpha () gene: top SNP: rs7673984, odds ratio=1.12 (95% CI:1.08-1.16), p=5.55×10. No other genome-wide significant loci were identified in the combined analysis or European/Asian ancestry-specific analyses. Gene-based analysis identified three novel candidate genes for corneal astigmatism in Europeans-claudin-7 (), acid phosphatase 2, lysosomal (), and TNF alpha-induced protein 8 like 3 (). Conclusions: In addition to replicating a previously identified genome-wide significant locus for corneal astigmatism near the gene, gene-based analysis identified three novel candidate genes, , , and , that warrant further investigation to understand their role in the pathogenesis of corneal astigmatism. The much lower number of genetic variants and genes demonstrating an association with corneal astigmatism compared to published spherical equivalent GWAS analyses suggest a greater influence of rare genetic variants, non-additive genetic effects, or environmental factors in the development of astigmatism.
Keywords: Acid Phosphatase; Asian Continental Ancestry Group; Astigmatism; Claudins; Cohort Studies; Cornea; Corneal Diseases; European Continental Ancestry Group; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Odds Ratio; Polymorphism, Single Nucleotide; Receptor, Platelet-Derived Growth Factor alpha; Software

Global, regional, and national age-sex-specific mortality and life expectancy, 1950-2017: a systematic analysis for the Global Burden of Disease Study 2017. (Lancet, 2018)
BACKGROUND: Assessments of age-specific mortality and life expectancy have been done by the UN Population Division, Department of Economics and Social Affairs (UNPOP), the United States Census Bureau, WHO, and as part of previous iterations of the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD). Previous iterations of the GBD used population estimates from UNPOP, which were not derived in a way that was internally consistent with the estimates of the numbers of deaths in the GBD. The present iteration of the GBD, GBD 2017, improves on previous assessments and provides timely estimates of the mortality experience of populations globally. METHODS: The GBD uses all available data to produce estimates of mortality rates between 1950 and 2017 for 23 age groups, both sexes, and 918 locations, including 195 countries and territories and subnational locations for 16 countries. Data used include vital registration systems, sample registration systems, household surveys (complete birth histories, summary birth histories, sibling histories), censuses (summary birth histories, household deaths), and Demographic Surveillance Sites. In total, this analysis used 8259 data sources. Estimates of the probability of death between birth and the age of 5 years and between ages 15 and 60 years are generated and then input into a model life table system to produce complete life tables for all locations and years. Fatal discontinuities and mortality due to HIV/AIDS are analysed separately and then incorporated into the estimation. We analyse the relationship between age-specific mortality and development status using the Socio-demographic Index, a composite measure based on fertility under the age of 25 years, education, and income. There are four main methodological improvements in GBD 2017 compared with GBD 2016: 622 additional data sources have been incorporated; new estimates of population, generated by the GBD study, are used; statistical methods used in different components of the analysis have been further standardised and improved; and the analysis has been extended backwards in time by two decades to start in 1950. FINDINGS: Globally, 18·7% (95% uncertainty interval 18·4-19·0) of deaths were registered in 1950 and that proportion has been steadily increasing since, with 58·8% (58·2-59·3) of all deaths being registered in 2015. At the global level, between 1950 and 2017, life expectancy increased from 48·1 years (46·5-49·6) to 70·5 years (70·1-70·8) for men and from 52·9 years (51·7-54·0) to 75·6 years (75·3-75·9) for women. Despite this overall progress, there remains substantial variation in life expectancy at birth in 2017, which ranges from 49·1 years (46·5-51·7) for men in the Central African Republic to 87·6 years (86·9-88·1) among women in Singapore. The greatest progress across age groups was for children younger than 5 years; under-5 mortality dropped from 216·0 deaths (196·3-238·1) per 1000 livebirths in 1950 to 38·9 deaths (35·6-42·83) per 1000 livebirths in 2017, with huge reductions across countries. Nevertheless, there were still 5·4 million (5·2-5·6) deaths among children younger than 5 years in the world in 2017. Progress has been less pronounced and more variable for adults, especially for adult males, who had stagnant or increasing mortality rates in several countries. The gap between male and female life expectancy between 1950 and 2017, while relatively stable at the global level, shows distinctive patterns across super-regions and has consistently been the largest in central Europe, eastern Europe, and central Asia, and smallest in south Asia. Performance was also variable across countries and time in observed mortality rates compared with those expected on the basis of development. INTERPRETATION: This analysis of age-sex-specific mortality shows that there are remarkably complex patterns in population mortality across countries. The findings of this study highlight global successes, such as the large decline in under-5 mortality, which reflects significant local, national, and global commitment and investment over several decades. However, they also bring attention to mortality patterns that are a cause for concern, particularly among adult men and, to a lesser extent, women, whose mortality rates have stagnated in many countries over the time period of this study, and in some cases are increasing. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Female; Global Burden of Disease; Global Health; Humans; Infant; Infant, Newborn; Life Expectancy; Male; Middle Aged; Mortality; Sex Distribution; Socioeconomic Factors; Young Adult

Global, regional, and national age-sex-specific mortality for 282 causes of death in 195 countries and territories, 1980-2017: a systematic analysis for the Global Burden of Disease Study 2017. (Lancet, 2018)
BACKGROUND: Global development goals increasingly rely on country-specific estimates for benchmarking a nation's progress. To meet this need, the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2016 estimated global, regional, national, and, for selected locations, subnational cause-specific mortality beginning in the year 1980. Here we report an update to that study, making use of newly available data and improved methods. GBD 2017 provides a comprehensive assessment of cause-specific mortality for 282 causes in 195 countries and territories from 1980 to 2017. METHODS: The causes of death database is composed of vital registration (VR), verbal autopsy (VA), registry, survey, police, and surveillance data. GBD 2017 added ten VA studies, 127 country-years of VR data, 502 cancer-registry country-years, and an additional surveillance country-year. Expansions of the GBD cause of death hierarchy resulted in 18 additional causes estimated for GBD 2017. Newly available data led to subnational estimates for five additional countries-Ethiopia, Iran, New Zealand, Norway, and Russia. Deaths assigned International Classification of Diseases (ICD) codes for non-specific, implausible, or intermediate causes of death were reassigned to underlying causes by redistribution algorithms that were incorporated into uncertainty estimation. We used statistical modelling tools developed for GBD, including the Cause of Death Ensemble model (CODEm), to generate cause fractions and cause-specific death rates for each location, year, age, and sex. Instead of using UN estimates as in previous versions, GBD 2017 independently estimated population size and fertility rate for all locations. Years of life lost (YLLs) were then calculated as the sum of each death multiplied by the standard life expectancy at each age. All rates reported here are age-standardised. FINDINGS: At the broadest grouping of causes of death (Level 1), non-communicable diseases (NCDs) comprised the greatest fraction of deaths, contributing to 73·4% (95% uncertainty interval [UI] 72·5-74·1) of total deaths in 2017, while communicable, maternal, neonatal, and nutritional (CMNN) causes accounted for 18·6% (17·9-19·6), and injuries 8·0% (7·7-8·2). Total numbers of deaths from NCD causes increased from 2007 to 2017 by 22·7% (21·5-23·9), representing an additional 7·61 million (7·20-8·01) deaths estimated in 2017 versus 2007. The death rate from NCDs decreased globally by 7·9% (7·0-8·8). The number of deaths for CMNN causes decreased by 22·2% (20·0-24·0) and the death rate by 31·8% (30·1-33·3). Total deaths from injuries increased by 2·3% (0·5-4·0) between 2007 and 2017, and the death rate from injuries decreased by 13·7% (12·2-15·1) to 57·9 deaths (55·9-59·2) per 100 000 in 2017. Deaths from substance use disorders also increased, rising from 284 000 deaths (268 000-289 000) globally in 2007 to 352 000 (334 000-363 000) in 2017. Between 2007 and 2017, total deaths from conflict and terrorism increased by 118·0% (88·8-148·6). A greater reduction in total deaths and death rates was observed for some CMNN causes among children younger than 5 years than for older adults, such as a 36·4% (32·2-40·6) reduction in deaths from lower respiratory infections for children younger than 5 years compared with a 33·6% (31·2-36·1) increase in adults older than 70 years. Globally, the number of deaths was greater for men than for women at most ages in 2017, except at ages older than 85 years. Trends in global YLLs reflect an epidemiological transition, with decreases in total YLLs from enteric infections, respiratory infections and tuberculosis, and maternal and neonatal disorders between 1990 and 2017; these were generally greater in magnitude at the lowest levels of the Socio-demographic Index (SDI). At the same time, there were large increases in YLLs from neoplasms and cardiovascular diseases. YLL rates decreased across the five leading Level 2 causes in all SDI quintiles. The leading causes of YLLs in 1990-neonatal disorders, lower respiratory infections, and diarrhoeal diseases-were ranked second, fourth, and fifth, in 2017. Meanwhile, estimated YLLs increased for ischaemic heart disease (ranked first in 2017) and stroke (ranked third), even though YLL rates decreased. Population growth contributed to increased total deaths across the 20 leading Level 2 causes of mortality between 2007 and 2017. Decreases in the cause-specific mortality rate reduced the effect of population growth for all but three causes: substance use disorders, neurological disorders, and skin and subcutaneous diseases. INTERPRETATION: Improvements in global health have been unevenly distributed among populations. Deaths due to injuries, substance use disorders, armed conflict and terrorism, neoplasms, and cardiovascular disease are expanding threats to global health. For causes of death such as lower respiratory and enteric infections, more rapid progress occurred for children than for the oldest adults, and there is continuing disparity in mortality rates by sex across age groups. Reductions in the death rate of some common diseases are themselves slowing or have ceased, primarily for NCDs, and the death rate for selected causes has increased in the past decade. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Cause of Death; Child; Child, Preschool; Female; Global Burden of Disease; Global Health; Humans; Infant; Infant, Newborn; Life Expectancy; Male; Middle Aged; Sex Distribution; Socioeconomic Factors; Young Adult

Global, regional, and national burden of meningitis, 1990-2016: a systematic analysis for the Global Burden of Disease Study 2016. (Lancet Neurol, 2018)
BACKGROUND: Acute meningitis has a high case-fatality rate and survivors can have severe lifelong disability. We aimed to provide a comprehensive assessment of the levels and trends of global meningitis burden that could help to guide introduction, continuation, and ongoing development of vaccines and treatment programmes. METHODS: The Global Burden of Diseases, Injuries, and Risk Factors (GBD) 2016 study estimated meningitis burden due to one of four types of cause: pneumococcal, meningococcal, Haemophilus influenzae type b, and a residual category of other causes. Cause-specific mortality estimates were generated via cause of death ensemble modelling of vital registration and verbal autopsy data that were subject to standardised data processing algorithms. Deaths were multiplied by the GBD standard life expectancy at age of death to estimate years of life lost, the mortality component of disability-adjusted life-years (DALYs). A systematic analysis of relevant publications and hospital and claims data was used to estimate meningitis incidence via a Bayesian meta-regression tool. Meningitis deaths and cases were split between causes with meta-regressions of aetiological proportions of mortality and incidence, respectively. Probabilities of long-term impairment by cause of meningitis were applied to survivors and used to estimate years of life lived with disability (YLDs). We assessed the relationship between burden metrics and Socio-demographic Index (SDI), a composite measure of development based on fertility, income, and education. FINDINGS: Global meningitis deaths decreased by 21·0% from 1990 to 2016, from 403 012 (95% uncertainty interval [UI] 319 426-458 514) to 318 400 (265 218-408 705). Incident cases globally increased from 2·50 million (95% UI 2·19-2·91) in 1990 to 2·82 million (2·46-3·31) in 2016. Meningitis mortality and incidence were closely related to SDI. The highest mortality rates and incidence rates were found in the peri-Sahelian countries that comprise the African meningitis belt, with six of the ten countries with the largest number of cases and deaths being located within this region. Haemophilus influenzae type b was the most common cause of incident meningitis in 1990, at 780 070 cases (95% UI 613 585-978 219) globally, but decreased the most (-49·1%) to become the least common cause in 2016, with 397 297 cases (291 076-533 662). Meningococcus was the leading cause of meningitis mortality in 1990 (192 833 deaths [95% UI 153 358-221 503] globally), whereas other meningitis was the leading cause for both deaths (136 423 [112 682-178 022]) and incident cases (1·25 million [1·06-1·49]) in 2016. Pneumococcus caused the largest number of YLDs (634 458 [444 787-839 749]) in 2016, owing to its more severe long-term effects on survivors. Globally in 2016, 1·48 million (1·04-1·96) YLDs were due to meningitis compared with 21·87 million (18·20-28·28) DALYs, indicating that the contribution of mortality to meningitis burden is far greater than the contribution of disabling outcomes. INTERPRETATION: Meningitis burden remains high and progress lags substantially behind that of other vaccine-preventable diseases. Particular attention should be given to developing vaccines with broader coverage against the causes of meningitis, making these vaccines affordable in the most affected countries, improving vaccine uptake, improving access to low-cost diagnostics and therapeutics, and improving support for disabled survivors. Substantial uncertainty remains around pathogenic causes and risk factors for meningitis. Ongoing, active cause-specific surveillance of meningitis is crucial to continue and to improve monitoring of meningitis burdens and trends throughout the world. FUNDING: Bill & Melinda Gates Foundation.

Global, regional, and national comparative risk assessment of 84 behavioural, environmental and occupational, and metabolic risks or clusters of risks for 195 countries and territories, 1990-2017: a systematic analysis for the Global Burden of Disease Stu (Lancet, 2018)
BACKGROUND: The Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2017 comparative risk assessment (CRA) is a comprehensive approach to risk factor quantification that offers a useful tool for synthesising evidence on risks and risk-outcome associations. With each annual GBD study, we update the GBD CRA to incorporate improved methods, new risks and risk-outcome pairs, and new data on risk exposure levels and risk-outcome associations. METHODS: We used the CRA framework developed for previous iterations of GBD to estimate levels and trends in exposure, attributable deaths, and attributable disability-adjusted life-years (DALYs), by age group, sex, year, and location for 84 behavioural, environmental and occupational, and metabolic risks or groups of risks from 1990 to 2017. This study included 476 risk-outcome pairs that met the GBD study criteria for convincing or probable evidence of causation. We extracted relative risk and exposure estimates from 46 749 randomised controlled trials, cohort studies, household surveys, census data, satellite data, and other sources. We used statistical models to pool data, adjust for bias, and incorporate covariates. Using the counterfactual scenario of theoretical minimum risk exposure level (TMREL), we estimated the portion of deaths and DALYs that could be attributed to a given risk. We explored the relationship between development and risk exposure by modelling the relationship between the Socio-demographic Index (SDI) and risk-weighted exposure prevalence and estimated expected levels of exposure and risk-attributable burden by SDI. Finally, we explored temporal changes in risk-attributable DALYs by decomposing those changes into six main component drivers of change as follows: (1) population growth; (2) changes in population age structures; (3) changes in exposure to environmental and occupational risks; (4) changes in exposure to behavioural risks; (5) changes in exposure to metabolic risks; and (6) changes due to all other factors, approximated as the risk-deleted death and DALY rates, where the risk-deleted rate is the rate that would be observed had we reduced the exposure levels to the TMREL for all risk factors included in GBD 2017. FINDINGS: In 2017, 34·1 million (95% uncertainty interval [UI] 33·3-35·0) deaths and 1·21 billion (1·14-1·28) DALYs were attributable to GBD risk factors. Globally, 61·0% (59·6-62·4) of deaths and 48·3% (46·3-50·2) of DALYs were attributed to the GBD 2017 risk factors. When ranked by risk-attributable DALYs, high systolic blood pressure (SBP) was the leading risk factor, accounting for 10·4 million (9·39-11·5) deaths and 218 million (198-237) DALYs, followed by smoking (7·10 million [6·83-7·37] deaths and 182 million [173-193] DALYs), high fasting plasma glucose (6·53 million [5·23-8·23] deaths and 171 million [144-201] DALYs), high body-mass index (BMI; 4·72 million [2·99-6·70] deaths and 148 million [98·6-202] DALYs), and short gestation for birthweight (1·43 million [1·36-1·51] deaths and 139 million [131-147] DALYs). In total, risk-attributable DALYs declined by 4·9% (3·3-6·5) between 2007 and 2017. In the absence of demographic changes (ie, population growth and ageing), changes in risk exposure and risk-deleted DALYs would have led to a 23·5% decline in DALYs during that period. Conversely, in the absence of changes in risk exposure and risk-deleted DALYs, demographic changes would have led to an 18·6% increase in DALYs during that period. The ratios of observed risk exposure levels to exposure levels expected based on SDI (O/E ratios) increased globally for unsafe drinking water and household air pollution between 1990 and 2017. This result suggests that development is occurring more rapidly than are changes in the underlying risk structure in a population. Conversely, nearly universal declines in O/E ratios for smoking and alcohol use indicate that, for a given SDI, exposure to these risks is declining. In 2017, the leading Level 4 risk factor for age-standardised DALY rates was high SBP in four super-regions: central Europe, eastern Europe, and central Asia; north Africa and Middle East; south Asia; and southeast Asia, east Asia, and Oceania. The leading risk factor in the high-income super-region was smoking, in Latin America and Caribbean was high BMI, and in sub-Saharan Africa was unsafe sex. O/E ratios for unsafe sex in sub-Saharan Africa were notably high, and those for alcohol use in north Africa and the Middle East were notably low. INTERPRETATION: By quantifying levels and trends in exposures to risk factors and the resulting disease burden, this assessment offers insight into where past policy and programme efforts might have been successful and highlights current priorities for public health action. Decreases in behavioural, environmental, and occupational risks have largely offset the effects of population growth and ageing, in relation to trends in absolute burden. Conversely, the combination of increasing metabolic risks and population ageing will probably continue to drive the increasing trends in non-communicable diseases at the global level, which presents both a public health challenge and opportunity. We see considerable spatiotemporal heterogeneity in levels of risk exposure and risk-attributable burden. Although levels of development underlie some of this heterogeneity, O/E ratios show risks for which countries are overperforming or underperforming relative to their level of development. As such, these ratios provide a benchmarking tool to help to focus local decision making. Our findings reinforce the importance of both risk exposure monitoring and epidemiological research to assess causal connections between risks and health outcomes, and they highlight the usefulness of the GBD study in synthesising data to draw comprehensive and robust conclusions that help to inform good policy and strategic health planning. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Disabled Persons; Environmental Exposure; Female; Global Burden of Disease; Global Health; Health Risk Behaviors; Humans; Infant; Infant, Newborn; Life Expectancy; Male; Metabolic Diseases; Middle Aged; Occupational Diseases; Occupational Exposure; Quality-Adjusted Life Years; Risk Assessment; Sex Distribution; Socioeconomic Factors; Young Adult

Global, regional, and national disability-adjusted life-years (DALYs) for 359 diseases and injuries and healthy life expectancy (HALE) for 195 countries and territories, 1990-2017: a systematic analysis for the Global Burden of Disease Study 2017. (Lancet, 2018)
BACKGROUND: How long one lives, how many years of life are spent in good and poor health, and how the population's state of health and leading causes of disability change over time all have implications for policy, planning, and provision of services. We comparatively assessed the patterns and trends of healthy life expectancy (HALE), which quantifies the number of years of life expected to be lived in good health, and the complementary measure of disability-adjusted life-years (DALYs), a composite measure of disease burden capturing both premature mortality and prevalence and severity of ill health, for 359 diseases and injuries for 195 countries and territories over the past 28 years. METHODS: We used data for age-specific mortality rates, years of life lost (YLLs) due to premature mortality, and years lived with disability (YLDs) from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2017 to calculate HALE and DALYs from 1990 to 2017. We calculated HALE using age-specific mortality rates and YLDs per capita for each location, age, sex, and year. We calculated DALYs for 359 causes as the sum of YLLs and YLDs. We assessed how observed HALE and DALYs differed by country and sex from expected trends based on Socio-demographic Index (SDI). We also analysed HALE by decomposing years of life gained into years spent in good health and in poor health, between 1990 and 2017, and extra years lived by females compared with males. FINDINGS: Globally, from 1990 to 2017, life expectancy at birth increased by 7·4 years (95% uncertainty interval 7·1-7·8), from 65·6 years (65·3-65·8) in 1990 to 73·0 years (72·7-73·3) in 2017. The increase in years of life varied from 5·1 years (5·0-5·3) in high SDI countries to 12·0 years (11·3-12·8) in low SDI countries. Of the additional years of life expected at birth, 26·3% (20·1-33·1) were expected to be spent in poor health in high SDI countries compared with 11·7% (8·8-15·1) in low-middle SDI countries. HALE at birth increased by 6·3 years (5·9-6·7), from 57·0 years (54·6-59·1) in 1990 to 63·3 years (60·5-65·7) in 2017. The increase varied from 3·8 years (3·4-4·1) in high SDI countries to 10·5 years (9·8-11·2) in low SDI countries. Even larger variations in HALE than these were observed between countries, ranging from 1·0 year (0·4-1·7) in Saint Vincent and the Grenadines (62·4 years [59·9-64·7] in 1990 to 63·5 years [60·9-65·8] in 2017) to 23·7 years (21·9-25·6) in Eritrea (30·7 years [28·9-32·2] in 1990 to 54·4 years [51·5-57·1] in 2017). In most countries, the increase in HALE was smaller than the increase in overall life expectancy, indicating more years lived in poor health. In 180 of 195 countries and territories, females were expected to live longer than males in 2017, with extra years lived varying from 1·4 years (0·6-2·3) in Algeria to 11·9 years (10·9-12·9) in Ukraine. Of the extra years gained, the proportion spent in poor health varied largely across countries, with less than 20% of additional years spent in poor health in Bosnia and Herzegovina, Burundi, and Slovakia, whereas in Bahrain all the extra years were spent in poor health. In 2017, the highest estimate of HALE at birth was in Singapore for both females (75·8 years [72·4-78·7]) and males (72·6 years [69·8-75·0]) and the lowest estimates were in Central African Republic (47·0 years [43·7-50·2] for females and 42·8 years [40·1-45·6] for males). Globally, in 2017, the five leading causes of DALYs were neonatal disorders, ischaemic heart disease, stroke, lower respiratory infections, and chronic obstructive pulmonary disease. Between 1990 and 2017, age-standardised DALY rates decreased by 41·3% (38·8-43·5) for communicable diseases and by 49·8% (47·9-51·6) for neonatal disorders. For non-communicable diseases, global DALYs increased by 40·1% (36·8-43·0), although age-standardised DALY rates decreased by 18·1% (16·0-20·2). INTERPRETATION: With increasing life expectancy in most countries, the question of whether the additional years of life gained are spent in good health or poor health has been increasingly relevant because of the potential policy implications, such as health-care provisions and extending retirement ages. In some locations, a large proportion of those additional years are spent in poor health. Large inequalities in HALE and disease burden exist across countries in different SDI quintiles and between sexes. The burden of disabling conditions has serious implications for health system planning and health-related expenditures. Despite the progress made in reducing the burden of communicable diseases and neonatal disorders in low SDI countries, the speed of this progress could be increased by scaling up proven interventions. The global trends among non-communicable diseases indicate that more effort is needed to maximise HALE, such as risk prevention and attention to upstream determinants of health. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Aged; Communicable Diseases; Disabled Persons; Female; Global Burden of Disease; Health Status; Healthy Lifestyle; Humans; Life Expectancy; Male; Mortality; Mortality, Premature; Prevalence; Quality-Adjusted Life Years; Risk Factors; Socioeconomic Factors; Wounds and Injuries

Global, regional, and national incidence, prevalence, and years lived with disability for 354 diseases and injuries for 195 countries and territories, 1990-2017: a systematic analysis for the Global Burden of Disease Study 2017. (Lancet, 2018)
BACKGROUND: The Global Burden of Diseases, Injuries, and Risk Factors Study 2017 (GBD 2017) includes a comprehensive assessment of incidence, prevalence, and years lived with disability (YLDs) for 354 causes in 195 countries and territories from 1990 to 2017. Previous GBD studies have shown how the decline of mortality rates from 1990 to 2016 has led to an increase in life expectancy, an ageing global population, and an expansion of the non-fatal burden of disease and injury. These studies have also shown how a substantial portion of the world's population experiences non-fatal health loss with considerable heterogeneity among different causes, locations, ages, and sexes. Ongoing objectives of the GBD study include increasing the level of estimation detail, improving analytical strategies, and increasing the amount of high-quality data. METHODS: We estimated incidence and prevalence for 354 diseases and injuries and 3484 sequelae. We used an updated and extensive body of literature studies, survey data, surveillance data, inpatient admission records, outpatient visit records, and health insurance claims, and additionally used results from cause of death models to inform estimates using a total of 68 781 data sources. Newly available clinical data from India, Iran, Japan, Jordan, Nepal, China, Brazil, Norway, and Italy were incorporated, as well as updated claims data from the USA and new claims data from Taiwan (province of China) and Singapore. We used DisMod-MR 2.1, a Bayesian meta-regression tool, as the main method of estimation, ensuring consistency between rates of incidence, prevalence, remission, and cause of death for each condition. YLDs were estimated as the product of a prevalence estimate and a disability weight for health states of each mutually exclusive sequela, adjusted for comorbidity. We updated the Socio-demographic Index (SDI), a summary development indicator of income per capita, years of schooling, and total fertility rate. Additionally, we calculated differences between male and female YLDs to identify divergent trends across sexes. GBD 2017 complies with the Guidelines for Accurate and Transparent Health Estimates Reporting. FINDINGS: Globally, for females, the causes with the greatest age-standardised prevalence were oral disorders, headache disorders, and haemoglobinopathies and haemolytic anaemias in both 1990 and 2017. For males, the causes with the greatest age-standardised prevalence were oral disorders, headache disorders, and tuberculosis including latent tuberculosis infection in both 1990 and 2017. In terms of YLDs, low back pain, headache disorders, and dietary iron deficiency were the leading Level 3 causes of YLD counts in 1990, whereas low back pain, headache disorders, and depressive disorders were the leading causes in 2017 for both sexes combined. All-cause age-standardised YLD rates decreased by 3·9% (95% uncertainty interval [UI] 3·1-4·6) from 1990 to 2017; however, the all-age YLD rate increased by 7·2% (6·0-8·4) while the total sum of global YLDs increased from 562 million (421-723) to 853 million (642-1100). The increases for males and females were similar, with increases in all-age YLD rates of 7·9% (6·6-9·2) for males and 6·5% (5·4-7·7) for females. We found significant differences between males and females in terms of age-standardised prevalence estimates for multiple causes. The causes with the greatest relative differences between sexes in 2017 included substance use disorders (3018 cases [95% UI 2782-3252] per 100 000 in males vs s1400 [1279-1524] per 100 000 in females), transport injuries (3322 [3082-3583] vs 2336 [2154-2535]), and self-harm and interpersonal violence (3265 [2943-3630] vs 5643 [5057-6302]). INTERPRETATION: Global all-cause age-standardised YLD rates have improved only slightly over a period spanning nearly three decades. However, the magnitude of the non-fatal disease burden has expanded globally, with increasing numbers of people who have a wide spectrum of conditions. A subset of conditions has remained globally pervasive since 1990, whereas other conditions have displayed more dynamic trends, with different ages, sexes, and geographies across the globe experiencing varying burdens and trends of health loss. This study emphasises how global improvements in premature mortality for select conditions have led to older populations with complex and potentially expensive diseases, yet also highlights global achievements in certain domains of disease and injury. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Disabled Persons; Female; Global Burden of Disease; Global Health; Humans; Incidence; Infant; Infant, Newborn; Life Expectancy; Male; Middle Aged; Morbidity; Prevalence; Sex Distribution; Socioeconomic Factors; Wounds and Injuries; Young Adult

Gut microbiota characterisation in obese patients before and after bariatric surgery. - Campisciano, G; Palmisano, S; Cason, C; Giuricin, M; Silvestri, M; Guerra, M; Macor, D; De Manzini, N; Crocé, L S; Comar, M (Benef Microbes, 2018)
Intestinal microbiota analysis of obese patients after bariatric surgery showed that Proteobacteria decreased after laparoscopic sleeve gastrectomy (SG), while it increased after laparoscopic gastric bypass (LGB). Comparing to normal weight (NW) patients, obese patients that were selected for SG showed an almost equal amount of Firmicutes and Bacteroidetes and the ratio was not affected by the surgery. Obese patients before LGB showed a predominance of Bacteroidetes, whose amount regained a relative abundance similar to NW patients after surgery. Obese patients before LGB showed the predominance of Bacteroides, which decreased after surgery in favour of Prevotella, a bacterium associated with a healthy diet. The bacteria detected at the highest percentages belonged to biofilm forming species. In conclusion, in this study, we found that the characterization of the gut microbial communities and the modality of mucosal colonisation have a central role as markers for the clinical management of obesity and promote the maintenance of good health and the weight loss.
Keywords: Adult; Bariatric Surgery; Gastrointestinal Microbiome; Humans; Laparoscopy; Microbiota; Middle Aged; Obesity; Young Adult

High-Throughput Sequencing of microRNAs in Glucocorticoid Sensitive Paediatric Inflammatory Bowel Disease Patients. - De Iudicibus, Sara; Lucafò, Marianna; Vitulo, Nicola; Martelossi, Stefano; Zimbello, Rosanna; De Pascale, Fabio; Forcato, Claudio; Naviglio, Samuele; Di Silvestre, Alessia; Gerdol, Marco; Stocco, Gabriele; Valle, Giorgio; et al. (Int J Mol Sci, 2018)
The aim of this research was the identification of novel pharmacogenomic biomarkers for better understanding the complex gene regulation mechanisms underpinning glucocorticoid (GC) action in paediatric inflammatory bowel disease (IBD). This goal was achieved by evaluating high-throughput microRNA (miRNA) profiles during GC treatment, integrated with the assessment of expression changes in GC receptor (GR) heterocomplex genes. Furthermore, we tested the hypothesis that differentially expressed miRNAs could be directly regulated by GCs through investigating the presence of GC responsive elements (GREs) in their gene promoters. Ten IBD paediatric patients responding to GCs were enrolled. Peripheral blood was obtained at diagnosis (T0) and after four weeks of steroid treatment (T4). MicroRNA profiles were analyzed using next generation sequencing, and selected significantly differentially expressed miRNAs were validated by quantitative reverse transcription-polymerase chain reaction. In detail, 18 miRNAs were differentially expressed from T0 to T4, 16 of which were upregulated and 2 of which were downregulated. Out of these, three miRNAs (miR-144, miR-142, and miR-96) could putatively recognize the 3’UTR of the GR gene and three miRNAs (miR-363, miR-96, miR-142) contained GREs sequences, thereby potentially enabling direct regulation by the GR. In conclusion, we identified miRNAs differently expressed during GC treatment and miRNAs which could be directly regulated by GCs in blood cells of young IBD patients. These results could represent a first step towards their translation as pharmacogenomic biomarkers.
Keywords: Adolescent; Biomarkers; Child; Female; Gene Expression Regulation; Glucocorticoids; High-Throughput Nucleotide Sequencing; Humans; Inflammatory Bowel Diseases; Male; MicroRNAs; Receptors, Glucocorticoid; Transcriptome

How to predict response to anti-tumour necrosis factor agents in inflammatory bowel disease. - Naviglio, Samuele; Giuffrida, Paolo; Stocco, Gabriele; Lenti, Marco Vincenzo; Ventura, Alessandro; Corazza, Gino Roberto; Di Sabatino, Antonio (Expert Rev Gastroenterol Hepatol, 2018)
INTRODUCTION: Anti-tumor necrosis factor (TNF) agents have changed the therapeutic approach to inflammatory bowel disease (IBD). However, a considerable proportion of patients either do not primarily respond or lose response to treatment. Despite the long-standing experience in the use of these drugs, still there is the need of identifying the possible predictors of efficacy. Areas covered: We critically review the current knowledge on predictors of response to anti-TNF therapy - both those available in clinical practice and those still under investigation. Multiple factors are involved in treatment success, including disease phenotype and severity, adherence to medications, and pharmacogenomic, pharmacokinetic, and immunologic factors. Literature search was conducted in PubMed using keywords 'inflammatory bowel disease,' 'Crohn's disease,' and 'ulcerative colitis,' matched with 'antitumor necrosis factor,' 'biologic therapy,' 'clinical response,' 'predictors,' and 'efficacy,' Relevant articles were selected for review. Expert commentary: While the role of several factors in clinical practice is clearly established, other investigational markers have been proposed, mostly in small studies, yet for many of them little external validation exists. Therapeutic drug monitoring is emerging as a pivotal strategy to guide decisions in clinical practice. In the near future, novel markers could improve our ability to direct treatment and personalize therapy.
Keywords: Antibodies, Monoclonal; Biological Therapy; Gastrointestinal Agents; Humans; Inflammatory Bowel Diseases; Patient Selection; Prognosis; Treatment Outcome; Tumor Necrosis Factor-alpha

Human beta defensin-1 is involved in the susceptibility to adeno-tonsillar hypertrophy. - Zupin, Luisa; Celsi, Fulvio; Bresciani, Martina; Orzan, Eva; Grasso, Domenico Leonardo; Crovella, Sergio (Int J Pediatr Otorhinolaryngol, 2018)
INTRODUCTION: Innate immunity molecules are known to play a pivotal role in the homeostasis of the oral mucosa, permitting the presence of commensal microflora and, at the same time, providing a first line of defense against pathogens attempting to invade the oral cavity. Tonsils represent the local immune tissue in oral cavity, being able to provide a non-specific response to pathogens; however, in the presence of microbes or foreign materials present in the mouth tonsils could became infected and develop chronic inflammation, thus leading to hypertrophy. The etiology of the disease is multifactorial depending upon environmental and host factors, the latter including molecules of mucosal innate immunity. METHODS: Ninety-five children with adeno-tonsillar hypertrophy subjected to adeno-tonsillectomy were recruited at the pediatric otorhinolaryngology service of the Institute for Maternal and Child Health IRCCS Burlo Garofolo, Trieste (Italy). The specimen discarded from the surgery were used for genomic DNA extraction and genotyping, for mRNA extraction and gene expression analysis, finally the samples were cut and used to prepare slides to perform immunohistochemistry. RESULTS: Functional polymorphisms within DEFB1 gene, encoding the human beta defensin-1 (hBD-1), were analyzed finding association between DEFB1 rare haplotypes and susceptibility to adeno-tonsillar hypertrophy. DEFB1 mRNA expression was detected in the tonsils and the hBD-1 protein was localized at the epithelia of tonsils mainly in the proximity of the basal lamina. CONCLUSION: Our findings lead us to hypothesize an involvement of hBD-1 mediated innate immunity in the modulation of the susceptibility towards adeno-tonsillar hypertrophy development.
Keywords: Adenoidectomy; Adenoids; Adolescent; beta-Defensins; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Hypertrophy; Immunity, Innate; Immunohistochemistry; Italy; Male; Palatine Tonsil; Tonsillectomy

Immunohistologic analysis of the duodenal bulb: a new method for celiac disease diagnosis in children. - De Leo, Luigina; Villanacci, Vincenzo; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Di Leo, Grazia; Zanchi, Chiara; Bramuzzo, Matteo; Giudici, Fabiola; Ventura, Alessandro; Not, Tarcisio (Gastrointest Endosc, 2018)
BACKGROUND AND AIMS: Anti-tissue transglutaminase antibodies (anti-tTG) have simplified celiac disease (CD) diagnosis. However, in atypical forms of CD, intestinal biopsy sampling is still required. This prospective study investigates whether histologic analysis of the duodenal bulb combined with intestinal IgA anti-tTG deposit immunoassay makes CD diagnosis possible in at-risk children with low concentrations of serum anti-tTG. METHODS: Histologic and intestinal IgA anti-tTG deposit immunoassays were used. RESULTS: Two hundred forty-five symptomatic children positive for serum anti-tTG (>7 U/mL) were enrolled and divided into 3 groups: extensive duodenal atrophy (n = 209), with IgA anti-tTG deposits throughout the duodenum and high serum anti-tTG concentrations (157 ± 178 U/mL); bulb duodenal atrophy (n = 22), with widespread IgA anti-tTG deposits in 9 and in the bulb alone in 13 and low serum anti-tTG concentrations (13.9 ± 8.7 U/mL); and normal duodenum (n = 14), with widespread IgA anti-tTG deposits in 8 and in the bulb alone in 6 and low serum anti-tTG concentrations (10.6 ± 6.2 U/mL). All patients in the first 2 groups were diagnosed with CD and 8 from the third group. All improved after 1 year of gluten-free diet. Bulb duodenal analysis led to a 12% (30/245) increase in CD diagnosis. No CD-related lesions were observed in the 30 control subjects. CONCLUSIONS: In children at risk for CD, bulb duodenum biopsy sampling is essential to identify villous atrophy and detect IgA anti-tTG deposits even in absence of intestinal lesions. These mucosal autoantibodies could well represent a new standard for diagnosing CD.
Keywords: Adolescent; Autoantibodies; Celiac Disease; Child; Child, Preschool; Duodenum; Female; Humans; Immunoglobulin A; Immunohistochemistry; Infant; Male; Prospective Studies; Transglutaminases

Impact of near infrared light in pediatric blood drawing Centre on rate of first attempt success and time of procedure. - Conversano, Ester; Cozzi, Giorgio; Pavan, Matteo; Minute, Marta; Gortan, Elena; Montico, Marcella; Vecchi Brumatti, Liza; Ronfani, Luca; Barbi, Egidio (Ital J Pediatr, 2018)
BACKGROUND: Peripheral blood access and venipuncture are a stressful and painful experience in pediatric patients; moreover, it is estimated that more than one attempt is required to achieve the procedure in about one third of children. For this reason, we investigated if Near-infrared light technology routinely used, could give an advantage to venipuncture in a pediatric blood center setting. METHODS: We conducted an open, pseudo-randomized controlled trial with two parallel arms, in the blood-drawing center, with enrolment of 115 patients between 0 and 18 years, in 14 consecutive working days. Fifty-three subjects were enrolled in group 1 (VeinViewer®) and 62 in group 2 (control group). We divided patients into three subgroups considering their age (< 5 years, 6-10 years, > 10 years). The primary study outcome was to assess if the use of VeinViewer® was associated with a reduction of time to perform blood sampling. The secondary outcome was to analyze VienViewer®'s impact on first attempt success rate in blood sampling. RESULTS: No difference was found regarding the duration of blood sampling between the two groups, even after stratifying the patients into the three age subgroups. There was no difference between the two groups in the success at the first attempt in blood sampling. CONCLUSIONS: Routine use of VeinViewer® is not useful to reduce time of the procedure during venipuncture. TRIAL REGISTRATION: The study was registered with ClinicalTrials.gov, with number NCT03277092 , on September 8, 2017.
Keywords: Adolescent; Age Factors; Child; Child, Preschool; Female; Humans; Infant; Infant, Newborn; Infrared Rays; Lighting; Male; Phlebotomy; Time Factors

Investigation of the link between PROP taste perception and vegetables consumption using FAOSTAT data. - Mezzavilla, Massimo; Notarangelo, Michela; Concas, Maria Pina; Catamo, Eulalia; Gasparini, Paolo; Grillotti, Maria Gemma; Robino, Antonietta (Int J Food Sci Nutr, 2018)
In this work we investigated, in populations located in Central Asia, the relationship between PROP taste perception and vegetables liking and consumption using FAOSTAT dataset. Collected data were analysed using distance matrices, Mantel test and Pearson correlation. Populations showing similar ability in tasting PROP bitterness are more similar as respect to vegetable consumption (r = 0.63, p-value = .05). Moreover, a significant negative correlation was found between the percentage of Non Taster (NT) in different countries and the percentage of vegetable consumption (r = -0.87, p-value = .02), while a significant positive correlation emerged between the percentage of Super Taster (ST) and the percentage of vegetable liking (r = 0.87, p-value = .02). In our work we showed that differences in bitter perception among populations contributes to differences in vegetable liking and vegetable consumption. More in detail, populations with higher percentage of ST consume more vegetables than population where the majority of individuals are NT.

Iron-related toxicity of single-walled carbon nanotubes and crocidolite fibres in human mesothelial cells investigated by Synchrotron XRF microscopy. - Cammisuli, Francesca; Giordani, Silvia; Gianoncelli, Alessandra; Rizzardi, Clara; Radillo, Lucia; Zweyer, Marina; Da Ros, Tatiana; Salomè, Murielle; Melato, Mauro; Pascolo, Lorella (Sci Rep, 2018)
Carbon nanotubes (CNTs) are promising products in industry and medicine, but there are several human health concerns since their fibrous structure resembles asbestos. The presence of transition metals, mainly iron, in the fibres seems also implicated in the pathogenetic mechanisms. To unravel the role of iron at mesothelial level, we compared the chemical changes induced in MeT-5A cells by the exposure to asbestos (crocidolite) or CNTs at different content of iron impurities (raw-SWCNTs, purified- and highly purified-SWCNTs). We applied synchrotron-based X-Ray Fluorescence (XRF) microscopy and soft X-ray imaging (absorption and phase contrast images) to monitor chemical and morphological changes of the exposed cells. In parallel, we performed a ferritin assay. X-ray microscopy imaging and XRF well localize the crocidolite fibres interacting with cells, as well as the damage-related morphological changes. Differently, CNTs presence could be only partially evinced by low energy XRF through carbon distribution and sometimes iron co-localisation. Compared to controls, the cells treated with raw-SWCNTs and crocidolite fibres showed a severe alteration of iron distribution and content, with concomitant stimulation of ferritin production. Interestingly, highly purified nanotubes did not altered iron metabolism. The data provide new insights for possible CNTs effects at mesothelial/pleural level in humans.
Keywords: Asbestos, Crocidolite; Cell Line; Epithelial Cells; Humans; Iron; Microscopy, Fluorescence; Nanotubes, Carbon

Joint Data Analysis in Nutritional Epidemiology: Identification of Observational Studies and Minimal Requirements. - Pinart, Mariona; Nimptsch, Katharina; Bouwman, Jildau; Dragsted, Lars O; Yang, Chen; De Cock, Nathalie; Lachat, Carl; Perozzi, Giuditta; Canali, Raffaella; Lombardo, Rosario; D'Archivio, Massimo; Guillaume, Michèle; et al. (J Nutr, 2018)
Background: Joint data analysis from multiple nutrition studies may improve the ability to answer complex questions regarding the role of nutritional status and diet in health and disease. Objective: The objective was to identify nutritional observational studies from partners participating in the European Nutritional Phenotype Assessment and Data Sharing Initiative (ENPADASI) Consortium, as well as minimal requirements for joint data analysis. Methods: A predefined template containing information on study design, exposure measurements (dietary intake, alcohol and tobacco consumption, physical activity, sedentary behavior, anthropometric measures, and sociodemographic and health status), main health-related outcomes, and laboratory measurements (traditional and omics biomarkers) was developed and circulated to those European research groups participating in the ENPADASI under the strategic research area of "diet-related chronic diseases." Information about raw data disposition and metadata sharing was requested. A set of minimal requirements was abstracted from the gathered information. Results: Studies (12 cohort, 12 cross-sectional, and 2 case-control) were identified. Two studies recruited children only and the rest recruited adults. All studies included dietary intake data. Twenty studies collected blood samples. Data on traditional biomarkers were available for 20 studies, of which 17 measured lipoproteins, glucose, and insulin and 13 measured inflammatory biomarkers. Metabolomics, proteomics, and genomics or transcriptomics data were available in 5, 3, and 12 studies, respectively. Although the study authors were willing to share metadata, most refused, were hesitant, or had legal or ethical issues related to sharing raw data. Forty-one descriptors of minimal requirements for the study data were identified to facilitate data integration. Conclusions: Combining study data sets will enable sufficiently powered, refined investigations to increase the knowledge and understanding of the relation between food, nutrition, and human health. Furthermore, the minimal requirements for study data may encourage more efficient secondary usage of existing data and provide sufficient information for researchers to draft future multicenter research proposals in nutrition.
Keywords: Adult; Biomarkers; Blood Glucose; Case-Control Studies; Child; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Diet; Epidemiology; Europe; Genomics; Health Status; Humans; Inflammation; Insulin; Life Style; Lipoproteins; Longitudinal Studies; Metabolomics; Nutritional Status; Observational Studies as Topic; Statistics as Topic

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).
Keywords: Blood Pressure; Cohort Studies; Continental Population Groups; Diastole; Epistasis, Genetic; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Smoking; Systole

Learning curve for the ultrasonographic diagnosis of deep endometriosis using a structured off-line training program. - Guerriero, Stefano; Pascual, M Angela; Ajossa, Silvia; Rodriguez, Ignacio; Zajicek, Michal; Rolla, Martino; Rams, Noelia Llop; Yulzari, Vered; Bardin, Ron; Buonomo, Francesca; Comparetto, Ornella; Perniciano, Maura; et al. (Ultrasound Obstet Gynecol, 2018)
OBJECTIVE: The aim of the present study was to assess the learning curves of trainees during a structured off-line/hands-on training program on the diagnosis of deep infiltrating endometriosis (DIE). METHODS: A two-week training program was conducted. One day was devoted to theoretical issues and guided off-line analysis of 10 volumes of three-dimensional (3D) ultrasound. During the following days, five sessions of real-time sonographic examinations were performed in a DIE referral center Ultrasound unit. In between sessions, the trainees analyzed four off-line sets, containing twenty-five 3D volumes each. At the end of each set, misinterpreted volumes were assessed with the trainer. One trainer and 4 trainees (all post-graduated Ob/Gyn with at least 5 years of experience in ultrasonography in Obstetrics and Gynecology but with no experience in DIE sonographic examinations) participated in the study. Presence or absence of DIE at surgery was considered as gold standard for the trainees. Trainee's results were evaluated by learning curve cumulative summation (LC-CUSUM) and the deviations of the level of trainees' performance at the control stage by CUSUM (standard CUSUM) for different locations of DIE. RESULTS: The trainees reached competence on average after 17 evaluations (range 21-14) for bladder locations, after 39 evaluations (range 60-30) for rectosigmoid locations, after 25 evaluations (range 34-14) for forniceal locations, after 44 evaluations (range 66-25) for utero-sacral locations (USL), after 21 evaluations (range 43-14) for rectovaginal septum (RVS) locations respectively, and kept the process under control with error levels of less than 4.5% until the end of the test. The overall accuracy for each trainee at the different locations ranged from 0.91 to 0.96 for bladder DIE, from 0.80 to 0.94 for recto-sigmoid DIE, from 0.90 to 0.94% for forniceal DIE, from 0.79 to 0.82 for utero-sacral ligaments DIE and from 0.89 to 0.97 for recto-vaginal septum DIE. CONCLUSIONS: The suggested two-weeks learning program based on a mix of off-line and live sessions is feasible and suggests a good performance in training for the diagnosis of DIE. This article is protected by copyright. All rights reserved.

Light element distribution in fresh and frozen-thawed human ovarian tissues: a preliminary study. - Pascolo, Lorella; Venturin, Irene; Gianoncelli, Alessandra; Bortul, Roberta; Zito, Gabriella; Giolo, Elena; Salomè, Murielle; Bedolla, Diana E; Altissimo, Matteo; Zweyer, Marina; Ricci, Giuseppe (Reprod Biomed Online, 2018)
RESEARCH QUESTION: Does synchrotron X-ray fluorescence (XRF) provide novel chemical information for the evaluation of human ovarian tissue cryopreservation protocols? DESIGN: Tissues from five patients undergoing laparoscopic surgery for benign gynaecological conditions were fixed for microscopic analysis either immediately or after cryopreservation. After fixation, fresh and slowly frozen samples were selected by light microscopy and transmission electron microscopy, and subsequently analysed with synchrotron XRF microscopy at different incident energies. RESULTS: The distributions of elements detected at 7.3 keV (S, P, K, Cl, Fe, and Os) and 1.5 keV (Na and Mg) were related to the changes revealed by light microscopy and transmission electron microscopy analyses. The light elements showed highly informative findings. The S distribution was found to be an indicator of extracellular component changes in the stromal tissues of the freeze-stored samples, further revealed by the transmission electron microscopy analyses. Low-quality follicles, frequent in the freeze-thawed tissues, showed a high Na level in the ooplasm. On the contrary, good-quality follicles were detected by a homogeneous Cl distribution. The occurrence of vacuolated follicles increased after cryopreservation, and the XRF analyses showed that the vacuolar structures contained mainly Cl and Na. CONCLUSIONS: The study demonstrates that elemental imaging techniques, particularly revealing the distribution of light elements, could be useful in establishing new cryopreservation protocols.
Keywords: Cryopreservation; Female; Humans; Microscopy, Electron, Transmission; Organ Preservation; Ovarian Follicle; Ovary

Long term outcome of eight patients with type 1 Leukocyte Adhesion Deficiency (LAD-1): Not only infections, but high risk of autoimmune complications. - De Rose, Domenico Umberto; Giliani, Silvia; Notarangelo, Lucia Dora; Lougaris, Vassilios; Lanfranchi, Arnalda; Moratto, Daniele; Martire, Baldassarre; Specchia, Fernando; Tommasini, Alberto; Plebani, Alessandro; Badolato, Raffaele (Clin Immunol, 2018)
Leukocyte Adhesion Deficiency type 1 (LAD-1) is a rare primary immunodeficiency due to mutations in the gene encoding for the common β-chain of the β2 integrin family (CD18). Herein, we describe clinical manifestations and long-term complications of eight LAD-1 patients. Four LAD-1 patients were treated with hematopoietic stem cell transplantation (HSCT), while the remaining four, including two with moderate LAD-1 deficiency, received continuous antibiotic prophylaxis. Untreated patients presented numerous infections and autoimmune manifestations. In particular, two of them developed renal and intestinal autoimmune diseases, despite the expression of Beta-2 integrin was partially conserved. Other two LAD-1 patients developed type 1 diabetes and autoimmune cytopenia after HSCT, suggesting that HSCT is effective for preventing infections in LAD-1, but does not prevent the risk of the autoimmune complications.

Lopinavir/Ritonavir Treatment Induces Oxidative Stress and Caspaseindependent Apoptosis in Human Glioblastoma U-87 MG Cell Line. - Gratton, Rossella; Tricarico, Paola Maura; Guimarães, Rafael Lima; Celsi, Fulvio; Crovella, Sergio (Curr HIV Res, 2018)
BACKGROUND: Lopinavir and Ritonavir (LPV/r) treatment is widely used to prevent HIV mother-to-child transmission. Nevertheless, studies related to the impact of these compounds on patients, in particular in the foetus and newborns, are strictly required due to the controversial findings reported in the literature concerning possible neurologic side effects following the administration of these drugs. OBJECTIVES: In our study, we evaluated the impact of LPV/r treatment on the human glioblastoma U- 87 MG cell line. METHODS: In order to evaluate the influence of Lopinavir and Ritonavir in terms of oxidative stress (ROS production), mitochondrial morphology and apoptotic cell death, the latter either in the presence or in the absence of caspase-3 and -9 inhibitors, we treated U-87 MG with increasing doses (0.1-1-10-25-50 µM) of Lopinavir and Ritonavir for 24h, either in single formulation or in combination. ROS production was measured by flow cytometry using H2DCFDA dye, mitochondrial morphology was evaluated using MitoRed dye and apoptotic cell death was monitored by flow cytometry using Annexin V-FITC and Propidium Iodide. RESULTS: We observed that co-treatment with Lopinavir and Ritonavir (25 and 50 µM) promoted a significant increase in ROS production, caused mitochondrial network damage and induced apoptosis in a caspase-independent manner. CONCLUSION: Based on our findings, concordant with others reported in the literature, we hypothesize that LPV/r treatment could not be entirely free from side effects, being aware of the need of validation in in vivo models, necessary to confirm our results.

Measuring performance on the Healthcare Access and Quality Index for 195 countries and territories and selected subnational locations: a systematic analysis from the Global Burden of Disease Study 2016. (Lancet, 2018)
BACKGROUND: A key component of achieving universal health coverage is ensuring that all populations have access to quality health care. Examining where gains have occurred or progress has faltered across and within countries is crucial to guiding decisions and strategies for future improvement. We used the Global Burden of Diseases, Injuries, and Risk Factors Study 2016 (GBD 2016) to assess personal health-care access and quality with the Healthcare Access and Quality (HAQ) Index for 195 countries and territories, as well as subnational locations in seven countries, from 1990 to 2016. METHODS: Drawing from established methods and updated estimates from GBD 2016, we used 32 causes from which death should not occur in the presence of effective care to approximate personal health-care access and quality by location and over time. To better isolate potential effects of personal health-care access and quality from underlying risk factor patterns, we risk-standardised cause-specific deaths due to non-cancers by location-year, replacing the local joint exposure of environmental and behavioural risks with the global level of exposure. Supported by the expansion of cancer registry data in GBD 2016, we used mortality-to-incidence ratios for cancers instead of risk-standardised death rates to provide a stronger signal of the effects of personal health care and access on cancer survival. We transformed each cause to a scale of 0-100, with 0 as the first percentile (worst) observed between 1990 and 2016, and 100 as the 99th percentile (best); we set these thresholds at the country level, and then applied them to subnational locations. We applied a principal components analysis to construct the HAQ Index using all scaled cause values, providing an overall score of 0-100 of personal health-care access and quality by location over time. We then compared HAQ Index levels and trends by quintiles on the Socio-demographic Index (SDI), a summary measure of overall development. As derived from the broader GBD study and other data sources, we examined relationships between national HAQ Index scores and potential correlates of performance, such as total health spending per capita. FINDINGS: In 2016, HAQ Index performance spanned from a high of 97·1 (95% UI 95·8-98·1) in Iceland, followed by 96·6 (94·9-97·9) in Norway and 96·1 (94·5-97·3) in the Netherlands, to values as low as 18·6 (13·1-24·4) in the Central African Republic, 19·0 (14·3-23·7) in Somalia, and 23·4 (20·2-26·8) in Guinea-Bissau. The pace of progress achieved between 1990 and 2016 varied, with markedly faster improvements occurring between 2000 and 2016 for many countries in sub-Saharan Africa and southeast Asia, whereas several countries in Latin America and elsewhere saw progress stagnate after experiencing considerable advances in the HAQ Index between 1990 and 2000. Striking subnational disparities emerged in personal health-care access and quality, with China and India having particularly large gaps between locations with the highest and lowest scores in 2016. In China, performance ranged from 91·5 (89·1-93·6) in Beijing to 48·0 (43·4-53·2) in Tibet (a 43·5-point difference), while India saw a 30·8-point disparity, from 64·8 (59·6-68·8) in Goa to 34·0 (30·3-38·1) in Assam. Japan recorded the smallest range in subnational HAQ performance in 2016 (a 4·8-point difference), whereas differences between subnational locations with the highest and lowest HAQ Index values were more than two times as high for the USA and three times as high for England. State-level gaps in the HAQ Index in Mexico somewhat narrowed from 1990 to 2016 (from a 20·9-point to 17·0-point difference), whereas in Brazil, disparities slightly increased across states during this time (a 17·2-point to 20·4-point difference). Performance on the HAQ Index showed strong linkages to overall development, with high and high-middle SDI countries generally having higher scores and faster gains for non-communicable diseases. Nonetheless, countries across the development spectrum saw substantial gains in some key health service areas from 2000 to 2016, most notably vaccine-preventable diseases. Overall, national performance on the HAQ Index was positively associated with higher levels of total health spending per capita, as well as health systems inputs, but these relationships were quite heterogeneous, particularly among low-to-middle SDI countries. INTERPRETATION: GBD 2016 provides a more detailed understanding of past success and current challenges in improving personal health-care access and quality worldwide. Despite substantial gains since 2000, many low-SDI and middle-SDI countries face considerable challenges unless heightened policy action and investments focus on advancing access to and quality of health care across key health services, especially non-communicable diseases. Stagnating or minimal improvements experienced by several low-middle to high-middle SDI countries could reflect the complexities of re-orienting both primary and secondary health-care services beyond the more limited foci of the Millennium Development Goals. Alongside initiatives to strengthen public health programmes, the pursuit of universal health coverage hinges upon improving both access and quality worldwide, and thus requires adopting a more comprehensive view-and subsequent provision-of quality health care for all populations. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Communicable Diseases; Global Burden of Disease; Health Services Accessibility; Humans; Noncommunicable Diseases; Quality of Health Care; Wounds and Injuries

Measuring progress from 1990 to 2017 and projecting attainment to 2030 of the health-related Sustainable Development Goals for 195 countries and territories: a systematic analysis for the Global Burden of Disease Study 2017. (Lancet, 2018)
BACKGROUND: Efforts to establish the 2015 baseline and monitor early implementation of the UN Sustainable Development Goals (SDGs) highlight both great potential for and threats to improving health by 2030. To fully deliver on the SDG aim of "leaving no one behind", it is increasingly important to examine the health-related SDGs beyond national-level estimates. As part of the Global Burden of Diseases, Injuries, and Risk Factors Study 2017 (GBD 2017), we measured progress on 41 of 52 health-related SDG indicators and estimated the health-related SDG index for 195 countries and territories for the period 1990-2017, projected indicators to 2030, and analysed global attainment. METHODS: We measured progress on 41 health-related SDG indicators from 1990 to 2017, an increase of four indicators since GBD 2016 (new indicators were health worker density, sexual violence by non-intimate partners, population census status, and prevalence of physical and sexual violence [reported separately]). We also improved the measurement of several previously reported indicators. We constructed national-level estimates and, for a subset of health-related SDGs, examined indicator-level differences by sex and Socio-demographic Index (SDI) quintile. We also did subnational assessments of performance for selected countries. To construct the health-related SDG index, we transformed the value for each indicator on a scale of 0-100, with 0 as the 2·5th percentile and 100 as the 97·5th percentile of 1000 draws calculated from 1990 to 2030, and took the geometric mean of the scaled indicators by target. To generate projections through 2030, we used a forecasting framework that drew estimates from the broader GBD study and used weighted averages of indicator-specific and country-specific annualised rates of change from 1990 to 2017 to inform future estimates. We assessed attainment of indicators with defined targets in two ways: first, using mean values projected for 2030, and then using the probability of attainment in 2030 calculated from 1000 draws. We also did a global attainment analysis of the feasibility of attaining SDG targets on the basis of past trends. Using 2015 global averages of indicators with defined SDG targets, we calculated the global annualised rates of change required from 2015 to 2030 to meet these targets, and then identified in what percentiles the required global annualised rates of change fell in the distribution of country-level rates of change from 1990 to 2015. We took the mean of these global percentile values across indicators and applied the past rate of change at this mean global percentile to all health-related SDG indicators, irrespective of target definition, to estimate the equivalent 2030 global average value and percentage change from 2015 to 2030 for each indicator. FINDINGS: The global median health-related SDG index in 2017 was 59·4 (IQR 35·4-67·3), ranging from a low of 11·6 (95% uncertainty interval 9·6-14·0) to a high of 84·9 (83·1-86·7). SDG index values in countries assessed at the subnational level varied substantially, particularly in China and India, although scores in Japan and the UK were more homogeneous. Indicators also varied by SDI quintile and sex, with males having worse outcomes than females for non-communicable disease (NCD) mortality, alcohol use, and smoking, among others. Most countries were projected to have a higher health-related SDG index in 2030 than in 2017, while country-level probabilities of attainment by 2030 varied widely by indicator. Under-5 mortality, neonatal mortality, maternal mortality ratio, and malaria indicators had the most countries with at least 95% probability of target attainment. Other indicators, including NCD mortality and suicide mortality, had no countries projected to meet corresponding SDG targets on the basis of projected mean values for 2030 but showed some probability of attainment by 2030. For some indicators, including child malnutrition, several infectious diseases, and most violence measures, the annualised rates of change required to meet SDG targets far exceeded the pace of progress achieved by any country in the recent past. We found that applying the mean global annualised rate of change to indicators without defined targets would equate to about 19% and 22% reductions in global smoking and alcohol consumption, respectively; a 47% decline in adolescent birth rates; and a more than 85% increase in health worker density per 1000 population by 2030. INTERPRETATION: The GBD study offers a unique, robust platform for monitoring the health-related SDGs across demographic and geographic dimensions. Our findings underscore the importance of increased collection and analysis of disaggregated data and highlight where more deliberate design or targeting of interventions could accelerate progress in attaining the SDGs. Current projections show that many health-related SDG indicators, NCDs, NCD-related risks, and violence-related indicators will require a concerted shift away from what might have driven past gains-curative interventions in the case of NCDs-towards multisectoral, prevention-oriented policy action and investments to achieve SDG aims. Notably, several targets, if they are to be met by 2030, demand a pace of progress that no country has achieved in the recent past. The future is fundamentally uncertain, and no model can fully predict what breakthroughs or events might alter the course of the SDGs. What is clear is that our actions-or inaction-today will ultimately dictate how close the world, collectively, can get to leaving no one behind by 2030. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Female; Global Burden of Disease; Global Health; Goals; Health Status; Health Status Indicators; Humans; Male; Mortality; Risk Factors; Sex Offenses; Sustainable Development; United Nations

MKRN3 levels in girls with central precocious puberty and correlation with sexual hormone levels: a pilot study. - Grandone, Anna; Cirillo, Grazia; Sasso, Marcella; Capristo, Carlo; Tornese, Gianluca; Marzuillo, Pierluigi; Luongo, Caterina; Rosaria Umano, Giuseppina; Festa, Adalgisa; Coppola, Ruggero; Miraglia Del Giudice, Emanuele; Perrone, Laura (Endocrine, 2018)
PURPOSE: Recently, mutations of makorin RING-finger protein 3 (MKRN3) have been described in familial central precocious puberty. Serum levels of this protein decline before the pubertal onset in healthy girls and boys. The aim of the study is to investigate MKRN3 circulating levels in patients with central precocious puberty. METHODS: We performed an observational cross-sectional study. We enrolled 17 patients with central precocious puberty aged 7 years (range: 2-8 years) and breast development onset <8 years; 17 prepubertal control age-matched patients aged 6.3 years (2-8.2); and 10 pubertal stage-matched control patients aged 11.4 years (9-14). Serum values of MKRN3, gonadotropins, (17)estradiol and Anti-Müllerian Hormone were evaluated and the MKRN3 genotyped in central precocious puberty patients. RESULTS: No MKRN3 mutation was found among central precocious puberty patients. MKRN3 levels were lower in patients with central precocious puberty compared to prepubertal age-matched ones (p: 0.0004) and comparable to those matched for pubertal stage. MKRN3 levels were inversely correlated to Body Mass Index Standard Deviations (r:-0.35; p:0.02), Luteinizing Hormone (r:-0.35; p:0.03), FSH (r:-0.37; p:0.02), and (17)estradiol (r: -0.36; p:0.02). CONCLUSIONS: We showed that girls with central precocious puberty had lower peripheral levels of MKRN3 compared to age-matched pairs and that they negatively correlated to gonadotropins, estrogen, and BMI. Our findings support the MKRN3 involvement in central precocious puberty also in absence of deleterious mutations, although our sample size is small. In addition our data suggest the role of MKRN3 in the complex mechanism controlling puberty onset and its interaction with other factors affecting puberty such as nutrition.
Keywords: Adolescent; Adolescent Nutritional Physiological Phenomena; Anti-Mullerian Hormone; Case-Control Studies; Child; Child Nutritional Physiological Phenomena; Child, Preschool; Cross-Sectional Studies; Female; Follicle Stimulating Hormone; Gonadotropin-Releasing Hormone; Humans; Luteinizing Hormone; Pilot Projects; Puberty, Precocious; Ribonucleoproteins; Sexual Maturation

MKRN3 Levels in Girls with Central Precocious Puberty during GnRHa Treatment: A Longitudinal Study. - Grandone, Anna; Cirillo, Grazia; Sasso, Marcella; Tornese, Gianluca; Luongo, Caterina; Festa, Adalgisa; Marzuillo, Pierluigi; Miraglia Del Giudice, Emanuele (Horm Res Paediatr, 2018)
BACKGROUND: Recently, mutations of makorin RING finger protein 3 (MKRN3) have been identified in familial central precocious puberty (CPP). Serum levels of this protein decline before the pubertal onset in healthy girls and boys and are lower in patients with CPP compared to prepubertal matched pairs. The aim of our study was to investigate longitudinal changes in circulating MKRN3 levels in patients with CPP before and during GnRH analogs (GnRHa) treatment. METHODS: We performed a longitudinal prospective study. We enrolled 15 patients with CPP aged 7.2 years (range: 2-8) with age at breast development onset < 8 years and 12 control girls matched for the time from puberty onset (mean age 11.8 ± 1.2 years). Serum values of MKRN3, gonadotropins, and 17β-estradiol were evaluated before and during treatment with GnRHa (at 6 and 12 months). The MKRN3 gene was genotyped in CPP patients. In the girls from the control group, only basal levels were analyzed. RESULTS: No MKRN3 mutations were found among CPP patients. MKRN3 levels declined significantly from baseline to 6 months of GnRHa treatment (p = 0.0007) and from 6 to 12 months of treatment (p = 0.003); MKRN3 levels at 6 months were significantly lower than in the control girls (p < 0.0001). CONCLUSIONS: We showed that girls with CPP had a decline in peripheral levels of MKRN3 during GnRHa treatment. Our data suggest a suppression of MKRN3 by continuous pharmacological administration of GnRHa.
Keywords: Brain Diseases; Case-Control Studies; Child; Child, Preschool; Female; Follicle Stimulating Hormone; Genotype; Gonadotropin-Releasing Hormone; Humans; Longitudinal Studies; Luteinizing Hormone; Male; Puberty, Precocious; Ribonucleoproteins

Multicenter randomized, double-blind controlled trial to evaluate the efficacy of laser therapy for the treatment of severe oral mucositis induced by chemotherapy in children: laMPO RCT. - Gobbo, Margherita; Verzegnassi, Federico; Ronfani, Luca; Zanon, Davide; Melchionda, Fraia; Bagattoni, Simone; Majorana, Alessandra; Bardellini, Elena; Mura, Rosamaria; Piras, Alessandra; Petris, Maria Grazia; Mariuzzi, Maria Livia; et al. (Pediatr Blood Cancer, 2018)
OBJECTIVES: To demonstrate the efficacy of laser photobiomodulation (PBM) compared to that of placebo on severe oral mucositis (OM) in pediatric oncology patients. The primary objective was the reduction of OM grade (World Health Organization [WHO] scale) 7 days after starting PBM. Secondary objectives were reduction of pain, analgesic consumption, and incidence of side effects. METHODS: One hundred and one children with WHO grade > 2 chemotherapy-induced OM were enrolled in eight Italian hospitals. Patients were randomized to either PBM or sham treatment for four consecutive days (days +1 to +4). On days +4, +7, and +11, OM grade, pain (following a 0-10 numeric pain rating scale, NRS) and need for analgesics were evaluated by an operator blinded to treatment. RESULTS: Fifty-one patients were allocated to the PBM group, and 50 were allocated to the sham group. In total, 93.7% of PBM patients and 72% of sham patients had OM grade < 3 WHO on day +7 (P = 0.01). A significant reduction of pain was registered on day +7 in the PBM versus sham group (NRS 1 [0-3] vs. 2.5 [1-5], P < 0.006). Reduced use of analgesics was reported in the PBM group, although it was not statistically significant. No significant adverse events attributable to treatment were recorded. CONCLUSIONS: PBM is a safe, feasible, and effective treatment for children affected by chemotherapy-induced OM, as it accelerates mucosal recovery and reduces pain.

A new form of inherited thrombocytopenia due to monoallelic loss of function mutation in the thrombopoietin gene. - Noris, Patrizia; Marconi, Caterina; De Rocco, Daniela; Melazzini, Federica; Pippucci, Tommaso; Loffredo, Giuseppe; Giangregorio, Tania; Pecci, Alessandro; Seri, Marco; Savoia, Anna (Br J Haematol, 2018)

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Continental Population Groups; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Orthopaedic challenges for mucopolysaccharidoses. - Borgo, Andrea; Cossio, Andrea; Gallone, Denise; Vittoria, Francesca; Carbone, Marco (Ital J Pediatr, 2018)
Mucopolysaccharidoses (MPS) are a group of diseases characterized by abnormal accumulation of glycosaminoglycans (GAGs). Although there are differences among the various disease types, the osteoarticular system is always involved. The aim of the present study was to establish a framework for MPS-related orthopaedic manifestations and for their treatment. The authors, affiliated to three different Italian Orthopaedic Centres, report data taken from the literature reviewed in light of their accumulated professional experience. Bone alterations make up what is known as dysostosis multiplex, involving the trunk and limbs and with typical radiological findings. Joints are affected by pathological tissue infiltrations. The cervical spinal cord is involved, with stenosis and cervical and occipitocervical instability. In MPS there is a much higher incidence of scoliosis compared with healthy subjects without any particular distinctive feature. Kyphosis of the spine is more frequent and also more severe because of its possible neurological complications, and it is localized at the thoracolumbar level with a malformed vertebra at the top of the deformity. Evolving forms, and those associated with neurological damage, require anteroposterior spine fusion. The hip is invariably involved, with dysplasia affecting the femoral neck (coxa valga), the femoral epiphysis (loss of sphericity, osteonecrosis), and the femoral acetabulum which is flared. All these features explain the tendency to progressive hip migration. Genu valgum is often found (a deviation of the physiological axis with an obtuse angle opening laterally). This deformity is often localized at the proximal tibial metaphysis; it causes functional limitations and leads to an irregular erosion of the articular cartilage. In young patients who still have the growth plate, it is possible to execute a medial hemiepiphysiodesis, a temporary inhibition of cartilage growth, with progressive axis correction. In this paper, the characterisation of clinical features and the review of treatments are divided into separate sections based on the part of the body involved. The conclusions of each section are presented as a summary. One section discusses the high risk of anaesthesia-related complications requiring the collaboration of specifically trained personnel.
Keywords: Bone Diseases; Humans; Mucopolysaccharidoses; Orthopedic Procedures

Paediatric Home Artificial Nutrition in Italy: Report from 2016 Survey on Behalf of Artificial Nutrition Network of Italian Society for Gastroenterology, Hepatology and Nutrition (SIGENP). - Lezo, Antonella; Capriati, Teresa; Spagnuolo, Maria Immacolata; Lacitignola, Laura; Goreva, Irina; Di Leo, Grazia; Cecchi, Nicola; Gandullia, Paolo; Amarri, Sergio; Forchielli, Maria Luisa; Dipasquale, Valeria; Parma, Barbara; et al. (Nutrients, 2018)
Home Artificial Nutrition (HAN) is a safe and efficacious technique that insures children's reintegration into the family, society and school. Epidemiological data on paediatric HAN in Italy are not available. AIM: to detect the prevalence and incidence of Home Parenteral Nutrition (HPN) and Home Enteral Nutrition (HEN), either via tube or mouth, in Italy in 2016. MATERIALS AND METHODS: a specific form was sent to all registered SIGENP members and investigators of local HAN centres, inviting them to provide the requested centre's data and demographics, underlying diseases and HAN characteristics of the patients. RESULTS: we recorded 3403 Italian patients on HAN aged 0 to 19 years from 22 centres: 2277 HEN, 950 Oral Nutritional Supplements (ONS) and 179 HPN programs. The prevalence of HEN (205 pts/million inhabitants) and HPN (16 pts/million inhabitants) has dramatically increased in Italy in the last 9 years. Neurodisabling conditions were the first indication for HEN by tube or mouth while HPN is mainly requested in digestive disorders. CONCLUSIONS: HAN is a widespread and rapidly growing treatment in Italy, as well as in other European countries. Awareness of its extent and characteristics helps improving HAN service and patients' quality of life.
Keywords: Adolescent; Age Factors; Child; Child Nutritional Physiological Phenomena; Child, Preschool; Enteral Nutrition; Female; Health Care Surveys; Home Care Services; Humans; Infant; Infant, Newborn; Italy; Male; Nutritional Status; Parenteral Nutrition, Home; Pediatrics; Time Factors; Young Adult

Pain Intensity and Risk of Bone Fracture in Children With Minor Extremity Injuries. - Zanchi, Chiara; Giangreco, Manuela; Ronfani, Luca; Germani, Claudio; Giorgi, Rita; Calligaris, Lorenzo; Norbedo, Stefania; Liccari, Giulio; Cozzi, Giorgio; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVES: Injuries are one of the most common causes of pediatric emergency department (ED) visit. The aim of this study was to investigate the relationship between the intensity of pain at the ED visit of children presenting with an extremity injury and the risk of fracture. METHODS: We conducted a retrospective study, considering all patients presenting to the ED of a children's hospital in Italy, with an accidental extremity injury, between May and December 2015. We selected all children aged 8 to 17 years who underwent an x-ray. Children with major, multiple, or nonextremity injuries were excluded. Age, sex, spontaneous and palpation pain, local swelling, time between injury, and medical evaluation were recorded. Sensibility and specificity of spontaneous and palpation pain in detecting a fracture were calculated. RESULTS: We reviewed 994 medical records; of these, 344 (34.6%) reported a fracture. Children's median age was 12 years (interquartile range [IQR], 10-14). Median spontaneous pain at the ED visit was not significantly different between children with and without a fracture: 4.0 (1.0-6.0) and 5 (1.0-6.0), respectively (P = 0.129). Children with mild palpation pain and children without an increase of pain of at least 2 points between spontaneous and palpation pain were fractured in 3.2% and 0.97% of cases, respectively. CONCLUSIONS: In this series, pain intensity in children with a minor extremity injury was not a good marker of fracture. Nevertheless, children with mild palpation pain or with a mild increase of pain between spontaneous and palpation pain had a low risk of fracture.

Pathological Significance and Prognostic Value of Surfactant Protein D in Cancer. - Mangogna, Alessandro; Belmonte, Beatrice; Agostinis, Chiara; Ricci, Giuseppe; Gulino, Alessandro; Ferrara, Ines; Zanconati, Fabrizio; Tripodo, Claudio; Romano, Federico; Kishore, Uday; Bulla, Roberta (Front Immunol, 2018)
Surfactant protein D (SP-D) is a pattern recognition molecule belonging to the Collectin (collagen-containing C-type lectin) family that has pulmonary as well as extra-pulmonary existence. In the lungs, it is a well-established opsonin that can agglutinate a range of microbes, and enhance their clearance phagocytosis and super-oxidative burst. It can interfere with allergen-IgE interaction and suppress basophil and mast cell activation. However, it is now becoming evident that SP-D is likely to be an innate immune surveillance molecule against tumor development. SP-D has been shown to induce apoptosis in sensitized eosinophils derived from allergic patients and a leukemic cell line p53 pathway. Recently, SP-D has been shown to suppress lung cancer progression interference with the epidermal growth factor signaling. In addition, a truncated form of recombinant human SP-D has been reported to induce apoptosis in pancreatic adenocarcinoma Fas-mediated pathway in a p53-independent manner. To further establish a correlation between SP-D presence/levels and normal and cancer tissues, we performed a bioinformatics analysis, using Oncomine dataset and the survival analysis platforms Kaplan-Meier plotter, to assess if SP-D can serve as a potential prognostic marker for human lung cancer, in addition to human gastric, breast, and ovarian cancers. We also analyzed immunohistochemically the presence of SP-D in normal and tumor human tissues. We conclude that (1) in the lung, gastric, and breast cancers, there is a lower expression of SP-D than normal tissues; (2) in ovarian cancer, there is a higher expression of SP-D than normal tissue; and (3) in lung cancer, the presence of SP-D could be associated with a favorable prognosis. On the contrary, at non-pulmonary sites such as gastric, breast, and ovarian cancers, the presence of SP-D could be associated with unfavorable prognosis. Correlation between the levels of SP-D and overall survival requires further investigation. Our analysis involves a large number of dataset; therefore, any trend observed is reliable. Despite apparent complexity within the results, it is evident that cancer tissues that produce less levels of SP-D compared to their normal tissue counterparts are probably less susceptible to SP-D-mediated immune surveillance mechanisms infiltrating immune cells.

Photobiomodulation at Multiple Wavelengths Differentially Modulates Oxidative Stress and . - Rupel, Katia; Zupin, Luisa; Colliva, Andrea; Kamada, Anselmo; Poropat, Augusto; Ottaviani, Giulia; Gobbo, Margherita; Fanfoni, Lidia; Gratton, Rossella; Santoro, Massimo; Di Lenarda, Roberto; Biasotto, Matteo; et al. (Oxid Med Cell Longev, 2018)
Photobiomodulation (PBM) is emerging as an effective strategy for the management of multiple inflammatory conditions, including oral mucositis (OM) in cancer patients who receive chemotherapy or radiotherapy. Still, the poor understanding of the mechanisms by which the light interacts with biological tissues and the heterogeneity of light sources and protocols employed worldwide significantly limits its applicability. Reactive oxygen species (ROS) are massively generated during the early phases of OM and play a major role in the pathogenesis of inflammation in general. Here, we report the results of a clinical and experimental study, aimed at evaluating the effect of laser light at different wavelengths on oxidative stress in oncologic patients suffering from OM and in two cell types abundantly present within the inflamed oral mucosa, neutrophil polymorphonuclear (PMN) granulocytes, and keratinocytes. In addition to standard ROS detection methods, we exploited a roGFP2-Orp1 genetically encoded sensor, allowing specific, quantitative, and dynamic imaging of redox events in living cells in response to oxidative stress and PBM. We found that the various wavelengths differentially modulate ROS production. In particular, the 660 nm laser light increases ROS production when applied either before or after an oxidative stimulus. In contrast, the 970 nm laser light exerted a moderate antioxidant activity both in the saliva of OM patients and in both cell types. The most marked reduction in the levels of ROS was detected in cells exposed either to the 800 nm laser light or to the combination of the three wavelengths. Overall, our study demonstrates that PBM exerts different effects on the redox state of both PMNs and keratinocytes depending on the used wavelength and prompts the validation of a multiwavelength protocol in the clinical settings.
Keywords: Adult; Aged; Aged, 80 and over; Female; Humans; Keratinocytes; Lasers, Semiconductor; Low-Level Light Therapy; Male; Middle Aged; Neutrophils; Oxidation-Reduction; Oxidative Stress; Stomatitis

Population and fertility by age and sex for 195 countries and territories, 1950-2017: a systematic analysis for the Global Burden of Disease Study 2017. (Lancet, 2018)
BACKGROUND: Population estimates underpin demographic and epidemiological research and are used to track progress on numerous international indicators of health and development. To date, internationally available estimates of population and fertility, although useful, have not been produced with transparent and replicable methods and do not use standardised estimates of mortality. We present single-calendar year and single-year of age estimates of fertility and population by sex with standardised and replicable methods. METHODS: We estimated population in 195 locations by single year of age and single calendar year from 1950 to 2017 with standardised and replicable methods. We based the estimates on the demographic balancing equation, with inputs of fertility, mortality, population, and migration data. Fertility data came from 7817 location-years of vital registration data, 429 surveys reporting complete birth histories, and 977 surveys and censuses reporting summary birth histories. We estimated age-specific fertility rates (ASFRs; the annual number of livebirths to women of a specified age group per 1000 women in that age group) by use of spatiotemporal Gaussian process regression and used the ASFRs to estimate total fertility rates (TFRs; the average number of children a woman would bear if she survived through the end of the reproductive age span [age 10-54 years] and experienced at each age a particular set of ASFRs observed in the year of interest). Because of sparse data, fertility at ages 10-14 years and 50-54 years was estimated from data on fertility in women aged 15-19 years and 45-49 years, through use of linear regression. Age-specific mortality data came from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2017 estimates. Data on population came from 1257 censuses and 761 population registry location-years and were adjusted for underenumeration and age misreporting with standard demographic methods. Migration was estimated with the GBD Bayesian demographic balancing model, after incorporating information about refugee migration into the model prior. Final population estimates used the cohort-component method of population projection, with inputs of fertility, mortality, and migration data. Population uncertainty was estimated by use of out-of-sample predictive validity testing. With these data, we estimated the trends in population by age and sex and in fertility by age between 1950 and 2017 in 195 countries and territories. FINDINGS: From 1950 to 2017, TFRs decreased by 49·4% (95% uncertainty interval [UI] 46·4-52·0). The TFR decreased from 4·7 livebirths (4·5-4·9) to 2·4 livebirths (2·2-2·5), and the ASFR of mothers aged 10-19 years decreased from 37 livebirths (34-40) to 22 livebirths (19-24) per 1000 women. Despite reductions in the TFR, the global population has been increasing by an average of 83·8 million people per year since 1985. The global population increased by 197·2% (193·3-200·8) since 1950, from 2·6 billion (2·5-2·6) to 7·6 billion (7·4-7·9) people in 2017; much of this increase was in the proportion of the global population in south Asia and sub-Saharan Africa. The global annual rate of population growth increased between 1950 and 1964, when it peaked at 2·0%; this rate then remained nearly constant until 1970 and then decreased to 1·1% in 2017. Population growth rates in the southeast Asia, east Asia, and Oceania GBD super-region decreased from 2·5% in 1963 to 0·7% in 2017, whereas in sub-Saharan Africa, population growth rates were almost at the highest reported levels ever in 2017, when they were at 2·7%. The global average age increased from 26·6 years in 1950 to 32·1 years in 2017, and the proportion of the population that is of working age (age 15-64 years) increased from 59·9% to 65·3%. At the national level, the TFR decreased in all countries and territories between 1950 and 2017; in 2017, TFRs ranged from a low of 1·0 livebirths (95% UI 0·9-1·2) in Cyprus to a high of 7·1 livebirths (6·8-7·4) in Niger. The TFR under age 25 years (TFU25; number of livebirths expected by age 25 years for a hypothetical woman who survived the age group and was exposed to current ASFRs) in 2017 ranged from 0·08 livebirths (0·07-0·09) in South Korea to 2·4 livebirths (2·2-2·6) in Niger, and the TFR over age 30 years (TFO30; number of livebirths expected for a hypothetical woman ageing from 30 to 54 years who survived the age group and was exposed to current ASFRs) ranged from a low of 0·3 livebirths (0·3-0·4) in Puerto Rico to a high of 3·1 livebirths (3·0-3·2) in Niger. TFO30 was higher than TFU25 in 145 countries and territories in 2017. 33 countries had a negative population growth rate from 2010 to 2017, most of which were located in central, eastern, and western Europe, whereas population growth rates of more than 2·0% were seen in 33 of 46 countries in sub-Saharan Africa. In 2017, less than 65% of the national population was of working age in 12 of 34 high-income countries, and less than 50% of the national population was of working age in Mali, Chad, and Niger. INTERPRETATION: Population trends create demographic dividends and headwinds (ie, economic benefits and detriments) that affect national economies and determine national planning needs. Although TFRs are decreasing, the global population continues to grow as mortality declines, with diverse patterns at the national level and across age groups. To our knowledge, this is the first study to provide transparent and replicable estimates of population and fertility, which can be used to inform decision making and to monitor progress. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Adolescent; Adult; Aged; Birth Rate; Child; Child, Preschool; Female; Global Burden of Disease; Global Health; Humans; Infant; Infant, Newborn; Male; Maternal Age; Middle Aged; Mortality; Population Density; Population Growth; Young Adult

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.
Keywords: Atrial Function; Atrioventricular Node; Electrocardiography; Electrophysiological Phenomena; Female; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Mutation, Missense; Risk Factors

Predictive value of the number of adverse reaction episodes for the IgE-mediated food allergy diagnosis. - Miceli Sopo, S; Gurnari, G; Monaco, S; Romano, A; Liotti, L; Cuomo, B; Dello Iacono, I; Badina, L; Longo, G; Calvani, M; Giannone, A; Calabrò, C; et al. (Allergol Immunopathol (Madr), 2018)
INTRODUCTION AND OBJECTIVES: The reproducibility of the adverse reaction increases the suggestiveness of a history of food allergy. However, the positive predictive value (PPV) of multiple adverse reaction episodes for the diagnosis of IgE-mediated food allergy is not known. This evaluation was the objective of our study. PATIENTS AND METHODS: We retrospectively studied 180 children with a history of non-anaphylactic adverse reactions after the ingestion of a food. All children had the prick test positive for the offending food and performed the oral food challenge (OFC) within 12 months after the last adverse reaction episode (ARE). We have evaluated whether increasing the number of ARE increased the probability that the OFC would be positive (failed). RESULTS: 93 patients (52%) presented one ARE, 49 (27%) presented two ARE, 24 (13%) presented three ARE, 14 (8%) patients presented≥four ARE. The OFC was positive in 94/180 (52%). The outcome of the OFC was found to be positively correlated with the number of ARE (OR=1.56; 95% CI=1.16-2.09; p=0.003). A PPV=100% was observed with a number of ARE≥five. CONCLUSIONS: The number of ARE is an important predictor of the diagnosis of food allergy, although less than we would have imagined. The number of ARE could be used to increase the predictability of the diagnostic tests currently in use, to define clinical prediction rules alternative to OFC and easy to use in clinical practice.

Rothmund-Thomson Syndrome: Insights from New Patients on the Genetic Variability Underpinning Clinical Presentation and Cancer Outcome. - Colombo, Elisa A; Locatelli, Andrea; Cubells Sánchez, Laura; Romeo, Sara; Elcioglu, Nursel H; Maystadt, Isabelle; Esteve Martínez, Altea; Sironi, Alessandra; Fontana, Laura; Finelli, Palma; Gervasini, Cristina; Pecile, Vanna; et al. (Int J Mol Sci, 2018)
Biallelic mutations in gene, a caretaker of the genome, cause Rothmund-Thomson type-II syndrome (RTS-II) and confer increased cancer risk if they damage the helicase domain. We describe five families exemplifying clinical and allelic heterogeneity of RTS-II, and report the effect of pathogenic variants by predictions and transcripts analyses. Complete phenotype of patients #39 and #42 whose affected siblings developed osteosarcoma correlates with their c.[1048_1049del], c.[1878+32_1878+55del] and c.[1568G>C;1573delT], c.[3021_3022del] variants which damage the helicase domain. Literature survey highlights enrichment of these variants affecting the helicase domain in patients with cancer outcome raising the issue of strict oncological surveillance. Conversely, patients #29 and #19 have a mild phenotype and carry, respectively, the unreported homozygous c.3265G>T and c.3054A>G variants, both sparing the helicase domain. Finally, despite matching several criteria for RTS clinical diagnosis, patient #38 is heterozygous for c.2412_2414del; no pathogenic CNVs out of those evidenced by high-resolution CGH-array, emerged as contributors to her phenotype.
Keywords: Adolescent; Adult; Cell Line, Tumor; Child; Female; Homozygote; Humans; Male; Mutation; Pedigree; Phenotype; RecQ Helicases; Rothmund-Thomson Syndrome

Secondary prevention of early-onset sepsis: a less invasive Italian approach for managing neonates at risk. - Berardi, Alberto; Tzialla, Chryssoula; Travan, Laura; Bua, Jenny; Santori, Daniele; Azzalli, Milena; Spada, Caterina; Lucaccioni, Laura (Ital J Pediatr, 2018)
Strategies to prevent early-onset sepsis (EOS) have led to a substantial decline in many countries. However, one of the most controversial topics in neonatology is the management of asymptomatic full-term and late preterm neonates at risk for EOS, and guidelines lack substantial consensus regarding this issue. A strategy for managing neonates, entirely based on serial physical examinations, has been developed in two Italian regions. This strategy seems safe, while reducing laboratory tests and unnecessary antibiotics. In the current commentary we provide area-based data concerning the prevention of EOS in 2 northern Italian regions, and we detail the results of their strategy for managing healthy-appearing newborns at risk for EOS.

Theophylline as a precision therapy in a young girl with PIK3R1 immunodeficiency. - Valencic, Erica; Grasso, Antonio Giacomo; Conversano, Ester; Lucafò, Marianna; Piscianz, Elisa; Gregori, Massimo; Conti, Francesca; Cancrini, Caterina; Tommasini, Alberto (J Allergy Clin Immunol Pract, 2018)

Total body irradiation and iron chelation treatment are associated with pancreatic injury following pediatric hematopoietic stem cell transplantation. - Maximova, Natalia; Gregori, Massimo; Simeone, Roberto; Sonzogni, Aurelio; Zanon, Davide; Boz, Giulia; D'Antiga, Lorenzo (Oncotarget, 2018)
Whereas many studies have addressed the risk of organ dysfunction following hematopoietic stem cell transplantation (HSCT), little is known about pancreatic susceptibility in this setting. We aimed to investigate the effect of iron overload (IO) and total body irradiation (TBI) on pancreatic function of children undergoing HSCT. We retrospectively evaluated children admitted between 2012-2016 fulfilling the following criteria: normal pancreatic iron concentration (PIC), regular pancreatic function before HSCT, availability of abdominal magnetic resonance imaging with gradient-recalled-echo sequences and a full set of biochemical markers of IO and pancreatic function performed before HSCT and at discharge. We divided the patients according to the use of TBI or myeloablative chemotherapy (MCHT) in the conditioning regimen. All patients with severe IO or moderate IO with a high risk of engraftment delay or transplantation-related complications underwent chelation therapy with deferoxamine (DFO) from the first day of conditioning to discharge. 63 patients had a HSCT in the study period, 13 did not fulfill the inclusion criteria; 50 (25 in each group) are included in the analysis, and did not show differences at baseline evaluation. At follow up testing the TBI group showed a significantly higher PIC (107,8±100,3 μmol/g vs 28,4±37,9 in MCHT group, p<0,0001). In the TBI group the patients who had DFO treatment had higher PIC (223,2±48,8 μmol/g vs 55,7±10,5 without DFO treatment, p<0,0001), and all patients having PIC >100 μmol/g at follow up had DFO-based chelation therapy, versus 26% of those with lower PIC (p<0,0001). The number of patients presenting exocrine pancreatic dysfunctions one month after transplantation was significantly higher in the TBI group (48% vs 4%; p<0.0001). The mean pancreatic volume reduction was significantly greater in the TBI group (39,1% vs 0,9% in the MCHT group; p<0,05), and was significantly worse on those who received DFO therapy. Based on our data, we suggest that TBI is detrimental for pancreatic functions, and speculate that DFO may contribute to the rapid pancreatic IO observed in these patients.

A transcriptomics study of hereditary angioedema attacks. - Castellano, Giuseppe; Divella, Chiara; Sallustio, Fabio; Montinaro, Vincenzo; Curci, Claudia; Zanichelli, Andrea; Bonanni, Erika; Suffritti, Chiara; Caccia, Sonia; Bossi, Fleur; Gallone, Anna; Schena, Francesco Paolo; et al. (J Allergy Clin Immunol, 2018)
BACKGROUND: Hereditary angioedema (HAE) caused by C1-inhibitor deficiency is a lifelong illness characterized by recurrent acute attacks of localized skin or mucosal edema. Activation of the kallikrein/bradykinin pathway at the endothelial cell level has a relevant pathogenetic role in acute HAE attacks. Moreover, other pathways are involved given the variable clinical expression of the disease in different patients. OBJECTIVE: We sought to explore the involvement of other putative genes in edema formation. METHODS: We performed a PBMC microarray gene expression analysis on RNA isolated from patients with HAE during an acute attack and compared them with the transcriptomic profile of the same patients in the remission phase. RESULTS: Gene expression analysis identified 23 genes significantly modulated during acute attacks that are involved primarily in the natural killer cell signaling and leukocyte extravasation signaling pathways. Gene set enrichment analysis showed a significant activation of relevant biological processes, such as response to external stimuli and protein processing (q < 0.05), suggesting involvement of PBMCs during acute HAE attacks. Upregulation of 2 genes, those encoding adrenomedullin and cellular receptor for urokinase plasminogen activator (uPAR), which occurs during an acute attack, was confirmed in PBMCs of 20 additional patients with HAE by using real-time PCR. Finally, in vitro studies demonstrated the involvement of uPAR in the generation of bradykinin and endothelial leakage. CONCLUSIONS: Our study demonstrates the increase in levels of adrenomedullin and uPAR in PBMCs during an acute HAE attack. Activation of these genes usually involved in regulation of vascular tone and in inflammatory response might have a pathogenic role by amplifying bradykinin production and edema formation in patients with HAE.

Ultrasound-guided genitofemoral nerve block for inguinal hernia repair in the male adult: a randomized controlled pilot study. - Frassanito, Luciano; Zanfini, Bruno A; Pitoni, Sara; Germini, Paolo; Del Vicario, Miryam; Draisci, Gaetano (Minerva Anestesiol, 2018)
BACKGROUND: Ultrasound-guided (USG) ilioinguinal/iliohypogastric nerve (II/IHN) block is a widely validated anesthetic technique for inguinal herniorrhaphy. As the spermatic cord, scrotum, and adjacent thigh receive sensory innervation from the genital branch of genitofemoral nerve (GFN), the addition of GFN block has been suggested to improve the quality of perioperative anesthesia and analgesia. The aim of this study is to compare GFN block plus II/IHN block with II/IHN block alone for intraoperative anesthesia and post-operative pain management. METHODS: We enrolled 80, ASA I-III, male adults scheduled for elective open herniorrhaphy. Patients were randomized to receive either USG II/IHN plus GFN block (Case Group) or USG II/IHN block alone (Control Group). The outcome measures were the assessment of postoperative VAS scores on coughing and the adequacy of anesthesia, measured with intraoperative requirement for extra local anesthetic (LA) infiltration and number of patients needing systemic sedation. RESULTS: The requirement of intraoperative additional doses of LA was significantly lower in the Case Group (median LA volume administered by the surgeon: 13.8±5.6 mL vs. 20.7±9.1 mL, P<0.05). Two patients in the Control Group needed systemic sedation. VAS scores at 15 minutes, 30 minutes, 1 hour, 2 hours, pre-discharge, and 24 hours were significantly lower in the Case Group (P<0.005). Four cases of femoral nerve block were reported, three in the Control Group, one in the Case Group (2.2% vs. 7.7%, P>0.05). CONCLUSIONS: The combination of GFN block and II/IHN block is associated with lower postoperative VAS scores and lower doses of intraoperative additional LA.

Vanishing Bile Ducts in the Long Term after Pediatric Hematopoietic Stem Cell Transplantation. - Maximova, Natalia; Sonzogni, Aurelio; Matarazzo, Lorenza; Ghirardi, Arianna; D'Antiga, Lorenzo (Biol Blood Marrow Transplant, 2018)
There are no structured studies on liver histology after hematopoietic stem cell transplantation (HSCT). We aimed to prospectively describe the clinicopathologic features of liver disease in the long term after HSCT in an observational, longitudinal study of liver histology in a consecutive cohort of children undergoing allogeneic HSCT. First liver biopsy was performed in presence of abnormal liver function tests and repeated per protocol thereafter. A previously reported semiquantitative score evaluating inflammation, cholestasis, and ductopenia (bile ducts-to-portal tracts ratio ≤ .5) was adopted. Graft-versus-host disease (GVHD) was diagnosed according to standard criteria. We evaluated 131 biopsies taken in 50 HSCTs performed in 47 children (mean age, 9.7 ± 5.2 years). Pre-HSCT chemotherapy was administered in 36 of 50 (72%). GVHD was diagnosed in 17 of 50 (34%). Over time the overall score decreased from a mean of 6 ± 2.7 to 3.25 ± .96 (P < .01), inflammation from 1.22 ± 1.19 to 1 ± 0 (not significant), and cholestasis from 3.9 ± 2.08 to 1.5 ± .58 (P < .01). Ductopenia, found in 113 of 131 biopsies (93%), worsened from .63 ± .35 to .16 ± .14 (P < .01). On multivariate analysis severe ductopenia (ratio ≤ .2) was associated with previous chemotherapy (P = .04), in particular with thiotepa, but not with history of GVHD. Vanishing bile duct syndrome after HSCT may be due to drug-induced liver disease. Longer follow-up will reveal whether these patients are prone to late liver-related morbidity and mortality.

What is known about deferasirox chelation therapy in pediatric HSCT recipients: two case reports of metabolic acidosis. - Fucile, Carmen; Mattioli, Francesca; Marini, Valeria; Gregori, Massimo; Sonzogni, Aurelio; Martelli, Antonietta; Maximova, Natalia (Ther Clin Risk Manag, 2018)
To date, in pediatric field, various hematological malignancies are increasingly treated with allogeneic hematopoietic stem cell transplantation (allo-HSCT). Iron overload and systemic siderosis often occur in this particular cohort of patients and are associated with poor prognosis. We describe herein the case of two allo-HSCT patients, on treatment with deferasirox; they showed histopathological elements compatible with venoocclusive disease or vanishing bile duct syndrome in ductopenic evolution before deferasirox started. The first patient developed drug-induced liver damage with metabolic acidosis and the second one a liver impairment with Fanconi syndrome. After withdrawing deferasirox treatment, both patients showed improvement. Measurements of drug plasma concentrations were performed by HPLC assay. The reduction and consequent disappearance of symptoms after the suspension of deferasirox substantiate its role in inducing hepatic damage, probably enabling the diagnosis of drug-induced liver damage. But the difficulties in diagnosing drug-related toxicity must be underlined, especially in compromised subjects. For these reasons, in patients requiring iron-chelating therapy, close and careful drug therapeutic monitoring is strongly recommended.

1000 Genomes-based meta-analysis identifies 10 novel loci for kidney function. - Gorski, Mathias; van der Most, Peter J; Teumer, Alexander; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Nolte, Ilja M; Cocca, Massimiliano; Taliun, Daniel; Gomez, Felicia; Li, Yong; Tayo, Bamidele; et al. (Sci Rep, 2017)
HapMap imputed genome-wide association studies (GWAS) have revealed >50 loci at which common variants with minor allele frequency >5% are associated with kidney function. GWAS using more complete reference sets for imputation, such as those from The 1000 Genomes project, promise to identify novel loci that have been missed by previous efforts. To investigate the value of such a more complete variant catalog, we conducted a GWAS meta-analysis of kidney function based on the estimated glomerular filtration rate (eGFR) in 110,517 European ancestry participants using 1000 Genomes imputed data. We identified 10 novel loci with p-value < 5 × 10 previously missed by HapMap-based GWAS. Six of these loci (HOXD8, ARL15, PIK3R1, EYA4, ASTN2, and EPB41L3) are tagged by common SNPs unique to the 1000 Genomes reference panel. Using pathway analysis, we identified 39 significant (FDR < 0.05) genes and 127 significantly (FDR < 0.05) enriched gene sets, which were missed by our previous analyses. Among those, the 10 identified novel genes are part of pathways of kidney development, carbohydrate metabolism, cardiac septum development and glucose metabolism. These results highlight the utility of re-imputing from denser reference panels, until whole-genome sequencing becomes feasible in large samples.
Keywords: Computational Biology; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Genotyping Techniques; Humans; Kidney; Polymorphism, Single Nucleotide

ADA2 deficiency (DADA2) as an unrecognised cause of early onset polyarteritis nodosa and stroke: a multicentre national study. - Caorsi, Roberta; Penco, Federica; Grossi, Alice; Insalaco, Antonella; Omenetti, Alessia; Alessio, Maria; Conti, Giovanni; Marchetti, Federico; Picco, Paolo; Tommasini, Alberto; Martino, Silvana; Malattia, Clara; et al. (Ann Rheum Dis, 2017)
OBJECTIVES: To analyse the prevalence of mutations in patients diagnosed with early onset livedo reticularis and/or haemorrhagic/ischaemic strokes in the context of inflammation or polyarteritis nodosa (PAN). Forty-eight patients from 43 families were included in the study. METHODS: Direct sequencing of was performed by Sanger analysis. Adenosine deaminase 2 (ADA2) enzymatic activity was analysed in monocyte isolated from patients and healthy controls incubated with adenosine and with or without an ADA1 inhibitor. RESULTS: Biallelic homozygous or compound heterozygous mutations were detected in 15/48 patients. A heterozygous disease-associated mutation (p.G47V) was observed in two affected brothers. The mean age of onset of the genetically positive patients was 24 months (6 months to 7 years). Ten patients displayed one or more cerebral strokes during their disease course. Low immunoglobulin levels were detected in six patients. Thalidomide and anti-TNF (tumour necrosis factor) blockers were the most effective drugs. Patients without mutations had a later age at disease onset, a lower prevalence of neurological and skin manifestations; one of these patients displayed all the clinical features of adenosine deaminase 2deficiency (DADA2) and a defective enzymatic activity suggesting the presence of a missed mutation or a synthesis defect. CONCLUSIONS: DADA2 accounts for paediatric patients diagnosed with PAN-like disease and strokes and might explain an unrecognised condition in patients followed by adult rheumatologist. Timely diagnosis and treatment with anti-TNF agents are crucial for the prevention of severe complications of the disease. Functional assay to measure ADA2 activity should complement genetic testing in patients with non-confirming genotypes.
Keywords: Adenosine Deaminase; Adolescent; Age of Onset; Case-Control Studies; Child; Child, Preschool; DNA Mutational Analysis; Female; Heterozygote; Homozygote; Humans; Immunoglobulins; Immunosuppressive Agents; Infant; Intercellular Signaling Peptides and Proteins; Italy; Livedo Reticularis; Male; Pedigree; Polyarteritis Nodosa; Stroke; Thalidomide; Tumor Necrosis Factor-alpha; Young Adult

Amniocentesis and chorionic villus sampling in HIV-infected pregnant women: a multicentre case series. - Floridia, M; Masuelli, G; Meloni, A; Cetin, I; Tamburrini, E; Cavaliere, A F; Dalzero, S; Sansone, M; Alberico, S; Guerra, B; Spinillo, A; Chiadò Fiorio Tin, M; et al. (BJOG, 2017)
OBJECTIVES: To assess in pregnant women with HIV the rates of amniocentesis and chorionic villus sampling (CVS), and the outcomes associated with such procedures. DESIGN: Observational study. Data from the Italian National Program on Surveillance on Antiretroviral Treatment in Pregnancy were used. SETTING: University and hospital clinics. POPULATION: Pregnant women with HIV. METHODS: Temporal trends were analysed by analysis of variance and by the Chi-square test for trend. Quantitative variables were compared by Student's t-test and categorical data by the Chi-square test, with odds ratios and 95% confidence intervals calculated. MAIN OUTCOME MEASURES: Rate of invasive testing, intrauterine death, HIV transmission. RESULTS: Between 2001 and 2015, among 2065 pregnancies in women with HIV, 113 (5.5%) had invasive tests performed. The procedures were conducted under antiretroviral treatment in 99 cases (87.6%), with a significant increase over time in the proportion of tests performed under highly active antiretroviral therapy (HAART) (100% in 2011-2015). Three intrauterine deaths were observed (2.6%), and 14 pregnancies were terminated because of fetal anomalies. Among 96 live newborns, eight had no information available on HIV status. Among the remaining 88 cases with either amniocentesis (n = 75), CVS (n = 12), or both (n = 1), two HIV transmissions occurred (2.3%). No HIV transmission occurred among the women who were on HAART at the time of invasive testing, and none after 2005. CONCLUSIONS: The findings reinforce the assumption that invasive prenatal testing does not increase the risk of HIV vertical transmission among pregnant women under suppressive antiretroviral treatment. TWEETABLE ABSTRACT: No HIV transmission occurred among women who underwent amniocentesis or CVS under effective anti-HIV regimens.
Keywords: Adult; Amniocentesis; Analysis of Variance; Anti-Retroviral Agents; Chi-Square Distribution; Chorionic Villi Sampling; Female; Fetal Death; HIV Infections; Humans; Infectious Disease Transmission, Vertical; Odds Ratio; Pregnancy; Pregnancy Complications, Infectious

ANCA-associated vasculitis in childhood: recent advances. - Calatroni, Marta; Oliva, Elena; Gianfreda, Davide; Gregorini, Gina; Allinovi, Marco; Ramirez, Giuseppe A; Bozzolo, Enrica P; Monti, Sara; Bracaglia, Claudia; Marucci, Giulia; Bodria, Monica; Sinico, Renato A; et al. (Ital J Pediatr, 2017)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides are rare systemic diseases that usually occur in adulthood. They comprise granulomatosis with polyangiitis (GPA, Wegener's), microscopic polyangiitis (MPA) and eosinophilic granulomatosis with polyangiitis (EGPA, Churg-Strauss syndrome). Their clinical presentation is often heterogeneous, with frequent involvement of the respiratory tract, the kidney, the skin and the joints. ANCA-associated vasculitis is rare in childhood but North-American and European cohort studies performed during the last decade have clarified their phenotype, patterns of renal involvement and their prognostic implications, and outcome. Herein, we review the main clinical and therapeutic aspects of childhood-onset ANCA-associated vasculitis, and provide preliminary data on demographic characteristics and organ manifestations of an Italian multicentre cohort.
Keywords: Age Distribution; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; Antibodies, Antineutrophil Cytoplasmic; Child; Child, Preschool; Churg-Strauss Syndrome; Female; Granulomatosis with Polyangiitis; Humans; Incidence; Male; Microscopic Polyangiitis; Rare Diseases; Risk Assessment; Severity of Illness Index; Sex Distribution; Survival Rate

and Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2017)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (: 111,666; : 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (, , and ; <3.7×10), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, (=5.4×10 by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of and -knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.
Keywords: Animals; Exome; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Protein Tyrosine Phosphatases; Proto-Oncogene Proteins; Son of Sevenless Proteins; Zebrafish

Association between thyroid hormones and TRAIL. - Bernardi, Stella; Bossi, Fleur; Toffoli, Barbara; Giudici, Fabiola; Bramante, Alessandra; Furlanis, Giulia; Stenner, Elisabetta; Secchiero, Paola; Zauli, Giorgio; Carretta, Renzo; Fabris, Bruno (Clin Biochem, 2017)
INTRODUCTION: Recent studies suggest that a circulating protein called TRAIL (TNF-related apoptosis-inducing ligand) might have a role in the regulation of body weight and metabolism. Interestingly, thyroid hormones seem to increase TRAIL tissue expression. This study aimed at evaluating whether overt thyroid disorders affected circulating TRAIL levels. METHODS: TRAIL circulating levels were measured in euthyroid, hyperthyroid, and hypothyroid patients before and after thyroid function normalization. Univariate and multivariate analyses were performed to evaluate the correlation between thyroid hormones and TRAIL. Then, the stimulatory effect of both triiodothyronine (T3) and thyroxine (T4) on TRAIL was evaluated in vitro on peripheral blood mononuclear cells. RESULTS: Circulating levels of TRAIL significantly increased in hyperthyroid and decreased in hypothyroid patients as compared to controls. Once thyroid function was restored, TRAIL levels normalized. There was an independent association between TRAIL and both fT3 and fT4. Consistent with these findings, T3 and T4 stimulated TRAIL release in vitro. CONCLUSION: Here we show that thyroid hormones are associated with TRAIL expression in vivo and stimulate TRAIL expression in vitro. Given the overlap between the metabolic effects of thyroid hormones and TRAIL, this work sheds light on the possibility that TRAIL might be one of the molecules mediating thyroid hormones peripheral effects.
Keywords: Aged; Female; Gene Expression Regulation; Humans; Hyperthyroidism; Hypothyroidism; Leukocytes, Mononuclear; Male; Middle Aged; Thyroxine; TNF-Related Apoptosis-Inducing Ligand; Triiodothyronine

Autoimmune neutropenia of childhood secondary to other autoimmune disorders: Data from the Italian neutropenia registry. - Farruggia, Piero; Puccio, Giuseppe; Fioredda, Francesca; Lanza, Tiziana; Porretti, Laura; Ramenghi, Ugo; Barone, Angelica; Bonanomi, Sonia; Finocchi, Andrea; Ghilardi, Roberta; Ladogana, Saverio; Marra, Nicoletta; et al. (Am J Hematol, 2017)
Keywords: Autoimmune Diseases; Child; Disease Susceptibility; Female; Humans; Immunoglobulins, Intravenous; Immunosuppressive Agents; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; Italy; Male; Neutropenia; Prevalence; Registries

Avoiding Ethanol Presence in DNA Samples Enhances the Performance of Ultraviolet Resonance Raman Spectroscopy Analysis. - Cammisuli, Francesca; Pascolo, Lorella; Morgutti, Marcello; Gessini, Alessandro; Masciovecchio, Claudio; D'Amico, Francesco (Appl Spectrosc, 2017)
Ethanol is an essential chemical reagent in DNA preparation as its use increases the yield of extraction. All methodologies for DNA isolation involve the use of ethanol in order to prevent DNA dissolution in water and to optimize the binding of DNA to chromatographic membranes. In this note, we show how the presence of ethanol traces in DNA aqueous solution affects ultraviolet Raman spectra, leading to possible misinterpretations. We report a simple method to remove the ethanol Raman features from the spectra, based on heating the DNA sample at 80 ℃, followed by a slow cooling procedure.
Keywords: DNA; Ethanol; Female; Humans; Placenta; Pregnancy; Spectrophotometry, Ultraviolet; Spectrum Analysis, Raman

A boy with fever and arthralgia. - Poropat, Federico; Pastore, Serena; Gesuete, Valentina; Barbi, Egidio (BMJ, 2017)
Keywords: Anti-Bacterial Agents; Anti-Inflammatory Agents, Non-Steroidal; Antibodies, Bacterial; Aortic Valve Insufficiency; Arthralgia; Child; Echocardiography; Echocardiography, Doppler, Color; Fever; Humans; Male; Mitral Valve Insufficiency; Rheumatic Fever; Rheumatic Heart Disease; Streptolysins

Child and Adolescent Health From 1990 to 2015: Findings From the Global Burden of Diseases, Injuries, and Risk Factors 2015 Study. - Kassebaum, Nicholas; Kyu, Hmwe Hmwe; Zoeckler, Leo; Olsen, Helen Elizabeth; Thomas, Katie; Pinho, Christine; Bhutta, Zulfiqar A; Dandona, Lalit; Ferrari, Alize; Ghiwot, Tsegaye Tewelde; Hay, Simon I; Kinfu, Yohannes; et al. (JAMA Pediatr, 2017)
Importance: Comprehensive and timely monitoring of disease burden in all age groups, including children and adolescents, is essential for improving population health. Objective: To quantify and describe levels and trends of mortality and nonfatal health outcomes among children and adolescents from 1990 to 2015 to provide a framework for policy discussion. Evidence Review: Cause-specific mortality and nonfatal health outcomes were analyzed for 195 countries and territories by age group, sex, and year from 1990 to 2015 using standardized approaches for data processing and statistical modeling, with subsequent analysis of the findings to describe levels and trends across geography and time among children and adolescents 19 years or younger. A composite indicator of income, education, and fertility was developed (Socio-demographic Index [SDI]) for each geographic unit and year, which evaluates the historical association between SDI and health loss. Findings: Global child and adolescent mortality decreased from 14.18 million (95% uncertainty interval [UI], 14.09 million to 14.28 million) deaths in 1990 to 7.26 million (95% UI, 7.14 million to 7.39 million) deaths in 2015, but progress has been unevenly distributed. Countries with a lower SDI had a larger proportion of mortality burden (75%) in 2015 than was the case in 1990 (61%). Most deaths in 2015 occurred in South Asia and sub-Saharan Africa. Global trends were driven by reductions in mortality owing to infectious, nutritional, and neonatal disorders, which in the aggregate led to a relative increase in the importance of noncommunicable diseases and injuries in explaining global disease burden. The absolute burden of disability in children and adolescents increased 4.3% (95% UI, 3.1%-5.6%) from 1990 to 2015, with much of the increase owing to population growth and improved survival for children and adolescents to older ages. Other than infectious conditions, many top causes of disability are associated with long-term sequelae of conditions present at birth (eg, neonatal disorders, congenital birth defects, and hemoglobinopathies) and complications of a variety of infections and nutritional deficiencies. Anemia, developmental intellectual disability, hearing loss, epilepsy, and vision loss are important contributors to childhood disability that can arise from multiple causes. Maternal and reproductive health remains a key cause of disease burden in adolescent females, especially in lower-SDI countries. In low-SDI countries, mortality is the primary driver of health loss for children and adolescents, whereas disability predominates in higher-SDI locations; the specific pattern of epidemiological transition varies across diseases and injuries. Conclusions and Relevance: Consistent international attention and investment have led to sustained improvements in causes of health loss among children and adolescents in many countries, although progress has been uneven. The persistence of infectious diseases in some countries, coupled with ongoing epidemiologic transition to injuries and noncommunicable diseases, require all countries to carefully evaluate and implement appropriate strategies to maximize the health of their children and adolescents and for the international community to carefully consider which elements of child and adolescent health should be monitored.
Keywords: Adolescent; Adolescent Health; Age Factors; Cause of Death; Child; Child Health; Child Mortality; Disabled Children; Female; Global Burden of Disease; Global Health; Humans; Male; Pregnancy; Pregnancy Complications; Risk Factors; Sex Factors; Wounds and Injuries

[Clinical and molecular study in a family with autosomal dominant hypohidrotic ectodermal dysplasia]. - Callea, Michele; Cammarata-Scalisi, Francisco; Willoughby, Colin E; Giglio, Sabrina R; Sani, Ilaria; Bargiacchi, Sara; Traficante, Giovanna; Bellacchio, Emanuele; Tadini, Gianluca; Yavuz, Izzet; Galeotti, Angela; Clarich, Gabriella (Arch Argent Pediatr, 2017)
Hypohidrotic ectodermal dysplasia (HED) is a rare disease characterized by deficiency in development of structure derived from the ectoderm and is caused by mutations in the genes EDA, EDAR, or EDARADD. Phenotypes caused by mutations in these three may exhibit similar clinical features, explained by a common signaling pathway. Mutations in EDA gene cause X linked HED, which is the most common form. Mutations in EDAR and EDARADD genes cause autosomal dominant and recessive form of HED. The most striking clinical findings in HED are hypodontia, hypotrichosis and hypohidrosis that can lead to episodes of hyperthermia. We report on clinical findings in a child with HED with autosomal dominant inheritance pattern with a heterozygous mutation c.1072C>T (p.Arg358X) in the EDAR gene. A review of the literature with regard to other cases presenting the same mutation has been carried out and discussed.
Keywords: Child, Preschool; Ectodermal Dysplasia 1, Anhidrotic; Edar Receptor; Humans; Male; Mutation; Pedigree

Combined use of AFM and soft X-ray microscopy to reveal fibres' internalization in mesothelial cells. - Gianoncelli, Alessandra; Kourousias, George; Cammisuli, Francesca; Cassese, Damiano; Rizzardi, Clara; Radillo, Oriano; Lazzarino, Marco; Pascolo, Lorella (Analyst, 2017)
Nanotoxicology and nanomedicine investigations often require the probing of nano-objects such as fibres and particles in biological samples and cells, whilst internalization and intracellular destiny are the main issues for in vitro cellular studies. Various high resolution microscopy techniques are well suited for providing this highly sought-after information. However, sample preparation, nanomaterial composition and sectioning challenges make it often difficult to establish whether the fibres or particles have been internalized or they are simply overlaying or underlying the biological matter. In this paper we suggest a novel suitable combination of two different microscopic techniques to reveal in intact cells the uptake of asbestos fibres by mesothelial cells. After exposure to asbestos fibres and fixation, cells were first analysed under the AFM instrument and then imaged under the TwinMic soft X-ray microscope at Elettra Sincrotrone. The suggested approach combines standard soft X-ray microscopy imaging and AFM microscopy, with a common non-invasive sample preparation protocol which drastically reduces the experimental uncertainty and provides a quick and definitive answer to the nanoparticle cellular and tissue uptake.
Keywords: Asbestos; Cell Line; Epithelial Cells; Epithelium; Humans; Microscopy, Atomic Force; X-Rays

Common variants in CLDN14 are associated with differential excretion of magnesium over calcium in urine. - Corre, Tanguy; Olinger, Eric; Harris, Sarah E; Traglia, Michela; Ulivi, Sheila; Lenarduzzi, Stefania; Belge, Hendrica; Youhanna, Sonia; Tokonami, Natsuko; Bonny, Olivier; Houillier, Pascal; Polasek, Ozren; et al. (Pflugers Arch, 2017)
The nature and importance of genetic factors regulating the differential handling of Ca and Mg by the renal tubule in the general population are poorly defined. We conducted a genome-wide meta-analysis of urinary magnesium-to-calcium ratio to identify associated common genetic variants. We included 9320 adults of European descent from four genetic isolates and three urban cohorts. Urinary magnesium and calcium concentrations were measured centrally in spot urine, and each study conducted linear regression analysis of urinary magnesium-to-calcium ratio on ~2.5 million single-nucleotide polymorphisms (SNPs) using an additive model. We investigated, in mouse, the renal expression profile of the top candidate gene and its variation upon changes in dietary magnesium. The genome-wide analysis evidenced a top locus (rs172639, p = 1.7 × 10), encompassing CLDN14, the gene coding for claudin-14, that was genome-wide significant when using urinary magnesium-to-calcium ratio, but not either one taken separately. In mouse, claudin-14 is expressed in the distal nephron segments specifically handling magnesium, and its expression is regulated by chronic changes in dietary magnesium content. A genome-wide approach identified common variants in the CLDN14 gene exerting a robust influence on the differential excretion of Mg over Ca in urine. These data highlight the power of urinary electrolyte ratios to unravel genetic determinants of renal tubular function. Coupled with mouse experiments, these results support a major role for claudin-14, a gene associated with kidney stones, in the differential paracellular handling of divalent cations by the renal tubule.
Keywords: Animals; Calcium; Claudins; Humans; Kidney Tubules; Magnesium; Polymorphism, Single Nucleotide; Urine

Complement Protein C1q Binds to Hyaluronic Acid in the Malignant Pleural Mesothelioma Microenvironment and Promotes Tumor Growth. - Agostinis, Chiara; Vidergar, Romana; Belmonte, Beatrice; Mangogna, Alessandro; Amadio, Leonardo; Geri, Pietro; Borelli, Violetta; Zanconati, Fabrizio; Tedesco, Francesco; Confalonieri, Marco; Tripodo, Claudio; Kishore, Uday; et al. (Front Immunol, 2017)
C1q is the first recognition subcomponent of the complement classical pathway, which acts toward the clearance of pathogens and apoptotic cells. C1q is also known to modulate a range of functions of immune and non-immune cells, and has been shown to be involved in placental development and sensorial synaptic pruning. We have recently shown that C1q can promote tumor by encouraging their adhesion, migration, and proliferation in addition to angiogenesis and metastasis. In this study, we have examined the role of human C1q in the microenvironment of malignant pleural mesothelioma (MPM), a rare form of cancer commonly associated with exposure to asbestos. We found that C1q was highly expressed in all MPM histotypes, particularly in epithelioid rather than in sarcomatoid histotype. C1q avidly bound high and low molecular weight hyaluronic acid (HA) its globular domain. C1q bound to HA was able to induce adhesion and proliferation of mesothelioma cells (MES) enhancement of ERK1/2, SAPK/JNK, and p38 phosphorylation; however, it did not activate the complement cascade. Consistent with the modular organization of the globular domain, we demonstrated that C1q may bind to HA through ghA module, whereas it may interact with human MES through the ghC. In conclusion, C1q highly expressed in MPM binds to HA and enhances the tumor growth promoting cell adhesion and proliferation. These data can help develop novel diagnostic markers and molecular targets for MPM.

Cubosomes for in vivo fluorescence lifetime imaging. - Biffi, Stefania; Andolfi, Laura; Caltagirone, Claudia; Garrovo, Chiara; Falchi, Angela M; Lippolis, Vito; Lorenzon, Andrea; Macor, Paolo; Meli, Valeria; Monduzzi, Maura; Obiols-Rabasa, Marc; Petrizza, Luca; et al. (Nanotechnology, 2017)
Herein we provided the first proof of principle for in vivo fluorescence optical imaging application using monoolein-based cubosomes in a healthy mouse animal model. This formulation, administered at a non-cytotoxic concentration, was capable of providing both exogenous contrast for NIR fluorescence imaging with very high efficiency and chemospecific information upon lifetime analysis. Time-resolved measurements of fluorescence after the intravenous injection of cubosomes revealed that the dye rapidly accumulated mainly in the liver, while lifetimes profiles obtained in vivo allowed for discriminating between free dye or dye embedded within the cubosome nanostructure after injection.
Keywords: Animals; Carbocyanines; Cell Survival; Drug Compounding; Erythrocytes; Female; Fluorescent Dyes; Glycerides; Humans; Injections, Intravenous; Liposomes; Liver; Mice; Mice, Inbred BALB C; Nanoparticles; NIH 3T3 Cells; Optical Imaging; Particle Size; Spectroscopy, Near-Infrared; Time-Lapse Imaging

DEFB1 polymorphisms and salivary hBD-1 concentration in Oral Lichen Planus patients and healthy subjects. - Polesello, Vania; Zupin, Luisa; Di Lenarda, Roberto; Biasotto, Matteo; Pozzato, Gabriele; Ottaviani, Giulia; Gobbo, Margherita; Crovella, Sergio; Segat, Ludovica (Arch Oral Biol, 2017)
OBJECTIVES: The aetiology of Oral Lichen Planus (OLP), a chronic inflammatory disease of oral mucosa, is not yet well understood. Since innate immunity may be hypothesized as involved in the susceptibility to OLP, we studied human beta defensin 1 (hBD-1) an antimicrobial peptide constitutively expressed in the saliva, looking at functional genetic variants possibly able to diminish hBD-1 production an consequently conferring major susceptibility to OLP. DESIGN: We analysed three DEFB1 polymorphisms at 5' UTR, -52G>A (rs1799946), -44C>G (rs1800972), -20G>A (rs11362) and two DEFB1 polymorphisms at 3'UTR, c*5G>A (rs1047031), c*87A>G (rs1800971), with the aim of correlating these genetic variants and hBD-1 salivary level in a group of OLP patients and in healthy subjects. We also evaluated hBD-1 salivary concentrations, using ELISA, in OLP and healthy controls. RESULTS: We compared hBD-1 concentrations in OLP and healthy subjects: hBD-1 concentration was significantly higher in OLP patients respect to control. When considering the correlation between DEFB1 polymorphisms genotypes and hBD-1 expression levels, significant results were obtained for SNPs -52G>A (p=0.03 both in OLP patients and healthy individuals) and -44C>G (p=0.02 in OLP patients). CONCLUSIONS: hBD-1 production was different between OLP and healthy subjects (not age-matched with OLP). DEFB1 gene polymorphisms, -52G>A and -44C>G, correlated with hBD-1 salivary concentrations.
Keywords: 5' Untranslated Regions; Adult; Aged; Aged, 80 and over; beta-Defensins; Female; Genetic Predisposition to Disease; Genotype; Humans; Lichen Planus, Oral; Male; Middle Aged; Polymorphism, Single Nucleotide; Saliva; Sequence Analysis, DNA

Diagnosis and management of newly diagnosed childhood autoimmune haemolytic anaemia. Recommendations from the Red Cell Study Group of the Paediatric Haemato-Oncology Italian Association. - Ladogana, Saverio; Maruzzi, Matteo; Samperi, Piera; Perrotta, Silverio; Del Vecchio, Giovanni C; Notarangelo, Lucia D; Farruggia, Piero; Verzegnassi, Federico; Masera, Nicoletta; Saracco, Paola; Fasoli, Silvia; Miano, Maurizio; et al. (Blood Transfus, 2017)
Autoimmune haemolytic anaemia is an uncommon disorder to which paediatric haematology centres take a variety of diagnostic and therapeutic approaches. The Red Cell Working Group of the Italian Association of Paediatric Onco-haematology (Associazione Italiana di Ematologia ed Oncologia Pediatrica, AIEOP) developed this document in order to collate expert opinions on the management of newly diagnosed childhood autoimmune haemolytic anaemia.The diagnostic process includes the direct and indirect antiglobulin tests; recommendations are given regarding further diagnostic tests, specifically in the cases that the direct and indirect antiglobulin tests are negative. Clear-cut definitions of clinical response are stated. Specific recommendations for treatment include: dosage of steroid therapy and tapering modality for warm autoimmune haemolytic anaemia; the choice of rituximab as first-line therapy for the rare primary transfusion-dependent cold autoimmune haemolytic anaemia; the indications for supportive therapy; the need for switching to second-line therapy. Each statement is provided with a score expressing the level of appropriateness and the agreement among participants.
Keywords: Anemia, Hemolytic, Autoimmune; Blood Transfusion; Child; Coombs Test; Disease Management; Hematology; Humans; Immunoglobulin M; Italy; Pediatrics; Societies, Medical; Steroids

Enrichment of low-frequency functional variants revealed by whole-genome sequencing of multiple isolated European populations. - Xue, Yali; Mezzavilla, Massimo; Haber, Marc; McCarthy, Shane; Chen, Yuan; Narasimhan, Vagheesh; Gilly, Arthur; Ayub, Qasim; Colonna, Vincenza; Southam, Lorraine; Finan, Christopher; Massaia, Andrea; et al. (Nat Commun, 2017)
The genetic features of isolated populations can boost power in complex-trait association studies, and an in-depth understanding of how their genetic variation has been shaped by their demographic history can help leverage these advantageous characteristics. Here, we perform a comprehensive investigation using 3,059 newly generated low-depth whole-genome sequences from eight European isolates and two matched general populations, together with published data from the 1000 Genomes Project and UK10K. Sequencing data give deeper and richer insights into population demography and genetic characteristics than genotype-chip data, distinguishing related populations more effectively and allowing their functional variants to be studied more fully. We demonstrate relaxation of purifying selection in the isolates, leading to enrichment of rare and low-frequency functional variants, using novel statistics, DVxy and SVxy. We also develop an isolation-index (Isx) that predicts the overall level of such key genetic characteristics and can thus help guide population choice in future complex-trait association studies.
Keywords: European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Humans; Polymorphism, Single Nucleotide; Whole Genome Sequencing

Epratuzumab and Blinatumomab as Therapeutic Antibodies for Treatment of Pediatric Acute Lymphoblastic Leukemia: Current Status and Future Perspectives. - Franca, Raffaella; Favretto, Diego; Granzotto, Marilena; Decorti, Giuliana; Rabusin, Marco; Stocco, Gabriele (Curr Med Chem, 2017)
BACKGROUND: More than 85% of children affected by acute lymphoblastic leukemia (ALL) are successfully treated; however relapse remains a remarkable clinical concern, with 50-60% of relapsing patients facing a fatal outcome. Management of relapsed patients includes standardized intensive risk-adapted regimens based on conventional drugs, and hematopoietic stem cells transplantation for patients with unfavourable features. Biological drugs, in particular the monoclonal antibody epratuzumab and the bi-functional recombinant single chain peptide blinatumomab, have been recently recognized as novel potential agents to be integrated in salvage ALL therapy to further improve rescue outcome. METHODS: A systematic search of peer-reviewed scientific literature and clinical trials in public databases has been carried out. Both clinical and pre-clinical studies have been included to summarize recent evidence on epratuzumab and blinatumomab for salvage ALL therapy. RESULTS: Sixty-two papers and 25 clinical trials were included. Although not all patients responded properly to these agents, their use in relapsed and refractory pediatric ALL seems promising. CONCLUSION: Phase 3 studies have recently begun and more consistent results about epratuzumab and blinatumomab safety and efficacy in comparison to conventional therapies are expected in the next years. Epratuzumab seems safe in the dosing scheme proposed in ALL, but its efficacy over the conventional chemotherapy is still questionable. Blinatumomab has shown promising results in high risk cases such as elder adult patients and conclusive studies on pediatric ALL are needed. Patient inter-individual variability to these agents has not been investigated in depth, but this issue needs to be addressed, in particular for blinatumomab.
Keywords: Antibodies, Bispecific; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Antineoplastic Agents; Child; Clinical Trials as Topic; Half-Life; Humans; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Sialic Acid Binding Ig-like Lectin 2

Essure Permanent Birth Control, Effectiveness and Safety: An Italian 11-Year Survey. - Franchini, Mario; Zizolfi, Brunella; Coppola, Carmela; Bergamini, Valentino; Bonin, Cecilia; Borsellino, Giovanni; Busato, Enrico; Calabrese, Stefania; Calzolari, Stefano; Fantin, Gian Piero; Giarrè, Giovanna; Litta, Piero; et al. (J Minim Invasive Gynecol, 2017)
STUDY OBJECTIVE: To describe safety, tolerability, and effectiveness results through a minimum 2-year follow-up of patients who underwent permanent sterilization with the Essure insert. DESIGN: A retrospective multicenter study (Canadian Task Force classification II2). SETTING: Seven general hospitals and 4 clinical teaching centers in Italy. PATIENTS: A total of 1968 women, mean age 39.5 years (range, 23-48 years) who underwent office hysteroscopic sterilization using the Essure insert between April 1, 2003, and December 30, 2014. INTERVENTION: The women underwent office hysteroscopic bilateral Essure insert placement, with satisfactory device location and tube occlusion based on hysterosalpingography or hysterosalpingo-contrast sonography (HyCoSy). MEASUREMENTS AND MAIN RESULTS: Placement rate, successful bilateral tubal occlusion, perioperative adverse events, early postoperative (during the first 3 months of follow-up), and late complications were evaluated. Satisfactory insertion was accomplished in 97.2% of women and, in 4, perforation and 1 expulsion were detected during hysterosalpingography. Three unintended pregnancies occurred before the 3-month confirmation test. Two pregnancies were reported among women relying on the Essure inserts. Postprocedure pain was minimal and brief; in 9 women, pelvic pain became intractable, necessitating removal of the devices via laparoscopy. On telephone interviews, overall satisfaction was rated as "very satisfied" by the majority of women (97.6%), and no long-term adverse events were reported. CONCLUSION: The findings from this extended Italian survey further support the effectiveness, tolerability, and satisfaction of Essure hysteroscopic sterilization when motivated women are selected and well informed of the potential risks of the device. Moreover, the results do not demonstrate an increased incidence of complications and pregnancies associated with long-term Essure use. Patients with a known hypersensitivity to nickel may be less suitable candidates for the Essure insert.
Keywords: Adult; Fallopian Tubes; Female; Follow-Up Studies; Humans; Hypersensitivity; Hysterosalpingography; Hysteroscopy; Italy; Laparoscopy; Middle Aged; Nickel; Pain; Pregnancy; Pregnancy, Unplanned; Retrospective Studies; Sterilization, Reproductive; Sterilization, Tubal; Surveys and Questionnaires; Young Adult

Extent, Time Course, and Moderators of Antipsychotic Treatment in Youth With Mood Disorders: Results of a Meta-Analysis and Meta-Regression Analyses. - Cervesi, Chiara; Park, Su Young; Galling, Britta; Molteni, Silvia; Masi, Gabriele; Gerhard, Tobias; Olfson, Mark; Correll, Christoph U (J Clin Psychiatry, 2017)
OBJECTIVE: To meta-analytically examine the trends and correlates of antipsychotic use in youth with mood disorders. METHODS: Systematic literature search without language restriction in PubMed/MEDLINE/PsycINFO from database inception through March 2015 using the following search terms: (antipsychotic* OR neuroleptic* OR "dopamine blocker*" OR antidopaminergic) AND (child* OR adolescen* OR pediatric OR youth) AND (prescription* OR prescrib* OR use OR utilization OR database OR pharmacoepidemiolog* OR frequency OR rate OR rates). Random effects meta-analysis and meta-regression analyses were conducted. STUDY SELECTION: Included were studies reporting on the frequency of (1) mood disorders in antipsychotic-treated youth (≤ 19 years) and (2) antipsychotic use in youth with mood disorders. DATA ABSTRACTION: Two independent investigators abstracted data on study, patient, and treatment characteristics. RESULTS: Forty-one studies were meta-analyzed (N = 518,919, mean ± SD age = 12.8 ± 1.8 years, males = 65.7%). Altogether, 24.2% of antipsychotic-treated youth had a mood disorder diagnosis (studies = 34, depression spectrum disorder = 10.9%, bipolar spectrum disorder = 13.6%). In longitudinal studies, the overall proportion increased significantly from 17.3% in 2000 (range, 1996-2009) to 24.5% in 2006 (range, 2004-2011) (odds ratio [OR] = 1.50; 95% confidence interval [CI], 1.26-1.79; P < .0001). This increase was driven entirely by bipolar spectrum diagnoses (2001 = 11.1%, 2006 = 16.3%, P < .0001), rather than depression spectrum diagnoses (2001 = 9.1%, 2007 = 9.2%, P = .77). Among youth with mood disorders (8 studies), 24.0% received antipsychotics (depression spectrum disorder = 4.6%; bipolar spectrum disorder = 44.0%). CONCLUSIONS: The proportion of youth with mood disorder diagnoses increased significantly among antipsychotic-treated youth, driven entirely by an increase in youth with bipolar spectrum disorders. Progress in understanding the reasons for these trends and for an evaluation of the appropriateness of the observed antipsychotic prescribing requires more detailed information than is available in traditional pharmacoepidemiologic databases.
Keywords: Adolescent; Antipsychotic Agents; Bipolar Disorder; Child; Cross-Sectional Studies; Drug Utilization; Female; Humans; Longitudinal Studies; Male; Mood Disorders; Off-Label Use; Regression Analysis

Factors Influencing the Phenotypic Characterization of the Oral Marker, PROP. - Tepper, Beverly J; Melis, Melania; Koelliker, Yvonne; Gasparini, Paolo; Ahijevych, Karen L; Tomassini Barbarossa, Iole (Nutrients, 2017)
In the last several decades, the genetic ability to taste the bitter compound, 6--propyltiouracil (PROP) has attracted considerable attention as a model for understanding individual differences in taste perception, and as an oral marker for food preferences and eating behavior that ultimately impacts nutritional status and health. However, some studies do not support this role. This review describes common factors that can influence the characterization of this phenotype including: (1) changes in taste sensitivity with increasing age; (2) gender differences in taste perception; and (3) effects of smoking and obesity. We suggest that attention to these factors during PROP screening could strengthen the associations between this phenotype and a variety of health outcomes ranging from variation in body composition to oral health and cancer risk.
Keywords: Food Preferences; Genetic Variation; Humans; Propylthiouracil; Taste Perception; Taste Threshold

Fetal monitoring indications for delivery and 2-year outcome in 310 infants with fetal growth restriction delivered before 32 weeks' gestation in the TRUFFLE study. - Visser, G H A; Bilardo, C M; Derks, J B; Ferrazzi, E; Fratelli, N; Frusca, T; Ganzevoort, W; Lees, C C; Napolitano, R; Todros, T; Wolf, H; Hecher, K (Ultrasound Obstet Gynecol, 2017)
OBJECTIVE: In the TRUFFLE (Trial of Randomized Umbilical and Fetal Flow in Europe) study on the outcome of early fetal growth restriction, women were allocated to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate (FHR) short-term variation (STV) on cardiotocography (CTG); (2) early changes in fetal ductus venosus (DV) waveform (DV-p95); and (3) late changes in fetal DV waveform (DV-no-A). However, many infants per monitoring protocol were delivered because of safety-net criteria, for maternal or other fetal indications, or after 32 weeks of gestation when the protocol was no longer applied. The objective of the present posthoc subanalysis was to investigate the indications for delivery in relation to 2-year outcome in infants delivered before 32 weeks to further refine management proposals. METHODS: We included all 310 cases of the TRUFFLE study with known outcome at 2 years' corrected age and seven fetal deaths, excluding seven cases with inevitable perinatal death. Data were analyzed according to the allocated fetal monitoring strategy in combination with the indication for delivery. RESULTS: Overall, only 32% of liveborn infants were delivered according to the specified monitoring parameter for indication for delivery; 38% were delivered because of safety-net criteria, 15% for other fetal reasons and 15% for maternal reasons. In the CTG-STV group, 51% of infants were delivered because of reduced STV. In the DV-p95 group, 34% of infants were delivered because of abnormal DV and, in the DV-no-A group, only 10% of infants were delivered accordingly. The majority of infants in the DV groups were delivered for the safety-net criterion of spontaneous decelerations in FHR. Two-year intact survival was highest in the DV groups combined compared with the CTG-STV group (P = 0.05 for live births only, P = 0.21 including fetal death), with no difference between DV groups. A poorer outcome in the CTG-STV group was restricted to infants delivered because of FHR decelerations in the safety-net subgroup. Infants delivered because of maternal reasons had the highest birth weight and a non-significantly higher intact survival. CONCLUSIONS: In this subanalysis of infants delivered before 32 weeks, the majority were delivered for reasons other than the allocated monitoring strategy indication. Since, in the DV group, CTG-STV criteria were used as a safety net but in the CTG-STV group, no DV safety-net criteria were applied, we speculate that the slightly poorer outcome in the CTG-STV group might be explained by the absence of DV data. The optimal timing of delivery of fetuses with early intrauterine growth restriction may therefore be best determined by monitoring them longitudinally, with both DV and CTG monitoring. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Cardiotocography; Delivery, Obstetric; Female; Fetal Growth Retardation; Fetal Monitoring; Fetus; Gestational Age; Humans; Infant, Newborn; Male; Netherlands; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal; Umbilical Arteries

Genetic structure in the Sherpa and neighboring Nepalese populations. - Cole, Amy M; Cox, Sean; Jeong, Choongwon; Petousi, Nayia; Aryal, Dhana R; Droma, Yunden; Hanaoka, Masayuki; Ota, Masao; Kobayashi, Nobumitsu; Gasparini, Paolo; Montgomery, Hugh; Robbins, Peter; et al. (BMC Genomics, 2017)
BACKGROUND: We set out to describe the fine-scale population structure across the Eastern region of Nepal. To date there is relatively little known about the genetic structure of the Sherpa residing in Nepal and their genetic relationship with the Nepalese. We assembled dense genotype data from a total of 1245 individuals representing Nepal and a variety of different populations resident across the greater Himalayan region including Tibet, China, India, Pakistan, Kazakhstan, Uzbekistan, Tajikistan and Kirghizstan. We performed analysis of principal components, admixture and homozygosity. RESULTS: We identified clear substructure across populations resident in the Himalayan arc, with genetic structure broadly mirroring geographical features of the region. Ethnic subgroups within Nepal show distinct genetic structure, on both admixture and principal component analysis. We detected differential proportions of ancestry from northern Himalayan populations across Nepalese subgroups, with the Nepalese Rai, Magar and Tamang carrying the greatest proportions of Tibetan ancestry. CONCLUSIONS: We show that populations dwelling on the Himalayan plateau have had a clear impact on the Northern Indian gene pool. We illustrate how the Sherpa are a remarkably isolated population, with little gene flow from surrounding Nepalese populations.
Keywords: Asian Continental Ancestry Group; Chromosomes, Human, Y; DNA; DNA, Mitochondrial; Ethnic Groups; Gene Flow; Genotype; Humans; Leukocytes; Likelihood Functions; Nepal; Principal Component Analysis

Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk. - Warren, Helen R; Evangelou, Evangelos; Cabrera, Claudia P; Gao, He; Ren, Meixia; Mifsud, Borbala; Ntalla, Ioanna; Surendran, Praveen; Liu, Chunyu; Cook, James P; Kraja, Aldi T; Drenos, Fotios; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.
Keywords: Adult; Blood Pressure; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genomic analyses identify hundreds of variants associated with age at menarche and support a role for puberty timing in cancer risk. - Day, Felix R; Thompson, Deborah J; Helgason, Hannes; Chasman, Daniel I; Finucane, Hilary; Sulem, Patrick; Ruth, Katherine S; Whalen, Sean; Sarkar, Abhishek K; Albrecht, Eva; Altmaier, Elisabeth; Amini, Marzyeh; et al. (Nat Genet, 2017)
The timing of puberty is a highly polygenic childhood trait that is epidemiologically associated with various adult diseases. Using 1000 Genomes Project-imputed genotype data in up to ∼370,000 women, we identify 389 independent signals (P < 5 × 10) for age at menarche, a milestone in female pubertal development. In Icelandic data, these signals explain ∼7.4% of the population variance in age at menarche, corresponding to ∼25% of the estimated heritability. We implicate ∼250 genes via coding variation or associated expression, demonstrating significant enrichment in neural tissues. Rare variants near the imprinted genes MKRN3 and DLK1 were identified, exhibiting large effects when paternally inherited. Mendelian randomization analyses suggest causal inverse associations, independent of body mass index (BMI), between puberty timing and risks for breast and endometrial cancers in women and prostate cancer in men. In aggregate, our findings highlight the complexity of the genetic regulation of puberty timing and support causal links with cancer susceptibility.
Keywords: Adolescent; Age Factors; Body Mass Index; Databases, Genetic; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomic Imprinting; Humans; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Neoplasms; Polymorphism, Single Nucleotide; Puberty; Quantitative Trait Loci; Ribonucleoproteins; Risk Factors

Gray platelet syndrome: Novel mutations of the NBEAL2 gene. - Bottega, Roberta; Nicchia, Elena; Alfano, Caterina; Glembotsky, Ana C; Pastore, Annalisa; Bertaggia-Calderara, Debora; Bisig, Bettina; Duchosal, Michel A; Arbesú, Guillermo; Alberio, Lorenzo; Heller, Paula G; Savoia, Anna (Am J Hematol, 2017)
Keywords: Adult; Alleles; Blood Proteins; Child; Female; Gene Expression; Gene Frequency; Genotype; Gray Platelet Syndrome; Humans; Male; Mutation; Phenotype; Platelet Aggregation; Platelet Count; Platelet Membrane Glycoproteins

How to monitor pregnancies complicated by fetal growth restriction and delivery before 32 weeks: post-hoc analysis of TRUFFLE study. - Ganzevoort, W; Mensing Van Charante, N; Thilaganathan, B; Prefumo, F; Arabin, B; Bilardo, C M; Brezinka, C; Derks, J B; Diemert, A; Duvekot, J J; Ferrazzi, E; Frusca, T; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: In the recent TRUFFLE study, it appeared that, in pregnancies complicated by fetal growth restriction (FGR) between 26 and 32 weeks' gestation, monitoring of the fetal ductus venosus (DV) waveform combined with computed cardiotocography (CTG) to determine timing of delivery increased the chance of infant survival without neurological impairment. However, concerns with the interpretation were raised, as DV monitoring appeared to be associated with a non-significant increase in fetal death, and some infants were delivered after 32 weeks, at which time the study protocol no longer applied. This secondary sensitivity analysis of the TRUFFLE study focuses on women who delivered before 32 completed weeks' gestation and analyzes in detail the cases of fetal death. METHODS: Monitoring data of 317 pregnancies with FGR that delivered before 32 weeks were analyzed, excluding those with absent outcome data or inevitable perinatal death. Women were allocated randomly to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate short-term variation (STV) on CTG; (2) early changes in fetal DV waveform; and (3) late changes in fetal DV waveform. Primary outcome was 2-year survival without neurological impairment. The association of the last monitoring data before delivery and infant outcome was assessed by multivariable analysis. RESULTS: Two-year survival without neurological impairment occurred more often in the two DV groups (both 83%) than in the CTG-STV group (77%), however, the difference was not statistically significant (P = 0.21). Among the surviving infants in the DV groups, 93% were free of neurological impairment vs 85% of surviving infants in the CTG-STV group (P = 0.049). All fetal deaths (n = 7) occurred in the groups with DV monitoring. Of the monitoring parameters obtained shortly before fetal death in these seven cases, an abnormal CTG was observed in only one case. Multivariable regression analysis of factors at study entry demonstrated that a later gestational age, higher estimated fetal weight-to-50 percentile ratio and lower umbilical artery pulsatility index (PI)/fetal middle cerebral artery-PI ratio were significantly associated with normal outcome. Allocation to DV monitoring had a smaller effect on outcome, but remained in the model (P < 0.1). Abnormal fetal arterial Doppler before delivery was significantly associated with adverse outcome in the CTG-STV group. In contrast, abnormal DV flow was the only monitoring parameter associated with adverse outcome in the DV groups, while fetal arterial Doppler, STV below the cut-off used in the CTG-STV group and recurrent decelerations in fetal heart rate were not. CONCLUSIONS: In accordance with the findings of the TRUFFLE study on monitoring and intervention management of very preterm FGR, we found that the proportion of infants surviving without neuroimpairment was not significantly different when the decision for delivery was based on changes in DV waveform vs reduced STV on CTG. The uneven distribution of fetal deaths towards the DV groups was probably a chance effect, and neurological outcome was better among surviving children in these groups. Before 32 weeks, delaying delivery until abnormalities in DV-PI or STV and/or recurrent decelerations in fetal heat rate occur, as defined by the study protocol, is likely to be safe and possibly benefits long-term outcome. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Central Nervous System Diseases; Child, Preschool; Female; Fetal Growth Retardation; Fetal Membranes, Premature Rupture; Gestational Age; Heart Rate, Fetal; Humans; Infant; Infant, Extremely Premature; Male; Middle Cerebral Artery; Pregnancy; Pulsatile Flow; Survival Analysis; Treatment Outcome; Ultrasonography, Prenatal; Uterine Artery

Immediate delivery or expectant management in gestational diabetes at term: the GINEXMAL randomised controlled trial. - Alberico, S; Erenbourg, A; Hod, M; Yogev, Y; Hadar, E; Neri, F; Ronfani, L; Maso, G (BJOG, 2017)
OBJECTIVE: To evaluate maternal and perinatal outcomes after induction of labour versus expectant management in pregnant women with gestational diabetes at term. DESIGN: Multicentre open-label randomised controlled trial. SETTING: Eight teaching hospitals in Italy, Slovenia, and Israel. SAMPLE: Singleton pregnancy, diagnosed with gestational diabetes by the International Association of Diabetes and Pregnancy Study Groups criteria (IADPSGC), between 38 and 39 weeks of gestation, without other maternal or fetal conditions. METHODS: Patients were randomly assigned to induction of labour or expectant management and intensive follow-up. Data were analysed by 'intention to treat'. MAIN OUTCOME MEASURES: The primary outcome was incidence of caesarean section. Secondary outcomes were maternal and perinatal mortality and morbidity. RESULTS: A total of 425 women were randomised to the study groups. The incidence of caesarean section was 12.6% in the induction group versus 11.7% in the expectant group. No difference was found between the two groups (relative risk, RR 1.06; 95% confidence interval, 95% CI 0.64-1.77; P = 0.81). The incidence of non-spontaneous delivery, either by caesarean section or by operative vaginal delivery, was 21.0 and 22.3%, respectively (RR 0.94; 95% CI 0.66-1.36; P = 0.76). Neither maternal nor fetal deaths occurred. The few cases of shoulder dystocia were solved without any significant birth trauma. CONCLUSIONS: In women with gestational diabetes, without other maternal or fetal conditions, no difference was detected in birth outcomes regardless of the approach used (i.e. active versus expectant management). Although the study was underpowered, the magnitude of the between-group difference was very small and without clinical relevance. TWEETABLE ABSTRACT: Immediate delivery or expectant management in gestational diabetes at term?
Keywords: Adult; Delivery, Obstetric; Diabetes, Gestational; Female; Humans; Infant, Newborn; Israel; Italy; Maternal Mortality; Perinatal Mortality; Pregnancy; Pregnancy Outcome; Slovenia; Term Birth; Watchful Waiting

Imported arboviral infections in Italy, July 2014-October 2015: a National Reference Laboratory report. - Fortuna, Claudia; Remoli, Maria Elena; Rizzo, Caterina; Benedetti, Eleonora; Fiorentini, Cristiano; Bella, Antonino; Argentini, Claudio; Farchi, Francesca; Castilletti, Concetta; Capobianchi, Maria Rosaria; Zammarchi, Lorenzo; Bartoloni, Alessandro; et al. (BMC Infect Dis, 2017)
BACKGROUND: Imported cases of infections due to Dengue (DENV) and Chikungunya (CHIKV) viruses and, more recently, Zika virus (ZIKV) are commonly reported among travelers returning from endemic regions. In areas where potentially competent vectors are present, the risk of autochthonous transmission of these vector-borne pathogens is relatively high. Laboratory surveillance is crucial to rapidly detect imported cases in order to reduce the risk of transmission. This study describes the laboratory activity performed by the National Reference Laboratory for Arboviruses (NRLA) at the Italian National Institute of Health in the period from July 2014 to October 2015. METHODS: Samples from 180 patients visited/hospitalized with a suspected DENV/CHIKV/ZIKV infection were sent to the NRLA from several Italian Hospitals and from Regional Reference Laboratories for Arboviruses, in agreement with the National Plan on human surveillance of vector-borne diseases. Both serological (ELISA IgM test and Plaque Reduction Neutralization Test-PRNT) and molecular assays (Real Time PCR tests, RT-PCR plus nested PCR and sequencing of positive samples) were performed. RESULTS: DENV infection was the most frequently diagnosed (80 confirmed/probable cases), and all four genotypes were detected. However, an increase in imported CHIKV cases (41 confirmed/probable cases) was observed, along with the detection of the first ZIKV cases (4 confirmed cases), as a consequence of the recent spread of both CHIKV and ZIKV in the Americas. CONCLUSIONS: Main diagnostic issues highlighted in our study are sensitivity limitations of molecular tests, and the importance of PRNT to confirm serological results for differential diagnosis of Arboviruses. The continuous evaluation of diagnostic strategy, and the implementation of laboratories networks involved in surveillance activities is essential to ensure correct diagnosis, and to improve the preparedness for a rapid and proper identification of viral threats.
Keywords: Chikungunya Fever; Chikungunya virus; Dengue; Dengue Virus; Disease Outbreaks; Female; Genotype; Humans; Italy; Male; Molecular Diagnostic Techniques; Population Surveillance; Public Health; Travel; Young Adult; Zika Virus; Zika Virus Infection

Intra-articular corticosteroids versus intra-articular corticosteroids plus methotrexate in oligoarticular juvenile idiopathic arthritis: a multicentre, prospective, randomised, open-label trial. - Ravelli, Angelo; Davì, Sergio; Bracciolini, Giulia; Pistorio, Angela; Consolaro, Alessandro; van Dijkhuizen, Evert Hendrik Pieter; Lattanzi, Bianca; Filocamo, Giovanni; Verazza, Sara; Gerloni, Valeria; Gattinara, Maurizio; Pontikaki, Irene; et al. (Lancet, 2017)
BACKGROUND: Little evidence-based information is available to guide the treatment of oligoarticular juvenile idiopathic arthritis. We aimed to investigate whether oral methotrexate increases the efficacy of intra-articular corticosteroid therapy. METHODS: We did this prospective, open-label, randomised trial at ten hospitals in Italy. Using a concealed computer-generated list, children younger than 18 years with oligoarticular-onset disease were randomly assigned (1:1) to intra-articular corticosteroids alone or in combination with oral methotrexate (15 mg/m; maximum 20 mg). Corticosteroids used were triamcinolone hexacetonide (shoulder, elbow, wrist, knee, and tibiotalar joints) or methylprednisolone acetate (ie, subtalar and tarsal joints). We did not mask patients or investigators to treatment assignments. Our primary outcome was the proportion of patients in the intention-to-treat population who had remission of arthritis in all injected joints at 12 months. This trial is registered with European Union Clinical Trials Register, EudraCT number 2008-006741-70. FINDINGS: Between July 7, 2009, and March 31, 2013, we screened 226 participants and randomly assigned 102 to intra-articular corticosteroids alone and 105 to intra-articular corticosteroids plus methotrexate. 33 (32%) patients assigned to intra-articular corticosteroids alone and 39 (37%) assigned to intra-articular corticosteroids and methotrexate therapy had remission of arthritis in all injected joints (p=0·48). Adverse events were recorded for 20 (17%) patients who received methotrexate, which led to permanent treatment discontinuation in two patients (one due to increased liver transaminases and one due to gastrointestinal discomfort). No patient had a serious adverse event. INTERPRETATION: Concomitant administration of methotrexate did not augment the effectiveness of intra-articular corticosteroid therapy. Future studies are needed to define the optimal therapeutic strategies for oligoarticular juvenile idiopathic arthritis. FUNDING: Italian Agency of Drug Evaluation.
Keywords: Adrenal Cortex Hormones; Arthritis, Juvenile; Humans; Injections, Intra-Articular; Italy; Methotrexate; Prospective Studies; Treatment Outcome

Intranasal Dexmedetomidine Sedation as Adjuvant Therapy in Acute Asthma Exacerbation With Marked Anxiety and Agitation. - Cozzi, Giorgio; Lega, Sara; Giorgi, Rita; Barbi, Egidio (Ann Emerg Med, 2017)
We describe 2 patients with acute asthma exacerbation who were admitted to the emergency department (ED) with severe agitation and restlessness as a prominent finding, for which bedside asthma treatment sedation with intranasal dexmedetomidine was performed. In both cases, dexmedetomidine allowed the patients to rest and improved tolerance to treatment. Dexmedetomidine is a unique sedative with an excellent safety profile and minimal effect on respiratory function. These properties render it particularly promising for the management of severe agitation in children admitted to the ED with acute asthma exacerbation.
Keywords: Acute Disease; Administration, Intranasal; Anxiety; Asthma; Child, Preschool; Dexmedetomidine; Emergency Service, Hospital; Female; Humans; Hypnotics and Sedatives; Infant; Psychomotor Agitation

ISL1 is a major susceptibility gene for classic bladder exstrophy and a regulator of urinary tract development. - Zhang, Rong; Knapp, Michael; Suzuki, Kentaro; Kajioka, Daiki; Schmidt, Johanna M; Winkler, Jonas; Yilmaz, Öznur; Pleschka, Michael; Cao, Jia; Kockum, Christina Clementson; Barker, Gillian; Holmdahl, Gundela; et al. (Sci Rep, 2017)
Previously genome-wide association methods in patients with classic bladder exstrophy (CBE) found association with ISL1, a master control gene expressed in pericloacal mesenchyme. This study sought to further explore the genetics in a larger set of patients following-up on the most promising genomic regions previously reported. Genotypes of 12 markers obtained from 268 CBE patients of Australian, British, German Italian, Spanish and Swedish origin and 1,354 ethnically matched controls and from 92 CBE case-parent trios from North America were analysed. Only marker rs6874700 at the ISL1 locus showed association (p = 2.22 × 10). A meta-analysis of rs6874700 of our previous and present study showed a p value of 9.2 × 10. Developmental biology models were used to clarify the location of ISL1 activity in the forming urinary tract. Genetic lineage analysis of Isl1-expressing cells by the lineage tracer mouse model showed Isl1-expressing cells in the urinary tract of mouse embryos at E10.5 and distributed in the bladder at E15.5. Expression of isl1 in zebrafish larvae staged 48 hpf was detected in a small region of the developing pronephros. Our study supports ISL1 as a major susceptibility gene for CBE and as a regulator of urinary tract development.
Keywords: Animals; Bladder Exstrophy; Embryo, Mammalian; Female; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Humans; Larva; LIM-Homeodomain Proteins; Mesoderm; Mice; Organogenesis; Polymorphism, Single Nucleotide; Pronephros; Protein Isoforms; Transcription Factors; Urinary Tract; Zebrafish

The Italian Society for Pediatric Nephrology (SINePe) consensus document on the management of nephrotic syndrome in children: Part I - Diagnosis and treatment of the first episode and the first relapse. - Pasini, Andrea; Benetti, Elisa; Conti, Giovanni; Ghio, Luciana; Lepore, Marta; Massella, Laura; Molino, Daniela; Peruzzi, Licia; Emma, Francesco; Fede, Carmelo; Trivelli, Antonella; Maringhini, Silvio; et al. (Ital J Pediatr, 2017)
This consensus document is aimed at providing an updated, multidisciplinary overview on the diagnosis and treatment of pediatric nephrotic syndrome (NS) at first presentation. It is the first consensus document of its kind to be produced by all the pediatric nephrology centres in Italy, in line with what is already present in other countries such as France, Germany and the USA. It is based on the current knowledge surrounding the symptomatic and steroid treatment of NS, with a view to providing the basis for a separate consensus document on the treatment of relapses. NS is one of the most common pediatric glomerular diseases, with an incidence of around 2-7 cases per 100000 children per year. Corticosteroids are the mainstay of treatment, but the optimal therapeutic regimen for managing childhood idiopathic NS is still under debate. In Italy, shared treatment guidelines were lacking and, consequently, the choice of steroid regimen was based on the clinical expertise of each individual unit. On the basis of the 2015 Cochrane systematic review, KDIGO Guidelines and more recent data from the literature, this working group, with the contribution of all the pediatric nephrology centres in Italy and on the behalf of the Italian Society of Pediatric Nephrology, has produced a shared steroid protocol that will be useful for National Health System hospitals and pediatricians. Investigations at initial presentation and the principal causes of NS to be screened are suggested. In the early phase of the disease, symptomatic treatment is also important as many severe complications can occur which are either directly related to the pathophysiology of the underlying NS or to the steroid treatment itself. To date, very few studies have been published on the prophylaxis and treatment of these early complications, while recommendations are either lacking or conflicting. This consensus provides indications for the prevention, early recognition and treatment of these complications (management of edema and hypovolemia, therapy and prophylaxis of infections and thromboembolic events). Finally, recommendations about the clinical definition of steroid resistance and its initial diagnostic management, as well as indications for renal biopsy are provided.
Keywords: Adrenal Cortex Hormones; Child; Child, Preschool; Consensus; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Humans; Italy; Male; Nephrotic Syndrome; Practice Guidelines as Topic; Prognosis; Recurrence; Retreatment; Societies, Medical; Survival Rate; Treatment Outcome

Lack of Prenylated Proteins, Autophagy Impairment and Apoptosis in SH-SY5Y Neuronal Cell Model of Mevalonate Kinase Deficiency. - Tricarico, Paola Maura; Romeo, Alessandra; Gratton, Rossella; Crovella, Sergio; Celsi, Fulvio (Cell Physiol Biochem, 2017)
BACKGROUND/AIMS: Mevalonate Kinase Deficiency (MKD), is a hereditary disease due to mutations in mevalonate kinase gene (MVK). MKD has heterogeneous clinical phenotypes: the correlation between MVK mutations and MKD clinical phenotype is still to be fully elucidated. Deficiency of prenylated proteins has been hypothesized as possible MKD pathogenic mechanism. Based on this hypothesis and considering that neurologic impairment characterizes Mevalonic Aciduria (MA), the most severe form of MKD, we studied the effects of I268T and N301T MVK mutations on protein prenylation, autophagy and programmed cell death in SH-SY5Y neuroblastoma cell lines. METHODS: SH-SY5Y cells were transiently transfected, with the pCMV-6 plasmid containing MVK wild type and the two mutated sequences. Protein prenylation levels were evaluated using GFP-RhoA-F to assess farnesylation, and GFP-RhoA to evaluate geranylgeranylation; autophagy was measured by evaluating LC3 and p62 protein levels, while Annexin V-FITC and Propidium Iodide staining allowed apoptosis detection. RESULTS: MVK mutants' over-expression causes decreased levels of farnesylation and geranylgeranylation, and also increased LC3 lipidation in SH-SY5Y, with concomitant p62 accumulation. Treatment with bafilomycin A1 (an inhibitor of vacuolar H+-ATPase, a late autophagy inhibitor) further increase LC3-II and p62 levels, suggesting that degradation of autophagolysosome could be impaired. SH-SY5Y, with both MVK mutants, showed apoptosis increase; the presence of N301T associated with augmented cell death. CONCLUSIONS: We hypothesize that mevalonate pathway impairment causes alteration of farnesylation and geranylgeranylation proteins and alteration of the autophagic flux; these changes can induce apoptosis, possibly more relevant in the presence of N301T mutation.
Keywords: Animals; Apoptosis; Autophagy; Cell Line, Tumor; Macrolides; Mevalonate Kinase Deficiency; Microtubule-Associated Proteins; Models, Biological; Mutation; Phosphotransferases (Alcohol Group Acceptor); Protein Prenylation; Rats

Longitudinal study of computerized cardiotocography in early fetal growth restriction. - Wolf, H; Arabin, B; Lees, C C; Oepkes, D; Prefumo, F; Thilaganathan, B; Todros, T; Visser, G H A; Bilardo, C M; Derks, J B; Diemert, A; Duvekot, J J; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: To explore whether, in early fetal growth restriction (FGR), the longitudinal pattern of fetal heart rate (FHR) short-term variation (STV) can be used to identify imminent fetal distress and whether abnormalities of FHR recordings are associated with 2-year infant outcome. METHODS: The original TRUFFLE study assessed whether, in early FGR, delivery based on ductus venosus (DV) Doppler pulsatility index (PI), in combination with safety-net criteria of very low STV on cardiotocography (CTG) and/or recurrent FHR decelerations, could improve 2-year infant survival without neurological impairment in comparison with delivery based on CTG monitoring only. This was a secondary analysis of women who delivered before 32 weeks and had consecutive STV data recorded > 3 days before delivery and known infant outcome at 2 years of age. Women who received corticosteroids within 3 days of delivery were excluded. Individual regression line algorithms of all STV values, except the last one before delivery, were calculated. Life tables and Cox regression analysis were used to calculate the daily risk for low STV or very low STV and/or FHR decelerations (below DV group safety-net criteria) and to assess which parameters were associated with this risk. Furthermore, it was assessed whether STV pattern, last STV value or recurrent FHR decelerations were associated with 2-year infant outcome. RESULTS: One hundred and forty-nine women from the original TRUFFLE study met the inclusion criteria. Using the individual STV regression lines, prediction of a last STV below the cut-off used by the CTG monitoring group had sensitivity of 42% and specificity of 91%. For each day after study inclusion, the median risk for low STV (CTG group cut-off) was 4% (interquartile range (IQR), 2-7%) and for very low STV and/or recurrent FHR decelerations (below DV group safety-net criteria) was 5% (IQR, 4-7%). Measures of STV pattern, fetal Doppler (arterial or venous), birth-weight multiples of the median and gestational age did not usefully improve daily risk prediction. There was no association of STV regression coefficients, a low last STV and/or recurrent FHR decelerations with short- or long-term infant outcomes. CONCLUSION: The TRUFFLE study showed that a strategy of DV monitoring with safety-net criteria of very low STV and/or recurrent FHR decelerations for delivery indication could increase 2-year infant survival without neurological impairment. This post-hoc analysis demonstrates that, in early FGR, the daily risk of abnormal CTG, as defined by the DV group safety-net criteria, is 5%, and that prediction is not possible. This supports the rationale for CTG monitoring more often than daily in these high-risk fetuses. Low STV and/or recurrent FHR decelerations were not associated with adverse infant outcome and it appears safe to delay intervention until such abnormalities occur, as long as DV-PI is within normal range. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Child, Preschool; Female; Fetal Growth Retardation; Fetal Heart; Heart Rate, Fetal; Humans; Infant; Infant, Newborn; Longitudinal Studies; Middle Cerebral Artery; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal

LTF and DEFB1 polymorphisms are associated with susceptibility toward chronic periodontitis development. - Zupin, L; Robino, A; Navarra, C O; Pirastu, N; Di Lenarda, R; Gasparini, P; Crovella, S; Bevilacqua, L (Oral Dis, 2017)
OBJECTIVES: Chronic periodontitis is a common pathological condition that affects the supporting tissue of the teeth, leading to progressive alveolar bone destruction and teeth loss. The disease is caused by bacteria and derives from an altered host immune and inflammatory response, also involving different factors such as the oral hygiene, smoking, and genetic background. The innate immune response, the first line of host defense, could also play an important role in the susceptibility to chronic periodontitis. In this study, we evaluated the possible association between periodontal disease and seven genetic variations within DEFB1 and LTF genes, encoding for β-defensins 1 and lactoferrin (two members of oral innate immune system), in an Italian isolated population. SUBJECTS AND METHODS: DEFB1 5'UTR g. -52G>A (rs1799946), g. -44C>G (rs1800972), g. -20G>A (rs11362), 3'UTR c*5G>A (rs1047031), c*87A>G (rs1800971), LTF p.Ala29Thr (rs1126477), and p.Lys47Arg (rs1126478) single nucleotide polymorphisms (SNPs) were analyzed in 155 healthy individuals and 439 chronic periodontitis patients from North-East Italy. RESULTS: Significant associations were found between periodontitis and g. -20G>A (rs11362) and g. -44C>G (rs1800972) SNPs in DEFB1 gene as well as p.Ala29Thr (rs1126477) and p.Lys47Arg (rs1126478) SNPs in LTF gene. DISCUSSION: Our results suggest the involvement of DEFB1 and LTF genetic variations in the susceptibility toward development of periodontitis.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; beta-Defensins; Case-Control Studies; Chronic Periodontitis; Female; Genetic Predisposition to Disease; Humans; Lactoferrin; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Metastatic neuroblastoma in infants: are survival rates excellent only within the stringent framework of clinical trials? - Di Cataldo, A; Agodi, A; Balaguer, J; Garaventa, A; Barchitta, M; Segura, V; Bianchi, M; Castel, V; Castellano, A; Cesaro, S; Couselo, J M; Cruz, O; et al. (Clin Transl Oncol, 2017)
INTRODUCTION: SIOPEN INES protocol yielded excellent 5-year survival rates for MYCN-non-amplified metastatic neuroblastoma. Patients deemed ineligible due to lack or delay of MYCN status or late registration were treated, but not included in the study. Our goal was to analyse survival at 10 years among the whole population. MATERIALS AND METHODS: Italian and Spanish metastatic INES patients' data are reported. SPSS 20.0 was used for statistical analysis. RESULTS: Among 98 infants, 27 had events and 19 died, while 79 were disease free. Five- and 10-year event-free survival (EFS) were 73 and 70 %, and overall survival (OS) was 81 and 74 %, respectively. MYCN status was significant for EFS, but not for OS in multivariate analysis. CONCLUSIONS: The survival rates of patients who complied with all the inclusion criteria for INES trials are higher compared to those that included also not registered patients. Five-year EFS and OS for INES 99.2 were 87.8 and 95.7 %, while our stage 4s population obtained 78 and 87 %. Concerning 99.3, 5-year EFS and OS were 86.7 and 95.6 %, while for stage 4 we registered 61 and 68 %. MYCN amplification had a strong impact on prognosis and therefore we consider it unacceptable that many patients were not studied for MYCN and probably inadequately treated. Ten-year survival rates were shown to decrease: EFS from 73 to 70 % and OS from 81 to 74 %, indicating a risk of late events, particularly in stage 4s. Population-based registries like European ENCCA WP 11-task 11 will possibly clarify these data.
Keywords: Biomarkers, Tumor; Child; Child, Preschool; Clinical Trials as Topic; Combined Modality Therapy; Female; Follow-Up Studies; Gene Amplification; Humans; Infant; Infant, Newborn; Male; N-Myc Proto-Oncogene Protein; Neoplasm Staging; Neuroblastoma; Prognosis; Survival Rate

"Milky" bowel and malrotation. - Poillucci, Gabriele; Degrassi, Ferruccio; Guida, Edoardo; Pederiva, Federica (Surgery, 2017)
Keywords: Appendectomy; Chylous Ascites; Digestive System Abnormalities; Follow-Up Studies; Humans; Infant, Newborn; Intestinal Volvulus; Laparotomy; Male; Rare Diseases; Severity of Illness Index; Tomography, X-Ray Computed; Treatment Outcome; Ultrasonography, Doppler

Mutations of RUNX1 in families with inherited thrombocytopenia. - De Rocco, Daniela; Melazzini, Federica; Marconi, Caterina; Pecci, Alessandro; Bottega, Roberta; Gnan, Chiara; Palombo, Flavia; Giordano, Paola; Coccioli, Maria Susanna; Glembotsky, Ana C; Heller, Paula G; Seri, Marco; et al. (Am J Hematol, 2017)
Keywords: Adult; Blood Platelets; Cell Size; Child; Child, Preschool; Core Binding Factor Alpha 2 Subunit; Female; Frameshift Mutation; Genes, Dominant; Heterozygote; Humans; Introns; Leukemia, Myeloid, Acute; Male; Middle Aged; Mutation, Missense; Protein Domains; RNA Splice Sites; Sequence Deletion; Thrombocythemia, Essential; Thrombopoietin; Transcriptional Activation; Young Adult

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near , , , , , and , and provide new replication evidence for a further 2 signals in and Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

A Novel Panel of Serum Biomarkers for MPM Diagnosis. - Bonotti, A; Foddis, R; Landi, S; Melaiu, O; De Santi, C; Giusti, L; Donadio, E; Ciregia, F; Mazzoni, M R; Lucacchini, A; Bovenzi, M; Comar, M; et al. (Dis Markers, 2017)
Exposure to asbestos is the main cause of malignant pleural mesothelioma (MPM), a highly aggressive cancer of the pleura. Since the only tools for early detection are based on radiological tests, some authors focused on serum markers (i.e., mesothelin). The aim of this study was the evaluation of new serum biomarkers to be used individually or in combination, in order to improve the outcome of patients whose disease would be diagnosed at an earlier stage. Serum and plasma were available from 43 subjects previously exposed to asbestos and 27 MPM patients, all being epithelioid type. All the new markers found differentially expressed in MPM and healthy subjects, by proteomic and genomic approaches, have been validated in the serum by the use of specific ELISA. The combined approach, using tools of genomics and proteomics, is found to be highly innovative for this type of disease and led to the identification of new serum markers in the diagnosis of MPM. These results, if confirmed in a larger series, may have a strong impact in this area, because early detection of this cancer in people at high risk could significantly improve the course of the disease and the clinical approach to an individualized therapy.
Keywords: Aged; Biomarkers, Tumor; Blood Proteins; Case-Control Studies; Female; Humans; Lung Neoplasms; Male; Mesothelioma; Middle Aged; Proteome

Outcome of childhood-onset full-house nephropathy. - Ruggiero, Barbara; Vivarelli, Marina; Gianviti, Alessandra; Pecoraro, Carmine; Peruzzi, Licia; Benetti, Elisa; Ventura, Giovanna; Pennesi, Marco; Murer, Luisa; Coppo, Rosanna; Emma, Francesco (Nephrol Dial Transplant, 2017)
Background: Patients with full-house nephropathy (FHN) present renal lesions that are indistinguishable from those of lupus nephritis (LN) but lack the systemic features necessary to meet diagnostic criteria for systemic lupus erithematosus (SLE). Some have been reported to develop a delayed SLE with time. The clinical outcome of children having FHN without SLE has never been reported. Methods: Children with biopsy-proven FHN were selected after excluding SLE cases by the absence of America College of Rheumatology criteria. The proportion of patients with complete (proteinuria <0.5 g/day) or partial remission (proteinuria ≤50% from baseline), relapse (estimated glomerular filtration rate <25% and/or proteinuria ≥50% from baseline) and progression to Stage III chronic kidney disease (CKD) was described according to age and gender groups with the Kaplan-Meier curve and compared with the Log-rank test. Entity of treatment was summarized by a score at induction (0-6 months) and maintenance (6-18 months). Cox-regression model was performed to test predictors of remission, relapse and progression to CKD. Results: Among 42 patients (28 pre-pubertal) who met the inclusion criteria, 39 (92.9%) achieved partial and 32 (76.2%) complete remission of nephropathy over 2.78 and 7.51 months of follow-up. At 10 years, the probability of progressing to CKD was 4.8%. Of those achieving remission, 18% had a renal flare mainly within 4 years after remission. Pre-pubertal males achieved complete remission more frequently than other patients but often relapsed; pre-pubertal females were treated more aggressively. Cox-regression analysis did not find independent predictors of remission or relapse. Conclusions: The outcome of the patients with FHN we investigated was encouraging. Recurrences are limited to the first 4 years following diagnosis, allowing progressive withdrawal of immunosuppression in patients achieving remission. Evaluation of risk factors for adverse outcome is necessary especially in pre-pubertal children.
Keywords: Adolescent; Age of Onset; Child; Disease Progression; Female; Glomerular Filtration Rate; Glomerulonephritis; Humans; Kidney Diseases; Lupus Erythematosus, Systemic; Lupus Nephritis; Male; Proteinuria; Recurrence; Remission Induction; Retrospective Studies; Risk Factors; Survival Rate

Pediatric gastrointestinal bleeding: Perspectives from the Italian Society of Pediatric Gastroenterology. - Romano, Claudio; Oliva, Salvatore; Martellossi, Stefano; Miele, Erasmo; Arrigo, Serena; Graziani, Maria Giovanna; Cardile, Sabrina; Gaiani, Federica; de'Angelis, Gian Luigi; Torroni, Filippo (World J Gastroenterol, 2017)
There are many causes of gastrointestinal bleeding (GIB) in children, and this condition is not rare, having a reported incidence of 6.4%. Causes vary with age, but show considerable overlap; moreover, while many of the causes in the pediatric population are similar to those in adults, some lesions are unique to children. The diagnostic approach for pediatric GIB includes definition of the etiology, localization of the bleeding site and determination of the severity of bleeding; timely and accurate diagnosis is necessary to reduce morbidity and mortality. To assist medical care providers in the evaluation and management of children with GIB, the "Gastro-Ped Bleed Team" of the Italian Society of Pediatric Gastroenterology, Hepatology and Nutrition (SIGENP) carried out a systematic search on MEDLINE PubMed (http://www.ncbi.nlm.nih.gov/pubmed/) to identify all articles published in English from January 1990 to 2016; the following key words were used to conduct the electronic search: "upper GIB" and "pediatric" [all fields]; "lower GIB" and "pediatric" [all fields]; "obscure GIB" and "pediatric" [all fields]; "GIB" and "endoscopy" [all fields]; "GIB" and "therapy" [all fields]. The identified publications included articles describing randomized controlled trials, reviews, case reports, cohort studies, case-control studies and observational studies. References from the pertinent articles were also reviewed. This paper expresses a position statement of SIGENP that can have an immediate impact on clinical practice and for which sufficient evidence is not available in literature. The experts participating in this effort were selected according to their expertise and professional qualifications.
Keywords: Adolescent; Child; Child, Preschool; Diagnostic Imaging; Endoscopy; Gastroenterology; Gastrointestinal Diseases; Gastrointestinal Hemorrhage; Hemodynamics; Humans; Infant; Infant, Newborn; Italy; Pediatrics; Recurrence; Societies, Medical

Pediatric Ovarian Torsion and its Recurrence: A Multicenter Study. - Bertozzi, Mirko; Esposito, Ciro; Vella, Claudio; Briganti, Vito; Zampieri, Nicola; Codrich, Daniela; Ubertazzi, Michele; Trucchi, Alessandro; Magrini, Elisa; Battaglia, Sonia; Bini, Vittorio; Conighi, Maria Luisa; et al. (J Pediatr Adolesc Gynecol, 2017)
STUDY OBJECTIVE: To report results of a retrospective multicentric Italian survey concerning the management of pediatric ovarian torsion (OT) and its recurrence. DESIGN: Multicenter retrospective cohort study. SETTING: Italian Units of Pediatric Surgery. PARTICIPANTS: Participants were female aged 1-14 years of age with surgically diagnosed OT between 2004 and 2014. INTERVENTIONS: Adnexal detorsion, adnexectomy, mass excision using laparoscopy or laparotomy. Different kinds of oophoropexy (OPY) for OT or recurrence, respectively. MAIN OUTCOME MEASURES: A total of 124 questionnaires were returned and analyzed to understand the current management of pediatric OT and its recurrence. The questionnaires concerned patient age, presence of menarche, OT site, presence and type of mass, performed procedure, OPY technique adopted, intra- and postoperative complications, recurrence and site, procedure performed for recurrence, OPY technique for recurrence, and 1 year follow-up of detorsed ovaries. RESULTS: Mean age at surgery was 9.79 ± 3.54 years. Performed procedures were open adnexectomy (52 of 125; 41.6%), laparoscopic adnexectomy (25 of 125; 20%), open detorsion (10 of 125; 8%), and laparoscopic detorsion (38 of 125; 30.4%). Recurrence occurred in 15 of 125 cases (12%) and resulted as significant (P = .012) if associated with a normal ovary at the first episode of torsion. Recurrence occurred only in 1 of 19 cases after OPY (5.2%). Ultrasonographic results of detorsed ovaries were not significant whether an OPY was performed or not (P = 1.00). CONCLUSION: Unfortunately, oophorectomy and open technique are still widely adopted even if not advised. Recurrence is not rare and the risk is greater in patients without ovarian masses. OPY does not adversely affect ultrasonographic results at 1 year. When possible OPY should be performed at the first episode of OT.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Female; Humans; Infant; Italy; Laparoscopy; Laparotomy; Menarche; Ovarian Diseases; Ovariectomy; Postoperative Complications; Recurrence; Retrospective Studies; Surveys and Questionnaires; Torsion Abnormality

Pregnant with HIV before age 25: data from a large national study in Italy, 2001-2016. - Floridia, M; Masuelli, G; Tamburrini, E; Cetin, I; Liuzzi, G; Martinelli, P; Guaraldi, G; Spinillo, A; Vimercati, A; Maso, G; Pinnetti, C; Frisina, V; et al. (Epidemiol Infect, 2017)
Young pregnant women with HIV may be at significant risk of unplanned pregnancy, lower treatment coverage, and other adverse pregnancy outcomes. In a large cohort of pregnant women with HIV in Italy, among 2979 pregnancies followed in 2001-2016, 9·0% were in women <25 years, with a significant increase over time (2001-2005: 7·0%; 2006-2010: 9·1%; 2011-2016: 12·2%, P < 0·001). Younger women had a lower rate of planned pregnancy (23·2% vs. 37·7%, odds ratio (OR) 0·50, 95% confidence interval (CI) 0·36-0·69), were more frequently diagnosed with HIV in pregnancy (46·5% vs. 20·9%, OR 3·29, 95% CI 2·54-4·25), and, if already diagnosed with HIV before pregnancy, were less frequently on antiretroviral treatment at conception (<25 years: 56·3%; ⩾25 years: 69·0%, OR 0·58, 95% CI 0·41-0·81). During pregnancy, treatment coverage was almost universal in both age groups (98·5% vs. 99·3%), with no differences in rate of HIV viral suppression at third trimester and adverse pregnancy outcomes. The data show that young women represent a growing proportion of pregnant women with HIV, and are significantly more likely to have unplanned pregnancy, undiagnosed HIV infection, and lower treatment coverage at conception. During pregnancy, antiretroviral treatment, HIV suppression, and pregnancy outcomes are similar compared with older women. Earlier intervention strategies may provide additional benefits in the quality of care for women with HIV.
Keywords: Adolescent; Cohort Studies; Female; HIV Infections; Humans; Italy; Odds Ratio; Pregnancy; Young Adult

Puzzling Results from Germline Mutations Analysis in a Group of Asbestos-Exposed Patients in a High-risk Area of Northeast Italy. - Rizzardi, Clara; Athanasakis, Emmanouil; Cammisuli, Francesca; Monego, Simeone Dal; DE Spelorzi, Yeraldin Chiquinquira Castillo; Costantinides, Fulvio; Giudici, Fabiola; Pinamonti, Maurizio; Canzonieri, Vincenzo; Melato, Mauro; Pascolo, Lorella (Anticancer Res, 2017)
BACKGROUND: Germline mutations of the oncosuppressor gene breast cancer 1-associated protein 1 (BAP1) were recently related to an autosomal-dominant tumor predisposition syndrome (BAP1-TPDS), characterized by uveal melanoma, malignant mesothelioma (MM), cutaneous melanoma, and other malignancies. The demonstration that BAP1 mutations are strongly associated with MM has provided a real breakthrough in the study of genetic predisposition in MM, that may explain why only a fraction of asbestos-exposed individuals go on to develop MM. MATERIALS AND METHODS: To evaluate the possible role of BAP1 mutations in the epidemiology of sporadic MM, and their relationship with asbestos exposure, we determined the prevalence of germline BAP1 mutations by the Sanger method in a group of 29 asbestos-exposed patients, 21 of which were diagnosed with MM. They were residents of Trieste, a ship-building town in Northeast Italy with a very high incidence of mesothelioma. RESULTS: We identified non-obviously pathogenetic germline sequence variants of BAP1 in 3/29 patients and in 2/21 MM cases (10%). CONCLUSION: Non obviously pathogenic germline sequence variants of BAP1 were found. Nevertheless, limitations of predictive web tools allowed us to comment on some interesting peculiarities of our findings.
Keywords: Aged; Aged, 80 and over; Asbestos; Environmental Exposure; Female; Germ-Line Mutation; Humans; Italy; Lung Neoplasms; Male; Mesothelioma; Middle Aged; Risk; Tumor Suppressor Proteins; Ubiquitin Thiolesterase

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Risk of hospitalisation after early-revisit in the emergency department. - Cozzi, Giorgio; Ghirardo, Sergio; Fiorese, Ilaria; Proietti, Ilaria; Monasta, Lorenzo; Minute, Marta; Barbi, Egidio; Calligaris, Lorenzo (J Paediatr Child Health, 2017)
AIM: Early-revisits are frequent in the paediatric emergency department (ED) setting, but few data are available about early-revisited patients. The aim of this study was to investigate the hospitalisation rate of a population of early-revisited patients and to detect if an early-revisited patient was at risk of a more severe disease. METHODS: Between June 2014 and January 2015, we conducted a retrospective cohort study, considering all patients presented to the ED of a tertiary level children's hospital in Italy. We selected all patients who were revisited within 72 h from the initial visit (study cohort), while all other patients accessed in the same period were considered the control cohort. The two cohorts were compared for age, gender, triage category, hospitalisation rate, diagnosis at admission and hospital length of stay. RESULTS: In the study period, we reviewed 10 750 visits, of which 430 (4%) were unplanned revisits for the same chief complaint within 72 h from the initial visit. Hospitalisation rate of early-revisited patients was significantly higher compared to control patients (8.4 vs. 2.9%). Hospitalisation rate increases in parallel with the number of revisits, but in many cases, it was not directly related to a worst triage category, neither to a longer hospital length of stay. CONCLUSION: Early revisited patients in the ED had a significantly higher risk of hospitalisation, but this risk was only partially related to their clinical conditions.
Keywords: Adolescent; Child; Child, Preschool; Emergency Service, Hospital; Female; Hospitalization; Humans; Infant; Italy; Male; Retrospective Studies; Risk Assessment; Tertiary Care Centers; Time Factors

Safety and effectiveness of oral propranolol for infantile hemangiomas started before 5 weeks and after 5 months of age: an Italian multicenter experience. - El Hachem, Maya; Gesualdo, Francesco; Diociaiuti, Andrea; Berti, Irene; Vercellino, Nadia; Boccaletti, Valeria; Neri, Iria; Porcedda, Giulio; Greco, Antonella; Carnevale, Claudia; Oranges, Teresa; Cutrone, Mario; et al. (Ital J Pediatr, 2017)
BACKGROUND: Despite not being licensed for the treatment of infantile hemangiomas (IH) in infants younger than 5 weeks or older than 5 months, propranolol is often used in these age groups to prevent or to treat potentially severe complications. The objective of the present study was to review the experience of 8 Italian pediatric and dermatologic centers regarding propranolol treatment for IH started before 5 weeks or after 5 months of age. METHODS: We retrospectively reviewed the records of patients followed up for IH, on propranolol treatment started before 5 weeks or after 5 months of age, and collected information on sociodemographic data, treatment indications, IH involution, IH relapse, and treatment side effects. RESULTS: A total of 343 patients were enrolled; 15 were started on propranolol before 5 weeks (group 1), 328 were started after 5 months of age (group 2). The most frequent indications were permanent aesthetical disfigurement (91.8%) and function threatening complications (42.6%). In most cases, the treatment was effective. The involution was partial in 67.7% of patients. In 11.8% of cases a relapse was observed. No relapse was observed in group 1. Treatment complications were reported in 15.8% of children, most frequently sleep disorders (6.6%), followed by irritability (5.1%) and diarrhea (2.2%). Only a case of mild constipation was observed in group 1. CONCLUSION: The safety and effectiveness profile of propranolol in infants younger than 5 weeks or older than 5 months may be acceptable. Taking in account propranolol's potential in preventing severe complications, further studies should assess the acceptability of propranolol treatment, especially in the <5-week age group .
Keywords: Administration, Oral; Age Factors; Cohort Studies; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Hemangioma; Humans; Infant; Infant, Newborn; Italy; Male; Patient Safety; Propranolol; Retrospective Studies; Skin Neoplasms; Treatment Outcome

Surgery for distal hypospadias: what about the catheter? - Scarpa, Maria-Grazia; Perin, Giordano; Di Grazia, Massimo; Codrich, Daniela; Pederiva, Federica; Guida, Edoardo; Lembo, Maria Antonietta; Giannotta, Antonio; Schleef, Jurgen (Pediatr Med Chir, 2017)
No agreed recommendations exist for timing of urethral stent removal, after distal hypospadias surgery. We compared our preliminary case series with outcomes from literature: 18/44 patients were treated with catheter and 26/44 without it. The surgical outcome was comparable in the two groups. After hypospadias surgery, the main advantage of the immediate postoperative catheter removal was the shorter hospital stay without negatively affecting the care and home management.
Keywords: Child; Child, Preschool; Device Removal; Humans; Hypospadias; Infant; Length of Stay; Male; Retrospective Studies; Stents; Treatment Outcome; Urinary Catheterization

Targeted sequencing identifies novel variants involved in autosomal recessive hereditary hearing loss in Qatari families. - Alkowari, Moza K; Vozzi, Diego; Bhagat, Shruti; Krishnamoorthy, Navaneethakrishnan; Morgan, Anna; Hayder, Yousra; Logendra, Barathy; Najjar, Nehal; Gandin, Ilaria; Gasparini, Paolo; Badii, Ramin; Girotto, Giorgia; et al. (Mutat Res, 2017)
Hereditary hearing loss is characterized by a very high genetic heterogeneity. In the Qatari population the role of GJB2, the worldwide HHL major player, seems to be quite limited compared to Caucasian populations. In this study we analysed 18 Qatari families affected by non-syndromic hearing loss using a targeted sequencing approach that allowed us to analyse 81 genes simultaneously. Thanks to this approach, 50% of these families (9 out of 18) resulted positive for the presence of likely causative alleles in 6 different genes: CDH23, MYO6, GJB6, OTOF, TMC1 and OTOA. In particular, 4 novel alleles were detected while the remaining ones were already described to be associated to HHL in other ethnic groups. Molecular modelling has been used to further investigate the role of novel alleles identified in CDH23 and TMC1 genes demonstrating their crucial role in Ca2+ binding and therefore possible functional role in proteins. Present study showed that an accurate molecular diagnosis based on next generation sequencing technologies might largely improve molecular diagnostics outcome leading to benefits for both genetic counseling and definition of recurrence risk.
Keywords: Adolescent; Alleles; Cadherins; Child; Child, Preschool; Connexins; Female; GPI-Linked Proteins; Hearing Loss, Sensorineural; Humans; Infant; Male; Membrane Proteins; Models, Molecular; Mutation; Myosin Heavy Chains; Pedigree; Protein Conformation; Qatar; Sequence Analysis, DNA

Thrombogenesis in Thrombophilic Pregnancy: Evaluation of Low-Molecular-Weight Heparin Prophylaxis. - Simeone, Roberto; Giacomello, Roberta; Bruno, Germano; Parco, Sergio; Maximova, Natalia; Martinelli, Monica; Zito, Gabriella; Luppi, Stefania; Cervi, Gina; Ricci, Giuseppe (Acta Haematol, 2017)
The aim of this study is to investigate thrombogenesis and the hypercoagulable changes in pregnant women affected by thrombophilia who received low-molecular-weight heparin (LWMH) prophylaxis. We included 21 pregnant women affected by thrombophilia treated with LWMH and 20 nontreated normal pregnant women as the control group. The sample group of thrombophilic pregnant women included different conditions (factor V Leiden mutation, protein C deficiency, protein S deficiency, antiphospholipid antibodies syndrome, and combined defects). Three blood samples were collected during pregnancy (i.e., at 16, 20, and 24 weeks) and tested for activated partial thromboplastin time and prothrombin fragment F1 + 2 (F1 + 2); anti-FXa activity was tested only in treated thrombophilic pregnant women. F1 + 2 levels progressively increased during pregnancy in both study groups. However, the F1 + 2 increase in women exposed to heparin prophylaxis was significantly lower than that in normal pregnant women in all 3 measurements carried out during gestation (p < 0.05); a statistically significant inverse correlation between F1 + 2 levels and anti-Xa activity (R = -0.8575, p < 0.05) was observed in treated women during pregnancy. Our findings suggest that F1 + 2 in addition to anti-Xa measurement could be used to adjust LWMH prophylaxis, at least in high-risk pregnant women.
Keywords: Adult; Anticoagulants; Case-Control Studies; Factor Xa Inhibitors; Female; Heparin, Low-Molecular-Weight; Humans; Nadroparin; Partial Thromboplastin Time; Peptide Fragments; Pilot Projects; Pregnancy; Pregnancy Complications, Hematologic; Prothrombin; Thrombophilia; Thrombosis

Whole-body MRI reveals high incidence of osteonecrosis in children treated for Hodgkin lymphoma. - Littooij, Annemieke S; Kwee, Thomas C; Enríquez, Goya; Verbeke, Jonathan I M L; Granata, Claudio; Beishuizen, Auke; de Lange, Charlotte; Zennaro, Floriana; Bruin, Marrie C A; Nievelstein, Rutger A J (Br J Haematol, 2017)
Osteonecrosis is a well-recognized complication in patients treated with corticosteroids. The incidence of osteonecrosis in children treated for Hodgkin lymphoma is unknown because prospective whole-body magnetic resonance imaging (MRI) studies are lacking in this patient population. Paediatric patients with newly diagnosed Hodgkin lymphoma who were treated according to a uniform paediatric Hodgkin protocol were eligible for inclusion in this prospective study. Whole-body MRI was performed in all 24 included patients (mean age 15·1 years, 12 girls) both before treatment and after 2 cycles of chemotherapy, and in 16 patients after completion of chemotherapy. Osteonecrosis was identified in 10 patients (41·7%, 95% confidence interval: 22·0-61·4%), with a total of 56 osteonecrotic sites. Osteonecrosis was detected in 8 patients after 2 cycles of OEPA (vincristine, etoposide, prednisone, doxorubicin), and in 2 additional patients after completion of chemotherapy. Epiphyseal involvement of long bones was seen in 4 of 10 children. None of the patients with osteonecrosis had any signs of bone collapse at the times of scanning. Whole-body MRI demonstrates osteonecrosis to be a common finding occurring during therapy response assessment of paediatric Hodgkin lymphoma. Detection of early epiphyseal osteonecrosis could allow for treatment before bone collapse and joint damage may occur.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Doxorubicin; Epiphyses; Etoposide; Female; Hodgkin Disease; Humans; Incidence; Magnetic Resonance Imaging; Male; Osteonecrosis; Prednisone; Prospective Studies; Vincristine

Whole-Genome Sequencing Coupled to Imputation Discovers Genetic Signals for Anthropometric Traits. - Tachmazidou, Ioanna; Süveges, Dániel; Min, Josine L; Ritchie, Graham R S; Steinberg, Julia; Walter, Klaudia; Iotchkova, Valentina; Schwartzentruber, Jeremy; Huang, Jie; Memari, Yasin; McCarthy, Shane; Crawford, Andrew A; et al. (Am J Hum Genet, 2017)
Deep sequence-based imputation can enhance the discovery power of genome-wide association studies by assessing previously unexplored variation across the common- and low-frequency spectra. We applied a hybrid whole-genome sequencing (WGS) and deep imputation approach to examine the broader allelic architecture of 12 anthropometric traits associated with height, body mass, and fat distribution in up to 267,616 individuals. We report 106 genome-wide significant signals that have not been previously identified, including 9 low-frequency variants pointing to functional candidates. Of the 106 signals, 6 are in genomic regions that have not been implicated with related traits before, 28 are independent signals at previously reported regions, and 72 represent previously reported signals for a different anthropometric trait. 71% of signals reside within genes and fine mapping resolves 23 signals to one or two likely causal variants. We confirm genetic overlap between human monogenic and polygenic anthropometric traits and find signal enrichment in cis expression QTLs in relevant tissues. Our results highlight the potential of WGS strategies to enhance biologically relevant discoveries across the frequency spectrum.
Keywords: Anthropometry; Body Height; Cohort Studies; Databases, Genetic; DNA Methylation; Female; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Lipodystrophy; Male; Meta-Analysis as Topic; Obesity; Physical Chromosome Mapping; Quantitative Trait Loci; Sequence Analysis, DNA; Sex Characteristics; Syndrome; United Kingdom

Achieving effective hearing aid fitting within one month after identification of childhood permanent hearing impairment. - Bastanza, G; Gallus, R; De Carlini, M; Picciotti, P M; Muzzi, E; Ciciriello, E; Orzan, E; Conti, G (Acta Otorhinolaryngol Ital, 2016)
Diagnosis of child permanent hearing impairment (PHI) can be made with extreme timeliness compared to the past thanks to improvements in PHI identification through newborn hearing screening programmes. It now becomes essential to provide an effective amplification as quickly as possible in order to restore auditory function and favour speech and language development. The early fitting of hearing aids and possible later cochlear implantation indeed prompts the development of central auditory pathways, connections with secondary sensory brain areas, as well as with motor and articulatory cortex. The aim of this paper is to report the results of a strategic analysis that involves identification of strengths, weaknesses, opportunities and threats regarding the process of achieving early amplification in all cases of significant childhood PHI. The analysis is focused on the Italian situation and is part of the Italian Ministry of Health project CCM 2013 "Preventing Communication Disorders: a Regional Program for Early Identification, Intervention and Care of Hearing Impaired Children".

Acute lobar nephritis in children: Not so easy to recognize and manage. - Bibalo, Cristina; Apicella, Andrea; Guastalla, Veronica; Marzuillo, Pierluigi; Zennaro, Floriana; Tringali, Carmela; Taddio, Andrea; Germani, Claudio; Barbi, Egidio (World J Clin Pediatr, 2016)
Acute lobar nephritis (ALN) is a localized non-liquefactive inflammatory renal bacterial infection, which typically involves one or more lobes. ALN is considered to be a midpoint in the spectrum of upper urinary tract infection, a spectrum ranging from uncomplicated pyelonephritis to intrarenal abscess. This condition may be difficult to recognize due to the lack of specific symptoms and laboratory findings. Therefore the disease is probably underdiagnosed. Computed tomography scanning represents the diagnostic gold standard for ALN, but magnetic resonance imagine could be considered in order to limit irradiation. The diagnosis is relevant since initial intravenous antibiotic therapy and overall length of treatment should not be shorter than 3 wk. We review the literature and analyze the ALN clinical presentation starting from four cases with the aim to give to the clinicians the elements to suspect and recognize the ALN in children.

Acute myelitis as presenting symptom of HIV-HTLV-1 co-infection. - Cucca, A; Stragapede, L; Antonutti, L; Catalan, M; Caracciolo, I; Valentinotti, Romina; Granato, A; D'Agaro, P; Manganotti, P (J Neurovirol, 2016)
A 21-year-old woman presented with acute-onset spastic paraparesis. The MRI spinal scan revealed a contrast-enhanced T2 hyperintensity between C5-T2. The most common neurotropic pathogens were excluded by first level tests. Under suspicion of an acute immune-mediated myelitis, a corticosteroid therapy was administered. However, a seropositivity for both human immunodeficiency virus (HIV) type 1 and human T-lymphotropic virus (HTLV) subsequently emerged. An antiretroviral therapy was started while steroids discontinued. Patient's clinical conditions remained unchanged. HIV-HTLV-1 co-infection should be included in the differential diagnosis of any acute myelitis, even in patients with a preserved immune status and no risk factors.

An Animal Model for the Juvenile Non-Alcoholic Fatty Liver Disease and Non-Alcoholic Steatohepatitis. - Marin, Veronica; Rosso, Natalia; Dal Ben, Matteo; Raseni, Alan; Boschelle, Manuela; Degrassi, Cristina; Nemeckova, Ivana; Nachtigal, Petr; Avellini, Claudio; Tiribelli, Claudio; Gazzin, Silvia (PLoS One, 2016)
Non Alcoholic Fatty Liver Disease (NAFLD) and Non-Alcoholic Steatohepatitis (NASH) are the hepatic manifestations of the metabolic syndrome; worrisome is the booming increase in pediatric age. To recreate the full spectrum of juvenile liver pathology and investigate the gender impact, male and female C57Bl/6 mice were fed with high fat diet plus fructose in the drinking water (HFHC) immediately after weaning (equal to 3-years old human), and disease progression followed for 16 weeks, until adults (equal to 30-years old human). 100% of subjects of both genders on HFHC diet developed steatosis in 4weeks, and some degree of fibrosis in 8weeks, with the 86% of males and 15% of females presenting a stage 2 fibrosis at 16weeks. Despite a similar final liver damage both groups, a sex difference in the pathology progression was observed. Alterations in glucose homeostasis, dyslipidemia, hepatomegaly and obese phenotype were evident from the very beginning in males with an increased hepatic inflammatory activity. Conversely, such alterations were present in females only at the end of the HFHC diet (with the exception of insulin resistance and the hepatic inflammatory state). Interestingly, only females showed an altered hepatic redox state. This juvenile model appears a good platform to unravel the underlying gender dependent mechanisms in the progression from NAFLD to NASH, and to characterize novel therapeutic approaches.

Association of the HLA-G 3'UTR polymorphisms with colorectal cancer in Italy: a first insight. - Garziera, M; Catamo, E; Crovella, S; Montico, M; Cecchin, E; Lonardi, S; Mini, E; Nobili, S; Romanato, L; Toffoli, G (Int J Immunogenet, 2016)
This study aimed to explore functional and regulatory polymorphisms and haplotypes at the HLA-G 3'UTR region in colorectal cancer development. The presence of nonpolymorphic variants was also evaluated. Three-hundred and eight patients with colorectal cancer and 294 healthy controls were analysed at the germinal level. We found an association with increased risk of colorectal cancer for +2960 14-bp INDEL, +3196 C>G SNPs and UTR-2 haplotype, and a 'protective' role for +3003 T>C, +3010 C>G polymorphisms and UTR-4 haplotype. We detected in 3 distinct patients, a novel nucleotide change (+3037 C>A) and 2 already described rare variants, +3032 G/C (EUR MAF = 0.1%) and +3092 G/T (EUR MAF = 0%). This is the first study showing associations between different polymorphisms in the HLA-G 3'UTR and colorectal cancer susceptibility.

C1q acts in the tumour microenvironment as a cancer-promoting factor independently of complement activation. - Bulla, Roberta; Tripodo, Claudio; Rami, Damiano; Ling, Guang Sheng; Agostinis, Chiara; Guarnotta, Carla; Zorzet, Sonia; Durigutto, Paolo; Botto, Marina; Tedesco, Francesco (Nat Commun, 2016)
Complement C1q is the activator of the classical pathway. However, it is now recognized that C1q can exert functions unrelated to complement activation. Here we show that C1q, but not C4, is expressed in the stroma and vascular endothelium of several human malignant tumours. Compared with wild-type (WT) or C3- or C5-deficient mice, C1q-deficient (C1qa(-/-)) mice bearing a syngeneic B16 melanoma exhibit a slower tumour growth and prolonged survival. This effect is not attributable to differences in the tumour-infiltrating immune cells. Tumours developing in WT mice display early deposition of C1q, higher vascular density and an increase in the number of lung metastases compared with C1qa(-/-) mice. Bone marrow (BM) chimeras between C1qa(-/-) and WT mice identify non-BM-derived cells as the main local source of C1q that can promote cancer cell adhesion, migration and proliferation. Together these findings support a role for locally synthesized C1q in promoting tumour growth.
Keywords: Animals; Apoptosis; Cell Line, Tumor; Cell Movement; Cell Proliferation; Complement Activation; Complement C1q; Complement C3; Complement C5; Humans; Mice; Mice, Inbred C57BL; Mice, Knockout; Neoplasms

A Case of Prenatal Neurocytoma Associated With ATR-16 Syndrome. - Quadrifoglio, Mariachiara; Faletra, Flavio; Bussani, Rossana; Pecile, Vanna; Zennaro, Floriana; Grasso, Alessandra; Zandonà, Lorenzo; Alberico, Salvatore; Stampalija, Tamara (J Ultrasound Med, 2016)

Chemokines SNPs in HIV-1+ Patients and Healthy Controls from Northeast Brazil: Association with Protection against HIV-1 Infection. - Celerino da Silva, Ronaldo; Victor Campos Coelho, Antonio; Cláudio Arraes, Luiz; André Cavalcanti Brandão, Lucas; Lima Guimarães, Rafael; Crovella, Sergio (Curr HIV Res, 2016)
BACKGROUND: HIV-1 virus is known to infect the host mainly through CD4+ T-lymphocyte cells, by interactions among the viral envelope proteins, CD4 receptor and HIV-1 coreceptors, such as chemokines receptors. Variations in the genes encoding HIV-1 coreceptors and their natural ligands have been shown to modify HIV-1 infection susceptibility and disease progression. METHODS AND RESULTS: We analysed the distribution of SNPs in chemokines (CCL3, CCL4, CCL5, CXCL12) and chemokine receptor (CXCR6) genes, in 268 HIV-1 infected patients (HIV-1+) and 221 healthy controls from Northeast Brazil, and their possible connection with susceptibility to HIV-1 infection. The genotyping were performed through allele specific fluorogenic probes using real time PCR. We observed that the T alleles and AT genotype of rs1719153 CCL4 SNP were more frequent in healthy controls (19.8% and 35.0%, respectively) than in HIV-1+ patients (T allele: 14.1%; OR=0.67; 95%CI=0.47-0.95; p-value=0.020; and AT genotype: 24.4%; OR=0.61; 95%CI=0.40- 0.93; p-value=0.021) after correcting for age and sex. The rs1719134 (CCL3) and rs1719153 (CCL4) SNPs presented linkage disequilibrium (D'=0.83). The AT haplotype frequency was increased in healthy controls (17.3%) in relation to HIV-1+ patients (11.0%; OR=0.62; 95%CI=0.42-0.93; p-value=0.020). CONCLUSION: Since our results revealed an increased frequency of alleles and genotypes of CCL3/CCL4 SNPs and haplotype (CCL3-CCL4) among healthy controls, we suggest that these variations might have a potential protective role against HIV-1 infection.

Chronic nonbacterial osteomyelitis may be associated with renal disease and bisphosphonates are a good option for the majority of patients. - Pastore, Serena; Ferrara, Giovanna; Monasta, Lorenzo; Meini, Antonella; Cattalini, Marco; Martino, Silvana; Alessio, Maria; La Torre, Francesco; Teruzzi, Barbara; Gerloni, Valeria; Breda, Luciana; Taddio, Andrea; et al. (Acta Paediatr, 2016)
AIM: The aim of this Italian study was to describe the clinical features, treatment options and outcomes of a cohort of patients with chronic nonbacterial osteomyelitis (CNO). METHODS: This was a retrospective cohort study. Laboratory data, diagnostic imaging, histological features and clinical course are reported. RESULTS: We enrolled 47 patients diagnosed with CNO. Bone pain was the leading symptom, and multifocal disease was present in 87% of the patients. The majority of the bone lesions were located in the appendicular skeleton (58%). Extraosseous manifestations were present in 34% of the patients, and renal involvement was detected in four patients. Inflammatory indices were increased in 80%, and bone x-rays were negative in 15% of the patients. Nonsteroidal anti-inflammatory drugs (NSAIDs) were the first therapy for all patients, achieving clinical remission in 27%. A good response to NSAIDs was significantly associated with a better prognosis. Bisphosphonates were used in 26 patients, with remission in 73%. Only six patients (13%), all with spine involvement, developed sequelae. CONCLUSION: We found a possible association between CNO and renal disease. Bisphosphonates were more likely to lead to clinical remission when NSAIDs and corticosteroids had failed. Vertebral localisation was the only risk factor for potential sequelae.

Clinical and pathogenetic features of ETV6 related thrombocytopenia with predisposition to acute lymphoblastic leukemia. - Melazzini, Federica; Palombo, Flavia; Balduini, Alessandra; De Rocco, Daniela; Marconi, Caterina; Noris, Patrizia; Gnan, Chiara; Pippucci, Tommaso; Bozzi, Valeria; Faleschini, Michela; Barozzi, Serena; Doubek, Michael; et al. (Haematologica, 2016)
ETV6-related thrombocytopenia (ETV6-RT) is an autosomal dominant thrombocytopenia that has been recently identified in a few families and has been suspected to predispose to hematological malignancies. To gain further information on this disorder, we searched for ETV6 mutations in the 130 families with inherited thrombocytopenia of unknown origin from our cohort of 274 consecutive pedigrees with familial thrombocytopenia. We identified 20 ETV6-RT patients from 7 pedigrees. They have 5 different ETV6 variants, including three novel mutations affecting the highly conserved E26 transformation-specific domain. The relative frequency of ETV6-RT resulted 2.6% in the whole case series and 4.6% among the families with known forms of inherited thrombocytopenia. The degree of thrombocytopenia and bleeding tendency of ETV6-RT patients were mild, but 4 subjects developed B-cell acute lymphoblastic leukemia during childhood, resulting in a significantly increased incidence compared to the general population. Clinical and laboratory findings did not identify any peculiar defects that can be used to suspect this disorder by routine diagnostic workup. However, at variance with most inherited thrombocytopenias, platelet size was not enlarged. In vitro studies revealed that patients megakaryocytes have defective maturation and impaired proplatelet formation. Moreover, ETV6-RT platelets have reduced ability to spread on fibrinogen. Since also the dominant thrombocytopenias due to mutations in RUNX1 and ANKRD26 are characterized by normal platelet size and predispose to hematological malignancies, we suggest that mutation screening of ETV6, RUNX1 and ANKRD26 should be performed in all the subjects with autosomal dominant thrombocytopenia and normal platelet size.

Clinical Characteristics of Patients Carrying the Q703K Variant of the NLRP3 Gene: A 10-year Multicentric National Study. - Naselli, Aldo; Penco, Federica; Cantarini, Luca; Insalaco, Antonella; Alessio, Mariolina; Tommasini, Alberto; Maggio, Cristina; Obici, Laura; Gallizi, Romina; Cimmino, Marco; Signa, Sara; Lucherini, Orso Maria; et al. (J Rheumatol, 2016)
OBJECTIVE: The aim of our study was to analyze the clinical and functional effect of the p.Q703K (p. Q705K, c. 2107C>A) variant of the NLRP3 gene in a population of patients screened for suspected cryopyrin-associated periodic syndrome (CAPS). METHODS: Since 2002, 580 patients underwent molecular analysis for NLRP3. Data on clinical presentation, response to treatment, and longterm followup were collected using a uniform questionnaire. The pattern of cytokine secretion after lipopolysaccharide stimulation from isolated monocytes was analyzed in 3 patients carrying the p.Q703K variant and 1 patient with a chronic infantile neurologic, cutaneous, articular syndrome phenotype carrying both the p.M406I and p.Q703K, and compared with 7 patients with CAPS with sure pathogenic variants and 6 healthy controls. RESULTS: The p.Q703K variant was found in 57 screened patients with an overall allelic frequency of 5%. The frequency in normal controls was 5.5%. Clinical data at the moment of molecular analysis and at followup were available in 36 patients. Two patients displayed additional mutations of NLRP3. The mean followup was 2.5 years. Thirteen patients (39%) had a final diagnosis different from the original suspicion of CAPS. The remaining 21 patients displayed a mild phenotype mainly characterized by recurrent episodes of urticarial rash and arthralgia. Only 8 patients were treated with anti-interleukin (IL)-1 treatment, with a complete response in 5 patients. The pattern of secretion of IL-1β and other cytokines (IL-6 and IL-1 receptor antagonist) in patients did not display the aberrancies observed in patients with CAPS and was similar to that observed in healthy controls. CONCLUSION: The present study confirms the weak clinical and functional effect of the p.Q703K variant.

Consensus Conference on Clinical Management of pediatric Atopic Dermatitis. - Galli, Elena; Neri, Iria; Ricci, Giampaolo; Baldo, Ermanno; Barone, Maurizio; Belloni Fortina, Anna; Bernardini, Roberto; Berti, Irene; Caffarelli, Carlo; Calamelli, Elisabetta; Capra, Lucetta; Carello, Rossella; et al. (Ital J Pediatr, 2016)
The Italian Consensus Conference on clinical management of atopic dermatitis in children reflects the best and most recent scientific evidence, with the aim to provide specialists with a useful tool for managing this common, but complex clinical condition. Thanks to the contribution of experts in the field and members of the Italian Society of Pediatric Allergology and Immunology (SIAIP) and the Italian Society of Pediatric Dermatology (SIDerP), this Consensus statement integrates the basic principles of the most recent guidelines for the management of atopic dermatitis to facilitate a practical approach to the disease. The therapeutical approach should be adapted to the clinical severity and requires a tailored strategy to ensure good compliance by children and their parents. In this Consensus, levels and models of intervention are also enriched by the Italian experience to facilitate a practical approach to the disease.

Current concepts in management of pain in children in the emergency department. - Krauss, Baruch S; Calligaris, Lorenzo; Green, Steven M; Barbi, Egidio (Lancet, 2016)
Pain is common in children presenting to emergency departments with episodic illnesses, acute injuries, and exacerbation of chronic disorders. We review recognition and assessment of pain in infants and children and discuss the manifestations of pain in children with chronic illness, recurrent pain syndromes, and cognitive impairment, including the difficulties of pain management in these patients. Non-pharmacological interventions, as adjuncts to pharmacological management for acute anxiety and pain, are described by age and development. We discuss the pharmacological management of acute pain and anxiety, reviewing invasive and non-invasive routes of administration, pharmacology, and adverse effects.
Keywords: Acute Pain; Analgesics, Opioid; Anesthetics, Local; Anti-Inflammatory Agents, Non-Steroidal; Anxiety; Child; Emergency Medicine; Emergency Service, Hospital; Humans; Pain Management; Pediatrics; Stress, Psychological

DEFB1 gene polymorphisms and tuberculosis in a Northeastern Brazilian population. - Celerino da Silva, Ronaldo; da Cruz, Heidi Lacerda Alves; Brandão, Lucas André Cavalcanti; Guimarães, Rafael Lima; Montenegro, Lilian Maria Lapa; Schindler, Haiana Charifker; Segat, Ludovica; Crovella, Sergio (Braz J Microbiol, 2016)
β-Defensin-1, an antimicrobial peptide encoded by the DEFB1 gene, is known to play an important role in lung mucosal immunity. In our association study we analyzed three DEFB1 functional polymorphisms -52G>A (rs1799946), -44C>G (rs1800972) and -20G>A (rs11362) in 92 tuberculosis patients and 286 healthy controls, both from Northeast Brazil: no association was found between the studied DEFB1 polymorphisms and the disease. However we cannot exclude that this lack of association could be due to the low number of subjects analyzed, as suggested by the low statistical power achieved for the three analyzed SNPs (values between 0.16 and 0.50).

DEFB1 polymorphisms and susceptibility to recurrent tonsillitis in Italian children. - Zupin, Luisa; Polesello, Vania; Grasso, Domenico Leonardo; Crovella, Sergio; Segat, Ludovica (Int J Pediatr Otorhinolaryngol, 2016)
INTRODUCTION: The tonsils are secondary lymphoid organs fundamental for immune system response against pathogens within the oral cavity. Tonsillitis refers to inflammation of the pharyngeal tonsils that may include the adenoids and the lingual tonsils and that can be acute, recurrent, and chronic. Viral or bacterial infections, as well as immunologic factors are the main trigger to tonsillitis and disease's chronicity: the host immune responses, especially the innate one, could play an important role in susceptibility to the disease. OBJECTIVES: The current study aims at investigating the role of functional polymorphisms in the 5'UTR (c.-52G>A, c.-44G>C and c.-20G>A) of DEFB1 gene, encoding for the antimicrobial peptide human beta-defensin 1, in the predisposition to recurrent tonsillitis in children from North Eastern Italy. RESULTS: No significant correlation was found between DEFB1 allele, genotype and haplotype frequencies and recurrent tonsillitis susceptibility with the exception of an increased risk to disease development in patients carrying DEFB1 rare haplotypes. CONCLUSION: Our results may suggest that DEFB1 polymorphisms alone may not influence pathology susceptibility, however they could possibly concur, together with other factors involved in the genetic control of innate immune system, in the predisposition towards recurrent tonsillitis.

Does Preputial Reconstruction Increase Complication Rate of Hypospadias Repair? 20-Year Systematic Review and Meta-Analysis. - Castagnetti, Marco; Gnech, Michele; Angelini, Lorenzo; Rigamonti, Waifro; Bagnara, Vincenzo; Esposito, Ciro (Front Pediatr, 2016)
INTRODUCTION: We performed a systematic review of the literature on preputial reconstruction (PR) during hypospadias repair to determine the cumulative risk of preputial skin complications and the influence of PR on urethroplasty complications, namely, fistula formation and overall reoperation rate of the repair. MATERIALS AND METHODS: A systematic search of the literature published after 06/1995 was performed in 06/2015 using the keyword "hypospadias." Only studies on the outcome of PR in children, defined as dehiscence of the reconstructed prepuce or secondary phimosis needing circumcision, were selected. A meta-analysis of studies comparing PR vs. circumcision was performed for the outcomes "hypospadias fistula formation" and "reoperation rate." RESULTS: Twenty studies were identified. Nineteen reported the outcome of PR in 2115 patients. Overall, 95% (2016/2115) of patients undergoing PR had distal hypospadias. The cumulative rate of PR complications was 7.7% (163/2115 patients), including 5.7% (121/2115 patients) preputial dehiscences and 1.5% (35/2117 reported patients) secondary phimoses needing circumcision. A meta-analysis of seven studies comparing patients undergoing PR vs. circumcision showed no increased risk of urethral fistula formation associated with PR, odds ratio (OR) (Mantel-Haenszel, Fixed effect, 95% CI), 1.25 (0.80-1.97). Likewise, two studies comparing the overall reoperation rate did not show an increased risk of reoperation associated with PR, OR (Mantel-Haenszel, Random effect, 95% CI), 1.27 (0.45-3.58). CONCLUSION: PR carries an 8% risk of specific complications (dehiscence of reconstructed prepuce or secondary phimosis needing circumcision), but does not seem to increase the risk of urethroplasty complications, and the overall reoperation rate of hypospadias repair.

Effect of Early Versus Late Azathioprine Therapy in Pediatric Ulcerative Colitis. - Aloi, Marina; DʼArcangelo, Giulia; Bramuzzo, Matteo; Gasparetto, Marco; Martinelli, Massimo; Alvisi, Patrizia; Illiceto, Maria Teresa; Valenti, Simona; Distante, Manuela; Pellegrino, Salvatore; Gatti, Simona; Arrigo, Serena; et al. (Inflamm Bowel Dis, 2016)
BACKGROUND: We aimed at describing the efficacy of azathioprine (AZA) in pediatric ulcerative colitis, comparing the outcomes of early (0-6 months) versus late (6-24 months) initiation of therapy. METHODS: Children with ulcerative colitis treated with AZA within 24 months of diagnosis were included. Corticosteroid (CS)-free remission and mucosal healing (MH), assessed by endoscopy or fecal calprotectin, at 12 months were the primary outcomes. Patients were also compared for CS-free remission and MH, need for treatment escalation or surgery, number of hospitalizations, and adverse events during a 24-month follow-up. RESULTS: A total of 121 children entered the study (median age 10.5 ± 4.0 years, 59% girls). Seventy-six (63%) started AZA between 0 and 6 months (early group) and 45 (37%) started between 6 and 24 months (late group). Seventy-five percent and 53% of patients in the early and late group, respectively, received CS at the diagnosis (P = 0.01). CS-free remission at 1 year was achieved by 30 (50%) of the early and 23 (57%) of the late patients (P = 0.54). MH occurred in 37 (37%) patients at 1 year, with no difference between the 2 groups (33% early, 42% late; P = 0.56). No difference was found for the other outcomes. CONCLUSIONS: Introduction of AZA within 6 months of diagnosis seems not more effective than later treatment to achieve CS-free remission in pediatric ulcerative colitis. MH does not depend on the timing of AZA initiation; however, because of the incomplete comparability of the 2 groups at the diagnosis and the use of fecal calprotectin as a surrogate marker of MH, our results should be further confirmed by prospective studies.

Efficacy of ketamine in refractory convulsive status epilepticus in children: a protocol for a sequential design, multicentre, randomised, controlled, open-label, non-profit trial (KETASER01). - Rosati, Anna; Ilvento, Lucrezia; L'Erario, Manuela; De Masi, Salvatore; Biggeri, Annibale; Fabbro, Giancarlo; Bianchi, Roberto; Stoppa, Francesca; Fusco, Lucia; Pulitanò, Silvia; Battaglia, Domenica; Pettenazzo, Andrea; et al. (BMJ Open, 2016)
INTRODUCTION: Status epilepticus (SE) is a life-threatening neurological emergency. SE lasting longer than 120 min and not responding to first-line and second-line antiepileptic drugs is defined as 'refractory' (RCSE) and requires intensive care unit treatment. There is currently neither evidence nor consensus to guide either the optimal choice of therapy or treatment goals for RCSE, which is generally treated with coma induction using conventional anaesthetics (high dose midazolam, thiopental and/or propofol). Increasing evidence indicates that ketamine (KE), a strong N-methyl-d-aspartate glutamate receptor antagonist, may be effective in treating RCSE. We hypothesised that intravenous KE is more efficacious and safer than conventional anaesthetics in treating RCSE. METHODS AND ANALYSIS: A multicentre, randomised, controlled, open-label, non-profit, sequentially designed study will be conducted to assess the efficacy of KE compared with conventional anaesthetics in the treatment of RCSE in children. 10 Italian centres/hospitals are involved in enrolling 57 patients aged 1 month to 18 years with RCSE. Primary outcome is the resolution of SE up to 24 hours after withdrawal of therapy and is updated for each patient treated according to the sequential method. ETHICS AND DISSEMINATION: The study received ethical approval from the Tuscan Paediatric Ethics Committee (12/2015). The results of this study will be published in peer-reviewed journals and presented at international conferences. TRIAL REGISTRATION NUMBER: NCT02431663; Pre-results.

EPG5-related Vici syndrome: a paradigm of neurodevelopmental disorders with defective autophagy. - Byrne, Susan; Jansen, Lara; U-King-Im, Jean-Marie; Siddiqui, Ata; Lidov, Hart G W; Bodi, Istvan; Smith, Luke; Mein, Rachael; Cullup, Thomas; Dionisi-Vici, Carlo; Al-Gazali, Lihadh; Al-Owain, Mohammed; et al. (Brain, 2016)
Vici syndrome is a progressive neurodevelopmental multisystem disorder due to recessive mutations in the key autophagy gene EPG5. We report genetic, clinical, neuroradiological, and neuropathological features of 50 children from 30 families, as well as the neuronal phenotype of EPG5 knock-down in Drosophila melanogaster. We identified 39 different EPG5 mutations, most of them truncating and predicted to result in reduced EPG5 protein. Most mutations were private, but three recurrent mutations (p.Met2242Cysfs*5, p.Arg417*, and p.Gln336Arg) indicated possible founder effects. Presentation was mainly neonatal, with marked hypotonia and feeding difficulties. In addition to the five principal features (callosal agenesis, cataracts, hypopigmentation, cardiomyopathy, and immune dysfunction), we identified three equally consistent features (profound developmental delay, progressive microcephaly, and failure to thrive). The manifestation of all eight of these features has a specificity of 97%, and a sensitivity of 89% for the presence of an EPG5 mutation and will allow informed decisions about genetic testing. Clinical progression was relentless and many children died in infancy. Survival analysis demonstrated a median survival time of 24 months (95% confidence interval 0-49 months), with only a 10th of patients surviving to 5 years of age. Survival outcomes were significantly better in patients with compound heterozygous mutations (P = 0.046), as well as in patients with the recurrent p.Gln336Arg mutation. Acquired microcephaly and regression of skills in long-term survivors suggests a neurodegenerative component superimposed on the principal neurodevelopmental defect. Two-thirds of patients had a severe seizure disorder, placing EPG5 within the rapidly expanding group of genes associated with early-onset epileptic encephalopathies. Consistent neuroradiological features comprised structural abnormalities, in particular callosal agenesis and pontine hypoplasia, delayed myelination and, less frequently, thalamic signal intensity changes evolving over time. Typical muscle biopsy features included fibre size variability, central/internal nuclei, abnormal glycogen storage, presence of autophagic vacuoles and secondary mitochondrial abnormalities. Nerve biopsy performed in one case revealed subtotal absence of myelinated axons. Post-mortem examinations in three patients confirmed neurodevelopmental and neurodegenerative features and multisystem involvement. Finally, downregulation of epg5 (CG14299) in Drosophila resulted in autophagic abnormalities and progressive neurodegeneration. We conclude that EPG5-related Vici syndrome defines a novel group of neurodevelopmental disorders that should be considered in patients with suggestive features in whom mitochondrial, glycogen, or lysosomal storage disorders have been excluded. Neurological progression over time indicates an intriguing link between neurodevelopment and neurodegeneration, also supported by neurodegenerative features in epg5-deficient Drosophila, and recent implication of other autophagy regulators in late-onset neurodegenerative disease.
Keywords: Agenesis of Corpus Callosum; Animals; Autophagy; Cataract; Child, Preschool; Cross-Sectional Studies; Drosophila melanogaster; Female; Hippocampus; Humans; Male; Mutation; Neurodevelopmental Disorders; Proteins; Retrospective Studies

Evidence for three genetic loci involved in both anorexia nervosa risk and variation of body mass index. - Hinney, A; Kesselmeier, M; Jall, S; Volckmar, A-L; Föcker, M; Antel, J; Heid, I M; Winkler, T W; Grant, S F A; Guo, Y; Bergen, A W; Kaye, W; et al. (Mol Psychiatry, 2016)
The maintenance of normal body weight is disrupted in patients with anorexia nervosa (AN) for prolonged periods of time. Prior to the onset of AN, premorbid body mass index (BMI) spans the entire range from underweight to obese. After recovery, patients have reduced rates of overweight and obesity. As such, loci involved in body weight regulation may also be relevant for AN and vice versa. Our primary analysis comprised a cross-trait analysis of the 1000 single-nucleotide polymorphisms (SNPs) with the lowest P-values in a genome-wide association meta-analysis (GWAMA) of AN (GCAN) for evidence of association in the largest published GWAMA for BMI (GIANT). Subsequently we performed sex-stratified analyses for these 1000 SNPs. Functional ex vivo studies on four genes ensued. Lastly, a look-up of GWAMA-derived BMI-related loci was performed in the AN GWAMA. We detected significant associations (P-values <5 × 10(-5), Bonferroni-corrected P<0.05) for nine SNP alleles at three independent loci. Interestingly, all AN susceptibility alleles were consistently associated with increased BMI. None of the genes (chr. 10: CTBP2, chr. 19: CCNE1, chr. 2: CARF and NBEAL1; the latter is a region with high linkage disequilibrium) nearest to these SNPs has previously been associated with AN or obesity. Sex-stratified analyses revealed that the strongest BMI signal originated predominantly from females (chr. 10 rs1561589; Poverall: 2.47 × 10(-06)/Pfemales: 3.45 × 10(-07)/Pmales: 0.043). Functional ex vivo studies in mice revealed reduced hypothalamic expression of Ctbp2 and Nbeal1 after fasting. Hypothalamic expression of Ctbp2 was increased in diet-induced obese (DIO) mice as compared with age-matched lean controls. We observed no evidence for associations for the look-up of BMI-related loci in the AN GWAMA. A cross-trait analysis of AN and BMI loci revealed variants at three chromosomal loci with potential joint impact. The chromosome 10 locus is particularly promising given that the association with obesity was primarily driven by females. In addition, the detected altered hypothalamic expression patterns of Ctbp2 and Nbeal1 as a result of fasting and DIO implicate these genes in weight regulation.Molecular Psychiatry advance online publication, 17 May 2016; doi:10.1038/mp.2016.71.

Frequency of the CCR5-delta32 allele in Brazilian populations: A systematic literature review and meta-analysis. - Silva-Carvalho, Wlisses Henrique Veloso; De Moura, Ronald Rodrigues; Coelho, Antônio Victor Campos; Crovella, Sergio; Guimarães, Rafael Lima (Infect Genet Evol, 2016)
The CCR5 is a chemokine receptor widely expressed by several immune cells that are engaged in inflammatory responses. Some populations have individuals exhibiting a 32bp deletion in the CCR5 gene (CCR5-delta32) that produces a truncated non-functional protein not expressed on the cell surface. This polymorphism, known to be associated with susceptibility to infectious and inflammatory diseases, such as osteomyelitis, pre-eclampsia, systemic lupus erythematous, juvenile idiopathic arthritis, rheumatoid arthritis and HIV/AIDS, is more commonly found in European populations with average frequency of 10%. However, it is also possible to observe a significant frequency in other world populations, such as the Brazilian one. We performed a systematic review and meta-analysis of CCR5-delta32 genetic association studies in Brazilian populations throughout the country to estimate the frequency of this polymorphism. We also compared CCR5-delta32 frequencies across Brazilian regions. The systematic literature reviewed studies involving delta32 allele in Brazilian populations published from 1995 to 2015. Among the reviewed literature, 25 studies including 30 Brazilian populations distributed between the North, Northeast, South and Southeast regions were included in our meta-analysis. We observed an overall allelic frequency of 4% (95%-CI, 0.03-0.05), that was considered moderate and, notably, higher than some European populations, such as Cyprus (2.8%), Italy (3%) and Greece (2.4%). Regarding the regional frequency comparisons between North-Northeast (N-NE) and South-Southeast (S-SE) regions, we observed an allelic frequency of 3% (95%-CI, 0.02-0.04) and 4% (95%-CI, 0.03-0.05), respectively. The populations from S-SE regions had a slightly higher CCR5-delta32 frequency than N-NE regions (OR=1.41, p=0.002). Although there are several studies about the CCR5-delta32 polymorphism and its effect on the immune response of some infectious diseases, this report is the first meta-analysis study that provides a descriptive study of the distribution of CCR5-delta32 allele in Brazilian population.

Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function. - Pattaro, Cristian; Teumer, Alexander; Gorski, Mathias; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Garnaas, Maija; Tin, Adrienne; Sorice, Rossella; Li, Yong; Taliun, Daniel; Olden, Matthias; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.
Keywords: Gene Expression Regulation; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Renal Insufficiency, Chronic

Genome-wide association study identifies 74 loci associated with educational attainment. - Okbay, Aysu; Beauchamp, Jonathan P; Fontana, Mark Alan; Lee, James J; Pers, Tune H; Rietveld, Cornelius A; Turley, Patrick; Chen, Guo-Bo; Emilsson, Valur; Meddens, S Fleur W; Oskarsson, Sven; Pickrell, Joseph K; et al. (Nature, 2016)
Educational attainment is strongly influenced by social and other environmental factors, but genetic factors are estimated to account for at least 20% of the variation across individuals. Here we report the results of a genome-wide association study (GWAS) for educational attainment that extends our earlier discovery sample of 101,069 individuals to 293,723 individuals, and a replication study in an independent sample of 111,349 individuals from the UK Biobank. We identify 74 genome-wide significant loci associated with the number of years of schooling completed. Single-nucleotide polymorphisms associated with educational attainment are disproportionately found in genomic regions regulating gene expression in the fetal brain. Candidate genes are preferentially expressed in neural tissue, especially during the prenatal period, and enriched for biological pathways involved in neural development. Our findings demonstrate that, even for a behavioural phenotype that is mostly environmentally determined, a well-powered GWAS identifies replicable associated genetic variants that suggest biologically relevant pathways. Because educational attainment is measured in large numbers of individuals, it will continue to be useful as a proxy phenotype in efforts to characterize the genetic influences of related phenotypes, including cognition and neuropsychiatric diseases.
Keywords: Alzheimer Disease; Bipolar Disorder; Brain; Cognition; Computational Biology; Educational Status; Fetus; Gene Expression Regulation; Gene-Environment Interaction; Genome-Wide Association Study; Great Britain; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Schizophrenia

A Genome-Wide Association Study in isolated populations reveals new genes associated to common food likings. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; Amin, Najaf; Sala, Cinzia; Karssen, Lennart C; van Duijn, Cornelia; Toniolo, Daniela; Gasparini, Paolo (Rev Endocr Metab Disord, 2016)
Food preferences are the first factor driving food choice and thus nutrition. They involve numerous different senses such as taste and olfaction as well as various other factors such as personal experiences and hedonistic aspects. Although it is clear that several of these have a genetic basis, up to now studies have focused mostly on the effects of polymorphisms of taste receptor genes. Therefore, we have carried out one of the first large scale (4611 individuals) GWAS on food likings assessed for 20 specific food likings belonging to 4 different categories (vegetables, fatty, dairy and bitter). A two-step meta-analysis using three different isolated populations from Italy for the discovery step and two populations from The Netherlands and Central Asia for replication, revealed 15 independent genome-wide significant loci (p < 5 × 10(-8)) for 12 different foods. None of the identified genes coded for either taste or olfactory receptors suggesting that genetics impacts in determining food likings in a much broader way than simple differences in taste perception. These results represent a further step in uncovering the genes that underlie liking of common foods that in the end will greatly help understanding the genetics of human nutrition in general.

Geranylgeraniol and Neurological Impairment: Involvement of Apoptosis and Mitochondrial Morphology. - Marcuzzi, Annalisa; Piscianz, Elisa; Zweyer, Marina; Bortul, Roberta; Loganes, Claudia; Girardelli, Martina; Baj, Gabriele; Monasta, Lorenzo; Celeghini, Claudio (Int J Mol Sci, 2016)
Deregulation of the cholesterol pathway is an anomaly observed in human diseases, many of which have in common neurological involvement and unknown pathogenesis. In this study we have used Mevalonate Kinase Deficiency (MKD) as a disease-model in order to investigate the link between the deregulation of the mevalonate pathway and the consequent neurodegeneration. The blocking of the mevalonate pathway in a neuronal cell line (Daoy), using statins or mevalonate, induced an increase in the expression of the inflammasome gene (NLRP3) and programmed cell death related to mitochondrial dysfunction. The morphology of the mitochondria changed, clearly showing the damage induced by oxidative stress and the decreased membrane potential associated with the alterations of the mitochondrial function. The co-administration of geranylgeraniol (GGOH) reduced the inflammatory marker and the damage of the mitochondria, maintaining its shape and components. Our data allow us to speculate about the mechanism by which isoprenoids are able to rescue the inflammatory marker in neuronal cells, independently from the block of the mevalonate pathway, and about the fact that cell death is mitochondria-related.

Global diversity in the TAS2R38 bitter taste receptor: revisiting a classic evolutionary PROPosal. - Risso, Davide S; Mezzavilla, Massimo; Pagani, Luca; Robino, Antonietta; Morini, Gabriella; Tofanelli, Sergio; Carrai, Maura; Campa, Daniele; Barale, Roberto; Caradonna, Fabio; Gasparini, Paolo; Luiselli, Donata; et al. (Sci Rep, 2016)
The ability to taste phenylthiocarbamide (PTC) and 6-n-propylthiouracil (PROP) is a polymorphic trait mediated by the TAS2R38 bitter taste receptor gene. It has long been hypothesized that global genetic diversity at this locus evolved under pervasive pressures from balancing natural selection. However, recent high-resolution population genetic studies of TAS2Rs suggest that demographic events have played a critical role in the evolution of these genes. We here utilized the largest TAS2R38 database yet analyzed, consisting of 5,589 individuals from 105 populations, to examine natural selection, haplotype frequencies and linkage disequilibrium to estimate the effects of both selection and demography on contemporary patterns of variation at this locus. We found signs of an ancient balancing selection acting on this gene but no post Out-Of-Africa departures from neutrality, implying that the current observed patterns of variation can be predominantly explained by demographic, rather than selective events. In addition, we found signatures of ancient selective forces acting on different African TAS2R38 haplotypes. Collectively our results provide evidence for a relaxation of recent selective forces acting on this gene and a revised hypothesis for the origins of the present-day worldwide distribution of TAS2R38 haplotypes.

The Great Pretender: Pediatric Wandering Spleen: Two Case Reports and Review of the Literature. - Radillo, Lucia; Taddio, Andrea; Ghirardo, Sergio; Bramuzzo, Matteo; Pederiva, Federica; Maschio, Massimo; Barbi, Egidio (Pediatr Emerg Care, 2016)
Wandering spleen is a rare condition, typically not only due to embryological defects of the splenic ligaments, but also secondary to trauma and splenomegaly. The most common presentation is acute abdomen with a mobile abdominal mass or recurrent abdominal pain. However, the spleen may be temporary in its normal position, and patients could be asymptomatic. A familiarity, if present, strengthens the diagnostic suspect.Abdominal ultrasonography and computed tomography are the examination of choice, and the management is surgical.

Hepatic Gadolinium Deposition and Reversibility after Contrast Agent-enhanced MR Imaging of Pediatric Hematopoietic Stem Cell Transplant Recipients. - Maximova, Natalia; Gregori, Massimo; Zennaro, Floriana; Sonzogni, Aurelio; Simeone, Roberto; Zanon, Davide (Radiology, 2016)
Purpose To determine if hepatic gadolinium deposition occurs in pediatric patients with iron overload but normal renal and hepatic function who undergo gadolinium-based contrast agent (GBCA)-enhanced magnetic resonance (MR) imaging. Materials and Methods Design and execution of this study was approved by the Ethical Committee of Institute for Research in Maternal and Child Health Burlo Garofolo of Trieste (reference no. 1105/2015). Because of the retrospective nature of the study, the requirement to obtain informed consent was waived. Twenty-one recipients of allogeneic hematopoietic stem cell transplants who underwent GBCA-enhanced MR imaging for suspected infection or relapse followed by liver biopsy comprised the study group. The number of GBCA-enhanced MR examinations and cumulative gadolinium dose for each patient was analyzed by comparing liver histologic analysis and iron and gadolinium liver concentration (GLC). Eight patients had siderosis and underwent chelation therapy. The study group was compared with four control patients who were never exposed to GBCA. Statistical analysis was performed with Spearman rank coefficient for correlation. Results All 21 patients had positive correlations between GLC and total GBCA dose (r = 0.4486; P < .05) and between GLC and liver iron concentration (r = 0.56; P < .05). Patients who underwent deferoxamine therapy had a significant reduction of GLC (from 0.64 μg/g ± 0.29 to 0.20 μg/g ± 0.17 [standard deviation]; P < .05). Conclusion In the presence of siderosis, a transmetallation mechanism may be set off between ferric ion and gadoterate meglumine. Deferoxamine appears capable of binding to gadolinium ion. Further studies of the safety of GBCAs in severe siderosis are needed. Chelation should be considered in patients with iron overload and a history of GBCA exposure. (©) RSNA, 2016.

Heterologous Expression Systems for Plant Defensin Expression: Examples of Success and Pitfalls. - Gazzaneo, Luis Rs; Pandolfi, Valesca; Jesus, André Ls; Crovella, Sergio; Benko-Iseppon, Ana M; Freitas, Antonio Carlos (Curr Protein Pept Sci, 2016)
Defensins are a superfamily of antimicrobial peptides, present in vertebrates, invertebrates, fungi and plants, suggesting that they appeared prior to the divergence in eukaryotes. The destitution of toxicity to mammalian cells of plant defensins has led to a new research ground, i.e., their potential medical use against human infectious diseases. Isolating defensins from natural sources, like plant tissues, can be time-consuming, labor intensive and usually present low yields. Strategies for large-scale production of purified active defensins have been employed using heterologous expression systems (HES) for defensin production, usually based in E. coli system. Like any other technology, HES present limitations and drawbacks demanding a careful experimental design prior the system selection. This review is proposed to discuss some of the major concerns when choosing to heterologously express plant defensins, with special attention on bacterial expression system.

The Importance of Mortality Risk Assessment: Validation of the Pediatric Index of Mortality 3 Score. - Wolfler, Andrea; Osello, Raffaella; Gualino, Jenny; Calderini, Edoardo; Vigna, Gianluca; Santuz, Pierantonio; Amigoni, Angela; Savron, Fabio; Caramelli, Fabio; Rossetti, Emanuele; Cecchetti, Corrado; Corbari, Maurizio; et al. (Pediatr Crit Care Med, 2016)
OBJECTIVE: To evaluate the performance of the newest version of the Pediatric Index of Mortality 3 score and compare it with the Pediatric Index of Mortality 2 in a multicenter national cohort of children admitted to PICU. DESIGN: Retrospective, prospective cohort study. SETTING: Seventeen Italian PICUs. PATIENTS: All children 0 to 15 years old admitted in PICU from January 2010 to October 2014. INTERVENTIONS: None. MEASUREMENT AND MAIN RESULTS: Eleven thousand one hundred nine children were enrolled in the study. The mean Pediatric Index of Mortality 2 and 3 values of 4.9 and 3.9, respectively, differed significantly (p < 0.05). Overall mortality rate was 3.9%, and the standardized mortality ratio was 0.80 for Pediatric Index of Mortality 2 and 0.98 for Pediatric Index of Mortality 3 (p < 0.05). The area under the curve of the receiver operating characteristic curves was similar for Pediatric Index of Mortality 2 and Pediatric Index of Mortality 3. The Hosmer-Lemeshow test was not significant for Pediatric Index of Mortality 3 (p = 0.21) but was highly significant for Pediatric Index of Mortality 2 (p < 0.001), which overestimated death mainly in high-risk categories. CONCLUSIONS: Mortality indices require validation in each country where it is used. The new Pediatric Index of Mortality 3 score performed well in an Italian population. Both calibration and discrimination were appropriate, and the score more accurately predicted the mortality risk than Pediatric Index of Mortality 2.

In vitro sensitivity to methyl-prednisolone is associated with clinical response in pediatric idiopathic nephrotic syndrome. - Cuzzoni, E; De Iudicibus, S; Stocco, G; Favretto, D; Pelin, M; Messina, G; Ghio, L; Monti, E; Pasini, A; Montini, G; Decorti, G (Clin Pharmacol Ther, 2016)
The aim of this study was to evaluate the in vitro steroid sensitivity as a predictor of clinical response to glucocorticoids in childhood idiopathic nephrotic syndrome (INS). Seventy-four patients (median age 4.33, interquartile range [IQR] 2.82-7.23; 63.5% male) were enrolled in a prospective multicenter study: in vitro steroid inhibition of patients' peripheral blood mononuclear cell proliferation was evaluated by [methyl-(3) H] thymidine incorporation assay at disease onset (T0) and after 4 weeks (T4) of treatment. Steroid dependence was associated with increased in vitro sensitivity at T4 assessed both as drug concentration inducing 50% of inhibition (IC50 ; odds ratio [OR] = 0.48, 95% confidence interval [CI] = 0.24-0.85; P = 0.0094) and maximum inhibition at the highest drug concentration (Imax ; OR = 1.13, 95% CI = 1.02-1.31; P = 0.017). IC50 > 4.4 nM and Imax < 92% at T4 were good predictors for optimal clinical response. These results suggest that this test may be useful for predicting the response to glucocorticoid therapy in pediatric INS.

Innate and adaptive immunity in self-reported nonceliac gluten sensitivity versus celiac disease. - Di Sabatino, Antonio; Giuffrida, Paolo; Fornasa, Giulia; Salvatore, Chiara; Vanoli, Alessandro; Naviglio, Samuele; De Leo, Luigina; Pasini, Alessandra; De Amici, Mara; Alvisi, Costanza; Not, Tarcisio; Rescigno, Maria; et al. (Dig Liver Dis, 2016)
BACKGROUND: Immune mechanisms have been implicated in nonceliac gluten sensitivity (NCGS), a condition characterized by intestinal and/or extraintestinal symptoms caused by the ingestion of gluten in non-celiac/non-wheat allergic individuals. AIMS: We investigated innate and adaptive immunity in self-reported NCGS versus celiac disease (CD). METHODS: In the supernatants of ex vivo-cultured duodenal biopsies from 14 self-reported NCGS patients, 9 untreated and 10 treated CD patients, and 12 controls we detected innate cytokines - interleukin (IL)-15, tumor necrosis factor-α, IL-1β, IL-6, IL-12p70, IL-23, IL-27, IL-32α, thymic stromal lymphopoietin (TSLP), IFN-α-, adaptive cytokines - interferon (IFN)-γ, IL-17A, IL-4, IL-5, IL-10, IL-13-, chemokines - IL-8, CCL1, CCL2, CCL3, CCL4, CCL5, CXCL1, CXCL10-, granulocyte colony stimulating factor (G-CSF) and granulocyte-macrophage colony stimulating factor (GM-CSF). RESULTS: Mucosal innate and adaptive cytokines, chemokines and growth factors did not differ between self-reported NCGS, treated CD and controls. On the contrary, IL-6, IL-15, IL-27, IFN-α, IFN-γ, IL-17A, IL-23, G-CSF, GM-CSF, IL-8, CCL1 and CCL4 were significantly higher in untreated CD than in self-reported NCGS, treated CD and controls, while TSLP was significantly lower in untreated CD than in self-reported NCGS, treated CD and controls. CONCLUSION: In our hands, patients with self-reported NCGS showed no abnormalities of the mucosal immune response.

Isolation of the left innominate artery: a question of connection. - Gesuete, Valentina; Sanabor, Daniela; Benettoni, Alessandra; Bobbo, Marco; Ventura, Alessandro (J Cardiovasc Med (Hagerstown), 2016)

Lactoferrin gene polymorphisms in Italian patients with recurrent tonsillitis. - Zupin, Luisa; Angelelli, Francesco; Grasso, Domenico Leonardo; Crovella, Sergio (Int J Pediatr Otorhinolaryngol, 2016)
INTRODUCTION: Recurrent tonsillitis is an oral pathology characterized by inflammation of tonsils. The disease susceptibility depends upon environmental and host factors, specifically the innate immune response, the first line of host defence could play an important role. Among innate immunity members, lactoferrin, known for its antimicrobial properties, was previously correlated with the risk of oral pathology as periodontitis and dental caries. METHODS: 89 Italian children presenting recurrent tonsillitis and 95 healthy children were genotyped for two LTF non-synonymous polymorphisms, called Thr29Ala and Arg47Lys, in order to investigate their potential role in recurrent tonsillitis susceptibility. RESULTS: no different allele, genotype and haplotype frequency distributions were detected comparing patients and controls. CONCLUSION: data from the current study indicate that LTF polymorphisms might not be involved in recurrent tonsillitis development in our Italian population. However, since the importance of lactoferrin in oral immunity has been previously assessed, further studies should be necessary to unravel the potential role of LTF genetic variants in oral cavity.

Molecular diagnosis of thrombocytopenia-absent radius syndrome using next-generation sequencing. - Nicchia, E; Giordano, P; Greco, C; De Rocco, D; Savoia, A (Int J Lab Hematol, 2016)
INTRODUCTION: Thrombocytopenia-absent radius (TAR) syndrome is a rare autosomal recessive disease. Patients are compound heterozygotes for a loss-of-function allele, which in most cases is a large genomic deletion on chromosome 1q21.1 containing the RBM8A gene, and a noncoding variant located in the 5'UTR (rs139428292) or intronic (rs201779890) regions of RBM8A. As the molecular genetic testing in TAR requires multiple techniques for detection of copy-number variations (CNV) and nucleotide substitutions, we tested whether a next-generation sequencing (NGS) approach could identify both alterations. METHODS: Two unrelated families were analyzed with Ion PGM sequencing using a target panel of genes responsible for different forms of inherited thrombocytopenia. A statistical quantitative evaluation of amplicon coverage was performed to detect CNV, in particular those on the RBM8A gene. RESULTS: All the probands were apparently homozygous for the rare allele inherited by the father at the rs139428292 locus, suggesting the presence of a deletion on the maternal chromosome. The statistical analysis confirmed the hemizygous condition of RBM8A. CONCLUSION: We concluded that NGS approaches could be used as a cost-effective method for molecular investigation of TAR as they could simultaneously detect CNV and point mutations.

A multi-method approach to the molecular diagnosis of overt and borderline 11p15.5 defects underlying Silver-Russell and Beckwith-Wiedemann syndromes. - Russo, Silvia; Calzari, Luciano; Mussa, Alessandro; Mainini, Ester; Cassina, Matteo; Di Candia, Stefania; Clementi, Maurizio; Guzzetti, Sara; Tabano, Silvia; Miozzo, Monica; Sirchia, Silvia; Finelli, Palma; et al. (Clin Epigenetics, 2016)
BACKGROUND: Multiple (epi)genetic defects affecting the expression of the imprinted genes within the 11p15.5 chromosomal region underlie Silver-Russell (SRS) and Beckwith-Wiedemann (BWS) syndromes. The molecular diagnosis of these opposite growth disorders requires a multi-approach flowchart to disclose known primary and secondary (epi)genetic alterations; however, up to 20 and 30 % of clinically diagnosed BWS and SRS cases remain without molecular diagnosis. The complex structure of the 11p15 region with variable CpG methylation and low-rate mosaicism may account for missed diagnoses. Here, we demonstrate the relevance of complementary techniques for the assessment of different CpGs and the importance of testing multiple tissues to increase the SRS and BWS detection rate. RESULTS: Molecular testing of 147 and 450 clinically diagnosed SRS and BWS cases provided diagnosis in 34 SRS and 185 BWS patients, with 9 SRS and 21 BWS cases remaining undiagnosed and herein referred to as "borderline." A flowchart including complementary techniques and, when applicable, the analysis of buccal swabs, allowed confirmation of the molecular diagnosis in all borderline cases. Comparison of methylation levels by methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) in borderline and control cases defined an interval of H19/IGF2:IG-DMR loss of methylation that was distinct between "easy to diagnose" and "borderline" cases, which were characterized by values ≤mean -3 standard deviations (SDs) compared to controls. Values ≥mean +1 SD at H19/IGF2: IG-DMR were assigned to borderline hypermethylated BWS cases and those ≤mean -2 SD at KCNQ1OT1: TSS-DMR to hypomethylated BWS cases; these were supported by quantitative pyrosequencing or Southern blot analysis. Six BWS cases suspected to carry mosaic paternal uniparental disomy of chromosome 11 were confirmed by SNP array, which detected mosaicism till 10 %. Regarding the clinical presentation, borderline SRS were representative of the syndromic phenotype, with exception of one patient, whereas BWS cases showed low frequency of the most common features except hemihyperplasia. CONCLUSIONS: A conclusive molecular diagnosis was reached in borderline methylation cases, increasing the detection rate by 6 % for SRS and 5 % for BWS cases. The introduction of complementary techniques and additional tissue analyses into routine diagnostic work-up should facilitate the identification of cases undiagnosed because of mosaicism, a distinctive feature of epigenetic disorders.
Keywords: Beckwith-Wiedemann Syndrome; Blotting, Southern; Child; Child, Preschool; Chromosomes, Human, Pair 11; CpG Islands; DNA Methylation; Epigenesis, Genetic; Female; Humans; Infant; Male; Mosaicism; Multiplex Polymerase Chain Reaction; Oligonucleotide Array Sequence Analysis; Silver-Russell Syndrome

Non-additive genome-wide association scan reveals a new gene associated with habitual coffee consumption. - Pirastu, Nicola; Kooyman, Maarten; Robino, Antonietta; van der Spek, Ashley; Navarini, Luciano; Amin, Najaf; Karssen, Lennart C; van Duijn, Cornelia M; Gasparini, Paolo (Sci Rep, 2016)
Coffee is one of the most consumed beverages world-wide and one of the primary sources of caffeine intake. Given its important health and economic impact, the underlying genetics of its consumption has been widely studied. Despite these efforts, much has still to be uncovered. In particular, the use of non-additive genetic models may uncover new information about the genetic variants driving coffee consumption. We have conducted a genome-wide association study in two Italian populations using additive, recessive and dominant models for analysis. This has uncovered a significant association in the PDSS2 gene under the recessive model that has been replicated in an independent cohort from the Netherlands (ERF). The identified gene has been shown to negatively regulate the expression of the caffeine metabolism genes and can thus be linked to coffee consumption. Further bioinformatics analysis of eQTL and histone marks from Roadmap data has evidenced a possible role of the identified SNPs in regulating PDSS2 gene expression through enhancers present in its intron. Our results highlight a novel gene which regulates coffee consumption by regulating the expression of the genes linked to caffeine metabolism. Further studies will be needed to clarify the biological mechanism which links PDSS2 and coffee consumption.

Nonmuscle Myosin Heavy Chain IIA Mutation Predicts Severity and Progression of Sensorineural Hearing Loss in Patients With MYH9-Related Disease. - Verver, Eva J J; Topsakal, Vedat; Kunst, Henricus P M; Huygen, Patrick L M; Heller, Paula G; Pujol-Moix, Núria; Savoia, Anna; Benazzo, Marco; Fierro, Tiziana; Grolman, Wilko; Gresele, Paolo; Pecci, Alessandro (Ear Hear, 2016)
OBJECTIVES: MYH9-related disease (MYH9-RD) is an autosomal- dominant disorder deriving from mutations in MYH9, the gene for the nonmuscle myosin heavy chain (NMMHC)-IIA. MYH9-RD has a complex phenotype including congenital features, such as thrombocytopenia, and noncongenital manifestations, namely sensorineural hearing loss (SNHL), nephropathy, cataract, and liver abnormalities. The disease is caused by a limited number of mutations affecting different regions of the NMMHC-IIA protein. SNHL is the most frequent noncongenital manifestation of MYH9-RD. However, only scarce and anecdotal information is currently available about the clinical and audiometric features of SNHL of MYH9-RD subjects. The objective of this study was to investigate the severity and propensity for progression of SNHL in a large series of MYH9-RD patients in relation to the causative NMMHC-IIA mutations. DESIGN: This study included the consecutive patients diagnosed with MYH9-RD between July 2007 and March 2012 at four participating institutions. A total of 115 audiograms were analyzed from 63 patients belonging to 45 unrelated families with different NMMHC-IIA mutations. Cross-sectional analyses of audiograms were performed. Regression analysis was performed, and age-related typical audiograms (ARTAs) were derived to characterize the type of SNHL associated with different mutations. RESULTS: Severity of SNHL appeared to depend on the specific NMMHC-IIA mutation. Patients carrying substitutions at the residue R702 located in the short functional SH1 helix had the most severe degree of SNHL, whereas patients with the p.E1841K substitution in the coiled-coil region or mutations at the nonhelical tailpiece presented a mild degree of SNHL even at advanced age. The authors also disclosed the effects of different amino acid changes at the same residue: for instance, individuals with the p.R702C mutation had more severe SNHL than those with the p.R702H mutation, and the p.R1165L substitution was associated with a higher degree of hearing loss than the p.R1165C. In general, mild SNHL was associated with a fairly flat audiogram configuration, whereas severe SNHL correlated with downsloping configurations. ARTA plots showed that the most progressive type of SNHL was associated with the p.R702C, the p.R702H, and the p.R1165L substitutions, whereas the p.R1165C mutation correlated with a milder, nonprogressive type of SNHL than the p.R1165L. ARTA for the p.E1841K mutation demonstrated a mild degree of SNHL with only mild progression, whereas the ARTA for the mutations at the nonhelical tailpiece did not show any substantial progression. CONCLUSIONS: These data provide useful tools to predict the progression and the expected degree of severity of SNHL in individual MYH9-RD patients, which is especially relevant in young patients. Consequences in clinical practice are important not only for appropriate patient counseling but also for development of customized, genotype-driven clinical management. The authors recently reported that cochlear implantation has a good outcome in MYH9-RD patients; thus, stricter follow-up and earlier intervention are recommended for patients with unfavorable genotypes.

The one-step synthesis and surface functionalization of dumbbell-like gold-iron oxide nanoparticles: a chitosan-based nanotheranostic system. - Kostevsek, Nina; Locatelli, Erica; Garrovo, Chiara; Arena, Francesca; Monaco, Ilaria; Nikolov, Ivaylo Petrov; Sturm, Saso; Zuzek Rozman, Kristina; Lorusso, Vito; Giustetto, Pierangela; Bardini, Paola; Biffi, Stefania; et al. (Chem Commun (Camb), 2016)
The first one-step synthesis of dumbbell-like gold-iron oxide nanoparticles has been reported here. Surface functionalization with a biocompatible chitosan matrix allowed us to obtain a novel targetable diagnostic and therapeutic tool.

Pharmacogenetics driving personalized medicine: analysis of genetic polymorphisms related to breast cancer medications in Italian isolated populations. - Cocca, Massimiliano; Bedognetti, Davide; La Bianca, Martina; Gasparini, Paolo; Girotto, Giorgia (J Transl Med, 2016)
BACKGROUND: Breast cancer is the most common cancer in women characterized by a high variable clinical outcome among individuals treated with equivalent regimens and novel targeted therapies. In this study, we performed a population based approach intersecting high-throughput genotype data from Friuli Venezia Giulia (FVG) isolated populations with publically available pharmacogenomics information to estimate the frequency of genotypes correlated with responsiveness to breast cancer treatment thus improving the clinical management of this disease in an efficient and cost effective way. METHODS: A list of 80 variants reported to be related to the efficacy or toxicity of breast cancer drugs was obtained from PharmGKB database. Fourty-one were present in FVG, 1000G European (EUR) and ExAC (Non Finnish European) databases. Their frequency was extracted using PLINK software and the differences tested by Fisher's exact test. RESULTS: Statistical analyses revealed that 13 out of the 41 (32 %) variants were significantly different in frequency in our sample as compared to the EUR/ExAC cohorts. For nine variants the available level of evidence (LOE) included polymorphisms related to cyclophosphamide, tamoxifen, doxorubicin, fluorpyrimidine and paclitaxel. In particular, for trastuzumab two variants were detected: (1) rs1801274-G within FCGR2A and associated with decreased efficacy (LOE 2B); (2) rs1136201-G located within ERBB2 and associated with increased toxicity (LOE 3). Both these two variants were underrepresented in the FVG population compared to EUR/ExAC population thus suggesting a high therapeutic index of this drug in our population. Moreover, as regards fluoropyrimidines, the frequency of two polymorphisms within the DPYD gene associated with drug toxicity (e.g., rs2297595-C allele and rs3918290-T allele, LOE 2A and 1, respectively) was extremely low in FVG population thus suggesting that a larger number of FVG patients could benefit from full dosage of fluoropyrimidine therapy. CONCLUSIONS: All these findings increase the overall knowledge on the prevalence of specific variants related with breast cancer treatment responsiveness in FVG population and highlight the importance of assessing gene polymorphisms related with cancer medications in isolated communities.

Pitfalls and promises in FTIR spectromicroscopy analyses to monitor iron-mediated DNA damage in sperm. - Pascolo, Lorella; Bedolla, Diana E; Vaccari, Lisa; Venturin, Irene; Cammisuli, Francesca; Gianoncelli, Alessandra; Mitri, Elisa; Giolo, Elena; Luppi, Stefania; Martinelli, Monica; Zweyer, Marina; Ricci, Giuseppe (Reprod Toxicol, 2016)
Many drugs, chemicals, and environmental factors can impair sperm functionality by inducing DNA damage, one of the important causes of reduced fertility potential. The use of vibrational spectromicroscopy represents a promising approach for monitoring DNA integrity in sperm, although some limitations exist, depending from the experimental conditions. Here, we report that when using FTIR spectromicroscopy to reveal oxidative stress mediated by Fenton's reaction on hydrated sperm samples, DNA damage interpretation is partially compromised by unexpected cell surface precipitates. The precipitates give a broad band in the 1150-1000cm(-1) infrared region, which partially covers one of the signatures of DNA (phosphate stretching bands), and are detected as iron and oxygen containing material when using XRF spectroscopy. On the other hand, the analyses further support the potential of FTIR spectromicroscopy to reveal cellular oxidative damage events such as lipid peroxidation, protein misfolding and aggregations, as well as DNA strain breaks.

The prognostic value of biological markers in paediatric Hodgkin lymphoma. - Farruggia, Piero; Puccio, Giuseppe; Sala, Alessandra; Todesco, Alessandra; Buffardi, Salvatore; Garaventa, Alberto; Bottigliero, Gaetano; Bianchi, Maurizio; Zecca, Marco; Locatelli, Franco; Pession, Andrea; Pillon, Marta; et al. (Eur J Cancer, 2016)
BACKGROUND: Many biological and inflammatory markers have been proposed as having a prognostic value at diagnosis of Hodgkin lymphoma (HL), but very few have been validated in paediatric patients. We explored the significance of these markers in a large population of 769 affected children. PATIENTS AND METHODS: By using the database of patients enrolled in A.I.E.O.P. (Associazione Italiana di Emato-Oncologia Pediatrica) trial LH2004 for paediatric HL, we identified 769 consecutive patients treated with curative intent from 1st June 2004 to 1st April 2014 with ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine), or hybrid COPP/ABV (cyclophosphamide, vincristine, prednisone, procarbazine, doxorubicin, bleomycin and vinblastine) regimens. RESULTS: On multivariate analysis with categorical forms, the 5-year freedom from progression survival was significantly lower in patients with stage IV or elevated value of platelets, eosinophils and ferritin at diagnosis. Furthermore, stage IV and eosinophils seem to maintain their predictive value independently of interim (after IV cycles of chemotherapy) positron emission tomography. CONCLUSION: Using the combination of four simple markers such as stage IV and elevated levels of platelets, ferritin and eosinophils, it is possible to classify the patients into subgroups with very different outcomes.
Keywords: Adolescent; Age Factors; Antineoplastic Combined Chemotherapy Protocols; Biomarkers, Tumor; Blood Platelets; Child; Child, Preschool; Databases, Factual; Disease Progression; Disease-Free Survival; Eosinophils; Female; Ferritins; Hodgkin Disease; Humans; Infant; Infant, Newborn; Italy; Kaplan-Meier Estimate; Leukocyte Count; Male; Multivariate Analysis; Neoplasm Staging; Platelet Count; Predictive Value of Tests; Proportional Hazards Models; Retrospective Studies; Risk Factors; Time Factors; Treatment Outcome

Protective Role of BST2 Polymorphisms in Mother-to-Child Transmission of HIV-1 and Adult AIDS Progression. - Kamada, Anselmo J; Bianco, Anna M; Zupin, Luisa; Girardelli, Martina; Matte, Maria C C; Medeiros, Rúbia Marília de; Almeida, Sabrina Esteves de Matos; Rocha, Marineide M; Segat, Ludovica; Chies, José A B; Kuhn, Louise; Crovella, Sergio (J Acquir Immune Defic Syndr, 2016)
Bone marrow stromal cell antigen-2 (BST-2)/Tetherin is a restriction factor that prevents Human immunodeficiency virus type 1 (HIV-1) release from infected cells and mediates pro-inflammatory cytokine production. This study investigated the risk conferred by single nucleotide polymorphisms (rs919266, rs9192677, and rs9576) at BST-2 coding gene (BST2) in HIV-1 mother-to-child transmission and in disease progression. Initially, 101 HIV-1+ pregnant women and 331 neonates exposed to HIV-1 from Zambia were enrolled. Additional BST2 single nucleotide polymorphism analyses were performed in 2 cohorts with acquired immunodeficiency syndrome (AIDS) progression: an adult Brazilian cohort (37 rapid, 30 chronic and 21 long-term non-progressors) and an Italian pediatric cohort (21 rapid and 67 slow progressors). The rs9576A allele was nominally associated with protection during breastfeeding (P = 0.019) and individuals carrying rs919266 GA showed slower progression to AIDS (P = 0.033). Despite the influence of rs919266 and rs9576 on BST2 expression being still undetermined, a preventive role by BST2 polymorphisms was found during HIV-1 infection.

Putative modifier genes in mevalonate kinase deficiency. - Marcuzzi, Annalisa; Vozzi, Diego; Girardelli, Martina; Tricarico, Paola Maura; Knowles, Alessandra; Crovella, Sergio; Vuch, Josef; Tommasini, Alberto; Piscianz, Elisa; Bianco, Anna Monica (Mol Med Rep, 2016)
Mevalonate kinase deficiency (MKD) is an autosomal recessive auto‑inflammatory disease, caused by impairment of the mevalonate pathway. Although the molecular mechanism remains to be elucidated, there is clinical evidence suggesting that other regulatory genes may be involved in determining the phenotype. The identification of novel target genes may explain non‑homogeneous genotype‑phenotype correlations, and provide evidence in support of the hypothesis that novel regulatory genes predispose or amplify deregulation of the mevalonate pathway in this orphan disease. In the present study, DNA samples were obtained from five patients with MKD, which were then analyzed using whole exome sequencing. A missense variation in the PEX11γ gene was observed in homozygosis in P2, possibly correlating with visual blurring. The UNG rare gene variant was detected in homozygosis in P5, without correlating with a specific clinical phenotype. A number of other variants were found in the five analyzed DNA samples from the MKD patients, however no correlation with the phenotype was established. The results of the presents study suggested that further analysis, using next generation sequencing approaches, is required on a larger sample size of patients with MKD, who share the same MVK mutations and exhibit 'extreme' clinical phenotypes. As MVK mutations may be associated with MKD, the identification of specific modifier genes may assist in providing an earlier diagnosis.

A quasi randomized-controlled trial to evaluate the effectiveness of clowntherapy on children's anxiety and pain levels in emergency department. - Felluga, Margherita; Rabach, Ingrid; Minute, Marta; Montico, Marcella; Giorgi, Rita; Lonciari, Isabella; Taddio, Andrea; Barbi, Egidio (Eur J Pediatr, 2016)
UNLABELLED: The aim of the study is to investigate if the presence of medical clowns during painful procedures in the emergency department (ED) affects children's anxiety and pain. Forty children (4-11 years) admitted to the ED with the need of painful procedures were prospectively enrolled. They were randomly assigned to the clown group, where children interacted with clowns or to the control group in which they were entertained by parents and ED nurses. The children's anxiety was assessed by the Children's Anxiety and Pain Scales; pain was evaluated with the Numerical Rating Scale and Wong-Backer Scale, according to the children's age. Staff and clown's opinions were evaluated by means of dedicated questionnaires. Children's anxiety levels in the clown group were significantly lower than those compared with the control group, while children's pain levels did not change between the two groups. CONCLUSION: The presence of clowns in the ED before and during painful procedures was effective in reducing children's anxiety. WHAT IS KNOWN: • Anxiety and fear caused by medical procedures exacerbate children's pain and may interfere with the procedure. • To reduce anxiety, fear, and pain and to facilitate patient's evaluation, different non-pharmacological approaches have been proposed and positive effects of laughter and humor have been reported. What is New: • The presence of clowns in the waiting room and in the ED during medical evaluation and painful procedures helps to reduce children's anxiety.

A reference panel of 64,976 haplotypes for genotype imputation. - McCarthy, Shane; Das, Sayantan; Kretzschmar, Warren; Delaneau, Olivier; Wood, Andrew R; Teumer, Alexander; Kang, Hyun Min; Fuchsberger, Christian; Danecek, Petr; Sharp, Kevin; Luo, Yang; Sidore, Carlo; et al. (Nat Genet, 2016)
We describe a reference panel of 64,976 human haplotypes at 39,235,157 SNPs constructed using whole-genome sequence data from 20 studies of predominantly European ancestry. Using this resource leads to accurate genotype imputation at minor allele frequencies as low as 0.1% and a large increase in the number of SNPs tested in association studies, and it can help to discover and refine causal loci. We describe remote server resources that allow researchers to carry out imputation and phasing consistently and efficiently.

"Safety and utility of percutaneous liver biopsy in hematopoietic stem cell transplant pediatric recipients: a retrospective study". - Maximova, Natalia; Gregori, Massimo; Barbieri, Francesca; Pizzol, Antonio; Sonzogni, Aurelio (BMC Cancer, 2016)
BACKGROUND: Liver biopsies in pediatric hematopoietic stem cell transplantation (HSCT) patients are as and effective when performed at bedside in the Bone Marrow Transplant Unit (BMTU) than in the Day Surgery Unit (DSU), with better patient compliance and lower emotional distress for these children. METHODS: The study group consisted of 45 children who underwent allogeneic HSCT. We reviewed 68 liver biopsies performed between April 2006 and September 2015. 12 (17.6 %) biopsies were performed in the DSU and 56 (82.3 %) in the BMTU; nine (13.2 %) prior to HSCT and 59 (86.7 %) after HSCT. Pre-procedural behavioral status (subjective score) was evaluated by pediatric transplant physicians by filling in a questionnaire employing a three-point scale: "calm and cooperative", "agitated and non-cooperative" or "frightened and suffering". Objective score was obtained measuring patient's heart rate before the procedure and comparing it with mean heart rate. RESULTS: Patients who underwent the procedure at the BMTU experienced less emotional distress than those who underwent it in the DSU: 58.3 % of patients treated at the DSU were agitated as compared with 16.1 % of those treated at the BMTU (p < 0.01). Among the 59 biopsies performed after HSCT, 41 (69.5 %) were taken from symptomatic patients for a diagnostic purpose and 18 (30.5 %) in asymptomatic ones in order to rule out hepatic GVHD. Among these 18 procedures, GVHD was diagnosed in 16 (88.9 %) cases. Minor complications occurred in about 17 % of procedures (12 biopsies), at a rate of 25 % for the DSU location compared with 16 % for the BMTU location. Only two major complications were reported, one in the DSU and one in the BMTU. CONCLUSION: Liver biopsy performed at bedside in HSCT patients does not carry a higher risk of adverse events than the same procedure performed in the DSU and has lower emotional distress associated with better patient compliance, thus contributing significantly to a higher standard of care.

Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice. - Pascolo, Lorella; Zabucchi, Giuliano; Gianoncelli, Alessandra; Kourousias, George; Trevisan, Elisa; Pascotto, Ernesto; Casarsa, Claudia; Ryan, Chris; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; et al. (Toxicol Lett, 2016)
Human exposure to asbestos can cause a wide variety of lung diseases that are still a current major health concern, even if asbestos has been banned in many countries. It has been shown in many studies that asbestos fibers, ingested by alveolar macrophages, disrupt lung iron homeostasis by sequestering iron. Calcium can also be deposited on the fibers. The pathways along which iron and above all calcium interact with fibers are still unknown. Our aim was that of investigating if the iron accumulation induced by the inhaled asbestos fibers also involves calcium ions accumulation. Lung sections of asbestos-exposed mice were analyzed using an extremely sensitive procedure available at the synchrotron facilities, that provides morphological and chemical information based on X-ray fluorescence microspectroscopy (μ-XRF). In this study we show that (1) where conventional histochemical procedures revealed only weak deposits of iron and calcium, μ-XRF analysis is able to detect significant deposits of both iron and calcium on the inhaled asbestos fibers; (2) the extent of the deposition of these ions is proportionally directly related and (3) iron and calcium deposition on inhaled asbestos fibers is concomitant with the appearance of inflammatory and hyperplastic reactions.

Transcription factors involved in plant resistance to pathogens. - Amorim, Lidiane L B; da Fonseca-Dos-Santos, Romulo; Guida-Santos, Mauro; Crovella, Sergio; Benko-Iseppon, Ana Maria (Curr Protein Pept Sci, 2016)
Phytopathogenic microorganisms have a significant influence on survival and productivity of several crop plants. Transcription factors (TFs) are important players in the response to biotic stresses, as insect attack and pathogen infection. In face of such adversities many TF families have been previously reported as differentially expressed in plants as a reaction to bacterial, fungal and viral infection. This review highlights recent progresses in understanding the structure, function, signal regulation and interaction of transcription factors with other proteins in response to pathogens. Hence, we focus on three families of transcription factors: ERF, bZIP and WRKY, due to their abundance, importance and the availability of functionally well-characterized members in response to pathogen attack. Their roles and the possibilities related to the use of this knowledge for engineering pathogen resistance in crop plants are also discussed.

TRIM5 gene polymorphisms in HIV-1-infected patients and healthy controls from Northeastern Brazil. - Celerino da Silva, Ronaldo; Coelho, Antônio Victor Campos; Arraes, Luiz Claudio; Brandão, Lucas André Cavalcanti; Crovella, Sergio; Guimarães, Rafael Lima (Immunol Res, 2016)
Humans show heterogeneity in vulnerability to HIV-1 infection, partially under control of genes involved in host immunity and virus replication. TRIM5α protein has restriction activity against replication of many retroviruses. Human TRIM5 gene single nucleotide polymorphisms have been reported as involved in susceptibility to HIV-1 infection. We recruited 213 HIV-1-positive patients and 234 healthy uninfected controls from Northeast Brazil; two non-synonymous variants at exon 2, rs3740996 (H43Y) and rs10838525 (R136Q), and one regulatory polymorphism (rs16934386) at 5'UTR region of TRIM5 were analyzed. The R136Q variation presented significant differences between HIV-1-positive patients and healthy controls. The 136Q allele and the 136QQ genotype were more frequent in healthy controls (32.7 and 10.2 %, respectively) than in HIV-1-positive patients (136Q allele: 24.4 %; OR 0.66; CI 95 % 0.49-0.90; p value = 0.008/136QQ genotype: 4.2 %; OR 0.33; CI 95 % 0.13-0.79, p = 0.008) also after adjusting for age and sex. We also stratified our findings according to the presence of CCR5Δ32 variation, but the results remained the same. We observed that rs10838525 (R136Q) and rs3740996 (H43Y) were in linkage disequilibrium (D' = 0.71), forming four possible haplotypes. The H43-136Q haplotype was significantly more frequent in healthy controls (28.2 %) than in HIV-positive patients (21.4 %; OR 0.69; CI 95 % 0.50-0.96; p = 0.022). An increased frequency of allele (136Q) and genotype (136QQ) of the non-synonymous rs10838525 (R136Q) variant and the haplotype (43H-136Q) was observed among healthy controls individuals. Being aware of the limitation of this study (unavailability of exposed but uninfected individuals), we hypothesize a potential role for TRIM5 variations in the protection against HIV-1 infection.

Understanding the role of personality and alexithymia in food preferences and PROP taste perception. - Robino, Antonietta; Mezzavilla, Massimo; Pirastu, Nicola; La Bianca, Martina; Gasparini, Paolo; Carlino, Davide; Tepper, Beverly J (Physiol Behav, 2016)
Taste perception and food preferences are influenced by a variety of factors, including personality characteristics. The aims of this study were to examine the role of personality characteristics, such as alexithymia (a personality construct characterized by inability to identify, describe, and work with one's own feelings), in: 1) taste responses to the bitter genetic taste-marker PROP and 2) food liking. We studied 649 healthy subjects residing in six genetically-isolated villages of Northeast Italy. Data on PROP taste responsiveness, food liking, personality characteristics and TAS2R28 genotypes were collected. Results showed that PROP non-tasters had higher alexithymia scores than PROP tasters. Moreover, the presence of alexithymia in heterozygous individuals for the rs1726886 polymorphism of the TAS2R38 gene was associated with a reduction in the perceived intensity of PROP. Finally, higher alexithymia scores were associated with liking of alcohol, sweets and fats/meats whereas lower alexithymia scores were related to liking of vegetables, condiments and strong cheeses, Measures of temperament, character, anxiety and depression were also related to food liking. Our findings suggest that: 1) alexithymia, in addition to the TAS2R38 polymorphism, may play a role in responsiveness to the aversive and bitter taste of PROP; and 2) alexithymia, in combination with other personality traits, may provide important insights for better understanding food liking.

When a lymphatic malformation determines a bowel volvulus: Are clinical status and images always reliable? - Guida, Edoardo; Di Grazia, Massimo; Cattaruzzi, Elisabetta; Bussani, Rossana; Rigamonti, Waifro; Lembo, Maria Antonietta (Int J Surg Case Rep, 2016)
INTRODUCTION: An acute abdomen in the form of small-bowel volvulus could be a presentation of a lymphatic malformation in childhood. CASE PRESENTATION: A 5year old male was admitted to our Institute for an acute abdomen. Clinical aspects and radiological images were not specific for a certain diagnosis. Laparotomy revealed a big soft mass, with a milky content, completely involving about 50cm of ileus with a partial volvulus of the intestinal loop. A complete mass excision and also a bowel involved resection were performed. After a histological examination, a lymphatic malformation was diagnosed. DISCUSSION: The diagnosis of a mesenteric lymphatic malformation could be intraoperative and a complete resection should be the treatment of choice. Sometimes it could be necessary to perform an involved bowel tract resection in the case of volvolus with ischemia. CONCLUSIONS: Paediatricians and surgeons should bare in mind that an intrabdominal lymphatic malformation may present as a nonspecific an acute abdomen caused by a bowel volvolus and diagnosis may not be so simple preoperatively.

Advertisements of follow-on formula and their perception by pregnant women and mothers in Italy. - Cattaneo, Adriano; Pani, Paola; Carletti, Claudia; Guidetti, Margherita; Mutti, Valentina; Guidetti, Cecilia; Knowles, Alessandra (Arch Dis Child, 2015)
OBJECTIVE: To assess how follow-on formula milks for infants aged 6-12 months are presented to and understood by mothers. DESIGN: A quantitative and qualitative cross-sectional study including (1) an analysis of advertisements in three magazines for parents; (2) in-depth semistructured qualitative interviews to pregnant women on their perception of two advertisements for follow-on formula and (3) self-administered questionnaires for mothers to explore their exposure to and perception of formula advertisements. PARTICIPANTS: Eighty pregnant women 32-36 weeks of gestation with no previous children and 562 mothers of children <3 years old. SETTING: Maternal and child health centres in eight cities of Italy. RESULTS: Advertisements of formula (n=89) represented about 7% of all advertisements in the three magazines, the majority (58%) being for follow-on formula. Advertisements were parent-oriented, aimed at helping parents solve health problems of their babies or at eliciting good feelings, or both. The qualitative interviews to pregnant women showed inability to define the advertised products at first glance due to the ambiguity of the numeral 2 and the presumed age of the portrayed baby; this inability did not disappear after carefully viewing the advertisements and reading the text. When asked in the self-administered questionnaires whether they had ever come across advertisements of infant formula, 81% of mothers reported that they had, despite the legal inexistence of such advertisements, and 65% thought that it was for a product to be used from birth. CONCLUSIONS: Advertisements of follow-on formula are perceived by pregnant women and mothers as promoting infant formula.
Keywords: Adult; Advertising as Topic; Attitude to Health; Cross-Sectional Studies; Female; Humans; Infant; Infant Formula; Italy; Mothers; Perception; Periodicals as Topic; Pregnancy; Pregnant Women; Reading; Surveys and Questionnaires; Young Adult

Alendronate, a double-edged sword acting in the mevalonate pathway. - Tricarico, Paola Maura; Girardelli, Martina; Kleiner, Giulio; Knowles, Alessandra; Valencic, Erica; Crovella, Sergio; Marcuzzi, Annalisa (Mol Med Rep, 2015)
Aminobisphosphonate aledronate is a compound commonly used clinically for the treatment of osteoporosis and other bone diseases, as a result of it preventing bone resorption. However, in previous years it has also been used to obtain cellular and animal models of a rare genetic disorder termed Mevalonate Kinase Deficiency (MKD). MKD is caused by mutations affecting the mevalonate kinase enzyme, in the cholesterol pathway and alendronate can be used to biochemically mimic the genetic defect as it inhibits farnesyl pyrophosphate synthase in the same pathway. Despite evidence in favor of the inhibition exerted on the mevalonate pathway, there is at least one clinical case of MKD in which alendronate improved not only skeletal and bone fractures, as expected, but also MKD clinical features. Based on this finding, the present study assessed the anti‑inflammatory properties of this aminobisphosphonate in vitro. No anti‑inflammatory effects of alendronate were observed in the in vitro experiments. Since MKD lacks specific treatments, these results may assist scientists and physicians in making the decision as to the most suitable choice of therapeutic compounds for this neglected disease.

Altered germinal center reaction and abnormal B cell peripheral maturation in PI3KR1-mutated patients presenting with HIGM-like phenotype. - Lougaris, Vassilios; Faletra, Flavio; Lanzi, Gaetana; Vozzi, Diego; Marcuzzi, Annalisa; Valencic, Erica; Piscianz, Elisa; Bianco, AnnaMonica; Girardelli, Martina; Baronio, Manuela; Loganes, Claudia; Fasth, Anders; et al. (Clin Immunol, 2015)
Keywords: B-Lymphocytes; Child, Preschool; Female; Germinal Center; Humans; Hyper-IgM Immunodeficiency Syndrome; Infant; Male; Mutation; Phenotype; Phosphatidylinositol 3-Kinases; RNA Splice Sites; Sequence Analysis, DNA

Analysis of functional variants reveals new candidate genes associated with alexithymia. - Mezzavilla, Massimo; Ulivi, Sheila; Bianca, Martina La; Carlino, Davide; Gasparini, Paolo; Robino, Antonietta (Psychiatry Res, 2015)
In this study we explored the possible association between 36,915 functional variants and alexithymia, a personality trait characterized by the inability to identify and describe emotions and feelings. From our analysis, variants in the genes ABCB4, TP53AIP1, ARHGAP32 and TMEM88B were identified linked to the alexithymia phenotype.
Keywords: Adolescent; Adult; Affective Symptoms; Aged; Case-Control Studies; DNA-Binding Proteins; Emotions; Female; Humans; Male; Membrane Proteins; Middle Aged; P-Glycoproteins; Personality Inventory; Phenotype; Tumor Suppressor Proteins; Young Adult

Appendicitis in children less than five years old: A challenge for the general practitioner. - Marzuillo, Pierluigi; Germani, Claudio; Krauss, Baruch S; Barbi, Egidio (World J Clin Pediatr, 2015)
Acute appendicitis is one of the most common indications for abdominal surgery in pediatrics with peak incidence in the second decade of life. Acute appendicitis in the first years of life is an uncommon event. The clinical presentation is often varied and the diagnosis may be overshadowed by other medical conditions. Gastroenteritis is the most common misdiagnosis, with a history of diarrhea present in 33% to 41% of patients. Pain is the most common presenting symptom in children less than 5 years old, followed by vomiting, fever, anorexia and diarrhea. The most common physical sign is focal tenderness (61% of the patients) followed by guarding (55%), diffuse tenderness (39%), rebound (32%), and mass (6%). Neonatal appendicitis is a very rare disease with high mortality; presenting symptoms are nonspecific with abdominal distension representing the main clinical presentation. The younger the patient, the earlier perforation occurs: 70% of patients less than 3 years develop a perforation within 48 h of onset of symptoms. A timely diagnosis reduces the risk of complications. We highlight the epidemiology, pathophysiology, clinical signs and laboratory clues of appendicitis in young children and suggest an algorithm for early diagnosis.

Are all cases of paediatric essential thrombocythaemia really myeloproliferative neoplasms? Analysis of a large cohort. - Randi, Maria L; Geranio, Giulia; Bertozzi, Irene; Micalizzi, Concetta; Ramenghi, Ugo; Tucci, Fabio; Notarangelo, Lucia D; Ladogana, Saverio; Menna, Giuseppe; Giordano, Paola; Consarino, Caterina; Farruggia, Piero; et al. (Br J Haematol, 2015)
Sporadic essential thrombocythaemia (ET) is rare in paediatrics, and the diagnostic and clinical approach to paediatric cases cannot be simply copied from experience with adults. Here, we assessed 89 children with a clinical diagnosis of ET and found that 23 patients (25·8%) had a clonal disease. The JAK2 V617F mutation was identified in 14 children, 1 child had the MPL W515L mutation, and 6 had CALR mutations. The monoclonal X-chromosome inactivation pattern was seen in six patients (two with JAK2 V617F and two with CALR mutations). The other 66 patients (74·2%) had persistent thrombocytosis with no clonality. There were no clinical or haematological differences between the clonal and non-clonal patients. The relative proportion of ET-specific mutations in the clonal children was much the same as in adults. The higher prevalence of non-clonal cases suggests that some patients may not have myeloproliferative neoplasms, with significant implications for their treatment.
Keywords: Adolescent; Adult; Amino Acid Substitution; Child; Child, Preschool; Cohort Studies; Female; Hematologic Neoplasms; Humans; Infant; Janus Kinase 2; Male; Mutation, Missense; Neoplasm Proteins; Thrombocythemia, Essential

Assessment of the olfactory function in Italian patients with type 3 von Willebrand disease caused by a homozygous 253 Kb deletion involving VWF and TMEM16B/ANO2. - Cenedese, Valentina; Mezzavilla, Massimo; Morgan, Anna; Marino, Renato; Ettorre, Cosimo Pietro; Margaglione, Maurizio; Gasparini, Paolo; Menini, Anna (PLoS One, 2015)
Type 3 Von Willebrand disease is an autosomal recessive disease caused by the virtual absence of the von Willebrand factor (VWF). A rare 253 kb gene deletion on chromosome 12, identified only in Italian and German families, involves both the VWF gene and the N-terminus of the neighbouring TMEM16B/ANO2 gene, a member of the family named transmembrane 16 (TMEM16) or anoctamin (ANO). TMEM16B is a calcium-activated chloride channel expressed in the olfactory epithelium. As a patient homozygous for the 253 kb deletion has been reported to have an olfactory impairment possibly related to the partial deletion of TMEM16B, we assessed the olfactory function in other patients using the University of Pennsylvania Smell Identification Test (UPSIT). The average UPSIT score of 4 homozygous patients was significantly lower than that of 5 healthy subjects with similar sex, age and education. However, 4 other members of the same family, 3 heterozygous for the deletion and 1 wild type, had a slightly reduced olfactory function indicating that socio-cultural or other factors were likely to be responsible for the observed difference. These results show that the ability to identify odorants of the homozygous patients for the deletion was not significantly different from that of the other members of the family, showing that the 253 kb deletion does not affect the olfactory performance. As other genes may compensate for the lack of TMEM16B, we identified some predicted functional partners from in silico studies of the protein-protein network of TMEM16B. Calculation of diversity for the corresponding genes for individuals of the 1000 Genomes Project showed that TMEM16B has the highest level of diversity among all genes of the network, indicating that TMEM16B may not be under purifying selection and suggesting that other genes in the network could compensate for its function for olfactory ability.
Keywords: Adult; Case-Control Studies; Female; Genetic Association Studies; Homozygote; Humans; Italy; Male; Membrane Proteins; Middle Aged; Olfactory Mucosa; Olfactory Perception; Sequence Deletion; Smell; von Willebrand Disease, Type 3; von Willebrand Factor; Young Adult

Association Study between Cervical Lesions and Single or Multiple Vaccine-Target and Non-Vaccine Target Human Papillomavirus (HPV) Types in Women from Northeastern Brazil. - Chagas, Bárbara Simas; Comar, Manola; Gurgel, Ana Pavla Almeida Diniz; Paiva, Sérgio; Seraceni, Silva; de Freitas, Antonio Carlos; Crovella, Sergio (PLoS One, 2015)
We performed an association between high-grade squamous intraepithelial lesions (HSIL), low-grade squamous intraepithelial lesions (LSIL) and single or multiple vaccine-target as well as non-vaccine target Human papillomavirus (HPV) types. Using bead-based HPV genotyping, 594 gynecological samples were genotyped. An association between squamous intraepithelial lesion (SIL) and presence of HPV16, 18, 31, 58 and 56 types were calculated. The risk was estimated by using odds ratio (OR) and 95% of confidence intervals (CI). A total of 370 (62.3%) women were HPV positive. Among these, 157 (42.7%) presented a single HPV infection, and 212 (57.3%) were infected by more than one HPV type. HPV31 was the most prevalent genotype, regardless single and multiple HPV infections. Single infection with HPV31 was associated with LSIL (OR=2.32; 95%CI: 1.01 to 5.32; p=0.04); HPV31 was also associated with LSIL (OR=3.28; 95%CI: 1.74 to 6.19; p= 0.0002) and HSIL (OR=3.82; 95%CI: 2.10 to 6.97; p<0.001) in multiple HPV infections. Risk to harbor cervical lesions was observed in multiple HPV infections with regard to the HPV56 (OR=5.39; 95%CI: 2.44 to 11.90; p<0.001for LSIL; OR=5.37; 95%CI: 2.71 to 10.69; p<0.001) and HPV58 (OR=3.29; 95%CI: 1.34 to 8.09; p=0.0091 for LSIL; OR=3.55; 95%CI: 1.56 to 8.11; p=0.0026) genotypes. In addition, women coinfected with HPV16/31/56 types had 6 and 5-fold increased risk of HSIL (OR=6.46; 95%CI: 1.89 to 22.09; p=0.002) and LSIL (OR=5.22; 95%CI: 1.10 to 24.70; p=0.03), respectively. Multiple HPV infections without HPV16/18 has 2-fold increased risk of HSIL (OR=2.57; 95%CI: 1.41 to 4.70; p=0.002) and LSIL OR=2.03; 95%CI: 1.08 to 3.79; p=0.02). The results of this study suggest that single and multiple vaccine target as well as non-vaccine target HPV types are associated with LSIL and HSIL. These finding should be taken into consideration in the design of HPV vaccination strategies.

Bedside diagnosis of two major clinical phenotypes of hypertensive disorders of pregnancy. - Ferrazzi, E; Zullino, S; Stampalija, T; Vener, C; Cavoretto, P; Gervasi, M T; Vergani, P; Mecacci, F; Marozio, L; Oggè, G; Algeri, P; Ruffatti, A; et al. (Ultrasound Obstet Gynecol, 2015)
OBJECTIVE: We hypothesized that fetal abdominal circumference (AC) and Uterine Doppler Pulsatility Index (UtA-PI) could select two homogenous subgroups of women affected by hypertensive disorders of pregnancy (HDP), characterized by the coexistence of maternal hypertension with and without IUGR. METHODS: This is a multicentre study that studied cases affected by HDP in whom fetal AC and UtA-PI had been measured at admission to feto Maternal Medicine Units. Maternal characteristics, pregnancy complications and outcome were recorded. These data allowed us to model the characteristics of fetal growth in cases affected by HDP, and to design a composite index for risk factors of maternal metabolic syndrome (rfMMS) and composite index of severity for maternal organ and/or function damage (OFD). RESULTS: Measurements of fetal AC and UtA-PI allowed us to define a group of HDP with AGA fetuses (HDP-AGAf) diagnosed by normal fetal AC and a UtA-PI (#205), and a group of HDP with IUGR fetuses (HDP-IUGR) diagnosed by fetal AC <5(th) centile and UtA-PI >95(th) centile (#124). Curves fitted to birth-weight of the two groups were significantly different, and gestational age at admission for HDP, <34 or ≥34, had no effect on their models. When birth-weight was expressed as standard deviation score (SDS) of local reference charts, the average SDS (±standard error) corresponded to the 6(th) and 48(th) centile respectively. The risk of developing HDP-AGAf was significantly associated with risk factors for maternal metabolic syndrome (OR= 2.79;CI 1.57-4.97), independently of gestational age. The same risk factors yielded a non significant ORs of developing late onset HDP. Women with HDP-IUGR proved to be associated with the worst clinical outcomes. CONCLUSIONS: This study adds genuine new data based on simple prenatal bedside examinations, that might help to differentiate HDP with IUGR, from HDP with AGA fetuses, associated with different fetal growth patterns and different risk factors, not affected by gestational age at onset of the disease.

"Blaschkoid dyspigmentation" in a child: don't forget fibroblast chromosomal analysis. - Gortani, Giulia; Faletra, Flavio; Bruno, Irene; Berti, Irene; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Abnormalities, Multiple; Child, Preschool; Chromosomes; DNA; Female; Fibroblasts; Humans; Phenotype; Pigmentation Disorders

Brain-derived neurotrophic factor serum levels in genetically isolated populations: gender-specific association with anxiety disorder subtypes but not with anxiety levels or Val66Met polymorphism. - Carlino, Davide; Francavilla, Ruggiero; Baj, Gabriele; Kulak, Karolina; d'Adamo, Pio; Ulivi, Sheila; Cappellani, Stefania; Gasparini, Paolo; Tongiorgi, Enrico (PeerJ, 2015)
Anxiety disorders (ADs) are disabling chronic disorders with exaggerated behavioral response to threats. This study was aimed at testing the hypothesis that ADs may be associated with reduced neurotrophic activity, particularly of Brain-derived neurotrophic factor (BDNF), and determining possible effects of genetics on serum BDNF concentrations. In 672 adult subjects from six isolated villages in North-Eastern Italy with high inbreeding, we determined serum BDNF levels and identified subjects with different ADs subtypes such as Social and Specific Phobias (PHSOC, PHSP), Generalized Anxiety Disorder (GAD), and Panic Disorder (PAD). Analysis of the population as a whole or individual village showed no significant correlation between serum BDNF levels and Val66Met polymorphism and no association with anxiety levels. Stratification of subjects highlighted a significant decrease in serum BDNF in females with GAD and males with PHSP. This study indicates low heritability and absence of any impact of the Val66Met polymorphism on circulating concentrations of BDNF. Our results show that BDNF is not a general biomarker of anxiety but serum BDNF levels correlate in a gender-specific manner with ADs subtypes.

A case of Rubinstein-Taybi syndrome associated with growth hormone deficiency in childhood. - Tornese, Gianluca; Marzuillo, Pierluigi; Pellegrin, Maria Chiara; Germani, Claudio; Faleschini, Elena; Zennaro, Floriana; Grandone, Anna; Miraglia Del Giudice, Emanuele; Perrone, Laura; Ventura, Alessandro (Clin Endocrinol (Oxf), 2015)

Central venous access devices in pediatric malignancies: a position paper of Italian Association of Pediatric Hematology and Oncology. - Crocoli, Alessandro; Tornesello, Assunta; Pittiruti, Mauro; Barone, Angelica; Muggeo, Paola; Inserra, Alessandro; Molinari, Angelo Claudio; Grillenzoni, Valeria; Durante, Viviana; Cicalese, Maria Pia; Zanazzo, Giulio Andrea; Cesaro, Simone (J Vasc Access, 2015)
INTRODUCTION: Treatment of pediatric malignancies is becoming progressively more complex, implying the adoption of multimodal therapies. A reliable, long-lasting venous access represents one of the critical requirements for the success of those treatments. Recent technical innovations-such as minimally invasive procedures for placement, new devices and novel materials-have rapidly spread for clinical use in adult patients, but are still not consistently used in the pediatric population. METHODS: The Supportive Therapy Working Group of Italian Association of Hematology and Oncology (AIEOP) reviewed medical literature focusing on new aspects of central venous access devices (VADs) in pediatric patients affected by oncohematological diseases. RESULTS: Appropriate recommendations for clinical use in these patients have been discussed and formulated. CONCLUSIONS: The importance of the correct choice, management and use of VADs in pediatric oncohematological patients is a necessary prerequisite for an adequate standard of care, also considering the increased chances of cure and the longer life expectancy of those patients with modern therapies.

Characterization of 14 novel deletions underlying Rubinstein-Taybi syndrome: an update of the CREBBP deletion repertoire. - Rusconi, Daniela; Negri, Gloria; Colapietro, Patrizia; Picinelli, Chiara; Milani, Donatella; Spena, Silvia; Magnani, Cinzia; Silengo, Margherita Cirillo; Sorasio, Lorena; Curtisova, Vaclava; Cavaliere, Maria Luigia; Prontera, Paolo; et al. (Hum Genet, 2015)
Rubinstein-Taybi syndrome (RSTS) is a rare, clinically heterogeneous disorder characterized by cognitive impairment and several multiple congenital anomalies. The syndrome is caused by almost private point mutations in the CREBBP (~55% of cases) and EP300 (~8%) genes. The CREBBP mutational spectrum is variegated and characterized by point mutations (30-50 %) and deletions (~10%). The latter are diverse in size and genomic position and remove either the whole CREBBP gene and its flanking regions or only an intragenic portion. Here, we report 14 novel CREBBP deletions ranging from single exons to the whole gene and flanking regions which were identified by applying complementary cytomolecular techniques: fluorescence in situ hybridization, multiplex ligation-dependent probe amplification and array comparative genome hybridization, to a large cohort of RSTS patients. Deletions involving CREBBP account for 23% of our detected CREBBP mutations, making an important contribution to the mutational spectrum. Genotype-phenotype correlations revealed that patients with CREBBP deletions extending beyond this gene did not always have a more severe phenotype than patients harboring CREBBP point mutations, suggesting that neighboring genes play only a limited role in the etiopathogenesis of CREBBP-centerd contiguous gene syndrome. Accordingly, the extent of the deletion is not predictive of the severity of the clinical phenotype.
Keywords: Adolescent; Adult; Base Sequence; Child; Child, Preschool; Cohort Studies; CREB-Binding Protein; Female; Humans; Infant; Infant, Newborn; Male; Middle Aged; Point Mutation; Rubinstein-Taybi Syndrome; Sequence Deletion

Clinical aspects of Fanconi anemia individuals with the same mutation of FANCF identified by next generation sequencing. - Nicchia, Elena; Benedicenti, Francesco; Rocco, Daniela De; Greco, Chiara; Bottega, Roberta; Inzana, Francesca; Faleschini, Michela; Bonin, Serena; Cappelli, Enrico; Mogni, Massimo; Stanzial, Franco; Svahn, Johanna; et al. (Birth Defects Res A Clin Mol Teratol, 2015)
BACKGROUND: Fanconi anemia (FA) is a rare genetic disease characterized by congenital malformations, aplastic anemia and increased risk of developing malignancies. FA is genetically heterogeneous as it is caused by at least 17 different genes. Among these, FANCA, FANCC, and FANCG account for approximately 85% of the patients whereas the remaining genes are mutated in only a small percentage of cases. For this reason, the molecular diagnostic process is complex and not always extended to all the FA genes, preventing the characterization of individuals belonging to rare groups. METHODS: The FA genes were analyzed using a next generation sequencing approach in two unrelated families. RESULTS: The analysis identified the same, c.484_485del, homozygous mutation of FANCF in both families. A careful examination of three electively aborted fetuses in one family and one affected girl in the other indicated an association of the FANCF loss-of-function mutation with a severe phenotype characterized by multiple malformations. CONCLUSION: The systematic use of next generation sequencing will allow the recognition of individuals from rare complementation groups, a better definition of their clinical phenotypes, and consequently, an appropriate genetic counseling. Birth Defects Research (Part A) 103:1003-1010, 2015. © 2015 Wiley Periodicals, Inc.

Combined circulating epigenetic markers to improve mesothelin performance in the diagnosis of malignant mesothelioma. - Santarelli, Lory; Staffolani, Sara; Strafella, Elisabetta; Nocchi, Linda; Manzella, Nicola; Grossi, Paola; Bracci, Massimo; Pignotti, Elettra; Alleva, Renata; Borghi, Battista; Pompili, Cecilia; Sabbatini, Armando; et al. (Lung Cancer, 2015)
OBJECTIVES: Malignant mesothelioma (MM) is a highly aggressive tumor with poor prognosis. A major challenge is the development and application of early and highly reliable diagnostic marker(s). Serum biomarkers, such as 'soluble mesothelin-related proteins' (SMRPs), is the most studied and frequently used in MM. However, the low sensitivity of SMRPs for early MM limits its value; therefore, additional biomarkers are required. In this study, two epigenetically regulated markers in MM (microRNA-126, miR-126, and methylated thrombomodulin promoter, Met-TM) were combined with SMRPs and evaluated as a potential strategy to detect MM at an early stage. MATERIALS AND METHODS: A total of 188 subjects, including 45 MM patients, 99 asbestos-exposed subjects, and 44 healthy controls were prospectively enrolled, serum samples collected, and serum levels of SMRPs, miR-126 and Met-TM evaluated. Logistic regression analysis was performed to evaluate the diagnostic value of the three biomarkers. Using this approach, the performance of the '3-biomarker classifier' was tested by calculating the overall probability score of the MM and control samples, respectively, and the ROC curve was generated. RESULTS AND CONCLUSION: The combination of the three biomarkers was the best predictor to differentiate MM patients from asbestos-exposed subjects and healthy controls. The accuracy and cancer specificity was confirmed in a second validation cohort and lung cancer population. We propose that the combination of the two epigenetic biomarkers with SMRPs as a diagnosis for early MM overcomes the limitations of using SMRPs alone.

Comprehensive analysis of polymorphisms in the HLA-G 5' upstream regulatory and 3' untranslated regions in Brazilian patients with systemic lupus erythematosus. - Catamo, E; Addobbati, C; Segat, L; Sotero Fragoso, T; Tavares Dantas, A; de Ataíde Mariz, H; Ferreira da Rocha Junior, L; Branco PintoDuarte, A L; Coelho, A V C; de Moura, R R; Polesello, V; Crovella, S; et al. (Tissue Antigens, 2015)
This study aims to comprehensively analyze human leucocyte antigen (HLA)-G polymorphisms association with susceptibility to systemic lupus erythematosus (SLE) development and clinical manifestations. The HLA-G 5' upstream regulatory region (URR), 3' untranslated region (UTR) and a cytosine deletion at exon 3 (ΔC, HLA-G*0105N allele) were analyzed in 114 SLE patients and 128 healthy controls from North East Brazil. The +3003T>C (rs1707) C allele and the HG010101c extended HLA-G allele were significantly more frequent in SLE patients than healthy controls (+3003C allele frequency: 12% in SLE patients vs 6% in controls; odds ratio (OR), 2.10, 95% confidence interval (CI), 1.06-4.28, P = 0.026; HG010101c frequency: 11.8% in SLE patients and 6.3% in controls; OR, 2.14, 95% CI, 1.01-4.51, P = 0.046) and were associated with susceptibility for disease development. Other polymorphisms were associated with different clinical manifestations. Although HLA-G role in SLE disease is far from being elucidated yet, our association study results along with a systematic review and meta-analysis suggest that HLA-G might be able to slightly modulate the complex SLE phenotype (pooled OR, 1.14, 95% CI, 1.02-1.27, P = 0.021).

Connexin 26 variant carriers have a better gastrointestinal health: is this the heterozygote advantage? - Vuckovic, Dragana; Dallapiccola, Bruno; Franzè, Annamaria; Mauri, Lucia; Perrone, Maria Dolores; Gasparini, Paolo (Eur J Hum Genet, 2015)

Design, Synthesis, and Biological Characterization of Novel Mitochondria Targeted Dichloroacetate-Loaded Compounds with Antileukemic Activity. - Trapella, Claudio; Voltan, Rebecca; Melloni, Elisabetta; Tisato, Veronica; Celeghini, Claudio; Bianco, Sara; Fantinati, Anna; Salvadori, Severo; Guerrini, Remo; Secchiero, Paola; Zauli, Giorgio (J Med Chem, 2015)
The mitochondrial kinase inhibitor dichloroacetate (DCA) has recently received attention in oncology due to its ability to target glycolysis. However, DCA molecule exhibits poor bioavailability and cellular uptake with limited ability to reach its target mitochondria. To overcome these biases, we have synthesized novel DCA-loaded compounds. The selection of the most promising therapeutic molecule was evaluated by combining in vitro assays, to test the antitumoral potential on leukemic cells, and a preliminary characterization of the molecule stability in vivo, in mice. Among the newly synthesized compounds, we have selected the multiple DCA-loaded compound 10, characterized by a tertiary amine scaffold, because it exhibited enhanced (>30-fold) in vitro antitumor activity with respect to DCA and increased in vivo stability. On the basis of these results, we believe that compound 10 should be considered for further preclinical evaluations for the treatment of cancers and/or other diseases characterized by altered metabolic origin.

The diagnostic challenge of very early-onset enterocolitis in an infant with XIAP deficiency. - Girardelli, Martina; Arrigo, Serena; Barabino, Arrigo; Loganes, Claudia; Morreale, Giuseppe; Crovella, Sergio; Tommasini, Alberto; Bianco, Anna Monica (BMC Pediatr, 2015)
BACKGROUND: Aggressive course and resistance to treatments usually characterize very early onset inflammatory bowel disease (VEO-IBD). Some VEO-IBD cases are due to monogenic immune defects and can benefit from hematopoietic stem cell transplantation (HSCT). CASE PRESENTATION: We describe a Caucasian male baby who presented in the first months of life macrophage activation syndrome, followed by intractable colitis, recurrent episodes of fever and mild splenomegaly. After several immunological, genetic and clinical investigations, subsequently a therapeutic attempt with colectomy, analysis of VEO-IBD-associated genes, revealed a causative mutation in XIAP. The genetic diagnosis of a primary immune deficiency allowed curing the boy with hematopoietic stem cell transplantation. CONCLUSION: Our report, together with novel findings from recent literature, should contribute to increase awareness of monogenic immune defects as a cause of VEO-IBD. Comprehensive genetic analysis can allow a prompt diagnosis, resulting in the choice of effective treatments and sparing useless and damaging procedures.

Differential protein folding and chemical changes in lung tissues exposed to asbestos or particulates. - Pascolo, Lorella; Borelli, Violetta; Canzonieri, Vincenzo; Gianoncelli, Alessandra; Birarda, Giovanni; Bedolla, Diana E; Salomè, Murielle; Vaccari, Lisa; Calligaro, Carla; Cotte, Marine; Hesse, Bernhard; Luisi, Fernando; et al. (Sci Rep, 2015)
Environmental and occupational inhalants may induce a large number of pulmonary diseases, with asbestos exposure being the most risky. The mechanisms are clearly related to chemical composition and physical and surface properties of materials. A combination of X-ray fluorescence (μXRF) and Fourier Transform InfraRed (μFTIR) microscopy was used to chemically characterize and compare asbestos bodies versus environmental particulates (anthracosis) in lung tissues from asbestos exposed and control patients. μXRF analyses revealed heterogeneously aggregated particles in the anthracotic structures, containing mainly Si, K, Al and Fe. Both asbestos and particulates alter lung iron homeostasis, with a more marked effect in asbestos exposure. μFTIR analyses revealed abundant proteins on asbestos bodies but not on anthracotic particles. Most importantly, the analyses demonstrated that the asbestos coating proteins contain high levels of β-sheet structures. The occurrence of conformational changes in the proteic component of the asbestos coating provides new insights into long-term asbestos effects.

Directional dominance on stature and cognition in diverse human populations. - Joshi, Peter K; Esko, Tõnu; Mattsson, Hannele; Eklund, Niina; Gandin, Ilaria; Nutile, Teresa; Jackson, Anne U; Schurmann, Claudia; Smith, Albert V; Zhang, Weihua; Okada, Yukinori; Stančáková, Alena; et al. (Nature, 2015)
Homozygosity has long been associated with rare, often devastating, Mendelian disorders, and Darwin was one of the first to recognize that inbreeding reduces evolutionary fitness. However, the effect of the more distant parental relatedness that is common in modern human populations is less well understood. Genomic data now allow us to investigate the effects of homozygosity on traits of public health importance by observing contiguous homozygous segments (runs of homozygosity), which are inferred to be homozygous along their complete length. Given the low levels of genome-wide homozygosity prevalent in most human populations, information is required on very large numbers of people to provide sufficient power. Here we use runs of homozygosity to study 16 health-related quantitative traits in 354,224 individuals from 102 cohorts, and find statistically significant associations between summed runs of homozygosity and four complex traits: height, forced expiratory lung volume in one second, general cognitive ability and educational attainment (P < 1 × 10(-300), 2.1 × 10(-6), 2.5 × 10(-10) and 1.8 × 10(-10), respectively). In each case, increased homozygosity was associated with decreased trait value, equivalent to the offspring of first cousins being 1.2 cm shorter and having 10 months' less education. Similar effect sizes were found across four continental groups and populations with different degrees of genome-wide homozygosity, providing evidence that homozygosity, rather than confounding, directly contributes to phenotypic variance. Contrary to earlier reports in substantially smaller samples, no evidence was seen of an influence of genome-wide homozygosity on blood pressure and low density lipoprotein cholesterol, or ten other cardio-metabolic traits. Since directional dominance is predicted for traits under directional evolutionary selection, this study provides evidence that increased stature and cognitive function have been positively selected in human evolution, whereas many important risk factors for late-onset complex diseases may not have been.
Keywords: Biological Evolution; Blood Pressure; Body Height; Cholesterol, LDL; Cognition; Cohort Studies; Educational Status; Female; Forced Expiratory Volume; Genome, Human; Homozygote; Humans; Lung Volume Measurements; Male; Phenotype

Does defibrotide induce a delay to polymorphonuclear neutrophil engraftment after hematopoietic stem cell transplantation? Observation in a pediatric population. - Maximova, Natalia; Pizzol, Antonio; Giurici, Nagua; Granzotto, Marilena (Adv Ther, 2015)
INTRODUCTION: In recent years, defibrotide (DFT) has emerged as a promising therapy for veno-occlusive disease (VOD). The aim of this study was to investigate whether DFT prophylaxis affects neutrophil engraftment in patients undergoing hematopoietic stem cell transplantation (HSCT). METHODS: A cohort of 44 consecutive pediatric patients who underwent HSCT was retrospectively analyzed to see the role of DFT on engraftment. Patients were assigned into two groups based on the use or non-use of prophylaxis with DFT. RESULTS: The mean time to engraftment was statistically different between the two groups for both polymorphonuclear neutrophils (PMN) and white blood cells. CONCLUSION: Our study supports the hypothesis that prophylaxis with DFT for VOD leads to a delay to the engraftment of PMN in pediatric patients that underwent HSCT.

Effect of seminal leukocytes on in vitro fertilization and intracytoplasmic sperm injection outcomes. - Ricci, Giuseppe; Granzotto, Marilena; Luppi, Stefania; Giolo, Elena; Martinelli, Monica; Zito, Gabriella; Borelli, Massimo (Fertil Steril, 2015)
OBJECTIVE: To investigate the influence of seminal leukocytes on conventional IVF and intracytoplasmic sperm injection (ICSI) outcomes, using a flow cytometry method. DESIGN: Prospective study. SETTING: Tertiary infertility center and research institute. PATIENT(S): One hundred sixty-four couples undergoing conventional IVF or ICSI. INTERVENTION(S): Seminal leukocytes were counted by flow cytometry. MAIN OUTCOME MEASURE(S): Correlation between seminal leukocytes concentration and reproductive outcomes in IVF and ICSI cycles. RESULT(S): The median number of oocytes retrieved, the fertilization and cleavage rate, the median number and grade of embryos transferred, the median number of good-quality embryos transferred, and the median percentage of good-quality embryos from total embryos transferred, in leukocytospermic and non-leukocytospermic patients were not statistically different after either IVF or ICSI. Similarly, there were no significant differences between the two groups for implantation rate and clinical pregnancy rate. Multivariate logistic regression analysis showed that the reproductive outcomes were not influenced by adjustment for female age, infertility diagnosis, number of previous attempts, treatment protocol (GnRH agonist or antagonist), assisted reproduction procedure (IVF or ICSI), and leukocytospermia. By profiling the proper Poisson regression models, no leukocytospermia cut-off value was able to identify the subjects at risk for oocyte fertilization or embryo cleavage failure. CONCLUSION(S): Using a flow cytometry method, we demonstrated that leukocytospermia does not significantly influence IVF or ICSI outcomes. The same results were obtained by using lower or higher cut-off values for leukocytospermia (from 0.2 to 2 × 10(6)/mL).
Keywords: Adult; Female; Fertilization in Vitro; Flow Cytometry; Humans; Leukocytes; Male; Pregnancy; Pregnancy Rate; Prospective Studies; Semen; Sperm Injections, Intracytoplasmic

Efficacy of intravenous immunoglobulin therapy in giant cell hepatitis with autoimmune hemolytic anemia: A multicenter study. - Marsalli, Giulia; Nastasio, Silvia; Sciveres, Marco; Calvo, Pier Luigi; Ramenghi, Ugo; Gatti, Simona; Albano, Veronica; Lega, Sara; Ventura, Alessandro; Maggiore, Giuseppe (Clin Res Hepatol Gastroenterol, 2015)
BACKGROUND AND OBJECTIVE: Giant cell hepatitis with autoimmune hemolytic anemia (GCH-AHA) is a rare disease of infancy, of possible autoimmune mechanism with poor prognosis due to its scarce response to immunosuppressive drugs. The aim of this retrospective multicenter study was to evaluate the efficacy and safety of intravenous immunoglobulin (IVIg) treatment in inducing and maintaining remission of the liver disease, in patients with GCH-AHA. METHODS: Seven children with GCH-AHA, four newly diagnosed, and three in relapse, being treated with different therapies, received one to three IVIg infusions (0.5 to 2g/kg) in association with other immunosuppressive drugs. Subsequently five of them received monthly sequential IVIg infusions (mean 13.4, range 7-24). RESULTS: IVIg infusions as first-line therapy associated with prednisone and other immunosuppressive drugs significantly (P=0.04) reduced the aminotransferase activity in all patients and normalized prothombin activity in the only patient with severe liver dysfunction. Sequential monthly IVIg infusions determined a steroid-sparing effect and allowed a complete or partial remission in all patients, although with temporary efficacy, since relapse of the hemolytic anemia and/or of liver disease occurred in all patients. IVIg infusions were associated with mild side effects in two patients. CONCLUSIONS: IVIg infusion can be safely and effectively administered in patients with severe GCH-AHA at diagnosis, or in case of relapse, in association with other immunosuppressive drugs. Repeated IVIg infusions may help maintain remission, however, due to their temporary efficacy, they should not be routinely employed.

Failure of interferon-γ pre-treated mesenchymal stem cell treatment in a patient with Crohn's disease. - Taddio, Andrea; Tommasini, Alberto; Valencic, Erica; Biagi, Ettore; Decorti, Giuliana; De Iudicibus, Sara; Cuzzoni, Eva; Gaipa, Giuseppe; Badolato, Raffaela; Prandini, Alberto; Biondi, Andrea; Ventura, Alessandro (World J Gastroenterol, 2015)
Mesenchymal stem cells (MSC) are cells of stromal origin which exhibit unlimited self-renewal capacity and pluripotency in vitro. It has recently been observed that MSC may also exert a profound immunosuppressive and anti-inflammatory effect both in vitro and in vivo with consequent potential use in autoimmune disorders. We present the case of a patient suffering from childhood-onset, multidrug resistant and steroid-dependent Crohn's disease who underwent systemic infusions of MSC, which led to a temporary reduction in CCR4, CCR7 and CXCR4 expression by T-cells, and a temporary decrease in switched memory B-cells, In addition, following MSC infusion, lower doses of steroids were needed to inhibit proliferation of the patient's peripheral blood mononuclear cells. Despite these changes, no significant clinical benefit was observed, and the patient required rescue therapy with infliximab and subsequent autologous hematopoietic stem cell transplantation. The results of biological and in vitro observations after MSC use and the clinical effects of infusion are discussed, and a brief description is provided of previous data on MSC-based therapy in autoimmune disorders.

Functionalized synchrotron in-line phase-contrast computed tomography: a novel approach for simultaneous quantification of structural alterations and localization of barium-labelled alveolar macrophages within mouse lung samples. - Dullin, Christian; dal Monego, Simeone; Larsson, Emanuel; Mohammadi, Sara; Krenkel, Martin; Garrovo, Chiara; Biffi, Stefania; Lorenzon, Andrea; Markus, Andrea; Napp, Joanna; Salditt, Tim; Accardo, Agostino; et al. (J Synchrotron Radiat, 2015)
Functionalized computed tomography (CT) in combination with labelled cells is virtually non-existent due to the limited sensitivity of X-ray-absorption-based imaging, but would be highly desirable to realise cell tracking studies in entire organisms. In this study we applied in-line free propagation X-ray phase-contrast CT (XPCT) in an allergic asthma mouse model to assess structural changes as well as the biodistribution of barium-labelled macrophages in lung tissue. Alveolar macrophages that were barium-sulfate-loaded and fluorescent-labelled were instilled intratracheally into asthmatic and control mice. Mice were sacrificed after 24 h, lungs were kept in situ, inflated with air and scanned utilizing XPCT at the SYRMEP beamline (Elettra Synchrotron Light Source, Italy). Single-distance phase retrieval was used to generate data sets with ten times greater contrast-to-noise ratio than absorption-based CT (in our setup), thus allowing to depict and quantify structural hallmarks of asthmatic lungs such as reduced air volume, obstruction of airways and increased soft-tissue content. Furthermore, we found a higher concentration as well as a specific accumulation of the barium-labelled macrophages in asthmatic lung tissue. It is believe that XPCT will be beneficial in preclinical asthma research for both the assessment of therapeutic response as well as the analysis of the role of the recruitment of macrophages to inflammatory sites.
Keywords: Algorithms; Allergens; Animals; Asthma; Barium Sulfate; Cell Line, Transformed; Cell Movement; Contrast Media; Disease Models, Animal; Female; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Lung; Macrophages, Alveolar; Mice; Mice, Inbred BALB C; Microscopy, Fluorescence; Ovalbumin; Synchrotrons; Tomography, X-Ray Computed

Genetic analysis of Italian patients with congenital tufting enteropathy. - d'Apolito, Maria; Pisanelli, Daniela; Faletra, Flavio; Giardino, Ida; Gigante, Maddalena; Pettoello-Mantovani, Massimo; Goulet, Olivier; Gasparini, Paolo; Campanozzi, Angelo (World J Pediatr, 2015)
BACKGROUND: Congenital tufting enteropathy (CTE), an inherited autosomal recessive rare disease, is a severe diarrhea of infancy which is clinically characterized by absence of inflammation and presence of intestinal villous atrophy. Mutations in the EpCAM gene were identified to cause CTE. Recent cases of syndromic tufting enteropathy harboring the SPINT2 (19q13.2) mutation were described. METHODS: Four CTE Italian patients were clinically and immunohistochemically characterized. Direct DNA sequencing of EpCAM and SPINT2 genes was performed. RESULTS: All patients were of Italian origin. Three different mutations were detected (p.Asp219Metfs*15, Tyr186Phefs*6 and p.Ile146Asn) in the EpCAM gene; one of them is novel (p.Ile146Asn). Two patients (P1 and P2) showed compound heterozygosity revealing two mutations in separate alleles. A third patient (P3) was heterozygous for only one novel EpCAM missense mutation (p.Ile146Asn). In a syndromic patient (P4), no deleterious EpCAM mutation was found. Additional SPINT2 mutational analysis was performed. P4 showed a homozygous SPINT2 mutation (p.Y163C). No SPINT2 mutation was found in P3. CLDN7 was also evaluated as a candidate gene by mutational screening in P3 but no mutation was identified. CONCLUSIONS: This study presented a molecular characterization of CTE Italian patients, and identified three mutations in the EpCAM gene and one in the SPINT2 gene. One of EpCAM mutations was novel, therefore increasing the mutational spectrum of allelic variants of the EpCAM gene. Molecular analysis of the SPINT2 gene also allowed us to identify a SPINT2 substitution mutation (c.488A>G) recently found to be associated with syndromic CTE subjects.

Genetic evidence for an origin of the Armenians from Bronze Age mixing of multiple populations. - Haber, Marc; Mezzavilla, Massimo; Xue, Yali; Comas, David; Gasparini, Paolo; Zalloua, Pierre; Tyler-Smith, Chris (Eur J Hum Genet, 2015)
The Armenians are a culturally isolated population who historically inhabited a region in the Near East bounded by the Mediterranean and Black seas and the Caucasus, but remain under-represented in genetic studies and have a complex history including a major geographic displacement during World War I. Here, we analyse genome-wide variation in 173 Armenians and compare them with 78 other worldwide populations. We find that Armenians form a distinctive cluster linking the Near East, Europe, and the Caucasus. We show that Armenian diversity can be explained by several mixtures of Eurasian populations that occurred between ~3000 and ~2000 bce, a period characterized by major population migrations after the domestication of the horse, appearance of chariots, and the rise of advanced civilizations in the Near East. However, genetic signals of population mixture cease after ~1200 bce when Bronze Age civilizations in the Eastern Mediterranean world suddenly and violently collapsed. Armenians have since remained isolated and genetic structure within the population developed ~500 years ago when Armenia was divided between the Ottomans and the Safavid Empire in Iran. Finally, we show that Armenians have higher genetic affinity to Neolithic Europeans than other present-day Near Easterners, and that 29% of Armenian ancestry may originate from an ancestral population that is best represented by Neolithic Europeans.European Journal of Human Genetics advance online publication, 21 October 2015; doi:10.1038/ejhg.2015.206.

Genetic studies of body mass index yield new insights for obesity biology. - Locke, Adam E; Kahali, Bratati; Berndt, Sonja I; Justice, Anne E; Pers, Tune H; Day, Felix R; Powell, Corey; Vedantam, Sailaja; Buchkovich, Martin L; Yang, Jian; Croteau-Chonka, Damien C; Esko, Tõnu; et al. (Nature, 2015)
Obesity is heritable and predisposes to many diseases. To understand the genetic basis of obesity better, here we conduct a genome-wide association study and Metabochip meta-analysis of body mass index (BMI), a measure commonly used to define obesity and assess adiposity, in up to 339,224 individuals. This analysis identifies 97 BMI-associated loci (P < 5 × 10(-8)), 56 of which are novel. Five loci demonstrate clear evidence of several independent association signals, and many loci have significant effects on other metabolic phenotypes. The 97 loci account for ∼2.7% of BMI variation, and genome-wide estimates suggest that common variation accounts for >20% of BMI variation. Pathway analyses provide strong support for a role of the central nervous system in obesity susceptibility and implicate new genes and pathways, including those related to synaptic function, glutamate signalling, insulin secretion/action, energy metabolism, lipid biology and adipogenesis.
Keywords: Adipogenesis; Adiposity; Age Factors; Body Mass Index; Continental Population Groups; Energy Metabolism; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glutamic Acid; Humans; Insulin; Male; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Synapses

Genetic testing and genomic analysis: a debate on ethical, social and legal issues in the Arab world with a focus on Qatar. - El Shanti, Hatem; Chouchane, Lotfi; Badii, Ramin; Gallouzi, Imed Eddine; Gasparini, Paolo (J Transl Med, 2015)
In 2013 both Saudi Arabia and Qatar launched genome projects with the aim of providing information for better diagnosis, treatment and prevention of diseases and, ultimately to realize personalized medicine by sequencing hundred thousands samples. These population based genome activities raise a series of relevant ethical, legal and social issues general, related to the specific population structure as well as to the Islamic perspective on genomic analysis and genetic testing. To contribute to the debate, the Authors after reviewing the existing literature and taking advantage of their professional experience in the field and in the geographic area, discuss and provide their opinions. In particular, the Authors focus on the impact of consanguinity on population structure and disease frequency in the Arab world, on genetic testing and genomic analysis (i.e. technical aspects, impact, etc.) and on their regulations. A comparison between the Islamic perspective and the ethical, social and legal issues raised in other population contexts is also carried. In conclusion, this opinion article with an up-to-date contribution to the discussion on the relevance and impact of genomic analysis and genetic testing in the Arab world, might help in producing specific national guidelines on genetic testing and genomic analysis and help accelerate the implementation and roll out of genome projects in Muslim countries and more specifically in Qatar, and other countries of the Gulf.

Genetics of inflammatory bowel disease from multifactorial to monogenic forms. - Bianco, Anna Monica; Girardelli, Martina; Tommasini, Alberto (World J Gastroenterol, 2015)
Inflammatory bowel disease (IBD) is a group of chronic multifactorial disorders. According to a recent study, the number of IBD association loci is increased to 201, of which 37 and 27 loci contribute specifically to the development of Crohn's disease and ulcerative colitis respectively. Some IBD associated genes are involved in innate immunity, in the autophagy and in the inflammatory response such as NOD2, ATG16L1 and IL23R, while other are implicated in immune mediated disease (STAT3) and in susceptibility to mycobacterium infection (IL12B). In case of early onset of IBD (VEO-IBD) within the 6(th) year of age, the disease may be caused by mutations in genes responsible for severe monogenic disorders such as the primary immunodeficiency diseases. In this review we discuss how these monogenic disorders through different immune mechanisms can similarly be responsible of VEO-IBD phenotype. Moreover we would highlight how the identification of pathogenic genes by Next Generation Sequencing technologies can allow to obtain a rapid diagnosis and to apply specific therapies.

Genome sequencing elucidates Sardinian genetic architecture and augments association analyses for lipid and blood inflammatory markers. - Sidore, Carlo; Busonero, Fabio; Maschio, Andrea; Porcu, Eleonora; Naitza, Silvia; Zoledziewska, Magdalena; Mulas, Antonella; Pistis, Giorgio; Steri, Maristella; Danjou, Fabrice; Kwong, Alan; Ortega Del Vecchyo, Vicente Diego; et al. (Nat Genet, 2015)
We report ∼17.6 million genetic variants from whole-genome sequencing of 2,120 Sardinians; 22% are absent from previous sequencing-based compilations and are enriched for predicted functional consequences. Furthermore, ∼76,000 variants common in our sample (frequency >5%) are rare elsewhere (<0.5% in the 1000 Genomes Project). We assessed the impact of these variants on circulating lipid levels and five inflammatory biomarkers. We observe 14 signals, including 2 major new loci, for lipid levels and 19 signals, including 2 new loci, for inflammatory markers. The new associations would have been missed in analyses based on 1000 Genomes Project data, underlining the advantages of large-scale sequencing in this founder population.

Genome-wide association analysis on five isolated populations identifies variants of the HLA-DOA gene associated with white wine liking. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; Amin, Najaf; Sala, Cinzia; Karssen, Lennart C; van Duijn, Cornelia M; Toniolo, Daniela; Gasparini, Paolo (Eur J Hum Genet, 2015)
Wine is the most popular alcoholic beverage around the world and because of its importance in society has been widely studied. Understanding what drives its flavor has been a quest for decades but much is still unknown and will be determined at least in part by individual taste preferences. Recently studies in the genetics of taste have uncovered the role of different genes in the determination of food preferences giving new insight on its physiology. In this context we have performed a genome-wide association study on red and white wine liking using three isolated populations collected in Italy, and replicated our results on two additional populations coming from the Netherland and Central Asia for a total of 3885 samples. We have found a significant association (P=2.1 × 10(-8)) between white wine liking and rs9276975:C>T a polymorphism in the HLA-DOA gene encoding a non-canonical MHC II molecule, which regulates other MHC II molecules. The same association was also found with red wine liking (P=8.3 × 10(-6)). Sex-separated analysis have also revealed that the effect of HLA-DOA is twice as large in women as compared to men suggesting an interaction between this polymorphism and gender. Our results are one of the first examples of genome-wide association between liking of a commonly consumed food and gene variants. Moreover, our results suggest a role of the MHC system in the determination of food preferences opening new insight in this field in general.

Genome-wide association analysis on normal hearing function identifies PCDH20 and SLC28A3 as candidates for hearing function and loss. - Vuckovic, Dragana; Dawson, Sally; Scheffer, Deborah I; Rantanen, Taina; Morgan, Anna; Di Stazio, Mariateresa; Vozzi, Diego; Nutile, Teresa; Concas, Maria P; Biino, Ginevra; Nolan, Lisa; Bahl, Aileen; et al. (Hum Mol Genet, 2015)
Hearing loss and individual differences in normal hearing both have a substantial genetic basis. Although many new genes contributing to deafness have been identified, very little is known about genes/variants modulating the normal range of hearing ability. To fill this gap, we performed a two-stage meta-analysis on hearing thresholds (tested at 0.25, 0.5, 1, 2, 4, 8 kHz) and on pure-tone averages (low-, medium- and high-frequency thresholds grouped) in several isolated populations from Italy and Central Asia (total N = 2636). Here, we detected two genome-wide significant loci close to PCDH20 and SLC28A3 (top hits: rs78043697, P = 4.71E-10 and rs7032430, P = 2.39E-09, respectively). For both loci, we sought replication in two independent cohorts: B58C from the UK (N = 5892) and FITSA from Finland (N = 270). Both loci were successfully replicated at a nominal level of significance (P < 0.05). In order to confirm our quantitative findings, we carried out RT-PCR and reported RNA-Seq data, which showed that both genes are expressed in mouse inner ear, especially in hair cells, further suggesting them as good candidates for modulatory genes in the auditory system. Sequencing data revealed no functional variants in the coding region of PCDH20 or SLC28A3, suggesting that variation in regulatory sequences may affect expression. Overall, these results contribute to a better understanding of the complex mechanisms underlying human hearing function.

Germline mutations in ETV6 are associated with thrombocytopenia, red cell macrocytosis and predisposition to lymphoblastic leukemia. - Noetzli, Leila; Lo, Richard W; Lee-Sherick, Alisa B; Callaghan, Michael; Noris, Patrizia; Savoia, Anna; Rajpurkar, Madhvi; Jones, Kenneth; Gowan, Katherine; Balduini, Carlo L; Pecci, Alessandro; Gnan, Chiara; et al. (Nat Genet, 2015)
Some familial platelet disorders are associated with predisposition to leukemia, myelodysplastic syndrome (MDS) or dyserythropoietic anemia. We identified a family with autosomal dominant thrombocytopenia, high erythrocyte mean corpuscular volume (MCV) and two occurrences of B cell-precursor acute lymphoblastic leukemia (ALL). Whole-exome sequencing identified a heterozygous single-nucleotide change in ETV6 (ets variant 6), c.641C>T, encoding a p.Pro214Leu substitution in the central domain, segregating with thrombocytopenia and elevated MCV. A screen of 23 families with similar phenotypes identified 2 with ETV6 mutations. One family also had a mutation encoding p.Pro214Leu and one individual with ALL. The other family had a c.1252A>G transition producing a p.Arg418Gly substitution in the DNA-binding domain, with alternative splicing and exon skipping. Functional characterization of these mutations showed aberrant cellular localization of mutant and endogenous ETV6, decreased transcriptional repression and altered megakaryocyte maturation. Our findings underscore a key role for ETV6 in platelet formation and leukemia predisposition.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Erythrocytes, Abnormal; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Germ-Line Mutation; HEK293 Cells; Hematologic Diseases; Humans; Male; Mutation, Missense; Pedigree; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Proto-Oncogene Proteins c-ets; Repressor Proteins; Thrombocytopenia

The Global Burden of Cancer 2013. - Fitzmaurice, Christina; Dicker, Daniel; Pain, Amanda; Hamavid, Hannah; Moradi-Lakeh, Maziar; MacIntyre, Michael F; Allen, Christine; Hansen, Gillian; Woodbrook, Rachel; Wolfe, Charles; Hamadeh, Randah R; Moore, Ami; et al. (JAMA Oncol, 2015)
IMPORTANCE: Cancer is among the leading causes of death worldwide. Current estimates of cancer burden in individual countries and regions are necessary to inform local cancer control strategies. OBJECTIVE: To estimate mortality, incidence, years lived with disability (YLDs), years of life lost (YLLs), and disability-adjusted life-years (DALYs) for 28 cancers in 188 countries by sex from 1990 to 2013. EVIDENCE REVIEW: The general methodology of the Global Burden of Disease (GBD) 2013 study was used. Cancer registries were the source for cancer incidence data as well as mortality incidence (MI) ratios. Sources for cause of death data include vital registration system data, verbal autopsy studies, and other sources. The MI ratios were used to transform incidence data to mortality estimates and cause of death estimates to incidence estimates. Cancer prevalence was estimated using MI ratios as surrogates for survival data; YLDs were calculated by multiplying prevalence estimates with disability weights, which were derived from population-based surveys; YLLs were computed by multiplying the number of estimated cancer deaths at each age with a reference life expectancy; and DALYs were calculated as the sum of YLDs and YLLs. FINDINGS: In 2013 there were 14.9 million incident cancer cases, 8.2 million deaths, and 196.3 million DALYs. Prostate cancer was the leading cause for cancer incidence (1.4 million) for men and breast cancer for women (1.8 million). Tracheal, bronchus, and lung (TBL) cancer was the leading cause for cancer death in men and women, with 1.6 million deaths. For men, TBL cancer was the leading cause of DALYs (24.9 million). For women, breast cancer was the leading cause of DALYs (13.1 million). Age-standardized incidence rates (ASIRs) per 100 000 and age-standardized death rates (ASDRs) per 100 000 for both sexes in 2013 were higher in developing vs developed countries for stomach cancer (ASIR, 17 vs 14; ASDR, 15 vs 11), liver cancer (ASIR, 15 vs 7; ASDR, 16 vs 7), esophageal cancer (ASIR, 9 vs 4; ASDR, 9 vs 4), cervical cancer (ASIR, 8 vs 5; ASDR, 4 vs 2), lip and oral cavity cancer (ASIR, 7 vs 6; ASDR, 2 vs 2), and nasopharyngeal cancer (ASIR, 1.5 vs 0.4; ASDR, 1.2 vs 0.3). Between 1990 and 2013, ASIRs for all cancers combined (except nonmelanoma skin cancer and Kaposi sarcoma) increased by more than 10% in 113 countries and decreased by more than 10% in 12 of 188 countries. CONCLUSIONS AND RELEVANCE: Cancer poses a major threat to public health worldwide, and incidence rates have increased in most countries since 1990. The trend is a particular threat to developing nations with health systems that are ill-equipped to deal with complex and expensive cancer treatments. The annual update on the Global Burden of Cancer will provide all stakeholders with timely estimates to guide policy efforts in cancer prevention, screening, treatment, and palliation.

Global, regional, and national age-sex specific all-cause and cause-specific mortality for 240 causes of death, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. (Lancet, 2015)
BACKGROUND: Up-to-date evidence on levels and trends for age-sex-specific all-cause and cause-specific mortality is essential for the formation of global, regional, and national health policies. In the Global Burden of Disease Study 2013 (GBD 2013) we estimated yearly deaths for 188 countries between 1990, and 2013. We used the results to assess whether there is epidemiological convergence across countries. METHODS: We estimated age-sex-specific all-cause mortality using the GBD 2010 methods with some refinements to improve accuracy applied to an updated database of vital registration, survey, and census data. We generally estimated cause of death as in the GBD 2010. Key improvements included the addition of more recent vital registration data for 72 countries, an updated verbal autopsy literature review, two new and detailed data systems for China, and more detail for Mexico, UK, Turkey, and Russia. We improved statistical models for garbage code redistribution. We used six different modelling strategies across the 240 causes; cause of death ensemble modelling (CODEm) was the dominant strategy for causes with sufficient information. Trends for Alzheimer's disease and other dementias were informed by meta-regression of prevalence studies. For pathogen-specific causes of diarrhoea and lower respiratory infections we used a counterfactual approach. We computed two measures of convergence (inequality) across countries: the average relative difference across all pairs of countries (Gini coefficient) and the average absolute difference across countries. To summarise broad findings, we used multiple decrement life-tables to decompose probabilities of death from birth to exact age 15 years, from exact age 15 years to exact age 50 years, and from exact age 50 years to exact age 75 years, and life expectancy at birth into major causes. For all quantities reported, we computed 95% uncertainty intervals (UIs). We constrained cause-specific fractions within each age-sex-country-year group to sum to all-cause mortality based on draws from the uncertainty distributions. FINDINGS: Global life expectancy for both sexes increased from 65.3 years (UI 65.0-65.6) in 1990, to 71.5 years (UI 71.0-71.9) in 2013, while the number of deaths increased from 47.5 million (UI 46.8-48.2) to 54.9 million (UI 53.6-56.3) over the same interval. Global progress masked variation by age and sex: for children, average absolute differences between countries decreased but relative differences increased. For women aged 25-39 years and older than 75 years and for men aged 20-49 years and 65 years and older, both absolute and relative differences increased. Decomposition of global and regional life expectancy showed the prominent role of reductions in age-standardised death rates for cardiovascular diseases and cancers in high-income regions, and reductions in child deaths from diarrhoea, lower respiratory infections, and neonatal causes in low-income regions. HIV/AIDS reduced life expectancy in southern sub-Saharan Africa. For most communicable causes of death both numbers of deaths and age-standardised death rates fell whereas for most non-communicable causes, demographic shifts have increased numbers of deaths but decreased age-standardised death rates. Global deaths from injury increased by 10.7%, from 4.3 million deaths in 1990 to 4.8 million in 2013; but age-standardised rates declined over the same period by 21%. For some causes of more than 100,000 deaths per year in 2013, age-standardised death rates increased between 1990 and 2013, including HIV/AIDS, pancreatic cancer, atrial fibrillation and flutter, drug use disorders, diabetes, chronic kidney disease, and sickle-cell anaemias. Diarrhoeal diseases, lower respiratory infections, neonatal causes, and malaria are still in the top five causes of death in children younger than 5 years. The most important pathogens are rotavirus for diarrhoea and pneumococcus for lower respiratory infections. Country-specific probabilities of death over three phases of life were substantially varied between and within regions. INTERPRETATION: For most countries, the general pattern of reductions in age-sex specific mortality has been associated with a progressive shift towards a larger share of the remaining deaths caused by non-communicable disease and injuries. Assessing epidemiological convergence across countries depends on whether an absolute or relative measure of inequality is used. Nevertheless, age-standardised death rates for seven substantial causes are increasing, suggesting the potential for reversals in some countries. Important gaps exist in the empirical data for cause of death estimates for some countries; for example, no national data for India are available for the past decade. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cause of Death; Child; Child Mortality; Child, Preschool; Databases, Factual; Female; Global Health; Humans; Infant; Infant, Newborn; Life Expectancy; Life Tables; Male; Middle Aged; Models, Statistical; Mortality; Sex Distribution; Young Adult

Global, regional, and national comparative risk assessment of 79 behavioural, environmental and occupational, and metabolic risks or clusters of risks in 188 countries, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Forouzanfar, Mohammad H; Alexander, Lily; Anderson, H Ross; Bachman, Victoria F; Biryukov, Stan; Brauer, Michael; Burnett, Richard; Casey, Daniel; Coates, Matthew M; Cohen, Aaron; Delwiche, Kristen; Estep, Kara; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease, Injuries, and Risk Factor study 2013 (GBD 2013) is the first of a series of annual updates of the GBD. Risk factor quantification, particularly of modifiable risk factors, can help to identify emerging threats to population health and opportunities for prevention. The GBD 2013 provides a timely opportunity to update the comparative risk assessment with new data for exposure, relative risks, and evidence on the appropriate counterfactual risk distribution. METHODS: Attributable deaths, years of life lost, years lived with disability, and disability-adjusted life-years (DALYs) have been estimated for 79 risks or clusters of risks using the GBD 2010 methods. Risk-outcome pairs meeting explicit evidence criteria were assessed for 188 countries for the period 1990-2013 by age and sex using three inputs: risk exposure, relative risks, and the theoretical minimum risk exposure level (TMREL). Risks are organised into a hierarchy with blocks of behavioural, environmental and occupational, and metabolic risks at the first level of the hierarchy. The next level in the hierarchy includes nine clusters of related risks and two individual risks, with more detail provided at levels 3 and 4 of the hierarchy. Compared with GBD 2010, six new risk factors have been added: handwashing practices, occupational exposure to trichloroethylene, childhood wasting, childhood stunting, unsafe sex, and low glomerular filtration rate. For most risks, data for exposure were synthesised with a Bayesian meta-regression method, DisMod-MR 2.0, or spatial-temporal Gaussian process regression. Relative risks were based on meta-regressions of published cohort and intervention studies. Attributable burden for clusters of risks and all risks combined took into account evidence on the mediation of some risks such as high body-mass index (BMI) through other risks such as high systolic blood pressure and high cholesterol. FINDINGS: All risks combined account for 57·2% (95% uncertainty interval [UI] 55·8-58·5) of deaths and 41·6% (40·1-43·0) of DALYs. Risks quantified account for 87·9% (86·5-89·3) of cardiovascular disease DALYs, ranging to a low of 0% for neonatal disorders and neglected tropical diseases and malaria. In terms of global DALYs in 2013, six risks or clusters of risks each caused more than 5% of DALYs: dietary risks accounting for 11·3 million deaths and 241·4 million DALYs, high systolic blood pressure for 10·4 million deaths and 208·1 million DALYs, child and maternal malnutrition for 1·7 million deaths and 176·9 million DALYs, tobacco smoke for 6·1 million deaths and 143·5 million DALYs, air pollution for 5·5 million deaths and 141·5 million DALYs, and high BMI for 4·4 million deaths and 134·0 million DALYs. Risk factor patterns vary across regions and countries and with time. In sub-Saharan Africa, the leading risk factors are child and maternal malnutrition, unsafe sex, and unsafe water, sanitation, and handwashing. In women, in nearly all countries in the Americas, north Africa, and the Middle East, and in many other high-income countries, high BMI is the leading risk factor, with high systolic blood pressure as the leading risk in most of Central and Eastern Europe and south and east Asia. For men, high systolic blood pressure or tobacco use are the leading risks in nearly all high-income countries, in north Africa and the Middle East, Europe, and Asia. For men and women, unsafe sex is the leading risk in a corridor from Kenya to South Africa. INTERPRETATION: Behavioural, environmental and occupational, and metabolic risks can explain half of global mortality and more than one-third of global DALYs providing many opportunities for prevention. Of the larger risks, the attributable burden of high BMI has increased in the past 23 years. In view of the prominence of behavioural risk factors, behavioural and social science research on interventions for these risks should be strengthened. Many prevention and primary care policy options are available now to act on key risks. FUNDING: Bill & Melinda Gates Foundation.

Global, regional, and national disability-adjusted life years (DALYs) for 306 diseases and injuries and healthy life expectancy (HALE) for 188 countries, 1990-2013: quantifying the epidemiological transition. - Murray, Christopher J L; Barber, Ryan M; Foreman, Kyle J; Abbasoglu Ozgoren, Ayse; Abd-Allah, Foad; Abera, Semaw F; Aboyans, Victor; Abraham, Jerry P; Abubakar, Ibrahim; Abu-Raddad, Laith J; Abu-Rmeileh, Niveen M; Achoki, Tom; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease Study 2013 (GBD 2013) aims to bring together all available epidemiological data using a coherent measurement framework, standardised estimation methods, and transparent data sources to enable comparisons of health loss over time and across causes, age-sex groups, and countries. The GBD can be used to generate summary measures such as disability-adjusted life-years (DALYs) and healthy life expectancy (HALE) that make possible comparative assessments of broad epidemiological patterns across countries and time. These summary measures can also be used to quantify the component of variation in epidemiology that is related to sociodemographic development. METHODS: We used the published GBD 2013 data for age-specific mortality, years of life lost due to premature mortality (YLLs), and years lived with disability (YLDs) to calculate DALYs and HALE for 1990, 1995, 2000, 2005, 2010, and 2013 for 188 countries. We calculated HALE using the Sullivan method; 95% uncertainty intervals (UIs) represent uncertainty in age-specific death rates and YLDs per person for each country, age, sex, and year. We estimated DALYs for 306 causes for each country as the sum of YLLs and YLDs; 95% UIs represent uncertainty in YLL and YLD rates. We quantified patterns of the epidemiological transition with a composite indicator of sociodemographic status, which we constructed from income per person, average years of schooling after age 15 years, and the total fertility rate and mean age of the population. We applied hierarchical regression to DALY rates by cause across countries to decompose variance related to the sociodemographic status variable, country, and time. FINDINGS: Worldwide, from 1990 to 2013, life expectancy at birth rose by 6·2 years (95% UI 5·6-6·6), from 65·3 years (65·0-65·6) in 1990 to 71·5 years (71·0-71·9) in 2013, HALE at birth rose by 5·4 years (4·9-5·8), from 56·9 years (54·5-59·1) to 62·3 years (59·7-64·8), total DALYs fell by 3·6% (0·3-7·4), and age-standardised DALY rates per 100 000 people fell by 26·7% (24·6-29·1). For communicable, maternal, neonatal, and nutritional disorders, global DALY numbers, crude rates, and age-standardised rates have all declined between 1990 and 2013, whereas for non-communicable diseases, global DALYs have been increasing, DALY rates have remained nearly constant, and age-standardised DALY rates declined during the same period. From 2005 to 2013, the number of DALYs increased for most specific non-communicable diseases, including cardiovascular diseases and neoplasms, in addition to dengue, food-borne trematodes, and leishmaniasis; DALYs decreased for nearly all other causes. By 2013, the five leading causes of DALYs were ischaemic heart disease, lower respiratory infections, cerebrovascular disease, low back and neck pain, and road injuries. Sociodemographic status explained more than 50% of the variance between countries and over time for diarrhoea, lower respiratory infections, and other common infectious diseases; maternal disorders; neonatal disorders; nutritional deficiencies; other communicable, maternal, neonatal, and nutritional diseases; musculoskeletal disorders; and other non-communicable diseases. However, sociodemographic status explained less than 10% of the variance in DALY rates for cardiovascular diseases; chronic respiratory diseases; cirrhosis; diabetes, urogenital, blood, and endocrine diseases; unintentional injuries; and self-harm and interpersonal violence. Predictably, increased sociodemographic status was associated with a shift in burden from YLLs to YLDs, driven by declines in YLLs and increases in YLDs from musculoskeletal disorders, neurological disorders, and mental and substance use disorders. In most country-specific estimates, the increase in life expectancy was greater than that in HALE. Leading causes of DALYs are highly variable across countries. INTERPRETATION: Global health is improving. Population growth and ageing have driven up numbers of DALYs, but crude rates have remained relatively constant, showing that progress in health does not mean fewer demands on health systems. The notion of an epidemiological transition--in which increasing sociodemographic status brings structured change in disease burden--is useful, but there is tremendous variation in burden of disease that is not associated with sociodemographic status. This further underscores the need for country-specific assessments of DALYs and HALE to appropriately inform health policy decisions and attendant actions. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Aged; Chronic Disease; Communicable Diseases; Female; Global Health; Health Transition; Humans; Life Expectancy; Male; Middle Aged; Mortality, Premature; Quality-Adjusted Life Years; Socioeconomic Factors; Wounds and Injuries

Global, regional, and national incidence, prevalence, and years lived with disability for 301 acute and chronic diseases and injuries in 188 countries, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. (Lancet, 2015)
BACKGROUND: Up-to-date evidence about levels and trends in disease and injury incidence, prevalence, and years lived with disability (YLDs) is an essential input into global, regional, and national health policies. In the Global Burden of Disease Study 2013 (GBD 2013), we estimated these quantities for acute and chronic diseases and injuries for 188 countries between 1990 and 2013. METHODS: Estimates were calculated for disease and injury incidence, prevalence, and YLDs using GBD 2010 methods with some important refinements. Results for incidence of acute disorders and prevalence of chronic disorders are new additions to the analysis. Key improvements include expansion to the cause and sequelae list, updated systematic reviews, use of detailed injury codes, improvements to the Bayesian meta-regression method (DisMod-MR), and use of severity splits for various causes. An index of data representativeness, showing data availability, was calculated for each cause and impairment during three periods globally and at the country level for 2013. In total, 35 620 distinct sources of data were used and documented to calculated estimates for 301 diseases and injuries and 2337 sequelae. The comorbidity simulation provides estimates for the number of sequelae, concurrently, by individuals by country, year, age, and sex. Disability weights were updated with the addition of new population-based survey data from four countries. FINDINGS: Disease and injury were highly prevalent; only a small fraction of individuals had no sequelae. Comorbidity rose substantially with age and in absolute terms from 1990 to 2013. Incidence of acute sequelae were predominantly infectious diseases and short-term injuries, with over 2 billion cases of upper respiratory infections and diarrhoeal disease episodes in 2013, with the notable exception of tooth pain due to permanent caries with more than 200 million incident cases in 2013. Conversely, leading chronic sequelae were largely attributable to non-communicable diseases, with prevalence estimates for asymptomatic permanent caries and tension-type headache of 2·4 billion and 1·6 billion, respectively. The distribution of the number of sequelae in populations varied widely across regions, with an expected relation between age and disease prevalence. YLDs for both sexes increased from 537·6 million in 1990 to 764·8 million in 2013 due to population growth and ageing, whereas the age-standardised rate decreased little from 114·87 per 1000 people to 110·31 per 1000 people between 1990 and 2013. Leading causes of YLDs included low back pain and major depressive disorder among the top ten causes of YLDs in every country. YLD rates per person, by major cause groups, indicated the main drivers of increases were due to musculoskeletal, mental, and substance use disorders, neurological disorders, and chronic respiratory diseases; however HIV/AIDS was a notable driver of increasing YLDs in sub-Saharan Africa. Also, the proportion of disability-adjusted life years due to YLDs increased globally from 21·1% in 1990 to 31·2% in 2013. INTERPRETATION: Ageing of the world's population is leading to a substantial increase in the numbers of individuals with sequelae of diseases and injuries. Rates of YLDs are declining much more slowly than mortality rates. The non-fatal dimensions of disease and injury will require more and more attention from health systems. The transition to non-fatal outcomes as the dominant source of burden of disease is occurring rapidly outside of sub-Saharan Africa. Our results can guide future health initiatives through examination of epidemiological trends and a better understanding of variation across countries. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Acute Disease; Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Chronic Disease; Cost of Illness; Developed Countries; Developing Countries; Disabled Persons; Female; Global Health; Humans; Incidence; Infant; Infant, Newborn; Male; Middle Aged; Neglected Diseases; Prevalence; Residence Characteristics; Sex Distribution; Wounds and Injuries; Young Adult

Handlebar injury in children: The hidden danger. - Pederiva, Federica; Guida, Edoardo; Maschio, Massimo; Rigamonti, Waifro; Gregori, Massimo; Codrich, Daniela (Surgery, 2015)

Hysteroscopic chasing for endometrial cancer in a low-risk population: risks of overinvestigation. - Scrimin, Federica; Wiesenfeld, Uri; Galati, Emanuele F; Monasta, Lorenzo; Ricci, Giuseppe (Arch Gynecol Obstet, 2015)
PURPOSE: To evaluate the appropriateness of the indications for hysteroscopy done, in fertile and postmenopausal women, for the detection of endometrial cancer. METHODS: A retrospective analysis of 2673 consecutive women who underwent office hysteroscopy chasing for endometrial cancer between January 2012 and June 2014. According to their medical history only low-risk women entered the study. RESULTS: A total of 1070 patients entered the study. The main outcome measure was the appropriateness of the indications for hysteroscopy. Appropriateness was assessed on the basis of guidelines of scientific societies and histologic report. According to the algorithm developed for appropriateness, 44 % of procedures resulted in being inappropriate. In reproductive-aged women 57 % of hysteroscopies were inappropriate. In postmenopausal women inappropriate hysteroscopies were 45 %. In reproductive-aged women, the reasons for inappropriateness were: absence of abnormal uterine bleeding (AUB) or AUB without a trial of progestin therapy. In postmenopausal women, the reasons for inappropriateness were: ultrasound report of endometrial thickening or polyp without bleeding. CONCLUSIONS: Hysteroscopy is often recommended for inappropriate indications. More evidence is needed to identify the risks of overinvestigation, overdiagnosis, and related overtreatment and to better identify the threshold beyond which benefits are likely to outweigh harms.

Identification of a novel frameshift mutation in the EDAR gene causing autosomal dominant hypohidrotic ectodermal dysplasia. - Callea, M; Willoughby, C E; Nieminen, P; Di Stazio, M; Bellacchio, E; Giglio, S; Sani, I; Vinciguerra, A; Maglione, M; Tadini, G; Clarich, G (J Eur Acad Dermatol Venereol, 2015)

Impact of DEFB1 gene regulatory polymorphisms on hBD-1 salivary concentration. - Polesello, Vania; Zupin, Luisa; Di Lenarda, Roberto; Biasotto, Matteo; Ottaviani, Giulia; Gobbo, Margherita; Cecco, Luca; Alberi, Giulia; Pozzato, Gabriele; Crovella, Sergio; Segat, Ludovica (Arch Oral Biol, 2015)
OBJECTIVES: Human β-defensin 1 (hBD-1) is an antimicrobial peptide involved in epithelial defence of various tissues, also present in the saliva. Individual genetic variations within the DEFB1 gene, encoding for hBD-1, could influence gene expression and protein production. DESIGN: Three DEFB1 polymorphisms at 5' untranslated region (UTR), -52G > A (rs1799946), -44C > G (rs1800972) and -20G > A (rs11362), and two polymorphisms at DEFB1 3' UTR, c*5G > A (rs1047031) and c*87A > G (rs1800971), were analysed by direct sequencing and correlated with hDB-1 salivary concentration (tested with enzyme-linked immunosorbent assay (ELISA)) in 40 healthy subjects. RESULTS: Significant associations were found between individuals presenting different DEFB1 polymorphisms at positions -52 and -44 of the gene and hBD-1 salivary concentrations: -52 G/G carriers had higher levels of protein than G/A and A/A; -44C/G subjects showed a higher protein concentration than homozygous wild-type C/C. For the -20G > A, c*5G > A and c*87A > G polymorphisms, no statistically significant differences were found. Combined haplotype analysis confirmed the results obtained considering the single-nucleotide polymorphisms (SNPs) singularly. CONCLUSION: Polymorphisms in the DEFB1 gene influence hBD-1 production and, therefore, could modify the innate immune system responses and, consequently, the oral health.

Improved imputation of low-frequency and rare variants using the UK10K haplotype reference panel. - Huang, Jie; Howie, Bryan; McCarthy, Shane; Memari, Yasin; Walter, Klaudia; Min, Josine L; Danecek, Petr; Malerba, Giovanni; Trabetti, Elisabetta; Zheng, Hou-Feng; Gambaro, Giovanni; Richards, J Brent; et al. (Nat Commun, 2015)
Imputing genotypes from reference panels created by whole-genome sequencing (WGS) provides a cost-effective strategy for augmenting the single-nucleotide polymorphism (SNP) content of genome-wide arrays. The UK10K Cohorts project has generated a data set of 3,781 whole genomes sequenced at low depth (average 7x), aiming to exhaustively characterize genetic variation down to 0.1% minor allele frequency in the British population. Here we demonstrate the value of this resource for improving imputation accuracy at rare and low-frequency variants in both a UK and an Italian population. We show that large increases in imputation accuracy can be achieved by re-phasing WGS reference panels after initial genotype calling. We also present a method for combining WGS panels to improve variant coverage and downstream imputation accuracy, which we illustrate by integrating 7,562 WGS haplotypes from the UK10K project with 2,184 haplotypes from the 1000 Genomes Project. Finally, we introduce a novel approximation that maintains speed without sacrificing imputation accuracy for rare variants.

Increased rate of deleterious variants in long runs of homozygosity of an inbred population from Qatar. - Mezzavilla, Massimo; Vozzi, Diego; Badii, Ramin; Alkowari, Moza Khalifa; Abdulhadi, Khalid; Girotto, Giorgia; Gasparini, Paolo (Hum Hered, 2015)
OBJECTIVE: The aim of this study is to evaluate the fraction of putatively deleterious variants within genomic runs of homozygosity (ROH) regions in an inbred and selected cohort of Qatari individuals. METHODS: High-density SNP array analysis was performed in 36 individuals, and for 14 of them whole-exome sequencing (WES) was also carried out. RESULTS: In all individuals, regions characterized by a high (hotspot) or low (coldspot) degree of homozygosity in all the analysed individuals were mapped, and the most frequent hotspot regions were selected. WES data were exploited to identify the single nucleotide variations (SNVs) harboured by genes located within both regions in each individual. Evolutionary conservation-based algorithms were employed to predict the potential deleteriousness of SNVs. The amount of in silico predicted deleterious SNVs was significantly different (p < 0.05) between homozygosity hotspot and coldspot regions. CONCLUSION: Genes located within ROH hotspot regions contain a significant burden of predicted putatively deleterious variants compared to genes located outside these regions, suggesting inbreeding as a possible mechanism allowing an enrichment of putatively deleterious variants at the homozygous state.
Keywords: Cohort Studies; Consanguinity; Homozygote; Humans; Mutation; Polymorphism, Single Nucleotide; Qatar

Insights from Cardiac Mechanics after Three Decades from Successfully Repaired Aortic Coarctation. - Faganello, Giorgio; Fisicaro, Maurizio; Russo, Giulia; Iorio, Anita; Mazzone, Carmine; Grande, Eliana; Humar, Franco; Cherubini, Antonella; Pandullo, Claudio; Barbati, Giulia; Tarantini, Luigi; Benettoni, Alessandra; et al. (Congenit Heart Dis, 2015)
BACKGROUND AND AIMS: Patients who underwent a successful repair of the aortic coarctation show chronic hyperdynamic state and normal left ventricular (LV) geometry; however, there are few data regarding the LV systolic function in the long term. Accordingly, we assessed LV systolic mechanics and factors associated with LV systolic dysfunction (LVSD) in patients with repaired CoA. METHODS: Clinical and echocardiographic data from 19 repaired CoA were analyzed 28 ± 13 years after surgery. Stress-corrected midwall shortening (sc-MS) and mitral annular peak systolic velocity (S') were analyzed as indexes of LV circumferential and longitudinal systolic function, respectively. Echocardiographic data of CoA patients were compared with 19 patients matched for age and hypertension and 38 healthy controls. Sc-MS was considered impaired if <89%, S' if <8.5 cm/s (10th percentiles of healthy controls, respectively). RESULTS: There were no statistical differences between study groups in LV volumes, mass and geometry. LV ejection fraction and Sc-MS were similar in all groups, however, CoA group had a significantly lower peak S' in comparison with matched and healthy controls (7.1 ± 1.3, 10.3 ± 1.9, and 11.1 ± 1.5, respectively; all P < 0.001). Prevalence of longitudinal LVSD defined as low S' was 84% in CoA, 13% in matched, and 5% in healthy control group (all P<0.05). Multivariate logistic regression analysis revealed that low peak S' was independently related to higher E/E' ratio and the presence of CoA. CONCLUSIONS: Patients who underwent a successful repair of CoA commonly show asymptomatic longitudinal LVSD associated with worse LV diastolic function in the long-term follow-up.

Intranasal adminsitration of oxytocin in postnatal depression: implications for psychodynamic psychotherapy from a randomized double-blind pilot study. - Clarici, Andrea; Pellizzoni, Sandra; Guaschino, Secondo; Alberico, Salvatore; Bembich, Stefano; Giuliani, Rosella; Short, Antonia; Guarino, Giuseppina; Panksepp, Jaak (Front Psychol, 2015)
Oxytocin is a neuropeptide that is active in the central nervous system and is generally considered to be involved in prosocial behaviors and feelings. In light of its documented positive effect on maternal behavior, we designed a study to ascertain whether oxytocin exerts any therapeutic effects on depressive symptoms in women affected by maternal postnatal depression. A group of 16 mothers were recruited in a randomized double-blind study: the women agreed to take part in a brief course of psychoanalytic psychotherapy (12 sessions, once a week) while also being administered, during the 12-weeks period, a daily dose of intranasal oxytocin (or a placebo). The pre-treatment evaluation also included a personality assessment of the major primary-process emotional command systems described by Panksepp () and a semi-quantitative assessment by the therapist of the mother's depressive symptoms and of her personality. No significant effect on depressive symptomatology was found following the administration of oxytocin (as compared to a placebo) during the period of psychotherapy. Nevertheless, a personality trait evaluation of the mothers, conducted in our overall sample group, showed a decrease in the narcissistic trait only within the group who took oxytocin. The depressive (dysphoric) trait was in fact significantly affected by psychotherapy (this effect was only present in the placebo group so it may reflect a positive placebo effect enhancing the favorable influence of psychotherapy on depressive symptoms) but not in the presence of oxytocin. Therefore, the neuropeptide would appear to play some role in the modulation of cerebral functions involved in the self-centered (narcissistic) dimension of the suffering that can occur with postnatal depression. Based on these results, there was support for our hypothesis that what is generally defined as postnatal depression may include disturbances of narcissistic affective balance, and oxytocin supplementation can counteract that type of affective disturbance. The resulting improvements in well-being, reflected in better self-centering in post-partuent mothers, may in turn facilitate better interpersonal acceptance of (and interactions with) the child and thereby, improved recognition of the child's needs.

Laparoscopic orchiopexy: short term outcomes. Experience of a single centre. - Pederiva, F; Guida, E; Codrich, D; Scarpa, M G; Olenik, D; Schleef, J (Minerva Pediatr, 2015)
BACKGROUND: Increased infertility and smaller volume accompany undescended testis. Timing of orchiopexy is still a matter of debate. We evaluated the growth of nonpalpable testes after laparoscopic orchiopexy according to age at surgery, intraoperative findings and type of procedure. METHODS: Forty-one boys undergoing laparoscopy for nonpalpable testes were retrospectively reviewed and divided into two groups, ≤ 18 months and > 18 months, according to their age at surgery. RESULTS: At follow-up, 14 testes in the younger group had normal size, while 3 atrophied either after single (2) or two stage procedure (1). Similarly, in older boys 11 testes grew normally, while 5 atrophied after both procedures. CONCLUSION: Most of the nonpalpable testes grew normally after laparoscopic orchiopexy and the postoperative volume seemed independent from the surgical strategy. Both techniques led to a few cases of testicular hypotrophy In our experience, the age at surgery did not affect the outcome in terms of testicular growth.

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.

Life-threatening unilateral hearing impairments. Review of the literature on the association between inner ear malformations and meningitis. - Muzzi, E; Battelino, S; Gregori, M; Pellegrin, A; Orzan, E (Int J Pediatr Otorhinolaryngol, 2015)
BACKGROUND: Bacterial meningitis is a life threatening disease that can be triggered by a CSF leak through an inner ear malformation. Early identification of the specific type of cochleovestibular dysplasia and the associated risk of meningitis is of vital importance. OBJECTIVES: The objective of this review is to collect and discuss available data on the association between inner ear malformations and meningitis in children. METHODS: Electronic databases were crosschecked for obtaining relevant papers published in the last 20 years, and further cases were identified by hand searching through the references. Demographic data were extracted from full texts, together with information on the severity of hearing impairment, the type of inner ear anomaly, the site of cerebrospinal fluid leak, the number of recurrent meningitis episodes. RESULTS: Sixty-seven cases of meningitis related to inner ear malformation have been identified among 45 papers. Mean age at presentation is 3.60±3.00 (range 0.1-14) years. Average diagnostic delay from the first episode of meningitis is 3.44±3.41 (range 0.00-10.00) years. The number of meningitis episodes that occurred before the correct diagnosis and definitive surgical treatment is 3.27±1.81 (range 1.00-10.00). Unilateral hearing impairment affects 70% of patients. Six patients had normal hearing at presentation. Two children are dead from inner-ear-malformation-related meningitis among reviewed reports. CONCLUSION: A high number of paediatric patients carrying inner ear malformations, especially when associated with unilateral hearing impairment, could be at risk to develop recurrent bacterial meningitis. Universal newborn hearing screening programs should prompt a diagnostic work-up even in the case of unilateral hearing impairment, in order to prevent inner ear malformation-related meningitis.

Making patient centered care a reality: a survey of patient educational programs in Italian Cancer Research and Care Institutes. - Cipolat Mis, C; Truccolo, I; Ravaioli, V; Cocchi, S; Gangeri, L; Mosconi, P; Drace, C; Pomicino, L; Paradiso, A; De Paoli, P (BMC Health Serv Res, 2015)
BACKGROUND: Educational intervention represents an essential element of care for cancer patients; while several single institutions develop their own patient education (PE) programs on cancer, little information is available on the effective existence of PE programs at the level of research and care institutes. In Italy such institutes--Istituti di Ricovero e Cura a Carattere Scientifico--are appointed by the Ministry of Health, and 11 (Cancer Research & Care Istitute-CRCI) of the 48 are specific for cancer on the basis of specific requirements regarding cancer care, research and education. Therefore, they represent an ideal and homogeneous model through which to investigate PE policies and activities throughout the country. The objective of this study was to assess PE activities in Italian CRCI. METHODS: We carried out a survey on PE strategies and services through a questionnaire. Four key points were investigated: a) PE as a cancer care priority, b) activities that are routinely part of PE, c) real involvement of the patients, and d) involvement of healthcare workers in PE activities. RESULTS: Most CRCI (85%) completed the survey. All reported having ongoing PE activities, and 4 of the 11 considered PE an institutional activity. More than 90% of CRCI organize classes and prepare PE handouts, while other PE activities (e.g., Cancer Information Services, mutual support groups) are less frequently part of institutional PE programs. Patients are frequently involved in the organization and preparation of educational activities on the basis of their own needs. Various PE activities are carried out for caregivers in 8 (73%) out of 11 institutes. Finally, health care workers have an active role in the organization of PE programs, although nurses take part in these activities in only half of CRCI and pharmacists are seldom included. CONCLUSIONS: The information arising from our research constitutes a necessary framework to identify areas of development and to design new strategies and standards to disseminate the culture of PE. This may ultimately help and stimulate the establishment of institutional integrated PE programs, including policies and interventions that can benefit a significant proportion of cancer patients.

The mediating role of interpersonal conflict at work in the relationship between negative affectivity and biomarkers of stress. - Girardi, Damiano; Falco, Alessandra; De Carlo, Alessandro; Benevene, Paula; Comar, Manola; Tongiorgi, Enrico; Bartolucci, Giovanni Battista (J Behav Med, 2015)
This study examined the association between interpersonal conflict at work (ICW) and serum levels of three possible biomarkers of stress, namely the pro-inflammatory cytokines Interleukin 1 beta (IL-1β), Interleukin 12 (IL-12), and Interleukin 17 (IL-17). Additionally, this study investigated the role of negative affectivity (NA) in the relationship between ICW and the pro-inflammatory cytokines. Data from 121 employees in an Italian healthcare organization were analyzed using structural equation modeling. Results showed that ICW was positively associated with IL-1β, IL-12, and IL-17, after controlling for the effect of gender. Moreover, ICW completely mediated the relationship between NA and the pro-inflammatory cytokines IL-1β, IL-12, and IL-17. This mediating effect was significant after controlling for the effect of gender. Overall, this study suggests that work-related stress may be associated with biomarkers of inflammation, and that negative affectivity may influence the stress process affecting the exposure to psychosocial stressors.

Meta-analysis and time series modeling allow a systematic review of primary HIV-1 drug-resistant prevalence in Latin America and Caribbean. - Coelho, Antônio Victor Campos; De Moura, Ronald Rodrigues; da Silva, Ronaldo Celerino; Kamada, Anselmo Jiro; Guimarães, Rafael Lima; Brandão, Lucas André Cavalcanti; Coelho, Hemílio Fernandes Campos; Crovella, Sergio (Curr HIV Res, 2015)
Here we review the prevalence of HIV-1 primary drug resistance in Latin America and Caribbean using meta-analysis as well as time-series modeling. We also discuss whether there could be a drawback to HIV/AIDS programs due to drug resistance in Latin America and Caribbean in the next years. We observed that, although some studies report low or moderate primary drug resistance prevalence in Caribbean countries, this evidence needs to be updated. In other countries, such as Brazil and Argentina, the prevalence of drug resistance appears to be rising. Mutations conferring resistance against reverse transcriptase inhibitors were the most frequent in the analyzed populations (70% of all mutational events). HIV-1 subtype B was the most prevalent in Latin America and the Caribbean, although subtype C and B/F recombinants have significant contributions in Argentina and Brazil. Thus, we suggest that primary drug resistance in Latin America and the Caribbean could have been underestimated. Clinical monitoring should be improved to offer better therapy, reducing the risk for HIV-1 resistance emergence and spread, principally in vulnerable populations, such as men who have sex with men transmission group, sex workers and intravenous drug users.

Metal accumulation in the renal cortex of a pediatric patient with sickle cell disease: a case report and review of the literature. - Maximova, Natalia; Zanon, Davide; Pascolo, Lorella; Zennaro, Floriana; Gregori, Massimo; Grosso, Daniele; Sonzogni, Aurelio (J Pediatr Hematol Oncol, 2015)
BACKGROUND: Sickle cell disease (SCD) is a well-known multisystem illness characterized by vascular injury due to vasoocclusion and hemolysis, as well as infectious complications and iron overload, all of which contribute to high morbidity and mortality rates among children. In these patients, some authors have previously described iron cortical deposition in the kidney. We here report the first case in the literature of a girl affected by SCD showing an anomalous metal and rare element retention in the renal cortex. CASE PRESENTATION: A 10-year-old white girl affected by SCD underwent a routine magnetic resonance imaging investigation that evidenced a reduced signal intensity in the renal cortex, compatible with hemosiderin precipitation. Histologic and elemental analyses of the hepatic and the renal biotic samples, performed with inductively coupled plasma mass spectrometry, revealed that concomitant with the high iron deposition, toxic and potentially carcinogenic elements such as nickel, magnesium, rubidium, and gadolinuim were anomalously retained particularly in the kidney. CONCLUSIONS: The finding of rare and toxic elements in the kidney of SCD patients might be linked to the development of specific neoplastic transformations already described in this patient cohort. To be confirmed, our speculations need to be demonstrated in large sampling of patients.
Keywords: Anemia, Sickle Cell; Child; Female; Humans; Kidney Cortex; Metals; Spectrophotometry, Atomic

MID2 can substitute for MID1 and control exocytosis of lytic granules in cytotoxic T cells. - Boding, Lasse; Hansen, Ann K; Meroni, Germana; Levring, Trine B; Woetmann, Anders; Ødum, Niels; Bonefeld, Charlotte M; Geisler, Carsten (APMIS, 2015)
We have recently shown that the E3 ubiquitin ligase midline 1 (MID1) is upregulated in murine cytotoxic lymphocytes (CTL), where it controls exocytosis of lytic granules and the killing capacity. Accordingly, CTL from MID1 knock-out (MID1(-/-)) mice have a 25-30% reduction in exocytosis of lytic granules and cytotoxicity compared to CTL from wild-type (WT) mice. We wondered why the MID1 gene knock-out did not affect exocytosis and cytotoxicity more severely and speculated whether MID2, a close homologue of MID1, might partially compensate for the loss of MID1 in MID1(-/-) CTL. Here, we showed that MID2, like MID1, is upregulated in activated murine T cells. Furthermore, MID1(-/-) CTL upregulated MID2 two-twenty-fold stronger than CTL from WT mice, suggesting that MID2 might compensate for MID1. In agreement, transfection of MID2 into MID1(-/-) CTL completely rescued exocytosis of lytic granules in MID1(-/-) CTL, and vice versa, knock-down of MID2 inhibited exocytosis of lytic granules in both WT and MID1(-/-) CTL, demonstrating that both MID1 and MID2 play a central role in the regulation of granule exocytosis and that functional redundancy exists between MID1 and MID2 in CTL.
Keywords: Animals; Cytoplasmic Granules; Exocytosis; Interferon-gamma; Mice; Mice, Inbred C57BL; Mice, Knockout; Microtubule-Associated Proteins; Proteins; T-Lymphocytes, Cytotoxic; Transcription Factors; Up-Regulation

Modulation of genetic associations with serum urate levels by body-mass-index in humans. - Huffman, Jennifer E; Albrecht, Eva; Teumer, Alexander; Mangino, Massimo; Kapur, Karen; Johnson, Toby; Kutalik, Zoltán; Pirastu, Nicola; Pistis, Giorgio; Lopez, Lorna M; Haller, Toomas; Salo, Perttu; et al. (PLoS One, 2015)
We tested for interactions between body mass index (BMI) and common genetic variants affecting serum urate levels, genome-wide, in up to 42569 participants. Both stratified genome-wide association (GWAS) analyses, in lean, overweight and obese individuals, and regression-type analyses in a non BMI-stratified overall sample were performed. The former did not uncover any novel locus with a major main effect, but supported modulation of effects for some known and potentially new urate loci. The latter highlighted a SNP at RBFOX3 reaching genome-wide significant level (effect size 0.014, 95% CI 0.008-0.02, Pinter= 2.6 x 10-8). Two top loci in interaction term analyses, RBFOX3 and ERO1LB-EDARADD, also displayed suggestive differences in main effect size between the lean and obese strata. All top ranking loci for urate effect differences between BMI categories were novel and most had small magnitude but opposite direction effects between strata. They include the locus RBMS1-TANK (men, Pdifflean-overweight= 4.7 x 10-8), a region that has been associated with several obesity related traits, and TSPYL5 (men, Pdifflean-overweight= 9.1 x 10-8), regulating adipocytes-produced estradiol. The top-ranking known urate loci was ABCG2, the strongest known gout risk locus, with an effect halved in obese compared to lean men (Pdifflean-obese= 2 x 10-4). Finally, pathway analysis suggested a role for N-glycan biosynthesis as a prominent urate-associated pathway in the lean stratum. These results illustrate a potentially powerful way to monitor changes occurring in obesogenic environment.

Multicohort analysis of the maternal age effect on recombination. - Martin, Hilary C; Christ, Ryan; Hussin, Julie G; O'Connell, Jared; Gordon, Scott; Mbarek, Hamdi; Hottenga, Jouke-Jan; McAloney, Kerrie; Willemsen, Gonnecke; Gasparini, Paolo; Pirastu, Nicola; Montgomery, Grant W; et al. (Nat Commun, 2015)
Several studies have reported that the number of crossovers increases with maternal age in humans, but others have found the opposite. Resolving the true effect has implications for understanding the maternal age effect on aneuploidies. Here, we revisit this question in the largest sample to date using single nucleotide polymorphism (SNP)-chip data, comprising over 6,000 meioses from nine cohorts. We develop and fit a hierarchical model to allow for differences between cohorts and between mothers. We estimate that over 10 years, the expected number of maternal crossovers increases by 2.1% (95% credible interval (0.98%, 3.3%)). Our results are not consistent with the larger positive and negative effects previously reported in smaller cohorts. We see heterogeneity between cohorts that is likely due to chance effects in smaller samples, or possibly to confounders, emphasizing that care should be taken when interpreting results from any specific cohort about the effect of maternal age on recombination.

MultiMeta: an R package for meta-analyzing multi-phenotype genome-wide association studies. - Vuckovic, D; Gasparini, P; Soranzo, N; Iotchkova, V (Bioinformatics, 2015)
UNLABELLED: As new methods for multivariate analysis of genome wide association studies become available, it is important to be able to combine results from different cohorts in a meta-analysis. The R package MultiMeta provides an implementation of the inverse-variance-based method for meta-analysis, generalized to an n-dimensional setting. AVAILABILITY AND IMPLEMENTATION: The R package MultiMeta can be downloaded from CRAN. CONTACT: dragana.vuckovic@burlo.trieste.it; vi1@sanger.ac.uk SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.

Nasal irrigation with saline solution significantly improves oxygen saturation in infants with bronchiolitis. - Schreiber, Silvana; Ronfani, Luca; Ghirardo, Sergio; Minen, Federico; Taddio, Andrea; Jaber, Mohamad; Rizzello, Elisa; Barbi, Egidio (Acta Paediatr, 2015)
AIM: Published guidelines do not recommend nasal irrigation in bronchiolitis, but it is common practice in Italy, despite a lack of data on its benefits or adverse effects. This single-blind, multicentre, randomised controlled trial compared nasal irrigation using either isotonic 0.9% sodium chloride or hypertonic 3% sodium chloride with simple supportive care in infants with bronchiolitis. METHOD: We randomly assigned 133 Infants up one year of age, who were admitted to the emergency department with bronchiolitis and an oxygen saturation (SpO2) of between 88-94%, to the isotonic (n=47), hypertonic (n=44) or standard care (n=42) groups. Variations in SpO2 and the wheeze, air exchange, respiratory rate, muscle use (WARM) respiratory distress score were recorded at zero, five, 15, 20 and 50 minutes. RESULTS: Five minutes after the intervention, the median SpO2 value (95%) in the isotonic group was higher than both the hypertonic (94%) and the standard care (93%) groups. The differences between the isotonic and standard treatment groups were statistically significant at each time point, while the hypertonic group only reached significantly higher values after 50 minutes. However, the WARM score did not improve. CONCLUSION: A single nasal irrigation with saline solution significantly improved oxygen saturation in infants with bronchiolitis. This article is protected by copyright. All rights reserved.

A nationwide survey of PMM2-CDG in Italy: high frequency of a mild neurological variant associated with the L32R mutation. - Barone, Rita; Carrozzi, M; Parini, R; Battini, R; Martinelli, D; Elia, M; Spada, M; Lilliu, F; Ciana, G; Burlina, A; Leuzzi, V; Leoni, M; et al. (J Neurol, 2015)
PMM2-CDG (PMM2 gene mutations) is the most common congenital disorder of N-glycosylation. We conducted a nationwide survey to characterize the frequency, clinical features, glycosylation and genetic correlates in Italian patients with PMM2-CDG. Clinical information was obtained through a questionnaire filled in by the referral physicians including demographics, neurological and systemic features, neuroimaging data and genotype. Glycosylation analyses of serum transferrin were complemented by MALDI-Mass Spectrometry (MALDI-MS). Between 1996 and 2012, data on 37 Italian patients with PMM2-CDG were collected. All the patients with a severe phenotype were unable to walk unaided, 84 % had severe intellectual disability and 81 % microcephaly. Conversely, among 17 mildly affected patients 82 % had independent ambulation, 64 % had borderline to mild intellectual disability and 35 % microcephaly. Epilepsy and stroke-like events did not occur among patients with the mild phenotype. The rate and extent of systemic involvement were more pronounced in severely affected patients. The L32R misfolding mutation of the PMM2 gene occurred in 70 % of the patients with the mild phenotype and was associated with a less severe underglycosylation of serum Tf at MALDI-MS analyses. Despite their different disease severity, all patients had progressive (olivo)ponto-cerebellar atrophy that was the hallmark clinical feature for the diagnosis. A mild neurological phenotype of PMM2-CDG marked by preserved ambulatory ability and autonomy and associated with L32R mutation is particularly frequent in Italy. PMM2-CDG should be considered in patients with even mild developmental disability and/or unexplained progressive cerebellar atrophy.

New genetic loci link adipose and insulin biology to body fat distribution. - Shungin, Dmitry; Winkler, Thomas W; Croteau-Chonka, Damien C; Ferreira, Teresa; Locke, Adam E; Mägi, Reedik; Strawbridge, Rona J; Pers, Tune H; Fischer, Krista; Justice, Anne E; Workalemahu, Tsegaselassie; Wu, Joseph M W; et al. (Nature, 2015)
Body fat distribution is a heritable trait and a well-established predictor of adverse metabolic outcomes, independent of overall adiposity. To increase our understanding of the genetic basis of body fat distribution and its molecular links to cardiometabolic traits, here we conduct genome-wide association meta-analyses of traits related to waist and hip circumferences in up to 224,459 individuals. We identify 49 loci (33 new) associated with waist-to-hip ratio adjusted for body mass index (BMI), and an additional 19 loci newly associated with related waist and hip circumference measures (P < 5 × 10(-8)). In total, 20 of the 49 waist-to-hip ratio adjusted for BMI loci show significant sexual dimorphism, 19 of which display a stronger effect in women. The identified loci were enriched for genes expressed in adipose tissue and for putative regulatory elements in adipocytes. Pathway analyses implicated adipogenesis, angiogenesis, transcriptional regulation and insulin resistance as processes affecting fat distribution, providing insight into potential pathophysiological mechanisms.
Keywords: Adipocytes; Adipogenesis; Adipose Tissue; Age Factors; Body Fat Distribution; Body Mass Index; Continental Population Groups; Epigenesis, Genetic; Europe; Female; Genome, Human; Genome-Wide Association Study; Humans; Insulin; Insulin Resistance; Male; Models, Biological; Neovascularization, Physiologic; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Sex Characteristics; Transcription, Genetic; Waist-Hip Ratio

Next-generation sequencing and its initial applications for molecular diagnosis of systemic auto-inflammatory diseases. - Rusmini, Marta; Federici, Silvia; Caroli, Francesco; Grossi, Alice; Baldi, Maurizia; Obici, Laura; Insalaco, Antonella; Tommasini, Alberto; Caorsi, Roberta; Gallo, Eleonora; Olivieri, Alma Nunzia; Marzano, AngeloValerio; et al. (Ann Rheum Dis, 2015)
OBJECTIVES: Systemic auto-inflammatory disorders (SAIDs) are a heterogeneous group of monogenic diseases sharing a primary dysfunction of the innate immune system. More than 50% of patients with SAID does not show any mutation at gene(s) tested because of lack of precise clinical classification criteria and/or incomplete gene screening. To improve the molecular diagnosis and genotype interpretation of SAIDs, we undertook the development of a next-generation sequencing (NGS)-based protocol designed to simultaneous screening of 10 genes. METHODS: Fifty patients with SAID, already genotyped for the respective causative gene(s), were massively sequenced for the coding portions of MEFV, MVK, TNFRSF1A, NLRP3, NLRP12, NOD2, PSTPIP1, IL1RN, LPIN2 and PSMB8. Three different bioinformatic pipelines (Ion Reporter, CLC Bio Genomics Workbench, GATK-based in-house workflow) were compared. RESULTS: Once resulting variants were compared with the expected mutation list, no workflow turned out to be able to detect all the 79 variants known in the 50 DNAs. Additional variants were also detected, validated by Sanger sequencing and compared to assess true and false positive detection rates of the three workflows. Finally, the overall clinical picture of 34 patients was re-evaluated in the light of the new mutations found. CONCLUSIONS: The present gene panel has resulted suitable for molecular diagnosis of SAIDs. Moreover, genotype-phenotype correlation has confirmed that the interpretation of NGS data in patients with an undefined inflammatory phenotype is remarkably difficult, thus supporting the need of evidence-based and validated clinical criteria to be used concurrently with the genetic analysis for the final diagnosis and classification of patients with SAIDs.

Is "option B+" also being adopted in pregnant women in high-income countries? Temporal trends from a national study in Italy. - Floridia, Marco; Guaraldi, Giovanni; Ravizza, Marina; Tibaldi, Cecilia; Pinnetti, Carmela; Maccabruni, Anna; Molinari, Atim; Liuzzi, Giuseppina; Alberico, Salvatore; Meloni, Alessandra; Rizzi, Laura; Dalzero, Serena; et al. (Clin Infect Dis, 2015)
Keywords: Anti-Retroviral Agents; Antiretroviral Therapy, Highly Active; Developed Countries; Female; HIV Infections; Humans; Infant, Newborn; Italy; Patient Acceptance of Health Care; Pregnancy; Pregnancy Complications, Infectious

Pain activates a defined area of the somatosensory and motor cortex in newborn infants. - Bembich, Stefano; Brovedani, Pierpaolo; Cont, Gabriele; Travan, Laura; Grassi, Veronica; Demarini, Sergio (Acta Paediatr, 2015)

Patients' Induced Pluripotent Stem Cells to Model Drug Induced Adverse Events: A Role in Predicting Thiopurine Induced Pancreatitis? - Stocco, Gabriele; Lanzi, Gaetana; Yue, Fengming; Giliani, Silvia; Sasaki, Katsunori; Tommasini, Alberto; Pelin, Marco; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana (Curr Drug Metab, 2015)
Induced pluripotent stem cells (iPSC) can be produced from adult cells by transfecting them with a definite set of pluripotency-associated genes. Under adequate growth conditions and stimulation iPSC can differentiate to almost every somatic lineage in the body. Patients' derived iPSC are an innovative model to study mechanisms of adverse drug reactions in individual patients and in cell types that cannot be easily obtained from human subjects. Proof-of concept studies with known toxicants have been performed for liver, cardiovascular and central nervous system cells: neurons obtained from iPSC have been used to elucidate the mechanism of chemotherapy-induced peripheral neuropathy by evaluating the effects of neurotoxic drugs such as vincristine. However, no study has been performed yet on pancreatic tissue and drug induced pancreatitis. Thiopurines (azathioprine and mercaptopurine) are immunosuppressive antimetabolite drugs, commonly used to treat Crohn's disease. About 5% of Crohn's disease patients treated with thiopurines develop pancreatitis, a severe idiosyncratic adverse event; these patients have to stop thiopurine administration and may require medical treatment, with significant personal and social costs. Molecular mechanism of thiopurine induced pancreatitis (TIP) is currently unknown and no fully validated biomarker is available to assist clinicians in preventing this adverse event. Hence, in this review we have reflected upon the probable research applications of exocrine pancreatic cells generated from patient specific iPS cells. Such pancreatic cells can provide excellent insights into the molecular mechanism of TIP. In particular three hypotheses on the mechanism of TIP could be explored: drug biotransformation, innate immunity and adaptative immunity.

The p.Cys169Tyr variant of connexin 26 is not a polymorphism. - Zonta, Francesco; Girotto, Giorgia; Buratto, Damiano; Crispino, Giulia; Morgan, Anna; Abdulhadi, Khalid; Alkowari, Moza; Badii, Ramin; Gasparini, Paolo; Mammano, Fabio (Hum Mol Genet, 2015)
Mutations in the GJB2 gene, which encodes the gap junction protein connexin 26 (Cx26), are the primary cause of hereditary prelingual hearing impairment. Here, the p.Cys169Tyr missense mutation of Cx26 (Cx26C169Y), previously classified as a polymorphism, has been identified as causative of severe hearing loss in two Qatari families. We have analyzed the effect of this mutation using a combination of confocal immunofluorescence microscopy and molecular dynamics simulations. At the cellular level, our results show that the mutant protein fails to form junctional channels in HeLa transfectants despite being correctly targeted to the plasma membrane. At the molecular level, this effect can be accounted for by disruption of the disulfide bridge that Cys169 forms with Cys64 in the wild-type structure (Cx26WT). The lack of the disulfide bridge in the Cx26C169Y protein causes a spatial rearrangement of two important residues, Asn176 and Thr177. In the Cx26WT protein, these residues play a crucial role in the intra-molecular interactions that permit the formation of an intercellular channel by the head-to-head docking of two opposing hemichannels resident in the plasma membrane of adjacent cells. Our results elucidate the molecular pathogenesis of hereditary hearing loss due to the connexin mutation and facilitate the understanding of its role in both healthy and affected individuals.
Keywords: Alleles; Amino Acid Substitution; Cell Line; Connexins; Female; Gap Junctions; Gene Expression; Genotype; Hearing Loss; Humans; Immunohistochemistry; Male; Models, Molecular; Mutation, Missense; Pedigree; Polymorphism, Genetic; Protein Conformation; Protein Interaction Domains and Motifs; Transfection

Phenotypic and genetic characterization of a family carrying two Xq21.1-21.3 interstitial deletions associated with syndromic hearing loss. - Iossa, Sandra; Costa, Valerio; Corvino, Virginia; Auletta, Gennaro; Barruffo, Luigi; Cappellani, Stefania; Ceglia, Carlo; Cennamo, Giovanni; d'Adamo, Adamo Pio; D'Amico, Alessandra; Di Paolo, Nilde; Forte, Raimondo; et al. (Mol Cytogenet, 2015)
BACKGROUND: Sensorineural hearing impairment is a common pathological manifestation in patients affected by X-linked intellectual disability. A few cases of interstitial deletions at Xq21 with several different phenotypic characteristics have been described, but to date, a complete molecular characterization of the deletions harboring disease-causing genes is still missing. Thus, the aim of this study is to realize a detailed clinical and molecular analysis of a family affected by syndromic X-linked hearing loss with intellectual disability. RESULTS: Clinical analyses revealed a very complex phenotype that included inner ear malformations, vestibular problems, choroideremia and hypotonia with a peculiar pattern of phenotypic variability. Genomic analysis revealed, for the first time, the presence of two close interstitial deletions in the Xq21.1-21.3, harboring 11 protein coding, 9 non-coding genes and 19 pseudogenes. Among these, 3 protein coding genes have already been associated with X-linked hearing loss, intellectual disability and choroideremia. CONCLUSIONS: In this study we highlighted the presence of peculiar genotypic and phenotypic details in a family affected by syndromic X-linked hearing loss with intellectual disability. We identified two, previously unreported, Xq21.1-21.3 interstitial deletions. The two rearrangements, containing several genes, segregate with the clinical features, suggesting their role in the pathogenicity. However, not all the observed phenotypic features can be clearly associated with the known genes thus, further study is necessary to determine regions involved.

Polyclonal gammopathy after BKV infection in HSCT recipient: a novel trigger for plasma cells replication? - Maximova, Natalia; Pizzol, Antonio; Sonzogni, Aurelio; Gregori, Massimo; Granzotto, Marilena; Tamaro, Paolo (Virol J, 2015)
BACKGROUND: BK polyomavirus infects most of the general population. However, its clinical manifestations are almost exclusively seen in immunocompromised patients, particularly in kidney and hematopoietic stem cell transplantation recipients. CASE PRESENTATION: A 15-y-old female suffering from common B-cell acute lymphoblastic leukaemia underwent hematopoietic stem cell transplantation. The patient had reactivation of BKPyV infection and developed an haemorrhagic cystitis. Three months after transplant, BKPyV viremia and viruria increased and she developed a severe nephropathy associated to a polyclonal gammopathy with high levels of isolated IgM. CONCLUSION: This case report describes a rare and unexpected polyclonal gammopathy developed during a polyomavirus-associated nephropathy confirmed by immunohistochemical and laboratory analyses.

Polymorphisms in sweet taste genes (TAS1R2 and GLUT2), sweet liking, and dental caries prevalence in an adult Italian population. - Robino, Antonietta; Bevilacqua, Lorenzo; Pirastu, Nicola; Situlin, Roberta; Di Lenarda, Roberto; Gasparini, Paolo; Navarra, Chiara Ottavia (Genes Nutr, 2015)
The aim of the study was to assess the relationship between sweet taste genes and dental caries prevalence in a large sample of adults. In addition, the association between sweet liking and sugar intake with dental caries was investigated. Caries was measured by the decayed, missing, filled teeth (DMFT) index in 647 Caucasian subjects (285 males and 362 females, aged 18-65 years), coming from six villages in northeastern Italy. Sweet liking was assessed using a 9-point scale, and the mean of the liking given by each individual to specific sweet food and beverages was used to create a sweet liking score. Simple sugar consumption was estimated by a dietary history interview, considering both added sugars and sugar present naturally in foods. Our study confirmed that polymorphisms in TAS1R2 and GLUT2 genes are related to DMFT index. In particular, GG homozygous individuals for rs3935570 in TAS1R2 gene (p value = 0.0117) and GG homozygous individuals for rs1499821 in GLUT2 gene (p value = 0.0273) showed higher DMFT levels compared to both heterozygous and homozygous for the alternative allele. Furthermore, while the relationship sugar intake-DMFT did not achieve statistical significance (p value = 0.075), a significant association was identified between sweet liking and DMFT (p value = 0.004), independent of other variables. Our study showed that sweet taste genetic factors contribute to caries prevalence and highlighted the role of sweet liking as a predictor of caries risk. Therefore, these results may open new perspectives for individual risk identification and implementation of target preventive strategies, such as identifying high-risk patients before caries development.

Population genetic differentiation of height and body mass index across Europe. - Robinson, Matthew R; Hemani, Gibran; Medina-Gomez, Carolina; Mezzavilla, Massimo; Esko, Tõnu; Shakhbazov, Konstantin; Powell, Joseph E; Vinkhuyzen, Anna; Berndt, Sonja I; Gustafsson, Stefan; Justice, Anne E; Kahali, Bratati; et al. (Nat Genet, 2015)
Across-nation differences in the mean values for complex traits are common, but the reasons for these differences are unknown. Here we find that many independent loci contribute to population genetic differences in height and body mass index (BMI) in 9,416 individuals across 14 European countries. Using discovery data on over 250,000 individuals and unbiased effect size estimates from 17,500 sibling pairs, we estimate that 24% (95% credible interval (CI) = 9%, 41%) and 8% (95% CI = 4%, 16%) of the captured additive genetic variance for height and BMI, respectively, reflect population genetic differences. Population genetic divergence differed significantly from that in a null model (height, P < 3.94 × 10(-8); BMI, P < 5.95 × 10(-4)), and we find an among-population genetic correlation for tall and slender individuals (r = -0.80, 95% CI = -0.95, -0.60), consistent with correlated selection for both phenotypes. Observed differences in height among populations reflected the predicted genetic means (r = 0.51; P < 0.001), but environmental differences across Europe masked genetic differentiation for BMI (P < 0.58).

Positron emission tomography-laparoscopy based method in the prediction of complete cytoreduction in platinum-sensitive recurrent ovarian cancer. - Fanfani, Francesco; Monterossi, Giorgia; Fagotti, Anna; Gallotta, Valerio; Costantini, Barbara; Vizzielli, Giuseppe; Petrillo, Marco; Carbone, Maria Vittoria; Scambia, Giovanni (Ann Surg Oncol, 2015)
BACKGROUND: This study was designed to evaluate the positron emission tomography-laparoscopy-based method in the prediction of complete/optimal cytoreduction in platinum sensitive recurrent epithelial ovarian cancer patients. METHODS: We analysed 223 consecutive recurrent epithelial ovarian cancer patients. Inclusion criteria were absence of extra-abdominal disease and Eastern Cooperative Oncology Group Performance Status ≤2. Complete and optimal secondary cytoreduction are defined as macroscopic absence or less than 1 cm of residual tumor at the end of surgery. RESULTS: Laparoscopy was feasible in 210 of 223 patients (94.2 %). Laparoscopy stated 127 (60.5 %) possible cytoreductions and 83 (39.5 %) systemic chemotherapies. In the same population, AGO score evaluation avowed 150 possible cytoreduction (71.5 %) and 60 unresectable women (28.5 %). Overall, 115 of 210 patients (54.7 %) underwent successful secondary cytoreduction: complete and optimal cytoreduction was obtained in 103 (89.5 %) and 12 (10.5 %) patients, respectively. Laparoscopy obtained a positive predictive value of 91.3 %. Laparoscopy recovered to secondary cytoreduction 13 of 60 patients (21.7 %) deemed as not resectable according to AGO score. Forty-eight of 150 AGO score positive patients (32 %) were judged nonresectable by laparoscopy. CONCLUSIONS: This study confirmed that laparoscopy could be effective for the selection of platinum-sensitive recurrent epithelial ovarian cancer patients suitable for complete cytoreduction.
Keywords: Adult; Aged; Algorithms; Cytoreduction Surgical Procedures; Female; Humans; Laparoscopy; Middle Aged; Neoplasm Recurrence, Local; Neoplasm Staging; Neoplasms, Glandular and Epithelial; Ovarian Neoplasms; Positron-Emission Tomography; Tomography, X-Ray Computed

PRE- AND POSTNATAL MODIFICATIONS IN PARENTAL MENTAL REPRESENTATIONS IN THREE CASES OF FETAL GASTROSCHISIS DIAGNOSED DURING PREGNANCY. - Tripani, Antonella; Pellizzoni, Sandra; Giuliani, Rosella; Bembich, Stefano; Clarici, Andrea; Lonciari, Isabella; Ammaniti, Massimo (Infant Ment Health J, 2015)
The aim of this study was to identify possible effects of gastroschisis on parents' intrapsychic dynamics by applying an observational clinical approach. More specifically, we intend to (a) evaluate the representational style of parents informed about the diagnosis of fetal gastroschisis during pregnancy using the Interview of Maternal Representations During Pregnancy and the Interview of Paternal Representations During Pregnancy (M. Ammaniti, C. Candelori, M. Pola, & R. Tambelli, ) and (b) observe whether the baby's birth influences the parents' representational styles through the application of the same tools (the Interview of Maternal Representations After the Birth, M. Ammaniti & R. Tambelli, , and the Interview of Paternal Representations After the Birth, M. Ammaniti & R. Tambelli, ), adapted to the postnatal period. During the prenatal period, all parents showed a restricted/disinvested style. Three parents-one mother and two fathers-changed their styles from restricted/disinvested to integrated between pregnancy and Month 6 after the birth of their child. Clinical data from the interviews and observations are discussed in an attempt at better defining intrapsychic dynamics of parents after a diagnosis of gastroschisis.

PSIP1/LEDGF: a new gene likely involved in sensorineural progressive hearing loss. - Girotto, Giorgia; Scheffer, Deborah I; Morgan, Anna; Vozzi, Diego; Rubinato, Elisa; Di Stazio, Mariateresa; Muzzi, Enrico; Pensiero, Stefano; Giersch, Anne B; Corey, David P; Gasparini, Paolo (Sci Rep, 2015)
Hereditary Hearing Loss (HHL) is an extremely heterogeneous disorder. Approximately 30 out of 80 known HHL genes are associated with autosomal dominant forms. Here, we identified PSIP1/LEDGF (isoform p75) as a novel strong candidate gene involved in dominant HHL. Using exome sequencing we found a frameshift deletion (c.1554_1555del leading to p.E518Dfs*2) in an Italian pedigree affected by sensorineural mild-to-moderate HHL but also showing a variable eye phenotype (i.e. uveitis, optic neuropathy). This deletion led to a premature stop codon (p.T519X) with truncation of the last 12 amino acids. PSIP1 was recently described as a transcriptional co-activator regulated by miR-135b in vestibular hair cells of the mouse inner ear as well as a possible protector against photoreceptor degeneration. Here, we demonstrate that it is ubiquitously expressed in the mouse inner ear. The PSIP1 mutation is associated with a peculiar audiometric slope toward the high frequencies. These findings indicate that PSIP1 likely plays an important role in HHL.

A rapid screening of ancestry for genetic association studies in an admixed population from Pernambuco, Brazil. - Coelho, A V C; Moura, R R; Cavalcanti, C A J; Guimarães, R L; Sandrin-Garcia, P; Crovella, S; Brandão, L A C (Genet Mol Res, 2015)
Genetic association studies determine how genes influence traits. However, non-detected population substructure may bias the analysis, resulting in spurious results. One method to detect substructure is to genotype ancestry informative markers (AIMs) besides the candidate variants, quantifying how much ancestral populations contribute to the samples' genetic background. The present study aimed to use a minimum quantity of markers, while retaining full potential to estimate ancestries. We tested the feasibility of a subset of the 12 most informative markers from a previously established study to estimate influence from three ancestral populations: European, African and Amerindian. The results showed that in a sample with a diverse ethnicity (N = 822) derived from 1000 Genomes database, the 12 AIMs had the same capacity to estimate ancestries when compared to the original set of 128 AIMs, since estimates from the two panels were closely correlated. Thus, these 12 SNPs were used to estimate ancestry in a new sample (N = 192) from an admixed population in Recife, Northeast Brazil. The ancestry estimates from Recife subjects were in accordance with previous studies, showing that Northeastern Brazilian populations show great influence from European ancestry (59.7%), followed by African (23.0%) and Amerindian (17.3%) ancestries. Ethnicity self-classification according to skin-color was confirmed to be a poor indicator of population substructure in Brazilians, since ancestry estimates overlapped between classifications. Thus, our streamlined panel of 12 markers may substitute panels with more markers, while retaining the capacity to control for population substructure and admixture, thereby reducing sample processing time.

Rare coding variants and X-linked loci associated with age at menarche. - Lunetta, Kathryn L; Day, Felix R; Sulem, Patrick; Ruth, Katherine S; Tung, Joyce Y; Hinds, David A; Esko, Tõnu; Elks, Cathy E; Altmaier, Elisabeth; He, Chunyan; Huffman, Jennifer E; Mihailov, Evelin; et al. (Nat Commun, 2015)
More than 100 loci have been identified for age at menarche by genome-wide association studies; however, collectively these explain only ∼3% of the trait variance. Here we test two overlooked sources of variation in 192,974 European ancestry women: low-frequency protein-coding variants and X-chromosome variants. Five missense/nonsense variants (in ALMS1/LAMB2/TNRC6A/TACR3/PRKAG1) are associated with age at menarche (minor allele frequencies 0.08-4.6%; effect sizes 0.08-1.25 years per allele; P<5 × 10(-8)). In addition, we identify common X-chromosome loci at IGSF1 (rs762080, P=9.4 × 10(-13)) and FAAH2 (rs5914101, P=4.9 × 10(-10)). Highlighted genes implicate cellular energy homeostasis, post-transcriptional gene silencing and fatty-acid amide signalling. A frequently reported mutation in TACR3 for idiopathic hypogonatrophic hypogonadism (p.W275X) is associated with 1.25-year-later menarche (P=2.8 × 10(-11)), illustrating the utility of population studies to estimate the penetrance of reportedly pathogenic mutations. Collectively, these novel variants explain ∼0.5% variance, indicating that these overlooked sources of variation do not substantially explain the 'missing heritability' of this complex trait.

Recommendations for the use of long-term central venous catheter (CVC) in children with hemato-oncological disorders: management of CVC-related occlusion and CVC-related thrombosis. On behalf of the coagulation defects working group and the supportive the - Giordano, Paola; Saracco, Paola; Grassi, Massimo; Luciani, Matteo; Banov, Laura; Carraro, Francesca; Crocoli, Alessandro; Cesaro, Simone; Zanazzo, Giulio Andrea; Molinari, Angelo Claudio (Ann Hematol, 2015)
Central venous catheters (CVC), used for the management of children with hemato-oncological disorders, are burdened by a significant incidence of mechanical, infective, or thrombotic complications. These complications favor an increasing risk in prolongation of hospitalization, extra costs of care, and sometimes severe life-threatening events. No guidelines for the management of CVC-related occlusion and CVC-related thrombosis are available for children. To this aim, members of the coagulation defects working group and the supportive therapy working group of the Italian Association of Pediatric Hematology and Oncology (AIEOP) reviewed the pediatric and adult literature to propose the first recommendations for the management of CVC-related occlusion and CVC-related thrombosis in children with hemato-oncological disorders.
Keywords: Adult; Blood Coagulation Disorders; Catheter Obstruction; Catheterization, Central Venous; Central Venous Catheters; Child; Hematologic Neoplasms; Humans; Risk Factors; Thrombosis

RelB activation in anti-inflammatory decidual endothelial cells: a master plan to avoid pregnancy failure? - Masat, Elisa; Gasparini, Chiara; Agostinis, Chiara; Bossi, Fleur; Radillo, Oriano; De Seta, Francesco; Tamassia, Nicola; Cassatella, Marco A; Bulla, Roberta (Sci Rep, 2015)
It is known that excessive inflammation at fetal-maternal interface is a key contributor in a compromised pregnancy. Female genital tract is constantly in contact with microorganisms and several strategies must be adopted to avoid pregnancy failure. Decidual endothelial cells (DECs) lining decidual microvascular vessels are the first cells that interact with pro-inflammatory stimuli released into the environment by microorganisms derived from gestational tissues or systemic circulation. Here, we show that DECs are hypo-responsive to LPS stimulation in terms of IL-6, CXCL8 and CCL2 production. Our results demonstrate that DECs express low levels of TLR4 and are characterized by a strong constitutive activation of the non-canonical NF-κB pathway and a low responsiveness of the canonical pathway to LPS. In conclusion, DECs show a unique hypo-responsive phenotype to the pro-inflammatory stimulus LPS in order to control the inflammatory response at feto-maternal interface.

Role of Pharmacogenetics in Hematopoietic Stem Cell Transplantation Outcome in Children. - Franca, Raffaella; Stocco, Gabriele; Favretto, Diego; Giurici, Nagua; Decorti, Giuliana; Rabusin, Marco (Int J Mol Sci, 2015)
Hematopoietic stem cell transplantation (HSCT) is an established therapeutic procedure for several congenital and acquired disorders, both malignant and nonmalignant. Despite the great improvements in HSCT clinical practices over the last few decades, complications, such as graft vs. host disease (GVHD) and sinusoidal obstructive syndrome (SOS), are still largely unpredictable and remain the major causes of morbidity and mortality. Both donor and patient genetic background might influence the success of bone marrow transplantation and could at least partially explain the inter-individual variability in HSCT outcome. This review summarizes some of the recent studies on candidate gene polymorphisms in HSCT, with particular reference to pediatric cohorts. The interest is especially focused on pharmacogenetic variants affecting myeloablative and immunosuppressive drugs, although genetic traits involved in SOS susceptibility and transplant-related mortality are also reviewed.

A Shining Scrotal Fountain. - Copertino, Marco; Benelli, Elisa; Gregori, Massimo; Barbi, Egidio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Child; Edema; Humans; Male; Penile Diseases; Scrotum

Short Communication FYB polymorphisms in Brazilian patients with type I diabetes mellitus and autoimmune polyglandular syndrome type III. - Addobbati, C J C; de Azevêdo Silva, J; Tavares, N A C; Araujo, J; Guimarães, R L; Brandão, L; Crovella, S; Sandrin-Garcia, P (Genet Mol Res, 2015)
The aim of this study was to perform an association study between seven Fyn-binding protein gene (FYB)-tag single nucleotide polymorphisms (SNPs) and type I diabetes mellitus (T1DM), as well as with disease age of onset. We also assessed the role of FYB SNPs in the insurgence of autoimmune polyglandular syndrome type III (APSIII), characterized by the simultaneous presence of autoimmune thyroid disease and celiac disease, in patients with T1DM from a Northeastern Brazilian population. One hundred and seventy-seven patients with T1DM and 190 healthy individuals were genotyped for seven tag SNPs, covering most of the FYB locus, using real-time polymerase chain reaction amplification. There was no significant difference in the distribution of allele and genotype frequencies among patients and healthy individuals. Moreover, none of the tag SNPs were associated either to T1DM age of onset or to the insurgence of APSIII. However, since the FYB protein is a key component in T cell response, its gene variants might play a role in protein function, which might be testable in a population with different genetic backgrounds or by using functional assays.

Target sequencing approach intended to discover new mutations in non-syndromic intellectual disability. - Morgan, Anna; Gandin, Ilaria; Belcaro, Chiara; Palumbo, Pietro; Palumbo, Orazio; Biamino, Elisa; Dal Col, Valentina; Laurini, Erik; Pricl, Sabrina; Bosco, Paolo; Carella, Massimo; Ferrero, Giovanni Battista; et al. (Mutat Res, 2015)
The technological improvements over the last years made considerable progresses in the knowledge of the etiology of intellectual Disability (ID). However, at present very little is known about the genetic heterogeneity underlying the non-syndromic form of ID (NS-ID). To investigate the genetic basis of NS-ID we analyzed 43 trios and 22 isolated NS-ID patients using a targeted sequencing (TS) approach. 71 NS-ID genes have been selected and sequenced in all subjects. We found putative pathogenic mutations in 7 out of 65 patients. The pathogenic role of mutations was evaluated through sequence comparison and structural analysis was performed to predict the effect of alterations in a 3D computational model through molecular dynamics simulations. Additionally, a deep patient clinical re-evaluation has been performed after the molecular results. This approach allowed us to find novel pathogenic mutations with a detection rate close to 11% in our cohort of patients. This result supports the hypothesis that many NS-ID related genes still remain to be discovered and that NS-ID is a more complex phenotype compared to syndromic form, likely caused by a complex and broad interaction between genes alterations and environment factors.

Targeted tumor imaging of anti-CD20-polymeric nanoparticles developed for the diagnosis of B-cell malignancies. - Capolla, Sara; Garrovo, Chiara; Zorzet, Sonia; Lorenzon, Andrea; Rampazzo, Enrico; Spretz, Ruben; Pozzato, Gabriele; Núñez, Luis; Tripodo, Claudio; Macor, Paolo; Biffi, Stefania (Int J Nanomedicine, 2015)
The expectations of nanoparticle (NP)-based targeted drug delivery systems in cancer, when compared with convectional therapeutic methods, are greater efficacy and reduced drug side effects due to specific cellular-level interactions. However, there are conflicting literature reports on enhanced tumor accumulation of targeted NPs, which is essential for translating their applications as improved drug-delivery systems and contrast agents in cancer imaging. In this study, we characterized biodegradable NPs conjugated with an anti-CD20 antibody for in vivo imaging and drug delivery onto tumor cells. NPs' binding specificity mediated by anti-CD20 antibody was evaluated on MEC1 cells and chronic lymphocytic leukemia patients' cells. The whole-body distribution of untargeted NPs and anti-CD20 NPs were compared by time-domain optical imaging in a localized human/mouse model of B-cell malignancy. These studies provided evidence that NPs' functionalization by an anti-CD20 antibody improves tumor pharmacokinetic profiles in vivo after systemic administration and increases in vivo imaging of tumor mass compared to non-targeted NPs. Together, drug delivery and imaging probe represents a promising theranostics tool for targeting B-cell malignancies.

TNF-related apoptosis inducing ligand in ocular cancers and ocular diabetic complications. - Perri, Paolo; Zauli, Giorgio; Gonelli, Arianna; Milani, Daniela; Celeghini, Claudio; Lamberti, Giuseppe; Secchiero, Paola (Biomed Res Int, 2015)
TNF-related apoptosis inducing ligand (TRAIL) is an intensively studied cytokine, in particular for its anticancer activity. The discovery that conjunctival sac fluid contains extremely high levels of soluble TRAIL as compared to other body fluids suggested important implications in the context of the immunological surveillance of the eye, in particular of the anterior surface. In this review, we discuss the potential physiopathologic and therapeutic role of the TRAIL/TRAIL receptor system in a variety of ocular cancers. Moreover, since an increasing amount of data has indicated the important biological activities of the TRAIL/TRAIL receptor systems also in a completely different pathologic context such as diabetes mellitus, in the second part of this review we summarize the currently available data on the involvement of TRAIL in the ocular complications of diabetes mellitus as modulator of the inflammatory and angiogenic response in the eye.
Keywords: Apoptosis; Diabetes Complications; Diabetes Mellitus; Eye Neoplasms; Humans; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand

Two‑gene mutation in a single patient: Biochemical and functional analysis for a correct interpretation of exome results. - Bianco, Anna Monica; Faletra, Flavio; Vozzi, Diego; Girardelli, Martina; Knowles, Alessandra; Tommasini, Alberto; Zauli, Giorgio; Marcuzzi, Annalisa (Mol Med Rep, 2015)
Next-generation sequencing (NGS) has generated a large amount of sequence data with the requirement of frequent critical revisions of reported mutations. This innovative tool has proved to be effective in detecting pathogenic mutations; however, it requires a certain degree of experience to identify incidental findings. In the present study, whole exome sequencing analysis was performed for the molecular diagnosis and correct genotype/phenotype correlation between parents and a patient presenting with an atypical phenotype. In addition, mevalonic acid quantification and frequency analysis of detected variants in public databases and X‑chromosome inactivation (XCI) studies on the patient's mother were performed. V377I as well as the S135L mutations were identified on the mevalonate kinase deficiency gene and the levels of mevalonic acid in the patient were 5,496 µg/ml. A D59G variation, reported in ESP6500 in two healthy individuals, was found on the Martin Probst syndrome gene (RAB40AL). Based on XCI studies on the patient's mother, it is likely that RAB40AL escapes XCI, while still remaining balanced. In conclusion, the results of the present study indicated that the Martin Probst syndrome is an X‑linked condition, which is probably not caused by RAB40AL mutations. Although NGS is a powerful tool to identify pathogenic mutations, the analysis of genetic data requires expert critical revision of all detected variants.

Usher syndrome: an effective sequencing approach to establish a genetic and clinical diagnosis. - Lenarduzzi, S; Vozzi, D; Morgan, A; Rubinato, E; D'Eustacchio, A; Osland, T M; Rossi, C; Graziano, C; Castorina, P; Ambrosetti, U; Morgutti, M; Girotto, G (Hear Res, 2015)
Usher syndrome is an autosomal recessive disorder characterized by retinitis pigmentosa, sensorineural hearing loss and, in some cases, vestibular dysfunction. The disorder is clinically and genetically heterogeneous and, to date, mutations in 11 genes have been described. This finding makes difficult to get a precise molecular diagnosis and offer patients accurate genetic counselling. To overcome this problem and to increase our knowledge of the molecular basis of Usher syndrome, we designed a targeted resequencing custom panel. In a first validation step a series of 16 Italian patients with known molecular diagnosis were analysed and 31 out of 32 alleles were detected (97% of accuracy). After this step, 31 patients without a molecular diagnosis were enrolled in the study. Three out of them with an uncertain Usher diagnosis were excluded. One causative allele was detected in 24 out 28 patients (86%) while the presence of both causative alleles characterized 19 patients out 28 (68%). Sixteen novel and 27 known alleles were found in the following genes: USH2A (50%), MYO7A (7%), CDH23 (11%), PCDH15 (7%) and USH1G (2%). Overall, on the 44 patients the protocol was able to characterize 74 alleles out of 88 (84%). These results suggest that our panel is an effective approach for the genetic diagnosis of Usher syndrome leading to: 1) an accurate molecular diagnosis, 2) better genetic counselling, 3) more precise molecular epidemiology data fundamental for future interventional plans.
Keywords: Adult; Alleles; Cadherins; Extracellular Matrix Proteins; Female; Genetic Counseling; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Mutation; Myosins; Nerve Tissue Proteins; Usher Syndromes

Validation of the Italian translation of the affective neuroscience personality scales. - Pascazio, Lorenzo; Bembich, Stefano; Nardone, Ilaria B; Vecchiet, Cristina; Guarino, Giuseppina; Clarici, Andrea (Psychol Rep, 2015)
The theoretical perspective on affective neuroscience advanced by Panksepp, identified six basic innate affective systems: the SEEK, FEAR, ANGER, SADNESS, PLAY, and CARE systems. (3) It has been proposed that the fundamental elements of human personality and its variants may be based on the different expressions of these basic emotional systems and their combinations. A self-report inventory, the Affective Neuroscience Personality Scales (ANPS), has been devised with the aim of studying and evaluating personality from this perspective. This study reports data on the initial validation of ANPS Italian translation on a sample of 418 adult participants. Descriptive statistics for each scale were calculated, assessing also their internal consistency, as a measure of reliability and factorial validity. Acceptable internal consistency was found in all but one scale (SADNESS), and a second-order factor analysis identified a more general affective feature of personality hinging on relational characteristics, independent of the dimensions of general positive and negative affect.
Keywords: Adolescent; Adult; Affect; Aged; Aged, 80 and over; Female; Humans; Italy; Male; Middle Aged; Neurosciences; Personality; Personality Inventory; Psychometrics; Young Adult

Acquired long QT syndrome: a focus for the general pediatrician. - Marzuillo, Pierluigi; Benettoni, Alessandra; Germani, Claudio; Ferrara, Giovanna; D'Agata, Biancamaria; Barbi, Egidio (Pediatr Emerg Care, 2014)
Acquired long QT syndrome (LQTS) is a disorder of cardiac repolarization most often due to specific drugs, hypokalemia, or hypomagnesemia that may precipitate torsade de pointes and cause sudden cardiac death. Common presentations of the LQTS are palpitations, presyncope, syncope, cardiac arrest, and seizures. An abnormal 12-lead electrocardiogram obtained while the patient is at rest is the key to diagnosis. The occurrence of drug-induced LQTS is unpredictable in any given individual, but a common observation is that most patients have at least 1 identifiable risk factor in addition to drug exposure. The cornerstone of the management of acquired LQTS includes the identification and discontinuation of any precipitating drug and the correction of metabolic abnormalities, such as hypokalemia or hypomagnesemia. Most of the episodes of torsade de pointes are short-lived and terminate spontaneously. We propose a management protocol that could be useful for the daily practice in the emergency pediatric department to reduce the risk of acquired QT prolongation.
Keywords: Adolescent; Death, Sudden, Cardiac; Electrocardiography; Female; General Practitioners; Humans; Long QT Syndrome; Ondansetron; Risk Factors; Serotonin Antagonists

Analysis of 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. - Noris, Patrizia; Schlegel, Nicole; Klersy, Catherine; Heller, Paula G; Civaschi, Elisa; Pujol-Moix, Núria; Fabris, Fabrizio; Favier, Rémi; Gresele, Paolo; Latger-Cannard, Véronique; Cuker, Adam; Nurden, Paquita; et al. (Haematologica, 2014)
Pregnancy in women with inherited thrombocytopenias is a major matter of concern as both the mothers and the newborns are potentially at risk of bleeding. However, medical management of this condition cannot be based on evidence because of the lack of consistent information in the literature. To advance knowledge on this matter, we performed a multicentric, retrospective study evaluating 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. Neither the degree of thrombocytopenia nor the severity of bleeding tendency worsened during pregnancy and the course of pregnancy did not differ from that of healthy subjects in terms of miscarriages, fetal bleeding and pre-term births. The degree of thrombocytopenia in the babies was similar to that in the mother. Only 7 of 156 affected newborns had delivery-related bleeding, but 2 of them died of cerebral hemorrhage. The frequency of delivery-related maternal bleeding ranged from 6.8% to 14.2% depending on the definition of abnormal blood loss, suggesting that the risk of abnormal blood loss was increased with respect to the general population. However, no mother died or had to undergo hysterectomy to arrest bleeding. The search for parameters predicting delivery-related bleeding in the mother suggested that hemorrhages requiring blood transfusion were more frequent in women with history of severe bleedings before pregnancy and with platelet count at delivery below 50 × 10(9)/L.
Keywords: Adult; Female; Humans; Infant, Newborn; Pregnancy; Pregnancy Complications, Hematologic; Retrospective Studies; Thrombocytopenia; Young Adult

Association analysis of bitter receptor genes in five isolated populations identifies a significant correlation between TAS2R43 variants and coffee liking. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; d'Adamo, Pio; Amin, Najaf; D'Eustacchio, Angela; Navarini, Luciano; Sala, Cinzia; Karssen, Lennart C; et al. (PLoS One, 2014)
Coffee, one of the most popular beverages in the world, contains many different physiologically active compounds with a potential impact on people's health. Despite the recent attention given to the genetic basis of its consumption, very little has been done in understanding genes influencing coffee preference among different individuals. Given its markedly bitter taste, we decided to verify if bitter receptor genes (TAS2Rs) variants affect coffee liking. In this light, 4066 people from different parts of Europe and Central Asia filled in a field questionnaire on coffee liking. They have been consequently recruited and included in the study. Eighty-eight SNPs covering the 25 TAS2R genes were selected from the available imputed ones and used to run association analysis for coffee liking. A significant association was detected with three SNP: one synonymous and two functional variants (W35S and H212R) on the TAS2R43 gene. Both variants have been shown to greatly reduce in vitro protein activity. Surprisingly the wild type allele, which corresponds to the functional form of the protein, is associated to higher liking of coffee. Since the hTAS2R43 receptor is sensible to caffeine, we verified if the detected variants produced differences in caffeine bitter perception on a subsample of people coming from the FVG cohort. We found a significant association between differences in caffeine perception and the H212R variant but not with the W35S, which suggests that the effect of the TAS2R43 gene on coffee liking is mediated by caffeine and in particular by the H212R variant. No other significant association was found with other TAS2R genes. In conclusion, the present study opens new perspectives in the understanding of coffee liking. Further studies are needed to clarify the role of the TAS2R43 gene in coffee hedonics and to identify which other genes and pathways are involved in its genetics.
Keywords: Coffee; Genetic Association Studies; Humans; Polymorphism, Single Nucleotide; Receptors, G-Protein-Coupled; Taste

Association of CD209 and CD209L polymorphisms with tuberculosis infection in a Northeastern Brazilian population. - da Silva, Ronaldo Celerino; Segat, Ludovica; da Cruz, Heidi Lacerda Alves; Schindler, Haiana Charifker; Montenegro, Lilian Maria Lapa; Crovella, Sergio; Guimarães, Rafael Lima (Mol Biol Rep, 2014)
Tuberculosis (TB) caused by Mycobacterium tuberculosis, is major cause of morbidity and mortality worldwide. So far, many candidate genes have been investigated for their possible association with TB. Dendritic cell-specific intercellular adhesion molecule 3 (ICAM-3) grabbing non-integrin (DC-SIGN) and Liver/lymph node-specific intercellular adhesion molecule-grabbing non-integrin (L-SIGN), encoded by CD209 and CD209L genes respectively, are known for binding to M. tuberculosis on human dendritic cells and macrophages. We screened 4 single nucleotide polymorphisms (SNPs) in the promoter region of CD209, namely -939G>A (rs735240), -871A>G (rs735239), -336A>G (rs4804803) and -139G>A (rs2287886) and tandem repeat polymorphisms in exon 4 of CD209 and CD209L genes looking for association with TB in a Northeastern Brazilian population (295 subjects, 131 TB patients and 164 healthy controls). The -139G>A and -939G>A SNPs were associated with susceptibility to TB, and in particular with pulmonary and extra-pulmonary forms respectively. The -871A>G and -336A>G SNPs were associated, the first with protection to both pulmonary and extra-pulmonary TB, the latter only with the pulmonary form. An association between GGAG haplotype and protection to TB infection was also found. Also tandem repeat polymorphism in CD209L exon 4 was associated with TB infection. This study provides evidence of an association between CD209 and CD209L polymorphisms and TB development in a Brazilian population, suggesting that variations in these genes may influence the protection and susceptibility to infection caused by M. tuberculosis.
Keywords: Adult; Alleles; Brazil; Case-Control Studies; Cell Adhesion Molecules; Dendritic Cells; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Lectins, C-Type; Male; Mycobacterium tuberculosis; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Receptors, Cell Surface; Tuberculosis; Young Adult

An asymptomatic multiple magnet ingestion with transmesenteric entero-enteric fistula. - Pederiva, Federica; Daniela, Codrich; Scarpa, Maria-Grazia; Guida, Edoardo; Dragovic, Danica; Martelossi, Stefano (APSP J Case Rep, 2014)
Ingestion of foreign bodies is a common presenting complaint in the pediatric emergency department. We present a case of a child in whom disc battery ingestion was suspected initially. The immobility of the foreign body on few days of conservative management raised the suspicion of two magnets. At operation, two magnets were found in the bowel causing a transmesenteric entero-enteric fistula.

Autosomal recessive Stickler syndrome due to a loss of function mutation in the COL9A3 gene. - Faletra, Flavio; d'Adamo, Adamo P; Bruno, Irene; Athanasakis, Emmanouil; Biskup, Saskia; Esposito, Laura; Gasparini, Paolo (Am J Med Genet A, 2014)
Stickler syndrome (STL) is a clinically variable and genetically heterogeneous syndrome characterized by ophthalmic, articular, orofacial, and auditory manifestations. STL has been described with both autosomal dominant and recessive inheritance. The dominant form is caused by mutations of COL2A1 (STL 1, OMIM 108300), COL11A1 (STL 2, OMIM 604841), and COL11A2 (STL 3, OMIM 184840) genes, while recessive forms have been associated with mutations of COL9A1 (OMIM 120210) and COL9A2 (OMIM 120260) genes. Type IX collagen is a heterotrimeric molecule formed by three genetically distinct chains: α1, α2, and α3 encoded by the COL9A1, COL9A2, and COL9A3 genes. Up to this time, only heterozygous mutations of COL9A3 gene have been reported in human and related to: (1) multiple epiphyseal dysplasia type 3, (2) susceptibility to an intervertebral disc disease, and (3) hearing loss. Here, we describe the first autosomal recessive Stickler family due to loss of function mutations (c.1176_1198del, p.Gln393Cysfs*25) of COL9A3 gene. These findings extend further the role of collagen genes family in the disease pathogenesis.
Keywords: Adolescent; Arthritis; Bone and Bones; Child; Child, Preschool; Collagen Diseases; Collagen Type IX; Connective Tissue Diseases; DNA Mutational Analysis; Facies; Female; Genes, Recessive; Hearing Loss; Hearing Loss, Sensorineural; Homozygote; Humans; Male; Mutation; Pedigree; Retinal Detachment

Block of the mevalonate pathway triggers oxidative and inflammatory molecular mechanisms modulated by exogenous isoprenoid compounds. - Tricarico, Paola Maura; Kleiner, Giulio; Valencic, Erica; Campisciano, Giuseppina; Girardelli, Martina; Crovella, Sergio; Knowles, Alessandra; Marcuzzi, Annalisa (Int J Mol Sci, 2014)
Deregulation of the mevalonate pathway is known to be involved in a number of diseases that exhibit a systemic inflammatory phenotype and often neurological involvements, as seen in patients suffering from a rare disease called mevalonate kinase deficiency (MKD). One of the molecular mechanisms underlying this pathology could depend on the shortage of isoprenoid compounds and the subsequent mitochondrial damage, leading to oxidative stress and pro-inflammatory cytokines' release. Moreover, it has been demonstrated that cellular death results from the balance between apoptosis and pyroptosis, both driven by mitochondrial damage and the molecular platform inflammasome. In order to rescue the deregulated pathway and decrease inflammatory markers, exogenous isoprenoid compounds were administered to a biochemical model of MKD obtained treating a murine monocytic cell line with a compound able to block the mevalonate pathway, plus an inflammatory stimulus. Our results show that isoprenoids acted in different ways, mainly increasing the expression of the evaluated markers [apoptosis, mitochondrial dysfunction, nucleotide-binding oligomerization-domain protein-like receptors 3 (NALP3), cytokines and nitric oxide (NO)]. Our findings confirm the hypothesis that inflammation is triggered, at least partially, by the shortage of isoprenoids. Moreover, although further studies are necessary, the achieved results suggest a possible role for exogenous isoprenoids in the treatment of MKD.
Keywords: Animals; Apoptosis; Carotenoids; Carrier Proteins; Cell Line; Cytokines; Diterpenes; Humans; Mevalonate Kinase Deficiency; Mevalonic Acid; Mice; Mitochondria; Nitric Oxide; Phytol; Terpenes

A boy with sudden headache. - Norbedo, Stefania; Naviglio, Samuele; Murru, Flora Maria; Cavallin, Roberta; Giurici, Nagua; Rabusin, Marco; Barbi, Egidio (Pediatr Emerg Care, 2014)
Headache is a common presenting complaint in pediatric emergency departments. The goal of emergent evaluation is to identify those children with potentially life-threatening conditions. We present the case of an adolescent boy presenting with headache and hypertension who was diagnosed with a catecholamine-secreting abdominal paraganglioma. Genetic testing eventually led to the diagnosis of SDHB-related hereditary paraganglioma-pheochromocytoma syndrome. Alarm features ("red flags") in children presenting with headache are reviewed, as well as the main features of paragangliomas and the indications for genetic testing.
Keywords: Abdominal Neoplasms; Adolescent; Emergencies; Headache; Humans; Male; Paraganglioma

C1q as a unique player in angiogenesis with therapeutic implication in wound healing. - Bossi, Fleur; Tripodo, Claudio; Rizzi, Lucia; Bulla, Roberta; Agostinis, Chiara; Guarnotta, Carla; Munaut, Carine; Baldassarre, Gustavo; Papa, Giovanni; Zorzet, Sonia; Ghebrehiwet, Berhane; Ling, Guang Sheng; et al. (Proc Natl Acad Sci U S A, 2014)
We have previously shown that C1q is expressed on endothelial cells (ECs) of newly formed decidual tissue. Here we demonstrate that C1q is deposited in wound-healing skin in the absence of C4 and C3 and that C1q mRNA is locally expressed as revealed by real-time PCR and in situ hybridization. C1q was found to induce permeability of the EC monolayer, to stimulate EC proliferation and migration, and to promote tube formation and sprouting of new vessels in a rat aortic ring assay. Using a murine model of wound healing we observed that vessel formation was defective in C1qa(-/-) mice and was restored to normal after local application of C1q. The mean vessel density of wound-healing tissue and the healed wound area were significantly increased in C1q-treated rats. On the basis of these results we suggest that C1q may represent a valuable therapeutic agent that can be used to treat chronic ulcers or other pathological conditions in which angiogenesis is impaired, such as myocardial ischemia.
Keywords: Animals; Cell Proliferation; Complement C1q; DNA Primers; Endothelial Cells; Enzyme-Linked Immunosorbent Assay; Human Umbilical Vein Endothelial Cells; Humans; Immunoblotting; Immunohistochemistry; In Situ Hybridization; Mice; Mice, Inbred C57BL; Mice, Knockout; Neovascularization, Physiologic; Rats; Rats, Wistar; Real-Time Polymerase Chain Reaction; Wound Healing

Can Lactobacillus fermentum LF10 and Lactobacillus acidophilus LA02 in a slow-release vaginal product be useful for prevention of recurrent vulvovaginal candidiasis?: A clinical study. - Murina, Filippo; Graziottin, Alessandra; Vicariotto, Franco; De Seta, Francesco (J Clin Gastroenterol, 2014)
OBJECTIVE: To assess the effectiveness of the association of 2 specific strains, Lactobacillus fermentum LF10 (DSM 19187) and Lactobacillus acidophilus LA02 (DSM 21717), specifically formulated in slow-release effervescent tablets, in patients with recurrent vulvovaginal candidiasis. STUDY DESIGN: The study was a clinical trial of 58 women diagnosed with recurrent VVC (≥4 culture-confirmed episodes in a 12-mo period). All patients were given 200 mg of fluconazole orally as an induction dose for 3 alternate days during the first treatment week. Afterward, the patients were given a new product formulated in slow-release vaginal tablets containing at least 0.4 billion live cells of each of lactobacillus L. fermentum LF10 and L. acidophilus LA02 (first phase of the prophylactic period), on alternate days for 10 consecutive nights. Patients who were still free of symptoms were given 1 vaginal tablet every week for the next 10 weeks (second phase of the prophylactic period). Patients asymptomatic after the total duration of the observation phase (7 mo) were considered as responders. RESULTS: During the second 10-week prophylactic phase, 49 of 57 (86.0%) patients remained free of clinical recurrence, whereas symptomatic VVC occurred in 8 patients (14.0%). During the 7-month follow-up, 42 patients of 49 (85.7%) were symptom free at the end of the protocol, whereas clinical recurrences occurred in 7 women (14.3%). Overall, 42 of 58 women enrolled in the study (72.4%) experienced no clinical recurrence throughout the 7-month observation phase (responders). CONCLUSIONS: This study strengthens the evidence supporting the use of specific lactobacilli with well-demonstrated activities associated with the creation and maintenance of a vaginal biofilm that hinders the persistence of an infection caused by Candida.
Keywords: Administration, Intravaginal; Adult; Biofilms; Candidiasis, Vulvovaginal; Delayed-Action Preparations; Female; Humans; Italy; Lactobacillus acidophilus; Lactobacillus fermentum; Middle Aged; Probiotics; Recurrence; Tablets; Time Factors; Treatment Outcome; Vagina; Vulva; Young Adult

Class IV laser therapy as treatment for chemotherapy-induced oral mucositis in onco-haematological paediatric patients: a prospective study. - Chermetz, Maddalena; Gobbo, Margherita; Ronfani, Luca; Ottaviani, Giulia; Zanazzo, Giulio A; Verzegnassi, Federico; Treister, Nathaniel S; Di Lenarda, Roberto; Biasotto, Matteo; Zacchigna, Serena (Int J Paediatr Dent, 2014)
BACKGROUND: Oral mucositis is a debilitating side effect of chemotherapy. Laser therapy has recently demonstrated efficacy in the management of oral mucositis (OM). AIM: This prospective study was conducted to evaluate the efficacy of class IV laser therapy in patients affected by OM. DESIGN: Eighteen onco-haematological paediatric patients receiving chemotherapy and/or haematopoietic stem cell transplantation, prior to total body irradiation, affected by OM, were enrolled in this study. Patients were treated with class IV laser therapy for four consecutive days; the assessment of OM was performed through WHO Oral Mucositis Grading Objective Scale, and pain was evaluated through visual analogue scale. Patients completed a validated questionnaire, and photographs of lesions were taken during each session. Patients were re-evaluated 11 days after the first day of laser therapy. RESULTS: All patients demonstrated improvement in pain sensation, and all mucositis was fully resolved at the 11-day follow-up visit, with no apparent side effects. Laser therapy was well tolerated with remarkable reduction in pain associated with oral mucositis after 1-2 days of laser therapy. CONCLUSIONS: Given class IV laser therapy appears to be safe, non-invasive, and potentially effective, prospective, randomized, controlled trials are necessary to further assess efficacy and to determine optimal treatment parameters.

Common variants in UMOD associate with urinary uromodulin levels: a meta-analysis. - Olden, Matthias; Corre, Tanguy; Hayward, Caroline; Toniolo, Daniela; Ulivi, Sheila; Gasparini, Paolo; Pistis, Giorgio; Hwang, Shih-Jen; Bergmann, Sven; Campbell, Harry; Cocca, Massimiliano; Gandin, Ilaria; et al. (J Am Soc Nephrol, 2014)
Uromodulin is expressed exclusively in the thick ascending limb and is the most abundant protein excreted in normal urine. Variants in UMOD, which encodes uromodulin, are associated with renal function, and urinary uromodulin levels may be a biomarker for kidney disease. However, the genetic factors regulating uromodulin excretion are unknown. We conducted a meta-analysis of urinary uromodulin levels to identify associated common genetic variants in the general population. We included 10,884 individuals of European descent from three genetic isolates and three urban cohorts. Each study measured uromodulin indexed to creatinine and conducted linear regression analysis of approximately 2.5 million single nucleotide polymorphisms using an additive model. We also tested whether variants in genes expressed in the thick ascending limb associate with uromodulin levels. rs12917707, located near UMOD and previously associated with renal function and CKD, had the strongest association with urinary uromodulin levels (P<0.001). In all cohorts, carriers of a G allele of this variant had higher uromodulin levels than noncarriers did (geometric means 10.24, 14.05, and 17.67 μg/g creatinine for zero, one, or two copies of the G allele). rs12446492 in the adjacent gene PDILT (protein disulfide isomerase-like, testis expressed) also reached genome-wide significance (P<0.001). Regarding genes expressed in the thick ascending limb, variants in KCNJ1, SORL1, and CAB39 associated with urinary uromodulin levels. These data indicate that common variants in the UMOD promoter region may influence urinary uromodulin levels. They also provide insights into uromodulin biology and the association of UMOD variants with renal function.
Keywords: Creatinine; European Continental Ancestry Group; Genetic Variation; Humans; Polymorphism, Single Nucleotide; Uromodulin

A comparison of three scales for measuring pain in children with cognitive impairment. - Massaro, Marta; Ronfani, Luca; Ferrara, Giovanna; Badina, Laura; Giorgi, Rita; D'Osualdo, Flavio; Taddio, Andrea; Barbi, Egidio (Acta Paediatr, 2014)
AIM: Pain is a neglected problem in children with cognitive impairments, and few studies compare the clinical use of specific pain scales. We compared the Non-Communicating Children's Pain Checklist Postoperative Version (NCCPC-PV), the Echelle Douleur Enfant San Salvador (DESS) and the Children's Hospital of Eastern Ontario Pain Scale (CHEOPS). The first two were developed for children with cognitive impairment, and the third is a more general pain scale. METHODS: Two external observers and the child's caregiver assessed 40 children with cognitive impairment for pain levels. We assessed inter-rater agreement, correlation, dependence on knowledge of the child's behaviour, simplicity and adequacy in pain rating according to the caregiver for all three scales. RESULTS: The correlation between the NCCPC-PV and the DESS was strong (Spearman correlation coefficient = 0.76) and better than between each scale and the CHEOPS. Although the DESS showed better inter-rater agreement, it was more dependent on familiarity with the child and was judged more difficult to use by all observers. The NCCPC-PV was the easiest use and the most appropriate for rating the child's pain. CONCLUSION: The NCCPC-PV was the easiest to use for pain assessment in cognitively impaired children and should be adopted in clinical settings.

Consanguinity and hereditary hearing loss in Qatar. - Girotto, Giorgia; Mezzavilla, Massimo; Abdulhadi, Khalid; Vuckovic, Dragana; Vozzi, Diego; Khalifa Alkowari, Moza; Gasparini, Paolo; Badii, Ramin (Hum Hered, 2014)
Qatar is a sovereign state located on the Eastern coast of the Arabian Peninsula in the Persian Gulf. Its native population consists of 3 major subgroups: people of Arabian origin or Bedouins, those from an Eastern or Persian ancestry and individuals with African admixture. Historically, all types of consanguineous marriages have been and still are common in the Qatari population, particularly among first and double-first cousins. Thus, there is a higher risk for most inherited diseases including hereditary hearing loss (HHL). In particular, a hearing loss prevalence of 5.2% has been reported in Qatar, with parental consanguinity being more common among affected individuals as compared with unaffected ones. Our recent molecular results confirm a high homogeneity and level of inbreeding in Qatari HHL patients. Among all HHL genes, GJB2, the major player worldwide, accounts for a minor proportion of cases and at least 3 additional genes have been found to be mutated in Qatari patients. Interestingly, one gene, BDP1, has been described to cause HHL only in this country. These results point towards an unexpected level of genetic heterogeneity despite the high level of inbreeding. This review provides an up-to-date picture of HHL in Qatar and of the impact of consanguinity on this disease.
Keywords: Consanguinity; Hearing Loss; Homozygote; Humans; Inheritance Patterns; Pedigree; Prevalence; Principal Component Analysis; Qatar; Transcription Factor TFIIIB

Curcumin and inflammatory bowel disease: potential and limits of innovative treatments. - Vecchi Brumatti, Liza; Marcuzzi, Annalisa; Tricarico, Paola Maura; Zanin, Valentina; Girardelli, Martina; Bianco, Anna Monica (Molecules, 2014)
Curcumin belongs to the family of natural compounds collectively called curcuminoids and it possesses remarkable beneficial anti-oxidant, anti-inflammatory, anti-cancer, and neuroprotective properties. Moreover it is commonly assumed that curcumin has also been suggested as a remedy for digestive diseases such as inflammatory bowel diseases (IBD), a chronic immune disorder affecting the gastrointestinal tract and that can be divided in two major subgroups: Crohn's disease (CD) and Ulcerative Colitis (UC), depending mainly on the intestine tract affected by the inflammatory events. The chronic and intermittent nature of IBD imposes, where applicable, long-term treatments conducted in most of the cases combining different types of drugs. In more severe cases and where there has been no good response to the drugs, a surgery therapy is carried out. Currently, IBD-pharmacological treatments are generally not curative and often present serious side effects; for this reason, being known the relationship between nutrition and IBD, it is worthy of interesting the study and the development of new dietary strategy. The curcumin principal mechanism is the suppression of IBD inflammatory compounds (NF-κB) modulating immune response. This review summarizes literature data of curcumin as anti-inflammatory and anti-oxidant in IBD, trying to understand the different effects in CD e UC.
Keywords: Animals; Anti-Inflammatory Agents, Non-Steroidal; Chemistry, Pharmaceutical; Clinical Trials as Topic; Curcumin; Humans; Inflammatory Bowel Diseases; Molecular Targeted Therapy; Nanotechnology; Treatment Outcome

DC-SIGN polymorphisms are associated to type 1 diabetes mellitus. - da Silva, Ronaldo Celerino; Cunha Tavares, Nathália de Alencar; Moura, Ronald; Coelho, Antônio; Guimarães, Rafael Lima; Araújo, Jacqueline; Crovella, Sergio; Brandão, Lucas André Cavalcanti; Silva, Jaqueline de Azevêdo (Immunobiology, 2014)
Type I diabetes mellitus (T1DM) is an autoimmune disorder featured by raised glucoses levels. It has been hypothesised that raised glucose levels in T1DM might be recognised as PAMPs, leading to immune response by overloading the cell receptors for pathogens recognition. DC-SIGN is a transmembrane protein, present in dendritic cells (DC) and macrophages: it has an important role in inflammatory response and T cells activation. Notably, DC-SIGN activation and triggering of the immune response depend on the type of ligand, which may lead to a pro or anti-inflammatory pathway. In our association study, we analysed the SNPs rs4804803 (-336 A>G) and rs735239 (-871 A>G), both at DC-SIGN promoter region, in 210 T1DM patients and 157 healthy controls, also looking for a correlation with the age of onset of the disease. We found that the allele G and genotypes G/G and A/G of SNP-871 (rs735239), as well as the alleles G-G (rs735239-rs4804803) and genotypes combined AA-GG (rs735239-rs4804803) were associated with protection of T1DM development. We did not find association between these variations with the age of onset of the disease and the presence of other autoimmune disorders. Our results suggest that SNPs in DC-SIGN promoter region can be associated to protection for T1DM in the Northeast Brazilian population.
Keywords: Adolescent; Alleles; Case-Control Studies; Cell Adhesion Molecules; Child; Child, Preschool; Diabetes Mellitus, Type 1; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Infant; Infant, Newborn; Lectins, C-Type; Male; Odds Ratio; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Receptors, Cell Surface

Diagnostic accuracy of ultrasonography for hand bony fractures in paediatric patients. - Neri, Elena; Barbi, Egidio; Rabach, Ingrid; Zanchi, Chiara; Norbedo, Stefania; Ronfani, Luca; Guastalla, Veronica; Ventura, Alessandro; Guastalla, Pierpaolo (Arch Dis Child, 2014)
OBJECTIVE: Hand fractures are common in childhood, and radiography is the standard diagnostic procedure. US has been used to evaluate bone injuries, mainly in adults for long-bone trauma; there are only a few studies about hand fractures in children. The purpose of this study was to evaluate and confirm the safety and applicability of the US diagnostic procedure in comparison to X-ray diagnosis. STUDY DESIGN: This cross-sectional study involved a convenience sample of young patients (between 2 and 17 years old) who were taken to the emergency department due to hand trauma. After clinical assessment, patients with a suspected hand fracture first underwent X-ray, and subsequently US examination by two different operators; a radiologist experienced in US and a trained emergency physician in "double-blind" fashion. US and radiographic findings were then compared, and sensitivity as well as specificity was calculated. RESULTS: A total of 204 patients were enrolled in the study. Seventy-nine fractures of phalanges or metacarpals were detected by standard radiography. When US imaging was performed by an expert radiologist, 72 fractures were detected with sensitivity and a specificity of 91.1% and 97.6%, respectively. Sensitivity and specificity were found to be (respectively) 91.5% and 96.8% when US was performed by the ED physicians. CONCLUSIONS: US imaging showed excellent sensitivity and specificity results in the diagnosis of hand fractures in children. The study also showed a great agreement between the results of the US carried out by the senior radiologist and those carried out by the paediatric emergency physician, suggesting that US can be performed by an ED physician, allowing a rapid and accurate evaluation in ED and could become the first diagnostic approach whenever a hand fracture is suspected.
Keywords: Adolescent; Child; Child, Preschool; Cross-Sectional Studies; Double-Blind Method; Emergency Service, Hospital; Female; Fractures, Bone; Hand Bones; Humans; Italy; Male; Sensitivity and Specificity

DNA mismatch repair gene MSH6 implicated in determining age at natural menopause. - Perry, John R B; Hsu, Yi-Hsiang; Chasman, Daniel I; Johnson, Andrew D; Elks, Cathy; Albrecht, Eva; Andrulis, Irene L; Beesley, Jonathan; Berenson, Gerald S; Bergmann, Sven; Bojesen, Stig E; Bolla, Manjeet K; et al. (Hum Mol Genet, 2014)
The length of female reproductive lifespan is associated with multiple adverse outcomes, including breast cancer, cardiovascular disease and infertility. The biological processes that govern the timing of the beginning and end of reproductive life are not well understood. Genetic variants are known to contribute to ∼50% of the variation in both age at menarche and menopause, but to date the known genes explain <15% of the genetic component. We have used genome-wide association in a bivariate meta-analysis of both traits to identify genes involved in determining reproductive lifespan. We observed significant genetic correlation between the two traits using genome-wide complex trait analysis. However, we found no robust statistical evidence for individual variants with an effect on both traits. A novel association with age at menopause was detected for a variant rs1800932 in the mismatch repair gene MSH6 (P = 1.9 × 10(-9)), which was also associated with altered expression levels of MSH6 mRNA in multiple tissues. This study contributes to the growing evidence that DNA repair processes play a key role in ovarian ageing and could be an important therapeutic target for infertility.
Keywords: Age Factors; DNA-Binding Proteins; Female; Genome-Wide Association Study; Humans; Menopause; Polymorphism, Single Nucleotide

Experience from a single paediatric transplant centre with identification of some protective and risk factors concerning the development of hepatic veno-occlusive disease in children after allogeneic hematopoietic stem cell transplant. - Maximova, N; Ferrara, G; Minute, M; Pizzol, A; Kiren, V; Montico, M; Gregori, M; Tamaro, P (Int J Hematol, 2014)
Hepatic veno-occlusive disease (VOD) is a frequent and severe complication of hematopoietic stem cell transplantation (HSCT) affecting 9.6-17.3 % of cases. 200 HSCT, performed between January 1995 and March 2013 in our Paediatric HSCT Centre in Trieste, were retrospectively analysed to evaluate the frequency of VOD and to identify the associated risk factors. The frequency of VOD according to the Seattle criteria was 17 %, within the range reported in literature. The mortality rate was 37.5 % (75 out of 200 transplantations) in the general population and 73.5 % (25 out of 34) in VOD patients (p < 0.05). Veno-occlusive disease significantly decreased from 38 % (1995-2000) to 8 % (2007-2013) p < 0.05. Univariate and multivariate analyses identified sepsis and pre-transplant ferritin levels above 1000 ng/ml as two significant risk factors for VOD, while the use of tacrolimus appeared to be associated with a lower VOD risk. Veno-occlusive disease still remains an important cause of transplant-related mortality even if it appears to have decreased over the last few years.
Keywords: Adolescent; Child; Child, Preschool; Female; Hematopoietic Stem Cell Transplantation; Hepatic Veno-Occlusive Disease; Humans; Infant; Infant, Newborn; Male; Mortality; Retrospective Studies; Risk Factors; Transplantation, Homologous; Young Adult

Expression and replication studies to identify new candidate genes involved in normal hearing function. - Girotto, Giorgia; Vuckovic, Dragana; Buniello, Annalisa; Lorente-Cánovas, Beatriz; Lewis, Morag; Gasparini, Paolo; Steel, Karen P (PLoS One, 2014)
Considerable progress has been made in identifying deafness genes, but still little is known about the genetic basis of normal variation in hearing function. We recently carried out a Genome Wide Association Study (GWAS) of quantitative hearing traits in southern European populations and found several SNPs with suggestive but none with significant association. In the current study, we followed up these SNPs to investigate which of them might show a genuine association with auditory function using alternative approaches. Firstly, we generated a shortlist of 19 genes from the published GWAS results. Secondly, we carried out immunocytochemistry to examine expression of these 19 genes in the mouse inner ear. Twelve of them showed distinctive cochlear expression patterns. Four showed expression restricted to sensory hair cells (Csmd1, Arsg, Slc16a6 and Gabrg3), one only in marginal cells of the stria vascularis (Dclk1) while the others (Ptprd, Grm8, GlyBP, Evi5, Rimbp2, Ank2, Cdh13) in multiple cochlear cell types. In the third step, we tested these 12 genes for replication of association in an independent set of samples from the Caucasus and Central Asia. Nine out of them showed nominally significant association (p<0.05). In particular, 4 were replicated at the same SNP and with the same effect direction while the remaining 5 showed a significant association in a gene-based test. Finally, to look for genotype-phenotype relationship, the audiometric profiles of the three genotypes of the most strongly associated gene variants were analyzed. Seven out of the 9 replicated genes (CDH13, GRM8, ANK2, SLC16A6, ARSG, RIMBP2 and DCLK1) showed an audiometric pattern with differences between different genotypes further supporting their role in hearing function. These data demonstrate the usefulness of this multistep approach in providing new insights into the molecular basis of hearing and may suggest new targets for treatment and prevention of hearing impairment.
Keywords: Adult; Animals; DNA Replication; Gene Expression Profiling; Genome-Wide Association Study; Genotype; Hair Cells, Auditory; Hearing; Humans; Mice; Phenotype; Polymorphism, Single Nucleotide; Stria Vascularis

A general approach for haplotype phasing across the full spectrum of relatedness. - O'Connell, Jared; Gurdasani, Deepti; Delaneau, Olivier; Pirastu, Nicola; Ulivi, Sheila; Cocca, Massimiliano; Traglia, Michela; Huang, Jie; Huffman, Jennifer E; Rudan, Igor; McQuillan, Ruth; Fraser, Ross M; et al. (PLoS Genet, 2014)
Many existing cohorts contain a range of relatedness between genotyped individuals, either by design or by chance. Haplotype estimation in such cohorts is a central step in many downstream analyses. Using genotypes from six cohorts from isolated populations and two cohorts from non-isolated populations, we have investigated the performance of different phasing methods designed for nominally 'unrelated' individuals. We find that SHAPEIT2 produces much lower switch error rates in all cohorts compared to other methods, including those designed specifically for isolated populations. In particular, when large amounts of IBD sharing is present, SHAPEIT2 infers close to perfect haplotypes. Based on these results we have developed a general strategy for phasing cohorts with any level of implicit or explicit relatedness between individuals. First SHAPEIT2 is run ignoring all explicit family information. We then apply a novel HMM method (duoHMM) to combine the SHAPEIT2 haplotypes with any family information to infer the inheritance pattern of each meiosis at all sites across each chromosome. This allows the correction of switch errors, detection of recombination events and genotyping errors. We show that the method detects numbers of recombination events that align very well with expectations based on genetic maps, and that it infers far fewer spurious recombination events than Merlin. The method can also detect genotyping errors and infer recombination events in otherwise uninformative families, such as trios and duos. The detected recombination events can be used in association scans for recombination phenotypes. The method provides a simple and unified approach to haplotype estimation, that will be of interest to researchers in the fields of human, animal and plant genetics.
Keywords: Chromosome Mapping; Cohort Effect; Family; Genotype; Haplotypes; Humans; Models, Genetic; Pedigree; Phenotype; Recombination, Genetic

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genetic landscape of populations along the Silk Road: admixture and migration patterns. - Mezzavilla, Massimo; Vozzi, Diego; Pirastu, Nicola; Girotto, Giorgia; d'Adamo, Pio; Gasparini, Paolo; Colonna, Vincenza (BMC Genet, 2014)
BACKGROUND: The ancient Silk Road has been a trading route between Europe and Central Asia from the 2(nd) century BCE to the 15(th) century CE. While most populations on this route have been characterized, the genetic background of others remains poorly understood, and little is known about past migration patterns. The scientific expedition "Marco Polo" has recently collected genetic and phenotypic data in six regions (Georgia, Armenia, Azerbaijan, Uzbekistan, Kazakhstan, Tajikistan) along the Silk Road to study the genetics of a number of phenotypes. RESULTS: We characterized the genetic structure of these populations within a worldwide context. We observed a West-East subdivision albeit the existence of a genetic component shared within Central Asia and nearby populations from Europe and Near East. We observed a contribution of up to 50% from Europe and Asia to most of the populations that have been analyzed. The contribution from Asia dates back to ~25 generations and is limited to the Eastern Silk Road. Time and direction of this contribution are consistent with the Mongolian expansion era. CONCLUSIONS: We clarified the genetic structure of six populations from Central Asia and suggested a complex pattern of gene flow among them. We provided a map of migration events in time and space and we quantified exchanges among populations. Altogether these novel findings will support the future studies aimed at understanding the genetics of the phenotypes that have been collected during the Marco Polo campaign, they will provide insights into the history of these populations, and they will be useful to reconstruct the developments and events that have shaped modern Eurasians genomes.
Keywords: Asian Continental Ancestry Group; Commonwealth of Independent States; European Continental Ancestry Group; Gene Flow; Homozygote; Human Migration; Humans; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Sequence Analysis, DNA

Genome-wide association study of sexual maturation in males and females highlights a role for body mass and menarche loci in male puberty. - Cousminer, Diana L; Stergiakouli, Evangelia; Berry, Diane J; Ang, Wei; Groen-Blokhuis, Maria M; Körner, Antje; Siitonen, Niina; Ntalla, Ioanna; Marinelli, Marcella; Perry, John R B; Kettunen, Johannes; Jansen, Rick; et al. (Hum Mol Genet, 2014)
Little is known about genes regulating male puberty. Further, while many identified pubertal timing variants associate with age at menarche, a late manifestation of puberty, and body mass, little is known about these variants' relationship to pubertal initiation or tempo. To address these questions, we performed genome-wide association meta-analysis in over 11 000 European samples with data on early pubertal traits, male genital and female breast development, measured by the Tanner scale. We report the first genome-wide significant locus for male sexual development upstream of myocardin-like 2 (MKL2) (P = 8.9 × 10(-9)), a menarche locus tagging a developmental pathway linking earlier puberty with reduced pubertal growth (P = 4.6 × 10(-5)) and short adult stature (p = 7.5 × 10(-6)) in both males and females. Furthermore, our results indicate that a proportion of menarche loci are important for pubertal initiation in both sexes. Consistent with epidemiological correlations between increased prepubertal body mass and earlier pubertal timing in girls, body mass index (BMI)-increasing alleles correlated with earlier breast development. In boys, some BMI-increasing alleles associated with earlier, and others with delayed, sexual development; these genetic results mimic the controversy in epidemiological studies, some of which show opposing correlations between prepubertal BMI and male puberty. Our results contribute to our understanding of the pubertal initiation program in both sexes and indicate that although mechanisms regulating pubertal onset in males and females may largely be shared, the relationship between body mass and pubertal timing in boys may be complex and requires further genetic studies.

A girl with photosensitivity and hepatic steatosis. - Pavan, Matteo; Gortani, Giulia; Rubinato, Elisa; Faletra, Flavio; Pastore, Serena; Ventura, Alessandro (J Pediatr, 2014)
Keywords: Child; Diagnosis, Differential; Fatty Liver; Female; Humans; Photosensitivity Disorders; Protoporphyria, Erythropoietic

Global, regional, and national incidence and mortality for HIV, tuberculosis, and malaria during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Murray, Christopher J L; Ortblad, Katrina F; Guinovart, Caterina; Lim, Stephen S; Wolock, Timothy M; Roberts, D Allen; Dansereau, Emily A; Graetz, Nicholas; Barber, Ryan M; Brown, Jonathan C; Wang, Haidong; Duber, Herbert C; et al. (Lancet, 2014)
BACKGROUND: The Millennium Declaration in 2000 brought special global attention to HIV, tuberculosis, and malaria through the formulation of Millennium Development Goal (MDG) 6. The Global Burden of Disease 2013 study provides a consistent and comprehensive approach to disease estimation for between 1990 and 2013, and an opportunity to assess whether accelerated progress has occured since the Millennium Declaration. METHODS: To estimate incidence and mortality for HIV, we used the UNAIDS Spectrum model appropriately modified based on a systematic review of available studies of mortality with and without antiretroviral therapy (ART). For concentrated epidemics, we calibrated Spectrum models to fit vital registration data corrected for misclassification of HIV deaths. In generalised epidemics, we minimised a loss function to select epidemic curves most consistent with prevalence data and demographic data for all-cause mortality. We analysed counterfactual scenarios for HIV to assess years of life saved through prevention of mother-to-child transmission (PMTCT) and ART. For tuberculosis, we analysed vital registration and verbal autopsy data to estimate mortality using cause of death ensemble modelling. We analysed data for corrected case-notifications, expert opinions on the case-detection rate, prevalence surveys, and estimated cause-specific mortality using Bayesian meta-regression to generate consistent trends in all parameters. We analysed malaria mortality and incidence using an updated cause of death database, a systematic analysis of verbal autopsy validation studies for malaria, and recent studies (2010-13) of incidence, drug resistance, and coverage of insecticide-treated bednets. FINDINGS: Globally in 2013, there were 1·8 million new HIV infections (95% uncertainty interval 1·7 million to 2·1 million), 29·2 million prevalent HIV cases (28·1 to 31·7), and 1·3 million HIV deaths (1·3 to 1·5). At the peak of the epidemic in 2005, HIV caused 1·7 million deaths (1·6 million to 1·9 million). Concentrated epidemics in Latin America and eastern Europe are substantially smaller than previously estimated. Through interventions including PMTCT and ART, 19·1 million life-years (16·6 million to 21·5 million) have been saved, 70·3% (65·4 to 76·1) in developing countries. From 2000 to 2011, the ratio of development assistance for health for HIV to years of life saved through intervention was US$4498 in developing countries. Including in HIV-positive individuals, all-form tuberculosis incidence was 7·5 million (7·4 million to 7·7 million), prevalence was 11·9 million (11·6 million to 12·2 million), and number of deaths was 1·4 million (1·3 million to 1·5 million) in 2013. In the same year and in only individuals who were HIV-negative, all-form tuberculosis incidence was 7·1 million (6·9 million to 7·3 million), prevalence was 11·2 million (10·8 million to 11·6 million), and number of deaths was 1·3 million (1·2 million to 1·4 million). Annualised rates of change (ARC) for incidence, prevalence, and death became negative after 2000. Tuberculosis in HIV-negative individuals disproportionately occurs in men and boys (versus women and girls); 64·0% of cases (63·6 to 64·3) and 64·7% of deaths (60·8 to 70·3). Globally, malaria cases and deaths grew rapidly from 1990 reaching a peak of 232 million cases (143 million to 387 million) in 2003 and 1·2 million deaths (1·1 million to 1·4 million) in 2004. Since 2004, child deaths from malaria in sub-Saharan Africa have decreased by 31·5% (15·7 to 44·1). Outside of Africa, malaria mortality has been steadily decreasing since 1990. INTERPRETATION: Our estimates of the number of people living with HIV are 18·7% smaller than UNAIDS's estimates in 2012. The number of people living with malaria is larger than estimated by WHO. The number of people living with HIV, tuberculosis, or malaria have all decreased since 2000. At the global level, upward trends for malaria and HIV deaths have been reversed and declines in tuberculosis deaths have accelerated. 101 countries (74 of which are developing) still have increasing HIV incidence. Substantial progress since the Millennium Declaration is an encouraging sign of the effect of global action. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Epidemics; Female; Global Health; HIV Infections; Humans; Incidence; Malaria; Male; Mortality; Organizational Objectives; Sex Distribution; Tuberculosis

Global, regional, and national levels and causes of maternal mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Kassebaum, Nicholas J; Bertozzi-Villa, Amelia; Coggeshall, Megan S; Shackelford, Katya A; Steiner, Caitlyn; Heuton, Kyle R; Gonzalez-Medina, Diego; Barber, Ryan; Huynh, Chantal; Dicker, Daniel; Templin, Tara; Wolock, Timothy M; et al. (Lancet, 2014)
BACKGROUND: The fifth Millennium Development Goal (MDG 5) established the goal of a 75% reduction in the maternal mortality ratio (MMR; number of maternal deaths per 100,000 livebirths) between 1990 and 2015. We aimed to measure levels and track trends in maternal mortality, the key causes contributing to maternal death, and timing of maternal death with respect to delivery. METHODS: We used robust statistical methods including the Cause of Death Ensemble model (CODEm) to analyse a database of data for 7065 site-years and estimate the number of maternal deaths from all causes in 188 countries between 1990 and 2013. We estimated the number of pregnancy-related deaths caused by HIV on the basis of a systematic review of the relative risk of dying during pregnancy for HIV-positive women compared with HIV-negative women. We also estimated the fraction of these deaths aggravated by pregnancy on the basis of a systematic review. To estimate the numbers of maternal deaths due to nine different causes, we identified 61 sources from a systematic review and 943 site-years of vital registration data. We also did a systematic review of reports about the timing of maternal death, identifying 142 sources to use in our analysis. We developed estimates for each country for 1990-2013 using Bayesian meta-regression. We estimated 95% uncertainty intervals (UIs) for all values. FINDINGS: 292,982 (95% UI 261,017-327,792) maternal deaths occurred in 2013, compared with 376,034 (343,483-407,574) in 1990. The global annual rate of change in the MMR was -0·3% (-1·1 to 0·6) from 1990 to 2003, and -2·7% (-3·9 to -1·5) from 2003 to 2013, with evidence of continued acceleration. MMRs reduced consistently in south, east, and southeast Asia between 1990 and 2013, but maternal deaths increased in much of sub-Saharan Africa during the 1990s. 2070 (1290-2866) maternal deaths were related to HIV in 2013, 0·4% (0·2-0·6) of the global total. MMR was highest in the oldest age groups in both 1990 and 2013. In 2013, most deaths occurred intrapartum or postpartum. Causes varied by region and between 1990 and 2013. We recorded substantial variation in the MMR by country in 2013, from 956·8 (685·1-1262·8) in South Sudan to 2·4 (1·6-3·6) in Iceland. INTERPRETATION: Global rates of change suggest that only 16 countries will achieve the MDG 5 target by 2015. Accelerated reductions since the Millennium Declaration in 2000 coincide with increased development assistance for maternal, newborn, and child health. Setting of targets and associated interventions for after 2015 will need careful consideration of regions that are making slow progress, such as west and central Africa. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Cause of Death; Female; Global Health; HIV Infections; Humans; Maternal Mortality; Models, Statistical; Organizational Objectives; Pregnancy; Pregnancy Complications, Infectious; Risk Factors; Socioeconomic Factors; Time Factors

Global, regional, and national levels of neonatal, infant, and under-5 mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Wang, Haidong; Liddell, Chelsea A; Coates, Matthew M; Mooney, Meghan D; Levitz, Carly E; Schumacher, Austin E; Apfel, Henry; Iannarone, Marissa; Phillips, Bryan; Lofgren, Katherine T; Sandar, Logan; Dorrington, Rob E; et al. (Lancet, 2014)
BACKGROUND: Remarkable financial and political efforts have been focused on the reduction of child mortality during the past few decades. Timely measurements of levels and trends in under-5 mortality are important to assess progress towards the Millennium Development Goal 4 (MDG 4) target of reduction of child mortality by two thirds from 1990 to 2015, and to identify models of success. METHODS: We generated updated estimates of child mortality in early neonatal (age 0-6 days), late neonatal (7-28 days), postneonatal (29-364 days), childhood (1-4 years), and under-5 (0-4 years) age groups for 188 countries from 1970 to 2013, with more than 29,000 survey, census, vital registration, and sample registration datapoints. We used Gaussian process regression with adjustments for bias and non-sampling error to synthesise the data for under-5 mortality for each country, and a separate model to estimate mortality for more detailed age groups. We used explanatory mixed effects regression models to assess the association between under-5 mortality and income per person, maternal education, HIV child death rates, secular shifts, and other factors. To quantify the contribution of these different factors and birth numbers to the change in numbers of deaths in under-5 age groups from 1990 to 2013, we used Shapley decomposition. We used estimated rates of change between 2000 and 2013 to construct under-5 mortality rate scenarios out to 2030. FINDINGS: We estimated that 6·3 million (95% UI 6·0-6·6) children under-5 died in 2013, a 64% reduction from 17·6 million (17·1-18·1) in 1970. In 2013, child mortality rates ranged from 152·5 per 1000 livebirths (130·6-177·4) in Guinea-Bissau to 2·3 (1·8-2·9) per 1000 in Singapore. The annualised rates of change from 1990 to 2013 ranged from -6·8% to 0·1%. 99 of 188 countries, including 43 of 48 countries in sub-Saharan Africa, had faster decreases in child mortality during 2000-13 than during 1990-2000. In 2013, neonatal deaths accounted for 41·6% of under-5 deaths compared with 37·4% in 1990. Compared with 1990, in 2013, rising numbers of births, especially in sub-Saharan Africa, led to 1·4 million more child deaths, and rising income per person and maternal education led to 0·9 million and 2·2 million fewer deaths, respectively. Changes in secular trends led to 4·2 million fewer deaths. Unexplained factors accounted for only -1% of the change in child deaths. In 30 developing countries, decreases since 2000 have been faster than predicted attributable to income, education, and secular shift alone. INTERPRETATION: Only 27 developing countries are expected to achieve MDG 4. Decreases since 2000 in under-5 mortality rates are accelerating in many developing countries, especially in sub-Saharan Africa. The Millennium Declaration and increased development assistance for health might have been a factor in faster decreases in some developing countries. Without further accelerated progress, many countries in west and central Africa will still have high levels of under-5 mortality in 2030. FUNDING: Bill & Melinda Gates Foundation, US Agency for International Development.
Keywords: Child Mortality; Child, Preschool; Global Health; Humans; Infant; Infant Mortality; Infant, Newborn; Organizational Objectives; Risk Factors; Socioeconomic Factors

Hematopoietic stem cell transplantation effects on spinal cord compression in Hurler. - Ferrara, Giovanna; Maximova, Natalia; Zennaro, Floriana; Gregori, Massimo; Tamaro, Paolo (Pediatr Transplant, 2014)
Hurler syndrome type 1 (MPS-1) is an autosomal recessive lysosomal disorder due to the deficiency of the enzyme alpha-L-iduronidase which is necessary for the degradation of dermatan and heparan sulfate. It is characterized by deposit of glycosaminoglycans in tissues, progressive multisystem dysfunction, and early death. HSCT for children with MPS-I is effective, resulting in increased life expectancy and improvement of clinical parameters. The spinal MRI performed on a female 10 yr old undergoing HSCT at the age of 18 months and receiving ERT revealed a considerable decrease in soft tissue around the tip of odontoid causing a significant reduction in spinal cord compression. In light of this result, we suppose that combined ERT and HSCT are successful in Hurler I disease.
Keywords: Bone Marrow Transplantation; Child; Enzyme Replacement Therapy; Female; Glycosaminoglycans; Hematopoietic Stem Cell Transplantation; Humans; Iduronidase; Magnetic Resonance Imaging; Mucopolysaccharidosis I; Odontoid Process; Spinal Cord Compression; Treatment Outcome

Hereditary hearing loss: a 96 gene targeted sequencing protocol reveals novel alleles in a series of Italian and Qatari patients. - Vozzi, D; Morgan, A; Vuckovic, D; D'Eustacchio, A; Abdulhadi, K; Rubinato, E; Badii, R; Gasparini, P; Girotto, G (Gene, 2014)
Deafness is a really common disorder in humans. It can begin at any age with any degree of severity. Hereditary hearing loss is characterized by a vast genetic heterogeneity with more than 140 loci described in humans but only 65 genes so far identified. Families affected by hearing impairment would have real advantages from an early molecular diagnosis that is of primary relevance in genetic counseling. In this perspective, here we report a family-based approach employing Ion Torrent DNA sequencing technology to analyze coding and UTR regions of 96 genes related to hearing function and loss in a first series of 12 families coming from Italy and Qatar. Using this approach we were able to find the causative gene in 4 out of these 12 families (33%). In particular 5 novel alleles were identified in the following genes LOXHD1, TMPRSS3, TECTA and MYO15A already associated with hearing impairment. Our study confirms the usefulness of a targeted sequencing approach despite larger numbers are required for further validation and for defining a molecular epidemiology picture of hearing loss in these two countries.
Keywords: Alleles; Amino Acid Sequence; Carrier Proteins; Extracellular Matrix Proteins; Female; Genetic Testing; GPI-Linked Proteins; Hearing Loss; Humans; Italy; Male; Membrane Proteins; Molecular Sequence Data; Mutation; Myosins; Neoplasm Proteins; Pedigree; Qatar; Sequence Analysis, DNA; Serine Endopeptidases; Untranslated Regions

HPV and Chlamydia trachomatis co-detection in young asymptomatic women from high incidence area for cervical cancer. - Bellaminutti, Serena; Seraceni, Silva; De Seta, Francesco; Gheit, Tarik; Tommasino, Massimo; Comar, Manola (J Med Virol, 2014)
Chlamydia trachomatis causing chronic inflammatory diseases has investigated as possible human papillomavirus (HPV) cofactor in cervical cancer. The aim of this study is to evaluate the prevalence of Chlamydia trachomatis and HPV co-infection in different cohorts of asymptomatic women from a Northern Italy area at high incidence for cervical cancer. Cervical samples from 441 females were collected from Cervical Cancer Screening Program, Sexually Transmitted Infectious and Assisted Reproductive Technology centres. HPV and Chlamydia trachomatis were detected simultaneously and genotyped using a highly sensitive bead based assay. The overall prevalence of Chlamydia trachomatis was estimated 9.7%, in contrast with the reported national data of 2.3%, and co-infection with HPV was diagnosed in the 17% of the samples. In females ≤ 25 years of age, the infection reached a peak of 22% and co-infection with HPV of 45.8% (P < 0.001). Of note, in young females diagnosed with low grade cervical lesions, no significant difference between Chlamydia trachomatis and HPV distribution was observed, while differently, HPV co-infection was found significantly associated to the presence of intraepithelial lesions when compared to older females (20% vs. 1%; P < 0.001). In this study, the use of a high sensitive molecular technique exhibited higher analytical sensitivity than the referred assays for the diagnosis of Chlamydia trachomatis and HPV co-infection in asymptomatic females, leading to reduction of the potential to identify incorrectly the infection status. An active screening for timely treatment of Chlamydia trachomatis infection is suggested in young females to evaluate a possible decrease in incidence of pre-cancer intraepithelial lesions.
Keywords: Adolescent; Adult; Age Factors; Cervix Uteri; Chlamydia Infections; Chlamydia trachomatis; Coinfection; Female; Genotype; Humans; Incidence; Italy; Middle Aged; Papillomaviridae; Papillomavirus Infections; Prevalence; Young Adult

Human recombinant lysozyme downregulates advanced glycation endproduct-induced interleukin-6 production and release in an in-vitro model of human proximal tubular epithelial cells. - Gallo, Davide; Cocchietto, Moreno; Masat, Elisa; Agostinis, Chiara; Harei, Elisa; Veronesi, Paolo; Sava, Gianni (Exp Biol Med (Maywood), 2014)
Diabetic nephropathy is the leading cause of chronic renal disease and one of the major causes of cardiovascular mortality. Evidence suggests that its progression is due to the chronic hyperglycemia consequent to the production and accumulation of advanced glycation endproducts (AGEs). Lysozyme was shown to posses AGE-sequestering properties and the capacity to reduce the severity of the early stage manifestations of the diabetic nephropathy. This study was aimed to contribute to the understanding the molecular mechanisms of lysozyme effectiveness in the diabetic nephropathy, using an in-vitro cellular model, represented by the HK-2 cells, human proximal tubular epithelial cells. Lysozyme significantly reduced the AGE-induced IL-6 mRNA and an ELISA assay showed also a decreased release of the functional protein with a dose-dependent trend. In addition, lysozyme prevented macrophage recruitment, suggesting its capacity to elicit an anti-inflammatory action. We may conclude that the protective action of lysozyme on the nephrotoxic effects of AGE may depend, at least in part, on its ability to prevent the production and release of inflammatory mediators, such as IL-6 and to reduce macrophage recruitment in the inflammatory sites.
Keywords: Cell Line; Cell Movement; Cell Survival; Chemokine CX3CL1; Diabetic Nephropathies; Down-Regulation; Epithelial Cells; Glycosylation End Products, Advanced; Humans; Inflammation Mediators; Interleukin-18; Interleukin-6; Kidney Tubules, Proximal; Macrophage Activation; Macrophages; Muramidase; Recombinant Proteins; RNA, Messenger; Tumor Necrosis Factor-alpha; U937 Cells

Immunomodulation mediated by a herbal syrup containing a standardized Echinacea root extract: a pilot study in healthy human subjects on cytokine gene expression. - Dapas, B; Dall'Acqua, S; Bulla, R; Agostinis, C; Perissutti, B; Invernizzi, S; Grassi, G; Voinovich, D (Phytomedicine, 2014)
In this study, the immunomodulatory effect of a triply standardized Echinacea angustifolia root extract (Polinacea(®)) was evaluated in 10 healthy subjects. Ten ml of syrup containing one hundred mg of extract (corresponding to 4.7 mg of Echinacoside and 8.0mg of a high molecular weight-20,000 Da- polysaccharide) were administered as a herbal syrup once a day for one month. The immunomodulatory effect was evaluated before and after herbal syrup administration evaluating the expression levels of the cytokines IL-2, IL-8, IL-6 and TNF-α. Cytokine expression was studied in lympho-monocytes and in plasma samples measuring the mRNA and protein levels, respectively. The results were analysed by ANOVA and non-parametric Friedman rank sum tests; when possible it was adopted a pair-wise comparisons at different post-treatment times, using the paired t-tests with Holm correction. The correlation between the variations of cytokine plasma levels and the respective mRNA was carried out using a linear regression model. In lympho-monocytes our data indicate the up-regulation of the mRNA levels of IL-2 and IL-8 and the down regulation of the mRNA levels of the pro-inflammatory cytokines TNF-α and IL6. The differential regulation was maximal after 14 days of treatment. IL-2 up-regulation and IL-6 down-regulation were also confirmed at the protein level in plasma. Finally, the up-regulation of the mRNA of IL-2/IL-8 and the down-regulation of IL-6 positively correlated with the protein levels detected in the plasma. In conclusion, this pilot study suggests a relevant role for the standardized Echinacea angustifolia root extract in the control of cytokine expression. This first demonstration of the immuno-modulating activity of Echinacea angustifolia root extract in the healthy subject, supports at least in part the common use of such products as health promoting supplement.
Keywords: Adult; Cytokines; Down-Regulation; Echinacea; Female; Glycosides; Healthy Volunteers; Humans; Immunomodulation; Interleukin-2; Interleukin-6; Interleukin-8; Lymphocytes; Male; Middle Aged; Monocytes; Pilot Projects; Plant Extracts; Plant Roots; Tumor Necrosis Factor-alpha

Inhibition of mesenchymal stromal cells by pre-activated lymphocytes and their culture media. - Valencic, Erica; Loganes, Claudia; Cesana, Stefania; Piscianz, Elisa; Gaipa, Giuseppe; Biagi, Ettore; Tommasini, Alberto (Stem Cell Res Ther, 2014)
INTRODUCTION: Despite having a proven immunosuppressive potential in vitro, human mesenchymal stromal cells (MSCs) are reported to display variable efficacy in vivo and, in fact, their proven benefit in the clinical practice is still limited and controversial. METHODS: The interplay between clinical grade MSCs and pre-activated donor lymphocytes or selected lymphocyte subsets was studied in vitro. The kinetics of MSC growth and viability was evaluated by adhesion-dependent changes of culture plate impedance and biochemically by a colorimetric assay. Activation of natural killer (NK) cells was assessed as well, using a flow cytometry assay. RESULTS: A strong inhibition of MSC growth was rapidly induced by the addition of pre-activated lymphocytes but not of resting lymphocytes. Inhibition seems not to be attributable to a single cell population, as similar results can be obtained by depleting NK cells or by using either selected CD4+ or CD8+ lymphocytes. In addition, conditioned medium (CM) from activated lymphocytes was able to inhibit MSC growth in a dose-dependent manner. Furthermore, licensing with IFN-γ partially protected MSCs from pre-activated lymphocytes but not from their CM. These results suggest an inhibitory role of lymphocyte-activation-derived substances. However, the identification of a single molecule responsible for MSC inhibition remained elusive, even if preliminary experiments showed that ATP and, to a lesser extent, TNF-α might play a role. CONCLUSIONS: These results suggest that survival of MSCs can be affected by soluble mediators released by activated lymphocytes. Thus it can be hypothesized that MSC immunosuppressive action in vivo could be impaired by ongoing immune activation through the release of inflammatory mediators.
Keywords: CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Cell Proliferation; Cell Survival; Cells, Cultured; Coculture Techniques; Culture Media, Conditioned; Cytokines; Humans; Killer Cells, Natural; Lymphocyte Activation; Mesenchymal Stromal Cells

Insight into genetic determinants of resting heart rate. - Mezzavilla, Massimo; Iorio, Annamaria; Bobbo, Marco; D'Eustacchio, Angela; Merlo, Marco; Gasparini, Paolo; Ulivi, Sheila; Sinagra, Gianfranco (Gene, 2014)
BACKGROUND: Recent studies suggested that resting heart rate (RHR) might be an independent predictor of cardiovascular mortality and morbidity. Nonetheless, the interrelation between RHR and cardiovascular diseases is not clear. In order to resolve this puzzle, the importance of genetic determinants of RHR has been recently suggested, but it needs to be further investigated. OBJECTIVE: The aim of this study was to estimate the contribution of common genetic variations on RHR using Genome Wide Association Study. METHODS: We performed a Genome Wide Association Study in an isolated population cohort of 1737 individuals, the Italian Network on Genetic Isolates - Friuli Venezia Giulia (INGI-FVG). Moreover, a haplotype analysis was performed. A regression tree analysis was run to highlight the effect of each haplotype combination on the phenotype. RESULTS: A significant level of association (p<5 × 10(-8)) was detected for Single Nucleotide Polymorphisms (SNPs) in two genes expressed in the heart: MAML1 and CANX. Founding that the three different variants of the haplotype, which encompass both genes, yielded a phenotypic correlation. Indeed, a haplotype in homozygosity is significantly associated with the lower quartile of RHR (RHR ≤ 58 bpm). Moreover no significant association was found between cardiovascular risk factors and the different haplotype combinations. CONCLUSION: Mastermind-like 1 and Calnexin were found to be associated with RHR. We demonstrated a relation between a haplotype and the lower quartile of RHR in our populations. Our findings highlight that genetic determinants of RHR may be implicated in determining cardiovascular diseases and could allow a better risk stratification.
Keywords: Calnexin; Cardiovascular Diseases; DNA-Binding Proteins; Female; Genome-Wide Association Study; Haplotypes; Heart Rate; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Transcription Factors

Intestinal-mucosa anti-transglutaminase antibody assays to test for genetic gluten intolerance. - Quaglia, Sara; De Leo, Luigina; Ziberna, Fabiana; Vatta, Serena; Villanacci, Vincenzo; Granzotto, Marilena; Petix, Vincenzo; Martelossi, Stefano; Di Leo, Grazia; Torelli, Lucio; Not, Tarcisio (Cell Mol Immunol, 2014)
Keywords: Celiac Disease; Cell Surface Display Techniques; Child; Diet, Gluten-Free; Disease Progression; Early Diagnosis; Female; Follow-Up Studies; HLA-DQ Antigens; Humans; Immunoassay; Immunoglobulin A; Intestinal Mucosa; Male; Prospective Studies; Transglutaminases

Juvenile stroke in combined syndrome of hereditary hemorrhagic telangiectasia and juvenile polyposis. - Mazzucco, Sara; Benini, Luigi; Gallione, Carol; d'Adamo, Pio; Girelli, Domenico (Neurol Sci, 2014)
Keywords: Adult; Arteriovenous Malformations; Brain Ischemia; Chromosomes, Human, Pair 18; Echocardiography, Transesophageal; Embolism, Paradoxical; Embolization, Therapeutic; Epistaxis; Family Health; Humans; Intestinal Polyposis; Intracranial Embolism; Introns; Lod Score; Male; Pulmonary Artery; Smad4 Protein; Telangiectasia, Hereditary Hemorrhagic; Thalamus; Ultrasonography, Doppler, Transcranial

Long-term follow-up in children with benign convulsions associated with gastroenteritis. - Verrotti, Alberto; Moavero, Romina; Vigevano, Federico; Cantonetti, Laura; Guerra, Azzurra; Spezia, Elisabetta; Tricarico, Antonella; Nanni, Giuliana; Agostinelli, Sergio; Chiarelli, Francesco; Parisi, Pasquale; Capovilla, Giuseppe; et al. (Eur J Paediatr Neurol, 2014)
BACKGROUND: The outcome of benign convulsions associated with gastroenteritis (CwG) has generally been reported as being excellent. However, these data need to be confirmed in studies with longer follow-up evaluations. AIM: To assess the long-term neurological outcome of a large sample of children presenting with CwG. METHODS: We reviewed clinical features of 81 subjects presenting with CwG (1994-2010) from three different Italian centers with a follow-up period of at least 3 years. RESULTS: Follow-up period ranged from 39 months to 15 years (mean 9.8 years). Neurological examination and cognitive level at the last evaluation were normal in all the patients. A mild attention deficit was detected in three cases (3.7%). Fourteen children (17.3%) received chronic anti-epileptic therapy. Interictal EEG abnormalities detected at onset in 20 patients (24.7%) reverted to normal. Transient EEG epileptiform abnormalities were detected in other three cases (3.7%), and a transient photosensitivity in one (1.2%). No recurrence of CwG was observed. Three patients (3.7%) presented with a febrile seizure and two (2.5%) with an unprovoked seizure, but none developed epilepsy. CONCLUSIONS: The long-term evaluation of children with CwG confirms the excellent prognosis of this condition, with normal psychomotor development and low risk of relapse and of subsequent epilepsy.
Keywords: Adolescent; Anticonvulsants; Attention Deficit Disorder with Hyperactivity; Child; Child, Preschool; Electroencephalography; Epilepsy; Female; Gastroenteritis; Humans; Longitudinal Studies; Male; Neurologic Examination; Retrospective Studies

Medical treatments for endometriosis-associated pelvic pain. - Zito, Gabriella; Luppi, Stefania; Giolo, Elena; Martinelli, Monica; Venturin, Irene; Di Lorenzo, Giovanni; Ricci, Giuseppe (Biomed Res Int, 2014)
The main sequelae of endometriosis are represented by infertility and chronic pelvic pain. Chronic pelvic pain causes disability and distress with a very high economic impact. In the last decades, an impressive amount of pharmacological agents have been tested for the treatment of endometriosis-associated pelvic pain. However, only a few of these have been introduced into clinical practice. Following the results of the controlled studies available, to date, the first-line treatment for endometriosis associated pain is still represented by oral contraceptives used continuously. Progestins represent an acceptable alternative. In women with rectovaginal lesions or colorectal endometriosis, norethisterone acetate at low dosage should be preferred. GnRH analogues may be used as second-line treatment, but significant side effects should be taken into account. Nonsteroidal anti-inflammatory drugs are widely used, but there is inconclusive evidence for their efficacy in relieving endometriosis-associated pelvic pain. Other agents such as GnRH antagonist, aromatase inhibitors, immunomodulators, selective progesterone receptor modulators, and histone deacetylase inhibitors seem to be very promising, but there is not enough evidence to support their introduction into routine clinical practice. Some other agents, such as peroxisome proliferator activated receptors-γ ligands, antiangiogenic agents, and melatonin have been proven to be efficacious in animal studies, but they have not yet been tested in clinical studies.
Keywords: Endometriosis; Female; Gonadotropin-Releasing Hormone; Histone Deacetylase Inhibitors; Hormone Antagonists; Humans; Pain Management; Pelvic Pain; Progestins

Mevalonate kinase deficiency and IBD: shared genetic background. - Bianco, Anna Monica; Girardelli, Martina; Vozzi, Diego; Crovella, Sergio; Kleiner, Giulio; Marcuzzi, Annalisa (Gut, 2014)
Keywords: Genetic Predisposition to Disease; Humans; Inflammatory Bowel Diseases

Midline 1 directs lytic granule exocytosis and cytotoxicity of mouse killer T cells. - Boding, Lasse; Hansen, Ann K; Meroni, Germana; Johansen, Bo B; Braunstein, Thomas H; Bonefeld, Charlotte M; Kongsbak, Martin; Jensen, Benjamin A H; Woetmann, Anders; Thomsen, Allan R; Odum, Niels; von Essen, Marina R; et al. (Eur J Immunol, 2014)
Midline 1 (MID1) is a microtubule-associated ubiquitin ligase that regulates protein phosphatase 2A activity. Loss-of-function mutations in MID1 lead to the X-linked Opitz G/BBB syndrome characterized by defective midline development during embryogenesis. Here, we show that MID1 is strongly upregulated in murine cytotoxic lymphocytes (CTLs), and that it controls TCR signaling, centrosome trafficking, and exocytosis of lytic granules. In accordance, we find that the killing capacity of MID1(-/-) CTLs is impaired. Transfection of MID1 into MID1(-/-) CTLs completely rescued lytic granule exocytosis, and vice versa, knockdown of MID1 inhibited exocytosis of lytic granules in WT CTLs, cementing a central role for MID1 in the regulation of granule exocytosis. Thus, MID1 orchestrates multiple events in CTL responses, adding a novel level of regulation to CTL activation and cytotoxicity.
Keywords: Animals; Blotting, Western; Cytotoxicity, Immunologic; Exocytosis; Flow Cytometry; Mice; Mice, Knockout; Mice, Transgenic; Proteins; Reverse Transcriptase Polymerase Chain Reaction; Secretory Vesicles; T-Lymphocytes, Cytotoxic

Modulation of circulating cytokine-chemokine profile in patients affected by chronic venous insufficiency undergoing surgical hemodynamic correction. - Tisato, Veronica; Zauli, Giorgio; Gianesini, Sergio; Menegatti, Erica; Brunelli, Laura; Manfredini, Roberto; Zamboni, Paolo; Secchiero, Paola (J Immunol Res, 2014)
The expression of proinflammatory cytokines/chemokines has been reported in in vitro/ex vivo settings of chronic venous insufficiency (CVI), but the identification of circulating mediators that might be associated with altered hemodynamic forces or might represent innovative biomarkers is still missing. In this study, the circulating levels of 31 cytokines/chemokines involved in inflammatory/angiogenic processes were analysed in (i) CVI patients at baseline before surgical hemody namic correction, (ii) healthy subjects, and (iii) CVI patients after surgery. In a subgroup of CVI patients, in whom the baseline levels of cytokines/chemokines were analyzed in paired blood samples obtained from varicose vein and forearm vein, EGF, PDGF, and RANTES were increased at the varicose vein site as compared to the general circulation. Moreover, while at baseline, CVI patients showed increased levels of 14 cytokines/chemokines as compared to healthy subjects, 6 months after surgery, 11 cytokines/chemokines levels were significantly reduced in the treated CVI patients as compared to the CVI patients before surgery. Of note, a patient who exhibited recurrence of the disease 6 months after surgery, showed higher levels of EGF, PDGF, and RANTES compared to nonrecurrent patients, highlighting the potential role of the EGF/PDGF/RANTES triad as sensitive biomarkers in the context of CVI.
Keywords: Adult; Aged; Chemokines; Chronic Disease; Cytokines; Female; Hemodynamics; Humans; Male; Middle Aged; Saphenous Vein; Varicose Veins; Venous Insufficiency

Molecular analysis of Fanconi anemia: the experience of the Bone Marrow Failure Study Group of the Italian Association of Pediatric Onco-Hematology. - De Rocco, Daniela; Bottega, Roberta; Cappelli, Enrico; Cavani, Simona; Criscuolo, Maria; Nicchia, Elena; Corsolini, Fabio; Greco, Chiara; Borriello, Adriana; Svahn, Johanna; Pillon, Marta; Mecucci, Cristina; et al. (Haematologica, 2014)
Fanconi anemia is an inherited disease characterized by congenital malformations, pancytopenia, cancer predisposition, and sensitivity to cross-linking agents. The molecular diagnosis of Fanconi anemia is relatively complex for several aspects including genetic heterogeneity with mutations in at least 16 different genes. In this paper, we report the mutations identified in 100 unrelated probands enrolled into the National Network of the Italian Association of Pediatric Hematoly and Oncology. In approximately half of these cases, mutational screening was carried out after retroviral complementation analyses or protein analysis. In the other half, the analysis was performed on the most frequently mutated genes or using a next generation sequencing approach. We identified 108 distinct variants of the FANCA, FANCG, FANCC, FANCD2, and FANCB genes in 85, 9, 3, 2, and 1 families, respectively. Despite the relatively high number of private mutations, 45 of which are novel Fanconi anemia alleles, 26% of the FANCA alleles are due to 5 distinct mutations. Most of the mutations are large genomic deletions and nonsense or frameshift mutations, although we identified a series of missense mutations, whose pathogenetic role was not always certain. The molecular diagnosis of Fanconi anemia is still a tiered procedure that requires identifying candidate genes to avoid useless sequencing. Introduction of next generation sequencing strategies will greatly improve the diagnostic process, allowing a rapid analysis of all the genes.
Keywords: Amino Acid Substitution; Cell Line; Cohort Studies; Computational Biology; Databases, Nucleic Acid; Fanconi Anemia; Fanconi Anemia Complementation Group Proteins; Founder Effect; Genotype; Humans; Italy; Mosaicism; Mutation; Polymorphism, Single Nucleotide

Mutations of cytochrome c identified in patients with thrombocytopenia THC4 affect both apoptosis and cellular bioenergetics. - De Rocco, Daniela; Cerqua, Cristina; Goffrini, Paola; Russo, Giovanna; Pastore, Annalisa; Meloni, Francesca; Nicchia, Elena; Moraes, Carlos T; Pecci, Alessandro; Salviati, Leonardo; Savoia, Anna (Biochim Biophys Acta, 2014)
Inherited thrombocytopenias are heterogeneous diseases caused by at least 20 genes playing different role in the processes of megakaryopoiesis and platelet production. Some forms, such as thrombocytopenia 4 (THC4), are very rare and not well characterized. THC4 is an autosomal dominant mild thrombocytopenia described in only one large family from New Zealand and due to a mutation (G41S) of the somatic isoform of the cytochrome c (CYCS) gene. We report a novel CYCS mutation (Y48H) in patients from an Italian family. Similar to individuals carrying G41S, they have platelets of normal size and morphology, which are only partially reduced in number, but no prolonged bleeding episodes. In order to determine the pathogenetic consequences of Y48H, we studied the effects of the two CYCS mutations in yeast and mouse cellular models. In both cases, we found reduction of respiratory level and increased apoptotic rate, supporting the pathogenetic role of CYCS in thrombocytopenia.
Keywords: Amino Acid Sequence; Animals; Apoptosis; Base Sequence; Cells, Cultured; Child, Preschool; Cytochromes c; DNA Mutational Analysis; Embryo, Mammalian; Energy Metabolism; Family Health; Female; Fibroblasts; Humans; Lung; Male; Mice; Molecular Sequence Data; Mutation, Missense; Oxygen Consumption; Pedigree; Saccharomyces cerevisiae; Sequence Homology, Amino Acid; Thrombocytopenia

MYH9-related disease: a novel prognostic model to predict the clinical evolution of the disease based on genotype-phenotype correlations. - Pecci, Alessandro; Klersy, Catherine; Gresele, Paolo; Lee, Kieran J D; De Rocco, Daniela; Bozzi, Valeria; Russo, Giovanna; Heller, Paula G; Loffredo, Giuseppe; Ballmaier, Matthias; Fabris, Fabrizio; Beggiato, Eloise; et al. (Hum Mutat, 2014)
MYH9-related disease (MYH9-RD) is a rare autosomal-dominant disorder caused by mutations in the gene for nonmuscle myosin heavy chain IIA (NMMHC-IIA). MYH9-RD is characterized by a considerable variability in clinical evolution: patients present at birth with only thrombocytopenia, but some of them subsequently develop sensorineural deafness, cataract, and/or nephropathy often leading to end-stage renal disease (ESRD). We searched for genotype-phenotype correlations in the largest series of consecutive MYH9-RD patients collected so far (255 cases from 121 families). Association of genotypes with noncongenital features was assessed by a generalized linear regression model. The analysis defined disease evolution associated to seven different MYH9 genotypes that are responsible for 85% of MYH9-RD cases. Mutations hitting residue R702 demonstrated a complete penetrance for early-onset ESRD and deafness. The p.D1424H substitution associated with high risk of developing all the noncongenital manifestations of disease. Mutations hitting a distinct hydrophobic seam in the NMMHC-IIA head domain or substitutions at R1165 associated with high risk of deafness but low risk of nephropathy or cataract. Patients with p.E1841K, p.D1424N, and C-terminal deletions had low risk of noncongenital defects. These findings are essential to patients' clinical management and genetic counseling and are discussed in view of molecular pathogenesis of MYH9-RD.
Keywords: Adult; Age of Onset; Amino Acid Substitution; Cataract; Female; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Linear Models; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Risk Factors; Thrombocytopenia

Next generation sequencing in nonsyndromic intellectual disability: from a negative molecular karyotype to a possible causative mutation detection. - Athanasakis, Emmanouil; Licastro, Danilo; Faletra, Flavio; Fabretto, Antonella; Dipresa, Savina; Vozzi, Diego; Morgan, Anna; d'Adamo, Adamo P; Pecile, Vanna; Biarnés, Xevi; Gasparini, Paolo (Am J Med Genet A, 2014)
The identification of causes underlying intellectual disability (ID) is one of the most demanding challenges for clinical Geneticists and Researchers. Despite molecular diagnostics improvements, the vast majority of patients still remain without genetic diagnosis. Here, we report the results obtained using Whole Exome and Target Sequencing on nine patients affected by isolated ID without pathological copy number variations, which were accurately selected from an initial cohort of 236 patients. Three patterns of inheritance were used to search for: (1) de novo, (2) X-linked, and (3) autosomal recessive variants. In three of the nine proband-parent trios analyzed, we identified and validated two de novo and one X-linked potentially causative mutations located in three ID-related genes. We proposed three genes as ID candidate, carrying one de novo and three X-linked mutations. Overall, this systematic proband-parent trio approach using next generation sequencing could explain a consistent percentage of patients with isolated ID, thus increasing our knowledge on the molecular bases of this disease and opening new perspectives for a better diagnosis, counseling, and treatment.
Keywords: Computational Biology; Exome; Female; Genes, Recessive; Genes, X-Linked; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Intellectual Disability; Karyotype; Male; Mutation; Workflow

NF-κB pathways in hematological malignancies. - Gasparini, Chiara; Celeghini, Claudio; Monasta, Lorenzo; Zauli, Giorgio (Cell Mol Life Sci, 2014)
The nuclear factor κB or NF-κB transcription factor family plays a key role in several cellular functions, i.e. inflammation, apoptosis, cell survival, proliferation, angiogenesis, and innate and acquired immunity. The constitutive activation of NF-κB is typical of most malignancies and plays a major role in tumorigenesis. In this review, we describe NF-κB and its two pathways: the canonical pathway (RelA/p50) and the non-canonical pathway (RelB/p50 or RelB/p52). We then consider the role of the NF-κB subunits in the development and functional activity of B cells, T cells, macrophages and dendritic cells, which are the targets of hematological malignancies. The relevance of the two pathways is described in normal B and T cells and in hematological malignancies, acute and chronic leukemias (ALL, AML, CLL, CML), B lymphomas (DLBCLs, Hodgkin's lymphoma), T lymphomas (ATLL, ALCL) and multiple myeloma. We describe the interaction of NF-κB with the apoptotic pathways induced by TRAIL and the transcription factor p53. Finally, we discuss therapeutic anti-tumoral approaches as mono-therapies or combination therapies aimed to block NF-κB activity and to induce apoptosis (PARAs and Nutlin-3).
Keywords: Antineoplastic Agents; B-Lymphocytes; Carcinogenesis; Dendritic Cells; Gene Expression Regulation, Neoplastic; Hematologic Neoplasms; Humans; Imidazoles; Macrophages; NF-kappa B; Piperazines; Signal Transduction; T-Lymphocytes; TNF-Related Apoptosis-Inducing Ligand; Transcription Factor RelA; Transcription Factor RelB; Tumor Suppressor Protein p53

NLRP3 polymorphism is associated with protection against human T-lymphotropic virus 1 infection. - Kamada, Anselmo Jiro; Pontillo, Alessandra; Guimarães, Rafael Lima; Loureiro, Paula; Crovella, Sergio; Brandão, Lucas André Cavalcanti (Mem Inst Oswaldo Cruz, 2014)
Inter-individual heterogeneity in the response to human T-lymphotropic virus 1 (HTLV-1) infection has been partially attributed to host genetic background. The antiviral activity of the inflammasome cytoplasmic complex recognises viral molecular patterns and regulates immune responses via the activation of interleukin (IL)-1 family (IL-1, IL-18 and IL-33) members. The association between polymorphisms in the inflammasome receptors NLRP1 and NLRP3 and HTLV-1 infection was evaluated in a northeastern Brazilian population (84 HTLV-1 carriers and 155 healthy controls). NLRP3 rs10754558 G/G was associated with protection against HTLV-1 infection (p = 0.012; odds ratio = 0.37). rs10754558 affects NLRP3 mRNA stability; therefore, our results suggest that higher NLRP3 expression may augment first-line defences, leading to the effective protection against HTLV-1 infection.
Keywords: Adult; Brazil; Carrier Proteins; Female; Genetic Predisposition to Disease; HTLV-I Infections; Human T-lymphotropic virus 1; Humans; Inflammasomes; Interleukin-1; Male; Middle Aged; Polymorphism, Single Nucleotide; Protective Factors

A non-complement-fixing antibody to β2 glycoprotein I as a novel therapy for antiphospholipid syndrome. - Agostinis, Chiara; Durigutto, Paolo; Sblattero, Daniele; Borghi, Maria O; Grossi, Claudia; Guida, Filomena; Bulla, Roberta; Macor, Paolo; Pregnolato, Francesca; Meroni, Pier Luigi; Tedesco, Francesco (Blood, 2014)
A single-chain fragment variable (scFv) recognizing β2-glycoprotein 1 (β2GPI) from humans and other species was isolated from a human phage display library and engineered to contain an IgG1 hinge-CH2-CH3 domain. The scFv-Fc directed against β2GPI domain I-induced thrombosis and fetal loss, thus mimicking the effect of antibodies from patients with antiphospholipid syndrome (APS). Complement is involved in the biological effect of anti-β2GPI scFv-Fc, as demonstrated by its ability to promote in vitro and in vivo complement deposition and the failure to induce vascular thrombosis in C6-deficient rats and fetal loss in C5-depleted mice. A critical role for complement was also supported by the inability of the CH2-deleted scFv-Fc to cause vessel occlusion and pregnancy failure. This antibody prevented the pathological effects of anti-β2GPI antibodies from APS patients and displaced β2GPI-bound patient antibodies. The CH2-deleted antibody represents an innovative approach potentially useful to treat APS patients refractory to standard therapy.
Keywords: Abortion, Spontaneous; Animals; Antibodies, Monoclonal; Antiphospholipid Syndrome; Autoantigens; beta 2-Glycoprotein I; Complement Activation; Complement System Proteins; Human Umbilical Vein Endothelial Cells; Humans; Immunoglobulin G; Male; Mice; Protein Binding; Rats; Recombinant Proteins; Single-Chain Antibodies; Thrombosis; Trophoblasts

A novel deletion mutation involving TMEM38B in a patient with autosomal recessive osteogenesis imperfecta. - Rubinato, Elisa; Morgan, Anna; D'Eustacchio, Angela; Pecile, Vanna; Gortani, Giulia; Gasparini, Paolo; Faletra, Flavio (Gene, 2014)
Osteogenesis imperfecta (OI) is a hereditary bone disease characterized by decreased bone density and multiple fractures, usually inherited in an autosomal dominant manner. Several gene encoding proteins related to collagen metabolism have been described in some cases of autosomal recessive OI (including CRTAP, LEPRE1, PPIB, FKBP65, SERPINF1, BMP1, WNT1, FKBP10). Recently, TMEM38B, a gene that encodes TRIC-B, a monovalent cation-specific channel involved in calcium flux from intracellular stores and in cell differentiation, has been associated with autosomal recessive OI. Here, we describe the second deletion-mutation involving the TMEM38B gene in an 11 year-old Albanian female with a clinical phenotype of OI, born to parents with suspected consanguinity. SNP array analysis revealed a homozygous region larger than 2 Mb that overlapped with the TMEM38B locus and was characterized by a 35 kb homozygous deletion involving exons 1 and 2 of TMEM38B gene.
Keywords: Child; Chromosomes, Human, Pair 19; DNA Mutational Analysis; Exons; Female; Genes, Recessive; Homozygote; Humans; Ion Channels; Osteogenesis Imperfecta; Sequence Deletion

Novel missense mutation in the NOD2 gene in a patient with early onset ulcerative colitis: causal or chance association? - Girardelli, Martina; Vuch, Josef; Tommasini, Alberto; Crovella, Sergio; Bianco, Anna Monica (Int J Mol Sci, 2014)
Deregulated immune response to gut microflora in genetically predisposed individuals is typical for inflammatory bowel diseases. It is reasonable to assume that genetic association with the disease will be more pronounced in subjects with early onset than adult onset. The nucleotide-binding oligomerization domain containing-2 gene, commonly involved in multifactorial risk of Crohn's disease, and interleukin 10 receptor genes, associated with rare forms of early onset inflammatory bowel diseases, were sequenced in an early onset patient. We identified a novel variant in the NOD2 gene (c.2857A > G p.K953E) and two already described missense variants in the IL10RA gene (S159G and G351R). The new NOD2 missense variant was examined in silico with two online bioinformatics tools to predict the potentially deleterious effects of the mutation. Although cumulative effect of these variations in the early onset of the disease can be only hypothesized, we demonstrated that family information and in silico studies can be used to predict association with the disease.
Keywords: Age of Onset; Amino Acid Sequence; Base Sequence; Child; Colitis, Ulcerative; Crohn Disease; DNA Mutational Analysis; Genetic Predisposition to Disease; Genotype; Humans; Interleukin-10 Receptor alpha Subunit; Interleukin-10 Receptor beta Subunit; Molecular Sequence Data; Mutation, Missense; Nod2 Signaling Adaptor Protein; Polymorphism, Single Nucleotide; Risk Factors; Sequence Homology, Amino Acid

A novel P2RX2 mutation in an Italian family affected by autosomal dominant nonsyndromic hearing loss. - Faletra, Flavio; Girotto, Giorgia; d'Adamo, Adamo Pio; Vozzi, Diego; Morgan, Anna; Gasparini, Paolo (Gene, 2014)
Hereditary hearing loss (HHL) is a common disorder accounting for at least 60% of prelingual deafness. It is characterized by a large genetic heterogeneity, and despite the presence of a major gene, still there is a need to search for new causative mutations/genes. Very recently, a mutation within ATP-gated P2X(2) receptor (ligand-gated ion channel, purinergic receptor 2) gene (P2RX2) at DNFA41 locus has been reported leading to a bilateral and symmetrical sensorineural non-syndromic autosomal dominant HHL in two Chinese families. We performed a linkage analysis in a large Italian family with a dominant pattern of inheritance showing a significant 3.31 LOD score in a 2Mb region overlapping with the DNFA41 locus. Molecular analyses of P2RX2 identified a novel missense mutation (p.Gly353Arg) affecting a residue highly conserved across species. Visual inspection of the protein structure as obtained from comparative modeling suggests that substitution of the small glycine residue with a charged bulky residue such as an arginine that is close to the 'neck' of the region responsible for ion channel gating should have a high energetic cost and should lead to a severely destabilization of the fold. The identification of a second most likely causative mutation in P2RX2 gene further supports the possible role of this gene in causing autosomal dominant HHL.
Keywords: Amino Acid Sequence; Deafness; European Continental Ancestry Group; Female; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Male; Molecular Sequence Data; Mutation, Missense; Pedigree; Receptors, Purinergic P2X2

Paracetamol: a focus for the general pediatrician. - Marzuillo, Pierluigi; Guarino, Stefano; Barbi, Egidio (Eur J Pediatr, 2014)
UNLABELLED: Paracetamol (acetaminophen) is one of the most popular and widely used drugs for the treatment of pain and fever in children. This drug has multiple mechanisms of action, but its pharmacodynamic is still not well known. The central nervous system is the main site of action and it mirrors the paracetamol effect compartment. The recommended dosages and routes of administration should be different whether paracetamol is used for the treatment of pain or fever. For example, the rectal route, while being efficacious for the treatment of fever, should be avoided in pain management. Paracetamol is a safe drug, but some clinical conditions and concomitant drugs, which are frequent in clinical practice, may increase the risk of paracetamol toxicity. Therefore, it is important to optimize its administration to avoid overdoses and maximize its effect. The principal mediator of the paracetamol toxicity is the N-acetyl-p-benzo-quinone imine (NAPQI), a toxic product of the paracetamol metabolism, which could bind cysteine groups on proteins forming paracetamol-protein adduct in the liver. CONCLUSION: Although frequently prescribed, the concept of "effect compartment concentration" and the possible co-factors that could cause toxicity at recommended doses are not familiar to all pediatricians and general practitioners. We reviewed the literature concerning paracetamol mechanisms of action, we highlighted some relevant pharmacodynamic concepts for clinical practice, and we summarized the possible risk factors for toxicity at therapeutic dosages.
Keywords: Acetaminophen; Analgesics, Non-Narcotic; Child; Drug Overdose; Fever; Humans; Pain; Risk Factors

Parent-of-origin-specific allelic associations among 106 genomic loci for age at menarche. - Perry, John R B; Day, Felix; Elks, Cathy E; Sulem, Patrick; Thompson, Deborah J; Ferreira, Teresa; He, Chunyan; Chasman, Daniel I; Esko, Tõnu; Thorleifsson, Gudmar; Albrecht, Eva; Ang, Wei Q; et al. (Nature, 2014)
Age at menarche is a marker of timing of puberty in females. It varies widely between individuals, is a heritable trait and is associated with risks for obesity, type 2 diabetes, cardiovascular disease, breast cancer and all-cause mortality. Studies of rare human disorders of puberty and animal models point to a complex hypothalamic-pituitary-hormonal regulation, but the mechanisms that determine pubertal timing and underlie its links to disease risk remain unclear. Here, using genome-wide and custom-genotyping arrays in up to 182,416 women of European descent from 57 studies, we found robust evidence (P < 5 × 10(-8)) for 123 signals at 106 genomic loci associated with age at menarche. Many loci were associated with other pubertal traits in both sexes, and there was substantial overlap with genes implicated in body mass index and various diseases, including rare disorders of puberty. Menarche signals were enriched in imprinted regions, with three loci (DLK1-WDR25, MKRN3-MAGEL2 and KCNK9) demonstrating parent-of-origin-specific associations concordant with known parental expression patterns. Pathway analyses implicated nuclear hormone receptors, particularly retinoic acid and γ-aminobutyric acid-B2 receptor signalling, among novel mechanisms that regulate pubertal timing in humans. Our findings suggest a genetic architecture involving at least hundreds of common variants in the coordinated timing of the pubertal transition.
Keywords: Adolescent; Age Factors; Alleles; Body Mass Index; Breast Neoplasms; Cardiovascular Diseases; Child; Diabetes Mellitus, Type 2; Europe; Female; Genetic Loci; Genome-Wide Association Study; Genomic Imprinting; Humans; Hypothalamo-Hypophyseal System; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Obesity; Ovary; Parents; Polymorphism, Single Nucleotide; Potassium Channels, Tandem Pore Domain; Proteins; Quantitative Trait Loci; Receptors, GABA-B; Receptors, Retinoic Acid; Ribonucleoproteins

Piccolipiù, a multicenter birth cohort in Italy: protocol of the study. - Farchi, Sara; Forastiere, Francesco; Vecchi Brumatti, Liza; Alviti, Sabrina; Arnofi, Antonio; Bernardini, Tommaso; Bin, Maura; Brescianini, Sonia; Colelli, Valentina; Cotichini, Rodolfo; Culasso, Martina; De Bartolo, Paolo; et al. (BMC Pediatr, 2014)
BACKGROUND: The fetal and infant life are periods of rapid development, characterized by high susceptibility to exposures. Birth cohorts provide unique opportunities to study early-life exposures in association with child development and health, as well as, with longer follow-up, the early life origin of adult diseases. Piccolipiù is an Italian birth cohort recently set up to investigate the effects of environmental exposures, parental conditions and social factors acting during pre-natal and early post-natal life on infant and child health and development. We describe here its main characteristics. METHODS/DESIGN: Piccolipiù is a prospective cohort of expected 3000 newborns, who will be recruiting in six maternity units of five Italian cities (Florence, Rome, Trieste, Turin and Viareggio) since October 2011. Mothers are contacted during pregnancy or at delivery and are offered to participate in the study. Upon acceptance, their newborns are recruited at birth and followed up until at least 18 years of age. At recruitment, the mothers donate a blood sample and complete a baseline questionnaire. Umbilical cord blood, pieces of umbilical cord and heel blood spots are also collected. Postnatal follow-up currently occurs at 6, 12, and 24 months of age using on-line or postal self administered questionnaire; further questionnaires and medical examinations are envisaged. Questionnaires collect information on several factors, including mother's and/or child's environmental exposures, anthropometric measures, reproductive factors, diet, supplements, medical history, cognitive development, mental health and socioeconomic factors. Health promotion materials are also offered to parents. DISCUSSION: Piccolipiù will broaden our understanding of the contribution of early-life factors to infant and child health and development. Several hypotheses on the developmental origins of health can be tested or piloted using the data collected from the Piccolipiù cohort. By pooling these data with those collected by other existing birth cohorts it will be possible to validate previous findings and to study rare exposures and outcomes.
Keywords: Adolescent; Child; Child Development; Child Welfare; Child, Preschool; Cohort Studies; Environmental Exposure; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Socioeconomic Factors

Platelet diameters in inherited thrombocytopenias: analysis of 376 patients with all known disorders. - Noris, Patrizia; Biino, Ginevra; Pecci, Alessandro; Civaschi, Elisa; Savoia, Anna; Seri, Marco; Melazzini, Federica; Loffredo, Giuseppe; Russo, Giovanna; Bozzi, Valeria; Notarangelo, Lucia Dora; Gresele, Paolo; et al. (Blood, 2014)
Abnormalities of platelet size are one of the distinguishing features of inherited thrombocytopenias (ITs), and evaluation of blood films is recommended as an essential step for differential diagnosis of these disorders. Nevertheless, what we presently know about this subject is derived mainly from anecdotal evidence. To improve knowledge in this field, we evaluated platelet size on blood films obtained from 376 patients with all 19 forms of IT identified so far and found that these conditions differ not only in mean platelet diameter, but also in platelet diameter distribution width and the percentage of platelets with increased or reduced diameters. On the basis of these findings, we propose a new classification of ITs according to platelet size. It distinguishes forms with giant platelets, with large platelets, with normal or slightly increased platelet size, and with normal or slightly decreased platelet size. We also measured platelet diameters in 87 patients with immune thrombocytopenia and identified cutoff values for mean platelet diameter and the percentage of platelets with increased or reduced size that have good diagnostic accuracy in differentiating ITs with giant platelets and with normal or slightly decreased platelet size from immune thrombocytopenia and all other forms of IT.
Keywords: Adolescent; Adult; Blood Platelets; Case-Control Studies; Cell Size; Child; Child, Preschool; Diagnosis, Differential; Female; Hearing Loss, Sensorineural; Humans; Infant; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Purpura, Thrombocytopenic, Idiopathic; Thrombocytopenia; Young Adult

A population-based approach to study the impact of PROP perception on food liking in populations along the Silk Road. - Robino, Antonietta; Mezzavilla, Massimo; Pirastu, Nicola; Dognini, Maddalena; Tepper, Beverly J; Gasparini, Paolo (PLoS One, 2014)
Taste is one of the main factors determining food choices. Differences in PROP bitter taste perception have been implicated in individual differences in food preferences and selection. The present study examined associations between, PROP phenotypes, self-reported food liking and TAS2R38 polymorphisms, the major gene implicated in PROP bitterness, in six different populations of the Caucasus and Central Asia, located along the ancient Silk Road. Differences in the distribution of PROP phenotypes across populations were detected, with a higher frequency of super tasters in Tajikistan (31.3%) and Armenia (39.0%) and a higher frequency of non tasters in Georgia (50.9%). While no relationships were observed between PROP phenotypes and food liking using standard statistical tests, we used an approach based on comparison of distance matrices derived from these data. The first matrix compared the food liking ratings of each population to all others pairwise using the Kruskal-Wallis test (at p<0.00063), and the second one compared the distribution of PROP phenotypes across all populations in a similar manner calculating the chi-square statistic as a distance measure. A strong correlation between the two matrices was found (Mantel test: r = 0.67, p-value = 0.03), suggesting that the pattern of food liking across populations was closely related to the distribution of PROP phenotypes. This same relationship was not observed when TAS2R38 genotypes were substituted for PROP phenotypes in this analysis. Our data suggest that a population-based approach utilizing distance matrices is a useful technique for detecting PROP-related differences in food liking and can be applied to other taste phenotypes.
Keywords: Armenia; Azerbaijan; Food; Genetic Association Studies; Genotype; Haplotypes; Humans; Polymorphism, Single Nucleotide; Propylthiouracil; Receptors, G-Protein-Coupled; Tajikistan; Taste; Taste Perception; Uzbekistan

A precordial rub in a boy with a severe attack of ulcerative colitis. - Badina, Laura; Ferrara, Giovanna; Guastalla, Pierpaolo; Barbi, Egidio (Pediatr Emerg Care, 2014)
A case of a pneumomediastinum mimicking a pericarditis in a boy with an occult perforation due to ulcerative colitis is reported. Pneumomediastinum is a rare complication of severe attacks of ulcerative colitis, with or without the previous development of a toxic megacolon, that should be considered in the differential diagnosis.
Keywords: Adolescent; Colitis, Ulcerative; Diagnosis, Differential; Humans; Intestinal Perforation; Male; Mediastinal Emphysema; Pericarditis; Radiography, Thoracic

Pregnancy and postpartum following a prenatal diagnosis of fetal thoracoabdominal malformation: the parental perspective. - Giuliani, Rosella; Tripani, Antonella; Pellizzoni, Sandra; Clarici, Andrea; Lonciari, Isabella; D'Ottavio, Giuseppina; Schleef, Jurgen (J Pediatr Surg, 2014)
PURPOSE: The study's aim was to evaluate how information related to a prenatal diagnosis of fetal malformation could modify parenthood experience descriptions during pregnancy and after the child's birth. METHODS: A longitudinal case-control clinical study was conducted. Data on parenthood experience descriptions collected using a validated semantic differential technique during pregnancy and after the child's birth were compared between seven couples of parents receiving a prenatal diagnosis of fetal malformation and seven couples without any fetal diagnosis. RESULTS: Our results show that during pregnancy parents in the clinical group describe themselves as more fragile, passive, and timid [p=0.007] than those in the control group. On the other hand, after the child's birth, there are no significant differences between groups. CONCLUSIONS: Data are discussed with reference to better knowledge of the psychological dynamics involved in becoming a parent and to rational planning of support for parents receiving a diagnosis of fetal malformation.
Keywords: Adult; Case-Control Studies; Counseling; Cystic Adenomatoid Malformation of Lung, Congenital; Female; Hernia, Diaphragmatic; Hernias, Diaphragmatic, Congenital; Humans; Hydronephrosis; Kidney Diseases; Longitudinal Studies; Male; Musculoskeletal Abnormalities; Parents; Pregnancy; Psychological Tests; Stress, Psychological; Ultrasonography, Prenatal; Urogenital Abnormalities

Procedural sedation for intra-articular corticosteroid injections in juvenile idiopathic arthritis (JIA) should be a standard of care. - Pastore, Serena; Gortani, Giulia; Taddio, Andrea; Barbi, Egidio (Eur J Pediatr, 2014)
Keywords: Arthritis, Juvenile; Conscious Sedation; Female; Glucocorticoids; Humans; Male; Pain; Patient Preference

Radiological contrast media in the breastfeeding woman: a position paper of the Italian Society of Radiology (SIRM), the Italian Society of Paediatrics (SIP), the Italian Society of Neonatology (SIN) and the Task Force on Breastfeeding, Ministry of Health - Cova, Maria Assunta; Stacul, Fulvio; Quaranta, Roberto; Guastalla, Pierpaolo; Salvatori, Guglielmo; Banderali, Giuseppe; Fonda, Claudio; David, Vincenzo; Gregori, Massimo; Zuppa, Antonio Alberto; Davanzo, Riccardo (Eur Radiol, 2014)
OBJECTIVES: Breastfeeding is a well-recognised investment in the health of the mother-infant dyad. Nevertheless, many professionals still advise breastfeeding mothers to temporarily discontinue breastfeeding after contrast media imaging. Therefore, we performed this review to provide health professionals with basic knowledge and skills for appropriate use of contrast media. METHODS: A joint working group of the Italian Society of Radiology (SIRM), Italian Society of Paediatrics (SIP), Italian Society of Neonatology (SIN) and Task Force on Breastfeeding, Ministry of Health, Italy prepared a review of the relevant medical literature on the safety profile of contrast media for the nursing infant/child. RESULTS: Breastfeeding is safe for the nursing infant of any post-conceptional age after administration of the majority of radiological contrast media to the mother; only gadolinium-based agents considered at high risk of nephrogenic systemic fibrosis (gadopentetate dimeglumine, gadodiamide, gadoversetamide) should be avoided in the breastfeeding woman as a precaution; there is no need to temporarily discontinue breastfeeding or to express and discard breast milk following the administration of contrast media assessed as compatible with breastfeeding. CONCLUSIONS: Breastfeeding women should receive unambiguous professional advice and clear encouragement to continue breastfeeding after imaging with the compatible contrast media. KEY POINTS: • Breastfeeding is a well-known investment in the health of the mother-infant dyad. • Breastfeeding is safe after administration of contrast media to the mother. • There is no need to temporarily discontinue breastfeeding following administration of contrast media.
Keywords: Adult; Breast Feeding; Contrast Media; Female; Humans; Infant; Italy; Neonatology; Practice Guidelines as Topic; Radiology; Societies, Medical

A randomized trial of hyperimmune globulin to prevent congenital cytomegalovirus. - Revello, Maria Grazia; Lazzarotto, Tiziana; Guerra, Brunella; Spinillo, Arsenio; Ferrazzi, Enrico; Kustermann, Alessandra; Guaschino, Secondo; Vergani, Patrizia; Todros, Tullia; Frusca, Tiziana; Arossa, Alessia; Furione, Milena; et al. (N Engl J Med, 2014)
BACKGROUND: Congenital infection with human cytomegalovirus (CMV) is a major cause of morbidity and mortality. In an uncontrolled study published in 2005, administration of CMV-specific hyperimmune globulin to pregnant women with primary CMV infection significantly reduced the rate of intrauterine transmission, from 40% to 16%. METHODS: We evaluated the efficacy of hyperimmune globulin in a phase 2, randomized, placebo-controlled, double-blind study. A total of 124 pregnant women with primary CMV infection at 5 to 26 weeks of gestation were randomly assigned within 6 weeks after the presumed onset of infection to receive hyperimmune globulin or placebo every 4 weeks until 36 weeks of gestation or until detection of CMV in amniotic fluid. The primary end point was congenital infection diagnosed at birth or by means of amniocentesis. RESULTS: A total of 123 women could be evaluated in the efficacy analysis (1 woman in the placebo group withdrew). The rate of congenital infection was 30% (18 fetuses or infants of 61 women) in the hyperimmune globulin group and 44% (27 fetuses or infants of 62 women) in the placebo group (a difference of 14 percentage points; 95% confidence interval, -3 to 31; P=0.13). There was no significant difference between the two groups or, within each group, between the women who transmitted the virus and those who did not, with respect to levels of virus-specific antibodies, T-cell-mediated immune response, or viral DNA in the blood. The clinical outcome of congenital infection at birth was similar in the two groups. The number of obstetrical adverse events was higher in the hyperimmune globulin group than in the placebo group (13% vs. 2%). CONCLUSIONS: In this study involving 123 women who could be evaluated, treatment with hyperimmune globulin did not significantly modify the course of primary CMV infection during pregnancy. (Funded by Agenzia Italiana del Farmaco; CHIP ClinicalTrials.gov number, NCT00881517; EudraCT no. 2008-006560-11.).
Keywords: Adult; Amniocentesis; Cytomegalovirus; Cytomegalovirus Infections; Female; Fetal Diseases; Humans; Immunoglobulins; Infectious Disease Transmission, Vertical; Pregnancy; Pregnancy Complications, Infectious

Salt-inducible kinase 3, SIK3, is a new gene associated with hearing. - Wolber, Lisa E; Girotto, Giorgia; Buniello, Annalisa; Vuckovic, Dragana; Pirastu, Nicola; Lorente-Cánovas, Beatriz; Rudan, Igor; Hayward, Caroline; Polasek, Ozren; Ciullo, Marina; Mangino, Massimo; Steves, Claire; et al. (Hum Mol Genet, 2014)
Hearing function is known to be heritable, but few significant and reproducible associations of genetic variants have been identified to date in the adult population. In this study, genome-wide association results of hearing function from the G-EAR consortium and TwinsUK were used for meta-analysis. Hearing ability in eight population samples of Northern and Southern European ancestry (n = 4591) and the Silk Road (n = 348) was measured using pure-tone audiometry and summarized using principal component (PC) analysis. Genome-wide association analyses for PC1-3 were conducted separately in each sample assuming an additive model adjusted for age, sex and relatedness of subjects. Meta-analysis was performed using 2.3 million single-nucleotide polymorphisms (SNPs) tested against each of the three PCs of hearing ability in 4939 individuals. A single SNP lying in intron 6 of the salt-inducible kinase 3 (SIK3) gene was found to be associated with hearing PC2 (P = 3.7×10(-8)) and further supported by whole-genome sequence in a subset. To determine the relevance of this gene in the ear, expression of the Sik3 protein was studied in mouse cochlea of different ages. Sik3 was expressed in murine hair cells during early development and in cells of the spiral ganglion during early development and adulthood. Our results suggest a developmental role of Sik3 in hearing and may be required for the maintenance of adult auditory function.
Keywords: Age Factors; Animals; Cochlea; European Continental Ancestry Group; Genome-Wide Association Study; Hearing; Humans; Mice, Inbred C57BL; Polymorphism, Single Nucleotide; Protein Kinases

The second generation of HIV-1 vertically exposed infants: a case series from the Italian Register for paediatric HIV infection. - Calitri, Carmelina; Gabiano, Clara; Galli, Luisa; Chiappini, Elena; Giaquinto, Carlo; Buffolano, Wilma; Genovese, Orazio; Esposito, Susanna; Bernardi, Stefania; de Martino, Maurizio; Tovo, Pier-Angelo (BMC Infect Dis, 2014)
BACKGROUND: In the Highly Active Antiretroviral Therapy (HAART) era, the prognosis of children perinatally infected with HIV-1 has significantly improved, so the number of perinatally-infected females entering child-bearing age and experiencing motherhood is increasing. METHODS: A description of the medical history and pregnancy outcomes of women with perinatal acquired HIV-1 infection enrolled in the Italian Register for HIV infection in Children. RESULTS: Twenty-three women had 29 pregnancies. They had started an antiretroviral therapy at a median of 7.7 years (interquartile range, IQR 2.3 - 11.4), and had experienced a median of 4 therapeutic regimens (IQR 2-6). Twenty women (87%) had taken zidovudine (AZT) before pregnancy, in 14 cases as a starting monotherapy. In 21 pregnancies a protease inhibitor-based regimen was used. At delivery, the median of CD4+ T lymphocytes was 450/μL (IQR 275-522), and no viral load was detectable in 15 cases (reported in 21 pregnancies). Twenty-eight children were delivered through caesarean section (median gestational age: 38 weeks, IQR 36-38, median birth weight: 2550 grams, IQR 2270 - 3000). Intravenous AZT was administered during delivery in 26 cases. All children received oral AZT (median: 42 days, IQR 31 - 42), with no adverse events reported. No child acquired HIV-1 infection. CONCLUSIONS: Despite a long history of maternal infection, multiple antiretroviral regimens and, perhaps, the development of drug-resistant viruses, the risk of mother-to-child transmission does not seem to have increased among the second-generation of HIV-1 exposed infants.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Birth Weight; Cesarean Section; Child; Female; HIV Infections; HIV-1; Humans; Infant; Infectious Disease Transmission, Vertical; Italy; Male; Pediatrics; Pregnancy; Pregnancy Complications, Infectious; Pregnancy Outcome; Prospective Studies; Viral Load; Young Adult; Zidovudine

Soluble TRAIL is present at high concentrations in seminal plasma and promotes spermatozoa survival. - Zauli, Giorgio; Celeghini, Claudio; Monasta, Lorenzo; Martinelli, Monica; Luppi, Stefania; Gonelli, Arianna; Grill, Vittorio; Ricci, Giuseppe; Secchiero, Paola (Reproduction, 2014)
The expression of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL(TNFSF10)) and of its receptors (TRAILR1, TRAILR2, TRAILR3, and TRAILR4) have been documented in testis, but the presence of soluble TRAIL in seminal fluid, as well as the potential physiopathological role of the TRAIL/TRAILR system in spermatozoa, has not been previously investigated. Male donors (n=123) among couples presenting for infertility evaluation were consecutively enrolled in this study. The presence of soluble TRAIL was analyzed in seminal samples by ELISA, while the surface expression of TRAIL receptors was investigated by flow cytometry. High levels of soluble TRAIL were detected in seminal plasma (median, 11 621 pg/ml and mean±s.d., 13 371±8367 pg/ml) and flow cytometric analysis revealed a variable expression of TRAIL receptors in the sperm cellular fraction among different subjects. In addition, the effect of physiologically relevant concentrations of recombinant TRAIL was investigated on survival and motility of spermatozoa. Of interest, the in vitro exposure of capacitated spermatozoa to recombinant TRAIL (10 ng/ml) significantly preserved their overall survival. Therefore, the present study demonstrates for the first time the presence of elevated levels of the anti-inflammatory cytokine TRAIL in seminal fluids. Moreover, the demonstration that recombinant TRAIL promotes spermatozoa survival after capacitation suggests potential therapeutic implications.
Keywords: Adult; Apoptosis; Enzyme-Linked Immunosorbent Assay; Flow Cytometry; Humans; Infertility, Male; Male; Receptors, TNF-Related Apoptosis-Inducing Ligand; Semen; Sperm Capacitation; Sperm Motility; Spermatozoa; TNF-Related Apoptosis-Inducing Ligand

Teleradiology for remote consultation using iPad improves the use of health system human resources for paediatric fractures: prospective controlled study in a tertiary care hospital in Italy. - Zennaro, Floriana; Grosso, Daniele; Fascetta, Riccardo; Marini, Marta; Odoni, Luca; Di Carlo, Valentina; Dibello, Daniela; Vittoria, Francesca; Lazzerini, Marzia (BMC Health Serv Res, 2014)
BACKGROUND: The growing cost of health care and lack of specialised staff have set e-Health high on the European political agenda. In a prospective study we evaluated the effect of providing images for remote consultation through an iPad on the number of in-hospital orthopaedic consultations for children with bone fractures. METHODS: Children from 0 to 18 years diagnosed with a bone fracture by the radiologist during the hours when an orthopaedic service is provided only on-call were eligible for enrollment. Cases were enrolled prospectively during September and October 2013. A standard approach (verbal information only, no X-Ray provided remotely) was compared to an experimental approach (standard approach plus the provision of X-ray for remote consultation through an iPad). The primary outcome was the number of orthopaedic in-hospital consultations that occurred. Other outcomes included: immediate activation of other services; time needed for decision-making; technical difficulties; quality of images and diagnostic confidence (on a likert scale of 1 to 10). RESULTS: Forty-two children were enrolled in the study. Number of in-hospital consultancies dropped from 32/42 (76.1%) when no X-ray was provided to 16/42 (38%) when the X-rays was provided (p < 0.001). With remote X-ray consultation in 14/42 (33.3%) cases services such as surgery and plaster room could be immediately activated, compared to no service activated without teleradiology (p < 0.001). Average time for decision making was 23.4 ± 21.8 minutes with remote X-ray consultation, compared to 56.2 ± 16.1 when the X-ray was not provided (p < 0.001). The comparison between images on the iPad and on the standard system for X- Ray visualisation resulted in a non statistically significant difference in the quality of images (average score 9.89 ± 0.37 vs 9.91 ± 0.30; p = 0.79), and in non statistically significant difference in diagnostic confidence (average score 9.91 ± 0.32 vs 9.92 ± 0.31; p = 0.88). CONCLUSIONS: Remote X-ray consultation through Aycan OsiriX PRO and iPad should be considered as a means for reducing the need of in-hospital orthopaedic consultation during on-call times, and potentially decrease the cost of care for the health system. In the future, alternative systems less expensive than Aycan OsiriX PRO should be further developed and tested.
Keywords: Adolescent; Child; Child, Preschool; Computers, Handheld; Decision Making; Fractures, Bone; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Remote Consultation; Teleradiology; Time Factors

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

A comparative analysis of serologic parameters and oxidative stress in osteoarthritis and rheumatoid arthritis: reply to Mishra and colleagues. - Girardelli, M; Bianco, A M; Marcuzzi, A; Crovella, S (Rheumatol Int, 2013)
In chronic diseases such as rheumatoid arthritis and osteoarthritis, the progression of the disease is characterized by stress oxidative, inflammation, and elevated levels of cholesterol. In mevalonate kinase deficiency, an auto-inflammatory disease, the correlation between inflammation and cholesterol levels is opposite. The metabolic pathway that underlies the production of cholesterol is the mevalonate pathway; it is also essential for the biosynthesis of isoprenoids involved in the control of several cell functions. This divergence of cholesterol levels, associated with these two inflammatory disorders, is probably due to a different etiology, pathogenesis, and progression.
Keywords: Arthritis, Rheumatoid; Female; Humans; Inflammation Mediators; Lipids; Male; Osteoarthritis; Oxidative Stress

Does EMLA cream application interfere with the success of venipuncture or venous cannulation? A prospective multicenter observational study. - Schreiber, S; Ronfani, L; Chiaffoni, G P; Matarazzo, L; Minute, M; Panontin, E; Poropat, F; Germani, C; Barbi, E (Eur J Pediatr, 2013)
UNLABELLED: Venipuncture and intravenous cannulation are the most common painful procedures performed on children. The most widely used topical anesthetic is eutectic mixture of local anesthetics (EMLA). EMLA use is associated with a transient cutaneous vasoconstriction which can make it difficult to identify veins. We assessed with a prospective, multicenter, observational study whether EMLA interferes with venipuncture and intravenous cannulation. The primary study outcome was a success at first attempt in the course of venipuncture or venous cannulation. The study enrolled 388 children; 255 of them received EMLA and 133 did not. Eighty-six percent of procedures were successful at the first attempt in the EMLA group and 76.7 % in the no EMLA group. CONCLUSION: In this study, EMLA use did not interfere with the success of venipuncture or venous cannulation in children.
Keywords: Anesthetics, Local; Catheterization, Peripheral; Child; Child, Preschool; Female; Humans; Lidocaine; Logistic Models; Male; Ointments; Phlebotomy; Prilocaine; Prospective Studies; Vasoconstriction

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

MYH9-related disease: five novel mutations expanding the spectrum of causative mutations and confirming genotype/phenotype correlations. - De Rocco, Daniela; Zieger, Barbara; Platokouki, Helen; Heller, Paula G; Pastore, Annalisa; Bottega, Roberta; Noris, Patrizia; Barozzi, Serena; Glembotsky, Ana C; Pergantou, Helen; Balduini, Carlo L; Savoia, Anna; et al. (Eur J Med Genet, 2013)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant syndromic disorder caused by mutations in MYH9, the gene encoding for the heavy chain of non-muscle myosin IIA (myosin-9). MYH9-RD is characterized by congenital macrothrombocytopenia and typical inclusion bodies in neutrophils associated with a variable risk of developing sensorineural deafness, presenile cataract, and/or progressive nephropathy. The spectrum of mutations responsible for MYH9-RD is limited. We report five families, each with a novel MYH9 mutation. Two mutations, p.Val34Gly and p.Arg702Ser, affect the motor domain of myosin-9, whereas the other three, p.Met847_Glu853dup, p.Lys1048_Glu1054del, and p.Asp1447Tyr, hit the coiled-coil tail domain of the protein. The motor domain mutations were associated with more severe clinical phenotypes than those in the tail domain.
Keywords: Adolescent; Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; Child; Child, Preschool; Exons; Female; Genes, Dominant; Genetic Association Studies; Humans; Male; Middle Aged; Models, Molecular; Molecular Motor Proteins; Molecular Sequence Data; Mutation; Myosin Heavy Chains; Pedigree; Protein Conformation; Sequence Alignment; Syndrome; Thrombocytopenia; Young Adult

A novel CRYBB2 missense mutation causing congenital autosomal dominant cataract in an Italian family. - Faletra, Flavio; d'Adamo, Adamo Pio; Pensiero, Stefano; Athanasakis, Emmanouil; Catalano, Dario; Bruno, Irene; Gasparini, Paolo (Ophthalmic Genet, 2013)
Congenital cataract is a leading cause of visual impairment in children and brings approximately 10% of childhood blindness worldwide. Molecular analysis revealed ~60 loci to be associated with several phenotypes of childhood cataracts. Until now, more than 30 loci and 18 genes on different chromosomes have been associated with autosomal dominant congenital cataract (ADCC). Here, we present a three-generation Italian family with a non syndromic ADCC. A linkage analysis carried out using HumanCytoSNP-12 DNA Analysis BeadChip led us to identify ten genomic regions virtually involved in the disease. All the genes located in these regions were scored for possible relationship with ADCC and, according to a strict clinical and genetic selection, 4 genes have been analyzed. A novel sequence variant was found in the CRYBB2 gene (p.Ser143Phe). This variant affects a conserved aminoacid in the third Greek key motif of the protein, cosegregates with the disease phenotype in all affected individuals and is not present both in the unaffected family members and 100 healthy control subjects. Finally, we identified the first CRYBB2 mutation in an Italian family causing a clinical picture of ADCC.
Keywords: Amino Acid Sequence; beta-Crystallin B Chain; Cataract; DNA Mutational Analysis; Female; Genes, Dominant; Genetic Linkage; Genotype; Humans; Italy; Male; Molecular Sequence Data; Mutation, Missense; Pedigree; Phenotype

Safety and efficacy of infliximab and adalimumab for refractory uveitis in juvenile idiopathic arthritis: 1-year followup data from the Italian Registry. - Zannin, Maria E; Birolo, Carolina; Gerloni, Valeria M; Miserocchi, Elisabetta; Pontikaki, Irene; Paroli, Maria P; Bracaglia, Claudia; Shardlow, Alison; Parentin, Fulvio; Cimaz, Rolando; Simonini, Gabriele; Falcini, Fernanda; et al. (J Rheumatol, 2013)
OBJECTIVE: To evaluate safety and efficacy of adalimumab (ADA) and infliximab (IFX) for the treatment of juvenile idiopathic arthritis-related anterior uveitis (JIA-AU). METHODS: Starting January 2007, patients with JIA-AU treated with IFX and ADA were managed by a standard protocol and data were entered into the National Italian Registry (NIR). At baseline, all patients were refractory to standard immunosuppressive treatment and/or were corticosteroid-dependent. Data recorded every 3 months included uveitis course, number/type of ocular complications, drug-related adverse events (AE), treatment change or withdrawal, and laboratory measures. Data of patients treated for at least 1 year were retrieved from the NIR and analyzed using descriptive statistics. Treatment efficacy was based on change in uveitis course and in number of ocular complications. RESULTS: Up to December 2009, data for 108 patients with JIA-AU treated with anti-tumor necrosis factor-α agents were recorded in the NIR and data from 91, with at least 12 months' followup, were included in the study. Forty-eight patients were treated with IFX, 43 with ADA. Forty-seven patients (55.3%) achieved remission of AU, 28 (32.9%) had recurrent AU, and 10 (11.8%) maintained a chronic course. A higher remission rate was observed with ADA (67.4% vs 42.8% with IFX; p = 0.025). Ocular complications decreased from 0.47 to 0.32 per subject. Five patients experienced resolution of structural complications. No patient reported serious AE; 8 (8.8%) experienced 11 minor AE (9 with IFX, 2 with ADA). CONCLUSION: IFX and ADA appear to be effective and safe for treatment of refractory JIA-related uveitis, with a better performance of ADA in the medium-term period.
Keywords: Adolescent; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Female; Follow-Up Studies; Humans; Infant; Italy; Male; Registries; Treatment Outcome; Tumor Necrosis Factor-alpha; Uveitis

Is treatment with hydroxychloroquine effective in surfactant protein C deficiency? - Rabach, Ingrid; Poli, Furio; Zennaro, Floriana; Germani, Claudio; Ventura, Alessandro; Barbi, Egidio (Arch Bronconeumol, 2013)
We present the case of two twin brothers with surfactant protein C deficiency who were treated with hydroxychloroquine for three years, with apparent success. The exact physiopathology of this disease is not known and there is no specific treatment for it. There is merely news from a few previous descriptions in the literature about the use of hydroxychloroquine for surfactant protein C deficiency with satisfactory results. Two years after the treatment was withdrawn, the twins were evaluated once again: they presented no new infections, growth and general state were normal and chest CT showed a notable additional reduction in the interstitial pneumopathy. These data seem to cast some doubt on the efficacy of hydroxychloroquine, and they suggest that the clinical improvement was simply the natural evolution of the disease.
Keywords: Disease Progression; Diseases in Twins; Dyspnea; Failure to Thrive; Humans; Hydroxychloroquine; Infant, Newborn; Male; Pulmonary Alveolar Proteinosis; Pulmonary Surfactant-Associated Protein C; Respiratory Insufficiency; Tomography, X-Ray Computed; Twins, Monozygotic

Accuracy of diagnostic antibody tests for coeliac disease in children: summary of an evidence report. - Giersiepen, Klaus; Lelgemann, Monika; Stuhldreher, Nina; Ronfani, Luca; Husby, Steffen; Koletzko, Sibylle; Korponay-Szabó, Ilma R (J Pediatr Gastroenterol Nutr, 2012)
OBJECTIVE: The aim of this study was to summarise the evidence from 2004 to September 2009 on the performance of laboratory-based serological and point of care (POC) tests for diagnosing coeliac disease (CD) in children using histology as reference standard. PATIENTS AND METHODS: We searched MEDLINE and EMBASE for studies reporting on children for tests based on IgA and IgG anti-gliadin (AGA), endomysial (EmA), anti-transglutaminase-2 (TG2), and anti-deamidated gliadin peptides (DGP) antibodies or POC tests. For inclusion, histological analysis of duodenal biopsies and sensitivity and specificity for index tests had to be reported. Data were pooled and summary measures calculated for sensitivity, specificity, positive and negative likelihood ratios ("LR+", "LR-"), and diagnostic odds ratios (DOR). In case of elevated statistical heterogeneity, studies reaching 90% sensitivity or specificity were reported. RESULTS: A total of 2510 articles were reviewed; 16 entered meta-analysis, reporting on 3110 patients (1876 with CD, 1234 without CD). For IgA-EmA, sensitivity was ≥90% in 7/11 studies and pooled specificity 98.2%. For IgA-anti-TG2, 11/15 studies yielded sensitivities ≥90% and 13/15 specificities ≥90%. For IgA-DGP, sensitivity ranged between 80.7% and 95.1% (specificity 86.3%-93.1%); for IgG-DGP between 80.1% and 98.6% (specificity 86.0-96.9%). IgA-EmA had the highest pooled DOR (554) and LR+ (31.8) for a laboratory test, followed by IgA-anti-TG2, IgG-DGP, IgA-DGP and IgA-AGA. POC tests showed a pooled sensitivity of 96.4% for IgA-TG2 (specificity 97.7%). CONCLUSIONS: IgA-EmA and IgA-anti-TG2 tests appear highly accurate to diagnose CD. IgG-anti-DGP tests may help in excluding CD. IgA-AGA and IgA-DGP tests show inferior accuracy. POC tests may achieve high accuracy in the hands of experienced readers, but IgA-anti-TG2/EmA were superior.
Keywords: Autoantibodies; Biological Markers; Celiac Disease; Child; Gliadin; GTP-Binding Proteins; Humans; Immunoglobulin A; Immunoglobulin G; Point-of-Care Systems; Sensitivity and Specificity; Transglutaminases

Activation of the p53 pathway induces α-smooth muscle actin expression in both myeloid leukemic cells and normal macrophages. - Secchiero, Paola; Rimondi, Erika; di Iasio, Maria Grazia; Voltan, Rebecca; Gonelli, Arianna; Zauli, Giorgio (J Cell Physiol, 2012)
A range of cell types of mesenchymal origin express α-smooth muscle actin (α-SMA), a protein that plays a key role in controlling cell motility and differentiation along the fibrocyte and myofibroblast lineages. Although α-SMA is often expressed in stromal cells associated to a variety of cancers including hematological malignancies, up to now the role of anti-cancer drugs on α-SMA has not been deeply investigated. In this study, we demonstrated that Nutlin-3, the small molecule inhibitor of the MDM2/p53 interactions, significantly up-regulated the mRNA and protein levels of α-SMA in normal macrophages as well as in p53(wild-type) but not in p53(mutated/null) myeloid leukemic cells. The p53-dependence of α-SMA up-regulation induced by Nutlin-3 was demonstrated in experiments performed with siRNA for p53. Of note, Nutlin-3 mediated up-regulation of α-SMA in OCI leukemic cells was accompanied by cell adhesion to plastic substrate and by reduced cell migratory response in transwell assays. Notably, the role of α-SMA induction in the modulation of myeloid cell migration was clearly documented in α-SMA gene knockdown experiments. In addition, Nutlin-3 significantly up-regulated α-SMA expression in primary endothelial cells, but not in fibroblasts and mesenchymal stem cells (MSC). Conversely, transforming growth factor-β1 up-regulated α-SMA in fibroblasts and MSC, but not in macrophages and endothelial cells. Taken together, these data indicate that Nutlin-3 is a potent inducer of α-SMA in both normal and leukemic myeloid cells as well as in endothelial cells.
Keywords: Actins; Cell Movement; Cells, Cultured; Endothelial Cells; Fibroblasts; Humans; Imidazoles; Leukemia, Myeloid; Macrophages; Mesenchymal Stromal Cells; Piperazines; Proto-Oncogene Proteins c-mdm2; RNA, Small Interfering; Signal Transduction; Transforming Growth Factor beta1; Tumor Suppressor Protein p53

Alteration of liver enzymes is a feature of the MYH9-related disease syndrome. - Pecci, Alessandro; Biino, Ginevra; Fierro, Tiziana; Bozzi, Valeria; Mezzasoma, Annamaria; Noris, Patrizia; Ramenghi, Ugo; Loffredo, Giuseppe; Fabris, Fabrizio; Momi, Stefania; Magrini, Umberto; Pirastu, Mario; et al. (PLoS One, 2012)
BACKGROUND: MYH9-related disease (MYH9-RD) is a rare autosomal dominant genetic syndrome characterized by congenital thrombocytopenia associated with the risk of developing progressive nephropathy, sensorineural deafness, and presenile cataract. During the collection of a large case-series of patients with MYH9-RD we noticed several cases with unexplained elevation of liver enzymes. Our aim was to evaluate if the alteration of liver tests is a feature of the MYH9-RD and to define its clinical significance. METHODS AND FINDINGS: Data concerning liver tests, prospectively recorded in the Italian Registry for MYH9-RD, were collected and compared with those of three control populations: patients with autoimmune thrombocytopenia, patients with inherited thrombocytopenias other than MYH9-RD, and the participants to a large epidemiologic survey in an Italian geographic isolate. Thirty-eight of 75 evaluable MYH9-RD patients (50.7%) showed an elevation of ALT and/or AST, and 17 of 63 (27.0%) an increase of GGT. The increases ranged from 1.9 ± 0.7 to 2.7 ± 1.6 fold the upper normal limit. The prevalence of liver test alterations was significantly higher in MYH9-RD patients than in each of the control populations, with odds ratios ranging from 8.2 (95% CIs 2.2-44.8) to 24.7 (14.8-40.8). Clinical follow-up and more detailed liver studies of a subset of patients, including ultrasound liver scan, liver elastography and liver biopsy in one case, did not show any significant structural damage or evolution towards liver insufficiency. CONCLUSIONS: Elevation of liver enzymes is a frequent and previously unrecognized feature of the MYH9-RD syndrome; however, this defect does not appear to have poor prognostic value.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Aged; Aged, 80 and over; Biopsy; Case-Control Studies; Child; Child, Preschool; Demography; Female; Follow-Up Studies; Humans; Immunohistochemistry; Infant; Liver; Liver Function Tests; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Odds Ratio; Syndrome; Young Adult

Association between the JC polyomavirus infection and male infertility. - Comar, Manola; Zanotta, Nunzia; Croci, Eleonora; Murru, Immacolata; Marci, Roberto; Pancaldi, Cecilia; Dolcet, Ornella; Luppi, Stefania; Martinelli, Monica; Giolo, Elena; Ricci, Giuseppe; Tognon, Mauro (PLoS One, 2012)
In recent years the incidence of male infertility has increased. Many risk factors have been taken into consideration, including viral infections. Investigations into viral agents and male infertility have mainly been focused on human papillomaviruses, while no reports have been published on polyomaviruses and male infertility. The aim of this study was to verify whether JC virus and BK virus are associated with male infertility. Matched semen and urine samples from 106 infertile males and 100 fertile males, as controls, were analyzed. Specific PCR analyses were carried out to detect and quantify large T (Tag) coding sequences of JCV and BKV. DNA sequencing, carried out in Tag JCV-positive samples, was addressed to viral protein 1 (VP1) coding sequences. The prevalence of JCV Tag sequences in semen and urine samples from infertile males was 34% (72/212), whereas the BKV prevalence was 0.94% (2/212). Specifically, JCV Tag sequences were detected in 24.5% (26/106) of semen and 43.4% (46/106) of urine samples from infertile men. In semen and urine samples from controls the prevalence was 11% and 28%, respectively. A statistically significant difference (p<0.05) in JCV prevalence was disclosed in semen and urine samples of cases vs. controls. A higher JC viral DNA load was detected in samples from infertile males than in controls. In samples from infertile males the JC virus type 2 strain, subtype 2b, was more prevalent than ubiquitous type 1. JCV type 2 strain infection has been found to be associated with male infertility. These data suggest that the JC virus should be taken into consideration as an infectious agent which is responsible for male infertility.
Keywords: Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; BK Virus; Capsid Proteins; DNA, Viral; Humans; Infertility, Male; JC Virus; Male; Molecular Sequence Data; Polyomavirus Infections; Semen; Sequence Analysis, DNA; Tumor Virus Infections

Autoimmune-polyendocrinopathy-candidiasis-ectodermal-dystrophy in Calabria: clinical, immunological and genetic patterns. - Betterle, C; Ghizzoni, L; Cassio, A; Baronio, F; Cervato, S; Garelli, S; Barbi, E; Tonini, G (J Endocrinol Invest, 2012)
UNLABELLED: Autoimmune polyendocrinopathy-candidiasis-ectodermal- dystrophy (APECED), also known as autoimmune polyendocrine syndrome type 1 (APS-1), is a very rare disease. Diagnosis requires the presence of at least two of three major clinical features: chronic mucocutaneous candidiasis, chronic hypoparathyroidism, and Addison's disease. DESIGN: In this study, we analyzed Autoimmune Regulator (AIRE) gene mutations and genotype-phenotype correlation in APECED patients originating from Calabria, a region in the south of Italy. PATIENTS AND METHODS: Four patients and their first-degree relatives were evaluated for clinical manifestations, autoantibody presence and AIRE gene mutations. RESULTS: Three patients carried a homozygous W78R mutation on exon 2, typical of patients with APECED from Apulia; the fourth patient had a homozygous R203X mutation on exon 5, typical of APECED patients from Sicily. Clinical disease expression showed wide variability. Analysis of relatives allowed the identification of 6 heterozygotes, none of whom showed major findings of APECED. CONCLUSIONS: No AIRE gene mutations specific to Calabria were found in patients with APS-1, but mutations similar to those in patients from Apulia and Sicily. Heterozygosity for AIRE gene mutation is not associated with major findings of APECED.
Keywords: Adolescent; Adult; Autoantibodies; Child; Female; Genetic Association Studies; Heterozygote; Homozygote; Humans; Italy; Male; Mutation; Polyendocrinopathies, Autoimmune; Prognosis; Sicily; Transcription Factors; Young Adult

Burden of disease caused by otitis media: systematic review and global estimates. - Monasta, Lorenzo; Ronfani, Luca; Marchetti, Federico; Montico, Marcella; Vecchi Brumatti, Liza; Bavcar, Alessandro; Grasso, Domenico; Barbiero, Chiara; Tamburlini, Giorgio (PLoS One, 2012)
BACKGROUND: Otitis media (OM) is a leading cause of health care visits and drugs prescription. Its complications and sequelae are important causes of preventable hearing loss, particularly in developing countries. Within the Global Burden of Diseases, Injuries, and Risk Factors Study, for the year 2005 we estimated the incidence of acute OM, chronic suppurative OM, and related hearing loss and mortality for all ages and the 21 WHO regional areas. METHODS: We identified risk factors, complications and sequelae of OM. We carried out an extensive literature review (Medline, Embase, Lilacs and Wholis) which lead to the selection of 114 papers comprising relevant data. Data were available from 15 of the 21 WHO regions. To estimate incidence and prevalence for all countries we adopted a two stage approach based on risk factors formulas and regression modelling. RESULTS: Acute OM incidence rate is 10.85% i.e. 709 million cases each year with 51% of these occurring in under-fives. Chronic suppurative OM incidence rate is 4.76 ‰ i.e. 31 million cases, with 22.6% of cases occurring annually in under-fives. OM-related hearing impairment has a prevalence of 30.82 per ten-thousand. Each year 21 thousand people die due to complications of OM. CONCLUSIONS: Our study is the first attempt to systematically review the available information and provide global estimates for OM and related conditions. The overall burden deriving from AOM, CSOM and their sequelae is considerable, particularly in the first five years of life and in the poorest countries. The findings call for incorporating OM-focused action within preventive and case management strategies, with emphasis on the more affected.
Keywords: Cost of Illness; Hearing Loss; Humans; Internationality; Otitis Media

Chemerin regulates NK cell accumulation and endothelial cell morphogenesis in the decidua during early pregnancy. - Carlino, Claudia; Trotta, Eleonora; Stabile, Helena; Morrone, Stefania; Bulla, Roberta; Soriani, Alessandra; Iannitto, Maria Luisa; Agostinis, Chiara; Mocci, Carlo; Minozzi, Massimo; Aragona, Cesare; Perniola, Giorgia; et al. (J Clin Endocrinol Metab, 2012)
CONTEXT: Although decidual natural killer (NK) cell accumulation and vascular remodeling are critical steps to ensure successful pregnancy, the molecular mechanisms controlling these events are poorly defined. OBJECTIVE: Herein we analyzed whether chemerin, a recently identified chemoattractant involved in many pathophysiological processes, could be expressed in the uterine compartment and could regulate events relevant for the good outcome of pregnancy. DESIGN: Chemerin expression in human primary culture of stromal (ST) cells, extravillous trophoblast cells, and decidual endothelial cells (DEC) was analyzed by RT-PCR, ELISA, and Western blot. Migration through ST or DEC of peripheral blood and decidual (d) NK cells from pregnant women was performed using a transwell assay. A DEC capillary-like tube formation assay was used to evaluate endothelial morphogenesis. RESULTS: Chemerin is differentially expressed by decidual cells during early pregnancy being present at high levels in ST and extravillous trophoblast cells but not in DEC. Notably, ST cells from pregnant women exhibit and release higher levels of chemerin as compared with ST cells from menopausal or fertile nonpregnant women. Chemerin can support peripheral blood NK cell migration through both DEC and ST cells. Although dNK cells exhibit lower chemerin receptor (CMKLR1) expression than their blood counterpart, CMKLR1 engagement on dNK cells resulted in both ERK activation and migration through decidual ST cells. Interestingly, DEC also express CMKLR1 and undergo ERK activation and capillary-like tube structure formation upon exposure to chemerin. CONCLUSIONS: Our data indicate that chemerin is up-regulated during decidualization and might contribute to NK cell accumulation and vascular remodeling during early pregnancy.
Keywords: Capillaries; Cell Movement; Chemokines; Decidua; Endothelial Cells; Female; Humans; Killer Cells, Natural; MAP Kinase Signaling System; Neovascularization, Physiologic; Pregnancy; Pregnancy Trimester, First; Receptors, Chemokine; RNA, Messenger; Stromal Cells; Trophoblasts

A child with edema, lower limb deformity, and recurrent diarrhea. - Gortani, Giulia; Maschio, Massimo; Ventura, Alessandro (J Pediatr, 2012)
Keywords: Bone Retroversion; Capsule Endoscopy; Child, Preschool; Diarrhea; Edema; Humans; Knee Joint; Lymphangiectasis, Intestinal; Lymphedema; Male; Recurrence

Clinical and laboratory features of 103 patients from 42 Italian families with inherited thrombocytopenia derived from the monoallelic Ala156Val mutation of GPIbα (Bolzano mutation). - Noris, Patrizia; Perrotta, Silverio; Bottega, Roberta; Pecci, Alessandro; Melazzini, Federica; Civaschi, Elisa; Russo, Sabina; Magrin, Silvana; Loffredo, Giuseppe; Di Salvo, Veronica; Russo, Giovanna; Casale, Maddalena; et al. (Haematologica, 2012)
BACKGROUND: Bernard-Soulier syndrome is a very rare form of inherited thrombocytopenia that derives from mutations in GPIbα, GPIbβ, or GPIX and is typically inherited as a recessive disease. However, some years ago it was shown that the monoallelic c.515C>T transition in the GPIBA gene (Bolzano mutation) was responsible for macrothrombocytopenia in a few Italian patients. DESIGN AND METHODS: Over the past 10 years, we have searched for the Bolzano mutation in all subjects referred to our institutions because of an autosomal, dominant form of thrombocytopenia of unknown origin. RESULTS: We identified 42 new Italian families (103 cases) with a thrombocytopenia induced by monoallelic Bolzano mutation. Analyses of the geographic origin of affected pedigrees and haplotypes indicated that this mutation originated in southern Italy. Although the clinical expression was variable, patients with this mutation typically had a mild form of Bernard-Soulier syndrome with mild thrombocytopenia and bleeding tendency. The most indicative laboratory findings were enlarged platelets and reduced GPIb/IX/V platelet expression; in vitro platelet aggregation was normal in nearly all of the cases. CONCLUSIONS: Our study indicates that monoallelic Bolzano mutation is the most frequent cause of inherited thrombocytopenia in Italy, affecting 20% of patients recruited at our institutions during the last 10 years. Because many people from southern Italy have emigrated during the last century, this mutation may have spread to other countries.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Bernard-Soulier Syndrome; Child; Child, Preschool; Family Health; Female; Heterozygote; Humans; Infant; Italy; Male; Membrane Glycoproteins; Middle Aged; Mutation, Missense; Platelet Aggregation; Platelet Count; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Genetic; Thrombocytopenia; Thrombopoietin; Tubulin; Young Adult

A common genetic background could explain early-onset Crohn's disease. - Bianco, Anna Monica; Zanin, Valentina; Girardelli, Martina; Magnolato, Andrea; Martelossi, Stefano; Martellossi, Stefano; Tommasini, Alberto; Marcuzzi, Annalisa; Crovella, Sergio (Med Hypotheses, 2012)
Crohn's disease (CD) is a multifactorial disease, in which environmental, microbial and genetic factors play important roles. CD is characterized by a chronic granulomatous inflammation by necrotic scarring with aspects of full-thickness wall. In spite of affecting mainly young adults, sometimes, CD can be present in the first year of life (early onset Crohn disease, EOCD) showing an unpredictable course and being often more severe than at older ages. In this paper we propose the hypothesis that EOCD patients should be analyzed using a Mendelian approach with family studies aimed to identify new loci directly involved in the early onset Crohn's disease. So we will leave the classic association study approach used until now for the identification of genes responsible for susceptibility to CD and propose linkage family analysis as alternative and powerful tool for the identification of new genetic variants associated with familiar cases of EOCD.
Keywords: Crohn Disease; Genetic Linkage; Genetic Predisposition to Disease; Humans; Models, Biological

Comparison of hybrid capture II, linear array, and a bead-based multiplex genotyping assay for detection of human papillomavirus in women with negative pap test results and atypical squamous cells of undetermined significance. - Comar, Manola; Iannacone, Michelle R; Casalicchio, Giorgia; McKay-Chopin, Sandrine; Tommasino, Massimo; Gheit, Tarik (J Clin Microbiol, 2012)
Many methods with different levels of analytical sensitivity and clinical specificity have been developed to detect the presence of high-risk (HR) types of the human papillomavirus (HPV) in cervical samples. The Hybrid Capture II (HC-II) assay is broadly used for primary screening. In addition, several HPV genotyping assays, based on PCR methods, display higher sensitivity than the HC-II and are also used in screening programs. We evaluated the performance of three HPV DNA tests, namely, the HC-II, the Linear Array (LA) HPV genotyping assay, and an HPV type-specific E7 PCR bead-based multiplex genotyping assay (TS-MPG) that is a laboratory-developed method for the detection of HPV, in 94 women with atypical squamous cells of undetermined significance (ASC-US) and in cytological samples from 86 women with a negative Pap test. The HPV prevalence with the TS-MPG assay was increased compared to the prevalence with the LA and HC-II assays. The HPV DNA prevalence in women with ASC-US was greater with the TS-MPG assay (46.2%) than with the LA (36.3%) and HC-II (29.7%) assays. The HPV DNA prevalence in the control group was greater with the TS-MPG assay (32.1%) than with the LA assay (10.7%). Two women with ASC-US who were HPV DNA negative by the HC-II and positive by the TS-MPG or/and LA assays had lesions that progressed to low-grade squamous intraepithelial and high-grade squamous intraepithelial lesions. This study shows that the TS-MPG assay exhibited higher analytical sensitivity than the LA and HC-II assays for the detection of HPV DNA, which reduces the potential to incorrectly identify a woman's HPV infection status.
Keywords: Adult; DNA, Viral; Female; Humans; Molecular Diagnostic Techniques; Papillomavirus Infections; Sensitivity and Specificity; Uterine Cervical Neoplasms; Virology

Contribution of SNP arrays in diagnosis of deletion 2p11.2-p12. - Rocca, Maria Santa; Fabretto, Antonella; Faletra, Flavio; Carlet, Ombretta; Skabar, Aldo; Gasparini, Paolo; Pecile, Vanna (Gene, 2012)
Deletions of the short arm of chromosome 2 are exceedingly rare, having been reported in few patients. Furthermore most cases with deletion in 2p11.2-p12 have been studied using standard karyotype and so it is not possible to delineate the precise size of deletions. Here, we describe a 9-year-old girl with a 9.4 Mb de novo interstitial deletion of region 2p11.2-p12 identified by SNP array analysis. The deleted region encompasses over 40 known genes, including LRRTM1, CTNNA2 and REEP1, haploinsufficiency of which could explain some clinical features of this patient such as mental retardation, speech delay and gait abnormalities. A comparison of our case with previously reported patients who present deletions in 2p11.2-p12 was carried out. Our case adds new information to the deletion of 2p11.2-p12, improving the knowledge on this rearrangement.
Keywords: Abnormalities, Multiple; Child; Chromosomes, Human, Pair 2; Female; Humans; Intellectual Disability; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Sequence Deletion

De novo 6.9 Mb interstitial deletion on chromosome 4q31.1-q32.1 in a girl with severe speech delay and dysmorphic features. - Fabretto, Antonella; Santa Rocca, Maria; Perrone, Maria Dolores; Skabar, Aldo; Pecile, Vanna; Gasparini, Paolo (Am J Med Genet A, 2012)
Deletion of the terminal part of long arm of chromosome 4 is a condition characterized by facial dysmorphisms, cardiac and limb defects, and developmental delay. Deletions usually involve the terminal part of the chromosome and most frequently are interstitial. Here, we report a de novo interstitial deletion resulting in a microdeletion of 6.9 Mb involving 4q31.3-q32.1 segment, detected by SNPs-Array technique in a 4-year-old female showing severe speech delay, mild facial dysmorphisms, and joint laxity. Phenotype-genotype relationships looking at the genes involved in this part of the chromosome were also carried out and data compared with those previously described.
Keywords: Abnormalities, Multiple; Child, Preschool; Chromosome Deletion; Chromosomes, Human, Pair 4; Developmental Disabilities; Female; Genotype; Humans; Language Development Disorders; Phenotype; Sequence Deletion

De novo 911 Kb interstitial deletion on chromosome 1q43 in a boy with mental retardation and short stature. - Perrone, M D; Rocca, M S; Bruno, I; Faletra, F; Pecile, V; Gasparini, P (Eur J Med Genet, 2012)
Patients with distal deletions of chromosome 1q have a recognizable syndrome that includes microcephaly, hypoplasia or agenesis of the corpus callosum, and psychomotor retardation. Although these symptoms have been attributed to deletions of 1q42-1q44, the minimal chromosomal region involved has not yet defined. In this report, we describe a 7 years old male with mental retardation, cryptorchid testes, short stature and alopecia carrying only an interstitial de novo deletion of 911 Kb in the 1q43 region (239,597,095-240,508,817) encompassing three genes CHRM3, RPS7P5 and FMN2.
Keywords: Child; Chromosomes, Human, Pair 1; Dwarfism; Humans; Intellectual Disability; Male; Sequence Deletion

Delayed diagnosis of glycogen storage disease type III. - Minen, Federico; Cont, Gabriele; De Cunto, Angela; Martelossi, Stefano; Ventura, Alessandro; Maggiore, Giuseppe; Faletra, Flavio; Gasparini, Paolo; Cassandrini, Denise (J Pediatr Gastroenterol Nutr, 2012)
Keywords: Delayed Diagnosis; Diagnostic Errors; Glycogen Storage Disease Type I; Glycogen Storage Disease Type III; Humans; Infant; Liver; Male

Does the 1.5 Mb microduplication in chromosome band Xp22.31 have a pathogenetic role? New contribution and a review of the literature. - Faletra, Flavio; d'Adamo, Adamo Pio; Santa Rocca, Maria; Carrozzi, Marco; Perrone, Maria Dolores; Pecile, Vanna; Gasparini, Paolo (Am J Med Genet A, 2012)
Keywords: Chromosome Breakpoints; Chromosome Duplication; Chromosomes, Human, X; Hand Deformities, Congenital; Humans; Intellectual Disability; Karyotyping; Muscle Hypotonia; Polymorphism, Single Nucleotide; Protein Tyrosine Phosphatases

Effects of hormonal contraception on vaginal flora. - De Seta, Francesco; Restaino, Stefano; De Santo, Davide; Stabile, Guglielmo; Banco, Rubina; Busetti, Marina; Barbati, Giulia; Guaschino, Secondo (Contraception, 2012)
BACKGROUND: The sector of the market that deals with contraception offers a long list of different contraceptive methods. Within the estroprogestinic choice, the routes of administration are oral, transdermic and vaginal one. Even though efficacy is comparable with these methods, secondary and adverse effects are directly involved in the acceptability of the method. STUDY DESIGN: This was a prospective comparative study. During 1 year, we enrolled 60 asymptomatic women who voluntarily requested combined oral contraception (COC) or combined contraceptive vaginal ring (CCVR group). After a baseline study of vaginal milieu prior to starting hormonal contraception, we performed a follow-up. For each woman, we examined vaginal pH; quantification of leukocytes, lactobacilli, Candida and cocci on saline microscopy fluid; Gram stain with Nugent score and the presence of vaginal infection [culture for Trichomonas vaginalis, albicans and nonalbicans Candida, Group B Streptococcus (GBS)]. RESULTS: At the end of follow-up, there was a little change of vaginal milieu in both groups. We noted an increase of lactobacilli in the CCVR users and an increase of GBS in COC users. CONCLUSION: CCVR compared to COC users showed an increase of the number of lactobacilli in vaginal flora. It means that an increase of leukorrhea in that group could be protective in terms of prevention of vaginal imbalance/infection.
Keywords: Administration, Intravaginal; Adolescent; Adult; Bacterial Load; Candida; Candida albicans; Contraceptive Devices, Female; Contraceptives, Oral, Combined; Female; Humans; Hydrogen-Ion Concentration; Lactobacillus; Leukocyte Count; Middle Aged; Prospective Studies; Streptococcus agalactiae; Trichomonas vaginalis; Vagina

The effects of uterine fundal pressure (Kristeller maneuver) on pelvic floor function after vaginal delivery. - Sartore, Andrea; De Seta, Francesco; Maso, Gianpaolo; Ricci, Giuseppe; Alberico, Salvatore; Borelli, Massimo; Guaschino, Secondo (Arch Gynecol Obstet, 2012)
PURPOSE: To evaluate the role of uterine fundal pressure during the second stage of labor (Kristeller maneuver) on pelvic floor dysfunction (urinary and anal incontinence, genital prolapse, pelvic floor strength). METHODS: 522 primiparous women, enrolled 3 months after vaginal delivery, were divided in two groups: group A (297 women) identifies the women who received Kristeller maneuvers with different indications (e.g. fetal distress, failure to progress, mother exhaustion), group B (225 women) the women without maneuver. Participants were questioned about urogynecological symptoms and examined by Q-tip test, digital test, vaginal perineometry and uroflowmetric stop test score. RESULTS: Mediolateral episiotomies, dyspareunia and perineal pain were significantly higher in Kristeller group, whereas urinary and anal incontinence, genital prolapse and pelvic floor strength were not significantly different between the groups. CONCLUSIONS: Kristeller maneuver does not modify puerperal pelvic floor function but increases the rate of episiotomies.
Keywords: Delivery, Obstetric; Dyspareunia; Dystocia; Episiotomy; Fatigue; Fecal Incontinence; Female; Fetal Distress; Humans; Labor Stage, Second; Pain, Postoperative; Pelvic Floor; Pelvic Organ Prolapse; Perineum; Pregnancy; Pressure; Puerperal Disorders; Urinary Incontinence; Uterus

Efficacy of rifaximin vaginal tablets in treatment of bacterial vaginosis: a molecular characterization of the vaginal microbiota. - Cruciani, Federica; Brigidi, Patrizia; Calanni, Fiorella; Lauro, Vittoria; Tacchi, Raffaella; Donders, Gilbert; Peters, Klaus; Guaschino, Secondo; Vitali, Beatrice (Antimicrob Agents Chemother, 2012)
Bacterial vaginosis (BV) is a common vaginal disorder characterized by an alteration of the vaginal bacterial morphotypes, associated with sexually transmitted infections and adverse pregnancy outcomes. The purpose of the present study was to evaluate the impact of different doses of rifaximin vaginal tablets (100 mg/day for 5 days, 25 mg/day for 5 days, and 100 mg/day for 2 days) on the vaginal microbiota of 102 European patients with BV enrolled in a multicenter, double-blind, randomized, placebo-controlled study. An integrated molecular approach based on quantitative PCR (qPCR) and PCR-denaturing gradient gel electrophoresis (PCR-DGGE) was used to investigate the effects of vaginal tablets containing the antibiotic. An increase in members of the genus Lactobacillus and a decrease in the BV-related bacterial groups after the antibiotic treatment were demonstrated by qPCR. PCR-DGGE profiles confirmed the capability of rifaximin to modulate the composition of the vaginal microbial communities and to reduce their complexity. This molecular analysis supported the clinical observation that rifaximin at 25 mg/day for 5 days represents an effective treatment to be used in future pivotal studies for the treatment of BV.
Keywords: Adolescent; Adult; Anti-Bacterial Agents; Double-Blind Method; Female; Humans; Lactobacillus; Metagenome; Middle Aged; Rifamycins; RNA, Ribosomal, 16S; Vagina; Vaginal Creams, Foams, and Jellies; Vaginosis, Bacterial; Young Adult

Endothelial cells obtained from patients affected by chronic venous disease exhibit a pro-inflammatory phenotype. - Tisato, Veronica; Zauli, Giorgio; Voltan, Rebecca; Gianesini, Sergio; di Iasio, Maria Grazia; Volpi, Ilaria; Fiorentini, Guido; Zamboni, Paolo; Secchiero, Paola (PLoS One, 2012)
BACKGROUND: The inflammatory properties of vein endothelium in relation to chronic venous disease (CVD) have been poorly investigated. Therefore, new insights on the characteristics of large vein endothelium would increase our knowledge of large vessel physiopathology. METHODOLOGY/PRINCIPAL FINDINGS: Surgical specimens of veins were obtained from the tertiary venous network (R3) and/or saphenous vein (SF) of patients affected by CVD and from control individuals. Highly purified venous endothelial cell (VEC) cultures obtained from CVD patients were characterized for morphological, phenotypic and functional properties compared to control VEC. An increase of CD31/PECAM-1, CD146 and ICAM-1 surface levels was documented at flow cytometry in pathological VEC with respect to normal controls. Of note, the strongest expression of these pro-inflammatory markers was observed in VEC obtained from patients with more advanced disease. Similarly, spontaneous cell proliferation and resistance to starvation was higher in pathological than in normal VEC, while the migratory response of VEC showed an opposite trend, being significantly lower in VEC obtained from pathological specimens. In addition, in keeping with a higher baseline transcriptional activity of NF-kB, the release of the pro-inflammatory cytokines osteoprotegerin (OPG) and vascular endothelial growth factor (VEGF) was higher in pathological VEC cultures with respect to control VEC. Interestingly, there was a systemic correlation to these in vitro data, as demonstrated by higher serum OPG and VEGF levels in CVD patients with respect to normal healthy controls. CONCLUSION/SIGNIFICANCE: Taken together, these data indicate that large vein endothelial cells obtained from CVD patients exhibit a pro-inflammatory phenotype, which might significantly contribute to systemic inflammation in CVD patients.
Keywords: Adult; Antigens, CD146; Antigens, CD31; Body Mass Index; Cell Culture Techniques; Endothelial Cells; Female; Flow Cytometry; Humans; Inflammation; Intercellular Adhesion Molecule-1; Kinetics; Male; Microscopy, Electron, Scanning; Middle Aged; Phenotype; Saphenous Vein; Vascular Diseases

European Society for Pediatric Gastroenterology, Hepatology, and Nutrition guidelines for the diagnosis of coeliac disease. - Husby, S; Koletzko, S; Korponay-Szabó, I R; Mearin, M L; Phillips, A; Shamir, R; Troncone, R; Giersiepen, K; Branski, D; Catassi, C; Lelgeman, M; Mäki, M; et al. (J Pediatr Gastroenterol Nutr, 2012)
OBJECTIVE: Diagnostic criteria for coeliac disease (CD) from the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) were published in 1990. Since then, the autoantigen in CD, tissue transglutaminase, has been identified; the perception of CD has changed from that of a rather uncommon enteropathy to a common multiorgan disease strongly dependent on the haplotypes human leukocyte antigen (HLA)-DQ2 and HLA-DQ8; and CD-specific antibody tests have improved. METHODS: A panel of 17 experts defined CD and developed new diagnostic criteria based on the Delphi process. Two groups of patients were defined with different diagnostic approaches to diagnose CD: children with symptoms suggestive of CD (group 1) and asymptomatic children at increased risk for CD (group 2). The 2004 National Institutes of Health/Agency for Healthcare Research and Quality report and a systematic literature search on antibody tests for CD in paediatric patients covering the years 2004 to 2009 was the basis for the evidence-based recommendations on CD-specific antibody testing. RESULTS: In group 1, the diagnosis of CD is based on symptoms, positive serology, and histology that is consistent with CD. If immunoglobulin A anti-tissue transglutaminase type 2 antibody titers are high (>10 times the upper limit of normal), then the option is to diagnose CD without duodenal biopsies by applying a strict protocol with further laboratory tests. In group 2, the diagnosis of CD is based on positive serology and histology. HLA-DQ2 and HLA-DQ8 testing is valuable because CD is unlikely if both haplotypes are negative. CONCLUSIONS: The aim of the new guidelines was to achieve a high diagnostic accuracy and to reduce the burden for patients and their families. The performance of these guidelines in clinical practice should be evaluated prospectively.
Keywords: Adolescent; Celiac Disease; Child; Duodenum; HLA-DQ Antigens; Humans; Immunoglobulin A; Transglutaminases

Evidence of inbreeding depression on human height. - McQuillan, Ruth; Eklund, Niina; Pirastu, Nicola; Kuningas, Maris; McEvoy, Brian P; Esko, Tõnu; Corre, Tanguy; Davies, Gail; Kaakinen, Marika; Lyytikäinen, Leo-Pekka; Kristiansson, Kati; Havulinna, Aki S; et al. (PLoS Genet, 2012)
Stature is a classical and highly heritable complex trait, with 80%-90% of variation explained by genetic factors. In recent years, genome-wide association studies (GWAS) have successfully identified many common additive variants influencing human height; however, little attention has been given to the potential role of recessive genetic effects. Here, we investigated genome-wide recessive effects by an analysis of inbreeding depression on adult height in over 35,000 people from 21 different population samples. We found a highly significant inverse association between height and genome-wide homozygosity, equivalent to a height reduction of up to 3 cm in the offspring of first cousins compared with the offspring of unrelated individuals, an effect which remained after controlling for the effects of socio-economic status, an important confounder (χ(2) = 83.89, df = 1; p = 5.2 × 10(-20)). There was, however, a high degree of heterogeneity among populations: whereas the direction of the effect was consistent across most population samples, the effect size differed significantly among populations. It is likely that this reflects true biological heterogeneity: whether or not an effect can be observed will depend on both the variance in homozygosity in the population and the chance inheritance of individual recessive genotypes. These results predict that multiple, rare, recessive variants influence human height. Although this exploratory work focuses on height alone, the methodology developed is generally applicable to heritable quantitative traits (QT), paving the way for an investigation into inbreeding effects, and therefore genetic architecture, on a range of QT of biomedical importance.
Keywords: Adult; Aged; Body Height; Consanguinity; Databases, Genetic; Family; Female; Genes, Recessive; Genetic Heterogeneity; Genome-Wide Association Study; Homozygote; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Extra-large letter spacing improves reading in dyslexia. - Zorzi, Marco; Barbiero, Chiara; Facoetti, Andrea; Lonciari, Isabella; Carrozzi, Marco; Montico, Marcella; Bravar, Laura; George, Florence; Pech-Georgel, Catherine; Ziegler, Johannes C (Proc Natl Acad Sci U S A, 2012)
Although the causes of dyslexia are still debated, all researchers agree that the main challenge is to find ways that allow a child with dyslexia to read more words in less time, because reading more is undisputedly the most efficient intervention for dyslexia. Sophisticated training programs exist, but they typically target the component skills of reading, such as phonological awareness. After the component skills have improved, the main challenge remains (that is, reading deficits must be treated by reading more--a vicious circle for a dyslexic child). Here, we show that a simple manipulation of letter spacing substantially improved text reading performance on the fly (without any training) in a large, unselected sample of Italian and French dyslexic children. Extra-large letter spacing helps reading, because dyslexics are abnormally affected by crowding, a perceptual phenomenon with detrimental effects on letter recognition that is modulated by the spacing between letters. Extra-large letter spacing may help to break the vicious circle by rendering the reading material more easily accessible.
Keywords: Attention; Awareness; Child; Dyslexia; Form Perception; France; Humans; Italy; Language; Pattern Recognition, Visual; Phonetics; Reading; Vision, Ocular; Visual Fields

Frequency of human papillomavirus types 16, 18, 31, and 33 and sites of cervical lesions in gynecological patients from Recife, Brazil. - Baldez da Silva, M F P T; Guimarães, V; Silva, M A R; Medeiros do Amaral, C M; Beçak, W; Stocco, R C; Freitas, A C; Crovella, S (Genet Mol Res, 2012)
Human papilloma virus (HPV) is a well-established cause of cervical cancer. While many studies have been performed so far on HPV viral biology, mode of infection and prevention measures, scanty information is available on lesion sites of infected women and the incidence of viral types at specific locations. We looked for a possible relationship between the most common viral types (HPVs 16, 18, 31, 33) found in Recife, PE, Brazil, and lesion sites. We examined 396 HPV-positive women at the Gynecological Unit of the IMIP at Recife; 288 women were positive for HPV 16, 18, 31, or 33, present as a single-virus type or as co-infection. HPV 16 was the most frequent virus type found in the vulva, vagina, uterine cervix-vagina, and uterine cervix. HPV 31 was the second prevalent virus type in vulva, vagina, uterine cervix-vagina, uterine cervix, and mole. HPVs 18 and 33 were present with similar frequencies in the mole-vulva region. Among the co-infections, HPV 16/18 and HPV16/31 were the most frequent in our study group, followed by HPV 16/33.
Keywords: Adolescent; Adult; Brazil; Cervix Uteri; DNA, Viral; Female; Human papillomavirus 16; Human papillomavirus 18; Human papillomavirus 31; Humans; Papillomavirus Infections; Uterine Cervical Diseases; Young Adult

Functional single-nucleotide polymorphisms in the DEFB1 gene are associated with systemic lupus erythematosus in Southern Brazilians. - Sandrin-Garcia, P; Brandão, L A C; Guimarães, R L; Pancoto, J A T; Donadi, E A; Lima-Filho, J L de; Segat, L; Crovella, S (Lupus, 2012)
Systemic lupus erythematosus (SLE) is an autoimmune disease that results in inflammation and tissue damage. The etiology of SLE remains unknown, but recent studies have shown that the innate immune system may have a role in SLE pathogenesis through the secretion of small cationic peptides named defensins. The aim of the study was to determine the possible involvement in SLE of three functional single nucleotide polymorphisms (SNPs) (c.-52G>A, c.-44C>G and c.-20G>A) in the 5'UTR region of DEFB1 gene, by analyzing them in a population of 139 SLE patients and 288 healthy controls. The c.-52G>A SNP showed significant differences in allele and genotype frequency distribution between SLE patients and controls (p = 0.01 and p = 0.02 respectively) indicating protection against SLE (A allele, OR = 0.68, AA genotype OR = 0.51). Significant differences were also observed for c.-44C>G SNP, the C/G genotype being associated with susceptibility to SLE (OR = 1.60, p = 0.04). Moreover, statistically significant differences between patients and controls were found for two DEFB1 haplotypes (GCA and GGG, p = 0.01 and p = 0.02 respectively). When considering DEFB1 SNPs and SLE clinical and laboratory manifestations, significant association was found with neuropsychiatric disorders, immunological alterations and anti-DNA antibodies. In conclusion, our results evidence a possible role for the c.-52G>A and c.-44C>G DEFB1 polymorphisms in SLE pathogenesis, that can be considered as possible risk factors for development of disease and disease-related clinical manifestations. Additional studies are needed, to corroborate these results as well as functional studies to understand the biological role of these SNPs in the pathogenesis of SLE.
Keywords: Adolescent; Adult; Aged; beta-Defensins; Brazil; Case-Control Studies; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Lupus Erythematosus, Systemic; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

Genetics of food preferences: a first view from silk road populations. - Pirastu, Nicola; Robino, Antonietta; Lanzara, Carmela; Athanasakis, Emmanouil; Esposito, Laura; Tepper, Beverly J; Gasparini, Paolo (J Food Sci, 2012)
Food preferences are the main factor driving food intake and choice. There are good reasons to suspect some genetic influence on food acceptance, not least because genetic factors are implicated in a number of factors that are likely to be related to food choice. In addition, some food dislikes show themselves early in life, before there is any evidence for aversive experiences. Although taste has been widely studied in regards of pure tastes such as bitter or sweet perception, the relationship between taste-related genes and food preferences has seldom been explored. In this work we investigated relationship of 37 taste-related genes with food preferences. The study was carried out during a scientific expedition through Caucasus and Central Asia (Silk Road) analyzing more than 400 samples from 5 different countries. A food preference questionnaire was administered to each participant and a DNA sample was obtained. Other information, such as age, sex, life style and anthropometrical measures, were also collected. We found significant associations with variants of: (1) TAS1R2 [Correction added after initial online publication on 27 Aug 2012. TAS1R3 was changed to TAS1R2.] gene and liking of Vodka (P= 1.6 × 10(-3)), white wine (P= 4.0 × 10(-4)) and lamb meat (P= 1.6 × 10(-3)); (2) PCLB2 gene and preference for Hot Tea (P= 8.0 × 10(-4)); (3) TPRV1 gene and beet liking (P= 3.8 × 10(-5)); and (4) ITPR3 gene and liking of both lamb meat (5.8 × 10(-4)) and sheep cheese (8.9×10(-4)). These findings give a new insight on a better understanding, of genetic factors influencing food preferences which is critical to the development of effective dietary interventions, especially for people that may be genetically not predisposed for liking specific nutrients.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Azerbaijan; Child; Choice Behavior; Cohort Studies; Female; Food Habits; Food Preferences; Gene Frequency; Genotype; Georgia; Humans; Kazakhstan; Linear Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Questionnaires; Tajikistan; Taste; Uzbekistan; Young Adult

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genomic profiling by whole-genome single nucleotide polymorphism arrays in Wilms tumor and association with relapse. - Perotti, Daniela; Spreafico, Filippo; Torri, Federica; Gamba, Beatrice; d'Adamo, Pio; Pizzamiglio, Sara; Terenziani, Monica; Catania, Serena; Collini, Paola; Nantron, Marilina; Pession, Andrea; Bianchi, Maurizio; et al. (Genes Chromosomes Cancer, 2012)
Despite the excellent survival rate of Wilms tumor (WT) patients, only approximately one-half of children who suffer tumor recurrence reach second durable remission. This underlines the need for novel markers to optimize initial treatment. We investigated 77 tumors using Illumina 370CNV-QUAD genotyping BeadChip arrays and compared their genomic profiles to detect copy number (CN) abnormalities and allelic ratio anomalies associated with the following clinicopathological variables: relapse (yes vs. no), age at diagnosis (≤ 24 months vs. >24 months), and disease stage (low stage, I and II, vs. high stage, III and IV). We found that CN gains at chromosome region 1q21.1-q31.3 were significantly associated with relapse. Additional genetic events, including allelic imbalances at chromosome arms 1p, 1q, 3p, 3q, and 14q were also found to occur at higher frequency in relapsing tumors. Interestingly, allelic imbalances at 1p and 14q also showed a borderline association with higher tumor stages. No genetic events were found to be associated with age at diagnosis. This is the first genome wide analysis with single nucleotide polymorphism (SNP) arrays specifically investigating the role of genetic anomalies in predicting WT relapse on cases prospectively enrolled in the same clinical trial. Our study, besides confirming the role of 1q gains, identified a number of additional candidate genetic markers, warranting further molecular investigations.
Keywords: Adolescent; Allelic Imbalance; Child; Child, Preschool; Chromosome Aberrations; DNA Copy Number Variations; Female; Genetic Markers; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Infant; Kaplan-Meier Estimate; Male; Polymorphism, Single Nucleotide; Prospective Studies; Recurrence; Wilms Tumor

High prevalence of serum antibodies reacting with simian virus 40 capsid protein mimotopes in patients affected by malignant pleural mesothelioma. - Mazzoni, Elisa; Corallini, Alfredo; Cristaudo, Alfonso; Taronna, Angelo; Tassi, Gianfranco; Manfrini, Marco; Comar, Manola; Bovenzi, Massimo; Guaschino, Roberto; Vaniglia, Francesca; Magnani, Corrado; Casali, Ferruccio; et al. (Proc Natl Acad Sci U S A, 2012)
Human malignant pleural mesothelioma (MPM) is considered a rare tumor, but recent estimations indicate that one-quarter million people will die of this neoplasm in Europe in the next three decades. The mineral asbestos is considered the main causative agent of this neoplasm. MPM is largely unresponsive to conventional chemotherapy/radiotherapy. In addition to asbestos exposure, genetic predisposition to asbestos carcinogenesis and to simian virus (SV)40 infection has also been suggested. SV40 is a DNA tumor virus found in some studies to be associated at high prevalence with MPM. SV40 sequences have also been detected, although at a lower prevalence than in MPM, in blood specimens from healthy donors. However, some studies have failed to reveal SV40 footprints in MPM and its association with this neoplasm. These conflicting results indicate the need for further investigations with new approaches. We report on the presence of antibodies in serum samples from patients affected by MPM that specifically react with two different SV40 mimotopes. The two SV40 peptides used in indirect ELISAs correspond to viral capsid proteins. ELISA with the two SV40 mimotopes gave overlapping results. Our data indicate that in serum samples from MPM-affected patients (n = 97), the prevalence of antibodies against SV40 viral capsid protein antigens is significantly higher (26%, P = 0.043) than in the control group (15%) represented by healthy subjects (n = 168) with the same median age (66 y) and sex. Our results suggest that SV40 is associated with a subset of MPM and circulates in humans.
Keywords: Amino Acid Sequence; Antibodies, Viral; Capsid Proteins; Enzyme-Linked Immunosorbent Assay; Female; Humans; Male; Mesothelioma; Molecular Sequence Data; Pleural Neoplasms; Pregnancy; Simian virus 40

Hydrogen sulfide down-regulates the expression and release of osteoprotegerin (OPG) by vascular endothelial cells. - Rimondi, Erika; di Iasio, Maria Grazia; Gonelli, Arianna; Celeghini, Claudio; Secchiero, Paola; Zauli, Giorgio (Invest New Drugs, 2012)
Keywords: Cell Death; Cytostatic Agents; Down-Regulation; Human Umbilical Vein Endothelial Cells; Humans; Hydrogen Sulfide; Osteoprotegerin; Tumor Necrosis Factor-alpha

Identification of a New Mutation (L46P) in the Human NOG Gene in an Italian Patient with Symphalangism Syndrome. - Athanasakis, E; Biarnés, X; Bonati, M T; Gasparini, P; Faletra, F (Mol Syndromol, 2012)
Proximal symphalangism (SYM1) is a joint morphogenesis disorder characterized by stapes ankylosis, proximal interphalangeal joint fusion, skeletal anomalies and conductive hearing loss. Noggin is a bone morphogenetic protein (BMP) antagonist essential for normal bone and joint development in humans and mice. Autosomal dominant mutations have been described in the NOG gene, encoding the noggin protein. We analyzed an Italian sporadic patient with SYM1 due to a novel NOG mutation (L46P) based on a c.137T>C transition. A different pathogenic mutation in the same codon (L46D) has been previously described in an in vivo chicken model. An in silico model shows a decreased binding affinity between noggin and BMP7 for both L46D and L46P compared to the wild type. Therefore, this codon should play an important role in BMP7 binding activity of the noggin protein and consequently to the joint morphogenesis.

Importance of bladder bowel dysfunction in patients with urinary tract infection. - Giurici, Nagua; Pennesi, Marco (J Pediatr, 2012)
Keywords: Cystoscopy; Female; Fever; Humans; Male; Ureteroscopy; Urinary Tract Infections; Vesico-Ureteral Reflux

In vivo anti-lymphoma activity of an agonistic human recombinant anti-TRAIL-R2 minibody. - Zauli, Giorgio; Corallini, Federica; Zorzet, Sonia; Grill, Vittorio; Marzari, Roberto; Secchiero, Paola (Invest New Drugs, 2012)
A new single-chain fragment variable (scFv) to TRAIL-R2 receptor produced as minibody (MB2.23) was characterized for anti-lymphoma activity in vivo. For this purpose, a disseminated lymphoma model was generated by intraperitoneal inoculation of BJAB cells in severe combined immunodeficiency mice. Two weekly injections with MB2.23 (10 mg/kg) were able to significantly increase the median survival time of lymphoma-bearing animals with respect to the vehicle-treated control mice, providing a rationale for further investigating the use of MB2.23 in anticancer therapy.
Keywords: Animals; Humans; Immunotherapy; Injections, Intraperitoneal; Lymphoma, B-Cell; Mice; Mice, SCID; Receptors, TNF-Related Apoptosis-Inducing Ligand; Single-Chain Antibodies; Time Factors; Xenograft Model Antitumor Assays

Inflammation profile of four early onset Crohn patients. - Marcuzzi, Annalisa; Girardelli, Martina; Bianco, Anna Monica; Martelossi, Stefano; Magnolato, Andrea; Tommasini, Alberto; Crovella, Sergio (Gene, 2012)
Crohn disease (CD) is a multifactorial disorder affecting mainly young adults. Sometimes, however, it can present in the first year of life (Early onset Crohn disease (EOCD)) showing an unpredictable course and can often be more severe than at older ages. Some cases have been associated to an underlying primary immunodeficiency such as IL10R deficiency. We studied the functional response to IL-10 and the genotype of IL-10 receptor in four patients with early onset crohn-like colitis. We found an IL10R variant, which may be associated with a decreased response to the cytokine in one patient. Further studies to determine its pathogenic effect should be performed. In addition IL-10 mediated inhibition of LPS-induced TNFα expression was measured in patient's monocytes.
Keywords: Crohn Disease; Cytokines; Humans; Inflammation; Monocytes; Nod2 Signaling Adaptor Protein; Polymorphism, Genetic; Receptors, Interleukin-10; Tumor Necrosis Factor-alpha

Influence of age, sex and ethnicity on platelet count in five Italian geographic isolates: mild thrombocytopenia may be physiological. - Biino, Ginevra; Gasparini, Paolo; d'Adamo, Pio; Ciullo, Marina; Nutile, Teresa; Toniolo, Daniela; Sala, Cinzia; Minelli, Cosetta; Gögele, Martin; Balduini, Carlo L (Br J Haematol, 2012)
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Female; Humans; Infant; Italy; Male; Middle Aged; Platelet Count; Reference Values; Sex Distribution; Thrombocytopenia; Young Adult

Integration of genome-wide association studies with biological knowledge identifies six novel genes related to kidney function. - Chasman, Daniel I; Fuchsberger, Christian; Pattaro, Cristian; Teumer, Alexander; Böger, Carsten A; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (Hum Mol Genet, 2012)
In conducting genome-wide association studies (GWAS), analytical approaches leveraging biological information may further understanding of the pathophysiology of clinical traits. To discover novel associations with estimated glomerular filtration rate (eGFR), a measure of kidney function, we developed a strategy for integrating prior biological knowledge into the existing GWAS data for eGFR from the CKDGen Consortium. Our strategy focuses on single nucleotide polymorphism (SNPs) in genes that are connected by functional evidence, determined by literature mining and gene ontology (GO) hierarchies, to genes near previously validated eGFR associations. It then requires association thresholds consistent with multiple testing, and finally evaluates novel candidates by independent replication. Among the samples of European ancestry, we identified a genome-wide significant SNP in FBXL20 (P = 5.6 × 10(-9)) in meta-analysis of all available data, and additional SNPs at the INHBC, LRP2, PLEKHA1, SLC3A2 and SLC7A6 genes meeting multiple-testing corrected significance for replication and overall P-values of 4.5 × 10(-4)-2.2 × 10(-7). Neither the novel PLEKHA1 nor FBXL20 associations, both further supported by association with eGFR among African Americans and with transcript abundance, would have been implicated by eGFR candidate gene approaches. LRP2, encoding the megalin receptor, was identified through connection with the previously known eGFR gene DAB2 and extends understanding of the megalin system in kidney function. These findings highlight integration of existing genome-wide association data with independent biological knowledge to uncover novel candidate eGFR associations, including candidates lacking known connections to kidney-specific pathways. The strategy may also be applicable to other clinical phenotypes, although more testing will be needed to assess its potential for discovery in general.
Keywords: Amino Acid Transport Systems, Basic; Antigens, CD98 Heavy Chain; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inhibin-beta Subunits; Intracellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-2; Membrane Proteins; Polymorphism, Single Nucleotide

International collaboration as a tool for diagnosis of patients with inherited thrombocytopenia in the setting of a developing country. - Glembotsky, A C; Marta, R F; Pecci, A; De Rocco, D; Gnan, C; Espasandin, Y R; Goette, N P; Negro, F; Noris, P; Savoia, A; Balduini, C L; Molinas, F C; et al. (J Thromb Haemost, 2012)
BACKGROUND: Inherited thrombocytopenias (ITs) are heterogeneous genetic disorders that frequently represent a diagnostic challenge. The requirement of highly specialized tests for diagnosis represents a particular problem in resource-limited settings. To overcome this difficulty, we applied a diagnostic algorithm and developed a collaboration program with a specialized international center in order to increase the diagnostic yield in a cohort of patients in Argentina. METHODS: Based on the algorithm, initial evaluation included collection of clinical data, platelet size, blood smear examination and platelet aggregation tests. Confirmatory tests were performed according to diagnostic suspicion, which included platelet glycoprotein expression, immunofluorescence for myosin-9 in granulocytes and platelet thrombospondin-1 and molecular screening of candidate genes. RESULTS: Thirty-one patients from 14 pedigrees were included; their median age was 32 (4-72) years and platelet count 72 (4-147)×10(9) L(-1). Autosomal dominant inheritance was found in nine (64%) pedigrees; 10 (71%) had large platelets and nine (29%) patients presented with syndromic forms. A definitive diagnosis was made in 10 of 14 pedigrees and comprised MYH9-related disease in four, while classic and monoallelic Bernard-Soulier syndrome, gray platelet syndrome, X-linked thrombocytopenia, thrombocytopenia 2 (ANKRD26 mutation) and familial platelet disorder with predisposition to acute myelogenous leukemia were diagnosed in one pedigree each. CONCLUSIONS: Adoption of an established diagnostic algorithm and collaboration with an expert referral center proved useful for diagnosis of IT patients in the setting of a developing country. This initiative may serve as a model to develop international networks with the goal of improving diagnosis and care of patients with these rare diseases.
Keywords: Adolescent; Adult; Aged; Algorithms; Argentina; Biological Markers; Child; Child, Preschool; Cooperative Behavior; Developing Countries; DNA Mutational Analysis; Feasibility Studies; Female; Flow Cytometry; Fluorescent Antibody Technique; Genetic Predisposition to Disease; Genetic Testing; Health Services Accessibility; Hematologic Tests; Heredity; Humans; International Cooperation; Italy; Male; Middle Aged; Molecular Motor Proteins; Myosin Heavy Chains; Pedigree; Phenotype; Platelet Count; Platelet Function Tests; Predictive Value of Tests; Prognosis; Referral and Consultation; Thrombocytopenia; Thrombospondin 1; Young Adult

Letter: inflammatory bowel disease, complementary and alternative medicine, and genetics. - Bianco, A M; Vuch, J; Girardelli, M; Zanin, V; Marcuzzi, A; Crovella, S (Aliment Pharmacol Ther, 2012)
Keywords: Complementary Therapies; Female; Humans; Inflammatory Bowel Diseases; Male; Medication Adherence

Lovastatin-induced apoptosis is modulated by geranylgeraniol in a neuroblastoma cell line. - Marcuzzi, Annalisa; Zanin, Valentina; Piscianz, Elisa; Tricarico, Paola Maura; Vuch, Josef; Girardelli, Martina; Monasta, Lorenzo; Bianco, Anna Monica; Crovella, Sergio (Int J Dev Neurosci, 2012)
Mevalonic aciduria (MA), the most severe form of mevalonate kinase deficiency (MKD), is still an orphan drug disease and the pathogenetic mechanisms underlying neuronal dysfunction is still poorly understood. In our study we have investigated the apoptotic mechanism mediated by the exposure of the cultured neuroblastoma cell line, SH-SY5Y, to lovastatin in absence or in presence of the isoprenoid, geranylgeraniol, with the aim of unraveling the pathogenesis of MA. Lovastatin, blocks the mevalonate pathway inhibiting the 3-hydroxy-3-methylglutaryl-CoA reductase (HMG-CR), an enzyme of the mevalonate pathway upstream the mevalonate kinase enzyme, reproducing biochemical features similar to those found in MKD. We demonstrate that apoptosis in neuronal lovastatin treated-cells is induced by the mitochondrial pathway, with caspase-9 as the initiator and caspase-3 as the effector caspase. The presence of geranylgeraniol modulates both the caspase-9 and caspase-3 activity in a dose-dependent way, confirming that this isoprenoid enters the mevalonate pathway, is metabolized and finally is able to by-pass the statin biochemical block reconstituting the mevalonate pathway. According to our findings, it should not be the time course adopted that modulates the apoptotic response but rather the isoprenoid itself. Being aware that our results have been obtained using a biochemical model of MKD, and not cells from patients with the disease, we believe our findings increase the knowledge of MA pathogenesis, and may possibly contribute to the development of novel therapeutic strategies.
Keywords: Analysis of Variance; Apoptosis; Caspases; Cell Line, Tumor; Diterpenes; Dose-Response Relationship, Drug; Drug Interactions; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Lovastatin; Neuroblastoma; Time Factors

Lutein and zeaxanthin supplementation in preterm infants to prevent retinopathy of prematurity: a randomized controlled study. - Dani, Carlo; Lori, Ilaria; Favelli, Federica; Frosini, Saverio; Messner, Hubert; Wanker, Petra; De Marini, Sergio; Oretti, Chiara; Boldrini, Antonio; Massimiliano, Ciantelli; Bragetti, Patrizia; Germini, Cristiana (J Matern Fetal Neonatal Med, 2012)
OBJECTIVES: Lutein and its isomer zeaxanthin (L/Z) function in the eye as antioxidant agents and blue-light filters. Our aim was to evaluate whether their administration could help decrease the occurrence of retinopathy of prematurity (ROP) in preterm infants. METHODS: Infants with gestational age ≤32 weeks were randomly assigned to receive a daily dose of L/Z (0.14 + 0.006 mg) or placebo until discharge. RESULTS: ROP occurrence was similar in the L/Z (11/58; 19%) and placebo (15/56; 27%) groups, as the occurrence of ROP at each stage and the need of eye surgery. CONCLUSION: L/Z supplementation was ineffective in preventing ROP in preterm infants and did not affect the outcome at discharge of our patients.
Keywords: Antioxidants; Drug Administration Schedule; Drug Combinations; Female; Humans; Infant, Newborn; Infant, Premature; Logistic Models; Lutein; Male; Retinopathy of Prematurity; Risk Factors; Treatment Outcome; Xanthophylls; Zeaxanthins

Mannose-binding lectin and MBL-associated serine protease-2 gene polymorphisms in a Brazilian population from Rio de Janeiro. - Ferraroni, N R; Segat, L; Guimarães, R L; Brandão, L A C; Crovella, S; Constantino-Silva, R N; Loja, C; da Silva Duarte, A J; Grumach, A S (Int J Immunogenet, 2012)
Mannose-binding lectin (MBL) is a protein able to bind to carbohydrate patterns on pathogen membranes; upon MBL binding, its' associated serine protease MBL-associated serine protease type 2 (MASP2) is autoactivated, promoting the activation of complement via the lectin pathway. For both MBL2 and MASP2 genes, the frequencies of polymorphisms are extremely variable between different ethnicities, and this aspect has to be carefully considered when performing genetic studies. While polymorphisms in the MBL-encoding gene (MBL2) have been associated, depending upon ethnicity, with several diseases in different populations, little is known about the distribution of MASP2 gene polymorphisms in human populations. The aim of our study was thus to determine the frequencies of MBL2 (exon 1 and promoter) and MASP2 (p.D371Y) polymorphisms in a Brazilian population from Rio de Janeiro. A total of 294 blood donor samples were genotyped for 27 polymorphisms in the MBL2 gene by direct sequencing of a region spanning from the promoter polymorphism H/L rs11003125 to the rs1800451 polymorphism (at codon 57 in the first exon of the gene). Genotyping for MASP2 p.D371Y was carried out using fluorogenic probes. To our knowledge, this is the first study reporting the prevalence of the MASP2 p.D371Y polymorphism in a Brazilian population. The C allele frequency 39% is something intermediate between the reported 14% in Europeans and 90% in Sub-Saharan Africans. MBL2 polymorphisms frequencies were quite comparable to those previously reported for admixed Brazilians. Both MBL2 and MASP2 polymorphisms frequencies reported in our study for the admixed Brazilian population are somehow intermediate between those reported in Europeans and Africans, reflecting the ethnic composition of the southern Brazilian population, estimated to derive from an admixture of Caucasian (31%), African (34%) and Native American (33%) populations. In conclusion, our population genetic study describes the frequencies of MBL2 and MASP2 functional SNPs in a population from Rio de Janeiro, with the aim of adding new information concerning the distribution of these SNPs in a previously unanalysed Brazilian population, thus providing a new genetic tool for the evaluation of the association of MBL2 and MASP2 functional SNPs with diseases in Brazil, with particular emphasis on the state of Rio de Janeiro.
Keywords: Adolescent; Adult; Brazil; Ethnic Groups; Exons; Female; Fluorescent Dyes; Gene Frequency; Genetics, Population; Genome, Human; HapMap Project; Humans; Male; Mannose-Binding Lectin; Mannose-Binding Protein-Associated Serine Proteases; Middle Aged; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Sequence Analysis, DNA; Young Adult

The MDM2 inhibitor Nutlin-3 modulates dendritic cell-induced T cell proliferation. - Gasparini, Chiara; Tommasini, Alberto; Zauli, Giorgio (Hum Immunol, 2012)
Nutlin-3, a small molecule inhibitor of the MDM2/p53 interaction, has been recently taken into consideration as a promising therapeutic tool for tumor treatment based on its ability to stabilize and activate the p53 transcription factor pathway. Since Nutlin-3 displays non cell-autonomous tumor-suppressor activities, we wanted to investigate its effect on dendritic cell functions, given the central role of these cells in the modulation of the immune response. We found that Nutlin-3 alone slightly affected the levels of major histocompatibility complex and costimulatory molecules and significantly promoted the ability of dendritic cells to stimulate T cells in the mixed lymphocyte reaction. Taken together, our findings suggest that the ability of Nutlin-3 to modulate dendritic cell functions and therefore lymphocyte proliferation might represent an additional important mechanism by which Nutlin-3 exerts its non cell-autonomous tumor-suppression function.
Keywords: Dendritic Cells; Humans; Imidazoles; Immunologic Factors; Immunophenotyping; Lymphocyte Activation; Piperazines; Proto-Oncogene Proteins c-mdm2; T-Lymphocytes

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Meta-analysis identifies multiple loci associated with kidney function-related traits in east Asian populations. - Okada, Yukinori; Sim, Xueling; Go, Min Jin; Wu, Jer-Yuarn; Gu, Dongfeng; Takeuchi, Fumihiko; Takahashi, Atsushi; Maeda, Shiro; Tsunoda, Tatsuhiko; Chen, Peng; Lim, Su-Chi; Wong, Tien-Yin; et al. (Nat Genet, 2012)
Chronic kidney disease (CKD), impairment of kidney function, is a serious public health problem, and the assessment of genetic factors influencing kidney function has substantial clinical relevance. Here, we report a meta-analysis of genome-wide association studies for kidney function-related traits, including 71,149 east Asian individuals from 18 studies in 11 population-, hospital- or family-based cohorts, conducted as part of the Asian Genetic Epidemiology Network (AGEN). Our meta-analysis identified 17 loci newly associated with kidney function-related traits, including the concentrations of blood urea nitrogen, uric acid and serum creatinine and estimated glomerular filtration rate based on serum creatinine levels (eGFRcrea) (P < 5.0 × 10(-8)). We further examined these loci with in silico replication in individuals of European ancestry from the KidneyGen, CKDGen and GUGC consortia, including a combined total of ∼110,347 individuals. We identify pleiotropic associations among these loci with kidney function-related traits and risk of CKD. These findings provide new insights into the genetics of kidney function.
Keywords: Asian Continental Ancestry Group; Blood Urea Nitrogen; Cohort Studies; Creatinine; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic; Uric Acid

Mevalonate kinase deficiency: disclosing the role of mevalonate pathway modulation in inflammation. - Marcuzzi, Annalisa; Crovella, Sergio; Monasta, Lorenzo; Vecchi Brumatti, Liza; Gattorno, Marco; Frenkel, Joost (Curr Pharm Des, 2012)
Inflammation is a highly regulated process involved both in the response to pathogens as well as in tissue homeostasis. In recent years, a complex network of proteins in charge of inflammation control has been revealed by the study of hereditary periodic fever syndromes. Most of these proteins belong to a few families and share the capability of sensing pathogen-associated and damageassociated molecular patterns. By interacting with each other, these proteins participate in the assembly of molecular platforms, called inflammasomes, which ultimately lead to the activation of cytokines, to the transcription of inflammatory genes or to the induction of cell apoptosis. Among hereditary periodic fever syndromes, mevalonate kinase deficiency (MKD) is the sole in which the phenotype did not directly associate with a deficiency of these proteins, but with a metabolic defect of the mevalonate pathway, highlighting the importance of this metabolic pathway in the inflammation control. Noteworthy, drugs acting on this pathway can greatly influence the inflammatory response. The modulation of inflammation by mevalonate pathway is of interest, since it may involve mechanisms not directly referable to inflammasomes. MKD provides a model to study these mechanisms and possibly to develop new classes of anti-inflammatory drugs.
Keywords: Animals; Anti-Inflammatory Agents; Apoptosis; Cytokines; Drug Design; Hereditary Autoinflammatory Diseases; Humans; Inflammasomes; Inflammation; Mevalonate Kinase Deficiency; Mevalonic Acid

miR-EdiTar: a database of predicted A-to-I edited miRNA target sites. - Laganà, Alessandro; Paone, Alessio; Veneziano, Dario; Cascione, Luciano; Gasparini, Pierluigi; Carasi, Stefania; Russo, Francesco; Nigita, Giovanni; Macca, Valentina; Giugno, Rosalba; Pulvirenti, Alfredo; Shasha, Dennis; et al. (Bioinformatics, 2012)
MOTIVATION: A-to-I RNA editing is an important mechanism that consists of the conversion of specific adenosines into inosines in RNA molecules. Its dysregulation has been associated to several human diseases including cancer. Recent work has demonstrated a role for A-to-I editing in microRNA (miRNA)-mediated gene expression regulation. In fact, edited forms of mature miRNAs can target sets of genes that differ from the targets of their unedited forms. The specific deamination of mRNAs can generate novel binding sites in addition to potentially altering existing ones. RESULTS: This work presents miR-EdiTar, a database of predicted A-to-I edited miRNA binding sites. The database contains predicted miRNA binding sites that could be affected by A-to-I editing and sites that could become miRNA binding sites as a result of A-to-I editing. AVAILABILITY: miR-EdiTar is freely available online at http://microrna.osumc.edu/mireditar. CONTACT: alessandro.lagana@osumc.edu or carlo.croce@osumc.edu SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: Adenosine; Binding Sites; Databases, Genetic; Gene Expression Regulation; Humans; Inosine; Internet; MicroRNAs; Nucleic Acid Conformation; RNA Editing

Molecular diagnosis of Usher syndrome: application of two different next generation sequencing-based procedures. - Licastro, Danilo; Mutarelli, Margherita; Peluso, Ivana; Neveling, Kornelia; Wieskamp, Nienke; Rispoli, Rossella; Vozzi, Diego; Athanasakis, Emmanouil; D'Eustacchio, Angela; Pizzo, Mariateresa; D'Amico, Francesca; Ziviello, Carmela; et al. (PLoS One, 2012)
Usher syndrome (USH) is a clinically and genetically heterogeneous disorder characterized by visual and hearing impairments. Clinically, it is subdivided into three subclasses with nine genes identified so far. In the present study, we investigated whether the currently available Next Generation Sequencing (NGS) technologies are already suitable for molecular diagnostics of USH. We analyzed a total of 12 patients, most of which were negative for previously described mutations in known USH genes upon primer extension-based microarray genotyping. We enriched the NGS template either by whole exome capture or by Long-PCR of the known USH genes. The main NGS sequencing platforms were used: SOLiD for whole exome sequencing, Illumina (Genome Analyzer II) and Roche 454 (GS FLX) for the Long-PCR sequencing. Long-PCR targeting was more efficient with up to 94% of USH gene regions displaying an overall coverage higher than 25×, whereas whole exome sequencing yielded a similar coverage for only 50% of those regions. Overall this integrated analysis led to the identification of 11 novel sequence variations in USH genes (2 homozygous and 9 heterozygous) out of 18 detected. However, at least two cases were not genetically solved. Our result highlights the current limitations in the diagnostic use of NGS for USH patients. The limit for whole exome sequencing is linked to the need of a strong coverage and to the correct interpretation of sequence variations with a non obvious, pathogenic role, whereas the targeted approach suffers from the high genetic heterogeneity of USH that may be also caused by the presence of additional causative genes yet to be identified.
Keywords: Child, Preschool; Exome; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Molecular Diagnostic Techniques; Pilot Projects; Sequence Analysis, DNA; Usher Syndromes

New insights in the sugarcane transcriptome responding to drought stress as revealed by superSAGE. - Kido, Éderson Akio; Ferreira Neto, José Ribamar Costa; Silva, Roberta Lane de Oliveira; Pandolfi, Valesca; Guimarães, Ana Carolina Ribeiro; Veiga, Daniela Truffi; Chabregas, Sabrina Moutinho; Crovella, Sergio; Benko-Iseppon, Ana Maria (ScientificWorldJournal, 2012)
In the scope of the present work, four SuperSAGE libraries have been generated, using bulked root tissues from four drought-tolerant accessions as compared with four bulked sensitive genotypes, aiming to generate a panel of differentially expressed stress-responsive genes. Both groups were submitted to 24 hours of water deficit stress. The SuperSAGE libraries produced 8,787,315 tags (26 bp) that, after exclusion of singlets, allowed the identification of 205,975 unitags. Most relevant BlastN matches comprised 567,420 tags, regarding 75,404 unitags with 164,860 different ESTs. To optimize the annotation efficiency, the Gene Ontology (GO) categorization was carried out for 186,191 ESTs (BlastN against Uniprot-SwissProt), permitting the categorization of 118,208 ESTs (63.5%). In an attempt to elect a group of the best tags to be validated by RTqPCR, the GO categorization of the tag-related ESTs allowed the in silico identification of 213 upregulated unitags responding basically to abiotic stresses, from which 145 presented no hits after BlastN analysis, probably concerning new genes still uncovered in previous studies. The present report analyzes the sugarcane transcriptome under drought stress, using a combination of high-throughput transcriptome profiling by SuperSAGE with the Solexa sequencing technology, allowing the identification of potential target genes during the stress response.
Keywords: Droughts; Gene Expression Profiling; Heat-Shock Response; Plant Proteins; Saccharum; Transcriptome

NF-κB as a target for modulating inflammatory responses. - Gasparini, Chiara; Feldmann, Marc (Curr Pharm Des, 2012)
The inflammatory response is of major importance in host defence, but is involved in all acute and chronic diseases. Multiple inflammatory cells and molecules are involved. Among the latter, the Nuclear Factor -κB (NF-κB) has been found to be most important and present in all cell types. NF-B regulates the expression of a large number of genes involved in inflammation. NF-κB plays a key role in the orchestration of the multifaceted inflammatory response, not only in the first pro-inflammatory phase, but also later in the regulation of the resolution of inflammation, when anti-inflammatory genes are expressed and apoptosis is induced. The review describes NF-κB and its two pathways: the canonical, mediated by the p65 and p50 subunits, and the non-canonical, mediated by the subunits RelB, p52 and p50. The relevance of the kinases and interactions leading to NF-κB activation is considered in different primary cells (i.e. macrophages, dendritic cells, fibroblasts, cells from inflammatory tissues), together with the response induced and the ligand involved. Then we overview the different steps to NF-B activation that can be targeted (IKKs, IκBα or NF-κB subunits themselves) with various technologies available i.e. small molecules peptides or nucleic acids. A rationale is provided for possible targets to consider, in the light that NF-κB signaling pathways regulates both pro-inflammatory and anti-inflammatory responses. The possibility of using NF-κB targeted dendritic cells in immunotherapy is considered.
Keywords: Acute Disease; Animals; Chronic Disease; Dendritic Cells; Gene Expression Regulation; Humans; Immunotherapy; Inflammation; NF-kappa B; Signal Transduction

NLRP1 polymorphisms in patients with asbestos-associated mesothelioma. - Girardelli, Martina; Maestri, Iva; Rinaldi, Rosa R; Tognon, Mauro; Boldorini, Renzo; Bovenzi, Massimo; Crovella, Sergio; Comar, Manola (Infect Agent Cancer, 2012)
UNLABELLED: BACKGROUND: An increasing incidence of malignant mesothelioma (MM) cases in patients with low levels of asbestos exposure suggests the interference of alternative cofactors. SV40 infection was detected, as co-morbidity factor, only in 22% of asbestos-MM patients from a North-Eastern Italy area. An additional mechanism of injury related to asbestos exposure in MM development has been recently associated to inflammatory responses, principally driven by interleukin (IL)-1 beta (ß) activated within the inflammasome complex.NLRP3 inflammosome has been described as the intracellular sensor for asbestos able to induce inflammasome activation and IL-1ß secretion while NLRP1 is expressed in lung epithelial cells and alveolar macrophages and contributes to the immune response and to survival/apoptosis balance. This study proposes to evaluate the impact of known NLRP3 and NLRP1 polymorphisms in the individual susceptibility to asbestos-induced mesothelioma in subjects from a hyperendemic area for MM. METHODS: 134 Italian patients with diagnosis of mesothelioma due (MMAE, n=69) or not (MMAF, n=65) to asbestos, 256 healthy Italian blood donors and 101 Italian healthy subjects exposed to asbestos (HCAE) were genotyped for NLRP1 (rs2670660 and rs12150220) and NLRP3 (rs35829419 and rs10754558) polymorphisms. RESULTS: While NLRP3 SNPs were not associated to mesothelioma, the NLRP1 rs12150220 allele T was significantly more frequent in MMAE (0.55) than in HCAE (0.41) (p=0.011; OR=1.79) suggesting a predisponent effect of this allele on the development of mesothelioma. This effect was amplified when the NLRP1 rs2670660 allele was combined with the NLRP1 rs12150220 allele (p=0.004; OR=0.52). CONCLUSION: Although NLRP3 SNPs was not involved in mesothelioma predisposition, these data proposed NLRP1 as a novel factor possibly involved in the development of mesothelioma.

Pegylated TRAIL retains anti-leukemic cytotoxicity and exhibits improved signal transduction activity with respect to TRAIL. - Gonelli, Arianna; Radillo, Oriano; Drioli, Sara; Rimondi, Erika; Secchiero, Paola; Maria Bonora, Gian (Invest New Drugs, 2012)
To improve the pharmacokinetic profile of tumor necrosis factor-related apoptosis inducing ligand (TRAIL) an N-terminal specific pegylation was performed to generate pegylated TRAIL (PEG-TRAIL). In in vitro experiments, we found that although PEG-TRAIL was slightly less efficient than recombinant TRAIL in promoting leukemic cell apoptosis, it showed an improved ability to promote migration of bone-marrow mesenchymal stem cells and to elicit the ERK1/2 intracellular signal transduction pathway. Overall, these data suggest that TRAIL pegylation retains, or even enhances, the biological activities of TRAIL relevant for its therapeutic applications.
Keywords: Antineoplastic Agents; Apoptosis; Caspase 3; Cell Movement; Dose-Response Relationship, Drug; HL-60 Cells; Humans; Leukemia; Mesenchymal Stromal Cells; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 3; Phosphorylation; Polyethylene Glycols; Recombinant Fusion Proteins; Signal Transduction; Time Factors; TNF-Related Apoptosis-Inducing Ligand

Phylloid pattern of hypomelanosis closely related to chromosomal abnormalities in the 13q detected by SNP array analysis. - Faletra, F; Berti, I; Tommasini, A; Pecile, V; Cleva, L; Alberini, E; Bruno, I; Gasparini, P (Dermatology, 2012)
Phylloid hypomelanosis is a distinct type of pigmentary mosaicism characterized by congenital hypochromic macules resembling a floral ornament with various elements such as round or oval patches, asymmetrical macules similar to begonia leaves, or oblong lesions. It has been found to be predominantly associated with abnormalities in chromosome 13 and sometimes as-sociated with different extracutaneous abnormalities. Here, we report 2 new cases of phylloid hypomelanosis due to mosaicism involving chromosome 13. The first one is a mosaicism for a supernumerary marker belonging to chromosome 13 and the second one is the first report of phylloid hypomelanosis associated with a mosaic deletion of 13q. Because of the extremely low level of mosaicism in these 2 cases, SNP array analysis on skin fibroblasts was carried out, showing a 13q21.33-q34 duplication (71,024,411-115,103,529) and a 13q13.3-q34 (38,368,012-115,103,529) deletion. Both cases underline on the one hand the strict connection between phylloid hypomelanosis and anomalies of chromosome 13, and on the other hand the relevance of the SNP array analysis on skin fibroblasts in the detection of low-level mosaicism.
Keywords: Chromosomes, Human, Pair 13; Humans; Hypopigmentation; Male; Mosaicism; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide

Polimorphisms in inflammasome genes are involved in the predisposition to systemic lupus erythematosus. - Pontillo, Alessandra; Girardelli, Martina; Kamada, Anselmo J; Pancotto, Joao A T; Donadi, Eduardo A; Crovella, Sergio; Sandrin-Garcia, Paula (Autoimmunity, 2012)
Recent findings provide evidence of inflammasome critical role in the predisposition to autoimmune disorders. The involvement of inflammasome in the pathogenesis of systemic lupus erythematosus (SLE) has been hypothesized even if no significant association within inflammasome genes mutations or polymorphisms and lupus has been reported yet. We analyzed 14 single nucleotide polymorphisms (SNPs) within 7 inflammasome genes (NLRP1, NLRP3, NLRC4, AIM2, CARD8, CASP1, IL1B) in 144 patients affected by systemic lupus erythematosus and in 158 healthy controls from Southern Brazilian (state of São Paulo) with the aim of disclosing the possible role of inflammasome genes in the susceptibility of SLE. Our results demonstrated that NLRP1 rs2670660 SNP and the NLRP1 rs12150220-rs2670660 A-G haplotype were associated with SLE in our study population, and in particular with the development of nephritis, rash and arthritis. These findings are concordant with previously reported association of NLRP1 with vitiligo and type-1 diabetes underlining once more the involvement of NALP1 inflammasome in the pathogenesis of autoimmune disorders.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Alleles; Apoptosis Regulatory Proteins; Brazil; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Inflammasomes; Lupus Erythematosus, Systemic; Male; Middle Aged; Polymorphism, Single Nucleotide

Polymorphisms in inflammasome' genes and susceptibility to HIV-1 infection. - Pontillo, Alessandra; Oshiro, Telma M; Girardelli, Martina; Kamada, Anselmo J; Crovella, Sergio; Duarte, Alberto J S (J Acquir Immune Defic Syndr, 2012)
The involvement of inflammasome genes in the susceptibility to HIV-1 infection was investigated. Twelve single nucleotide polymorphisms within NLRP1, NLRP3, NLRC4, CARD8, CASP1, and IL1B genes were analyzed in 150 HIV-1-infected Brazilian subjects and 158 healthy controls. The 2 polymorphisms rs10754558 in NLRP3 and rs1143634 in IL1B were significantly associated to the HIV-1 infection. These findings supported the previously hypothesized involvement of NALP3-inflammasome in HIV-1 pathogenesis, underlining once more the key role of inflammation and innate immunity in the susceptibility to HIV-1 infection.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Apoptosis Regulatory Proteins; Brazil; Calcium-Binding Proteins; CARD Signaling Adaptor Proteins; Carrier Proteins; Caspase 1; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; HIV Infections; HIV-1; Humans; Inflammasomes; Interleukin-1beta; Intracellular Signaling Peptides and Proteins; Male; Middle Aged; Neoplasm Proteins; Polymorphism, Single Nucleotide

Relation between maternal thrombophilia and stillbirth according to causes/associated conditions of death. - Monari, F; Alberico, S; Avagliano, L; Cetin, I; Cozzolino, S; Gargano, G; Marozio, L; Mecacci, F; Neri, I; Tranquilli, A L; Venturini, P; Facchinetti, F (Early Hum Dev, 2012)
OBJECTIVE: To investigate maternal thrombophilia in cases of Stillbirth (SB), also an uncertain topic because most case series were not characterised for cause/associated conditions of death. STUDY DESIGN: In a consecutive, prospective, multicentre design, maternal DNA was obtained in 171 cases of antenatal SB and 326 controls (uneventful pregnancy at term, 1:2 ratio). Diagnostic work-up of SB included obstetric history, neonatologist inspection, placenta histology, autopsy, microbiology/chromosome evaluations. Results audited in each centre were classified by two of us by using CoDAC. Cases were subdivided into explained SB where a cause of death was identified and although no defined cause was detected in the remnants, 64 cases found conditions associated with placenta-vascular disorders (including preeclampsia, growth restriction and placenta abruption - PVD). In the remnant 79 cases, no cause of death or associated condition was found. Antithrombin activity, Factor V Leiden, G20210A Prothrombin mutation (FII mutation) and acquired thrombophilia were analysed. RESULTS: Overall, the presence of a thrombophilic defect was significantly more prevalent in mothers with SBs compared to controls. In particular, SB mothers showed an increased risk of carrying Factor II mutation (OR=3.2, 95% CI: 1.3-8.3, p=0.01), namely in unexplained cases. Such mutation was significantly associated also with previous SB (OR=8.9, 95%CI 1.2-70.5). At multiple logistic regression, Factor II mutation was the only significantly associated variable with SB (adj OR=3.8, 95% CI: 1.3-13.5). CONCLUSION: These data suggest that Factor II mutation is the only condition specifically associated with unexplained SB and could represents a risk of recurrence. PVD-associated condition is unrelated to thrombophilia.
Keywords: Adult; Case-Control Studies; Cause of Death; Female; Fetal Diseases; Fetal Mortality; Humans; Infant, Newborn; Male; Placenta Diseases; Pre-Eclampsia; Pregnancy; Pregnancy Complications, Hematologic; Socioeconomic Factors; Stillbirth; Thrombophilia; Young Adult

Role of high molecular weight hyaluronic acid in postmenopausal vaginal discomfort. - Grimaldi, E F; Restaino, S; Inglese, S; Foltran, L; Sorz, A; Di Lorenzo, G; Guaschino, S (Minerva Ginecol, 2012)
AIM: Aim of the present study was to quantify the intensity of vulvovaginal symptoms before and after treatment with high molecular weight hyaluronic acid (HA), to test the tolerability and safety of the product, to evaluate the effect on the quality of life and the compliance to the treatment. METHODS: This was a double-blind randomized placebo-controlled study. In seven months we enrolled 36 post-menopausal women, equally distributed in placebo and active group. The evaluation was based on at least three atrophy-related signs and on the patient reported symptoms. After the written informed consent, the participants were instructed to apply the gel (drug or placebo) daily. Three days after the end of the treatment the patients received a final examination to evaluate the progress of symptoms, the presence of any adverse events and their correlation with the treatment. RESULTS: Self-evaluation scales and investigator evaluation showed that the vaginal dryness was significantly reduced both in placebo and in the active group; however, high molecular weight HA was the only active treatment in reducing significantly itching and burning (P<0.02 and <0.04 respectively). Both treatments significantly reduced vaginal atrophy (P<0.001), erythema (P<0.01 placebo and P<0.001 HA) and vaginal dryness (P<0.001), but HA treatment was significantly more effective on the first two symptoms. Both treatments were very well tolerated and compliance of the treatment was very high. CONCLUSION: High molecular weight HA could be effective in subjective and objective improvement of postmenopausal vaginal atrophy providing a good compliance. No adverse events occurred during the entire period of the study.
Keywords: Atrophy; Double-Blind Method; Female; Humans; Hyaluronic Acid; Middle Aged; Molecular Weight; Postmenopause; Vagina; Vaginal Diseases

Sexually transmitted infections and diseases: old and new challenges - part I - Introduction. - Guaschino, S; Zuccati, G (G Ital Dermatol Venereol, 2012)
Keywords: Humans; Sexually Transmitted Diseases

Successful induction of oral tolerance in Netherton syndrome. - Pastore, Serena; Gorlato, Gaia; Berti, Irene; Barbi, Egidio; Ventura, Alessandro (Allergol Immunopathol (Madr), 2012)
Keywords: Allergens; Alopecia; Child, Preschool; Desensitization, Immunologic; Disease-Free Survival; Eczema; Female; Food Hypersensitivity; Hair Follicle; Humans; Immune Tolerance; Immunoglobulin E; Infant, Newborn; Mouth; Netherton Syndrome; Treatment Outcome

Two Novel COH1 Mutations in an Italian Patient with Cohen Syndrome. - Athanasakis, E; Fabretto, A; Faletra, F; Mocenigo, M; Morgan, A; Gasparini, P (Mol Syndromol, 2012)
Cohen syndrome (CS) is an autosomal recessive disease caused by mutations in the COH1 gene. It is characterized by intellectual disability, hypotonia, joint hyperlaxity, severe myopia, characteristic facial dysmorphisms and, in some cases, intermittent isolated neutropenia. We investigated an Italian patient with CS together with his family. Genetic analysis disclosed 2 novel mutations: the first is an intronic mutation (c.8697-9A>G) creating a new splice site 8 nucleotides upstream, and the second is a duplication of 1 base (c.10156dupA) generating a premature stop codon. The compound heterozygous mutations explain the proband's phenotype and improved the knowledge of genotype-phenotype correlation.

Upper gastrointestinal involvement in paediatric onset Crohn's disease: prevalence and clinical implications. - Crocco, S; Martelossi, S; Giurici, N; Villanacci, V; Ventura, A (J Crohns Colitis, 2012)
BACKGROUND AND AIMS: Our study evaluated the prevalence, the characteristics and implications of the upper gastrointestinal localisation (UGI+) in paediatric Crohn's Disease (CD) patients. METHODS: This prospective study evaluated 45 newly diagnosed CD patients at diagnosis and follow up with respect to CD localisation. RESULTS: All patients presented CD at the colon and/or ileum. In 24/45 patients (53.3%, 12 F and 12 M) an UGI+ involvement was also found. UGI+ patients had a younger age of onset (10.9 years versus 12.6 years; P<0.05). PCDAI at diagnosis was significantly higher in the UGI+ (41 vs. 25 P<0.01). UGI+ patients were overall more symptomatic. Pancolitis and extraintestinal manifestations were also more frequent (19/24 (80%) vs. 12/21 (57%) P<0.01). Growth was more impaired at diagnosis in UGI+ patients. By the end of the follow-up (mean 3 years, range 2 to 4) no significant difference was found in PCDAI (17 in UGI+ patients vs. 11 in UGI- P=NS), or the number of relapses. Weight and growth catch-up in UGI+ patients were comparable to UGI- ones. However, UGI+ patients required a more aggressive therapeutic approach. CONCLUSION: At least half of paediatric onset CD patients have an upper gastrointestinal localisation. UGI+ patients present an earlier onset and a more severe disease. The final outcome does not differ, but UGI+ patients require a more aggressive therapeutic approach.
Keywords: Adolescent; Age of Onset; Child; Crohn Disease; Female; Humans; Male; Prospective Studies; Upper Gastrointestinal Tract

Use of specific antiretroviral regimens among HIV-infected women in Italy at time of conception: 2001-2011. - Floridia, Marco; Ravizza, Marina; Guaraldi, Giovanni; Pinnetti, Carmela; Martinelli, Pasquale; Tamburrini, Enrica (AIDS Patient Care STDS, 2012)
Keywords: Anti-HIV Agents; Drug Administration Schedule; Female; Fertilization; HIV Protease Inhibitors; HIV Seropositivity; Humans; Infectious Disease Transmission, Vertical; Italy; Pregnancy; Reverse Transcriptase Inhibitors; Sentinel Surveillance

Young girl with apical ballooning heart syndrome. - Berton, E; Vitali-Serdoz, L; Vallon, P; Maschio, M; Gortani, G; Benettoni, A (Int J Cardiol, 2012)
Keywords: Child; Diagnosis, Differential; Electrocardiography; Female; Humans; Takotsubo Cardiomyopathy

The active Zot domain (aa 288-293) increases ZO-1 and myosin 1C serine/threonine phosphorylation, alters interaction between ZO-1 and its binding partners, and induces tight junction disassembly through proteinase activated receptor 2 activation. - Goldblum, Simeon E; Rai, Usha; Tripathi, Amit; Thakar, Manjusha; De Leo, Luigina; Di Toro, Nicola; Not, Tarcisio; Ramachandran, Rithwik; Puche, Adam C; Hollenberg, Morley D; Fasano, Alessio (FASEB J, 2011)
Vibrio cholerae-derived zonula occludins toxin (Zot) is a multifunctional protein that reversibly disassembles intestinal tight junctions (tjs). Zot structure-function analysis has mapped this activity to aa 288-293, named AT1002. AT1002 reduced transepithelial electrical resistance across rat small intestine, ex vivo, as did Zot and its processed mature form, ΔG. AT1002 increased in vivo permeability to sugar tracers, whereas scrambled control peptides did not. Binding and barrier assays in proteinase activated receptor (PAR)(2)-expressing and PAR(2)-null cells established AT1002 activity to be PAR(2) dependent. Coincident with the increased intestinal permeability, confocal microscopy of AT1002-exposed rat intestinal IEC6 cells revealed displacement of ZO-1 and occludin from intercellular boundaries. In coimmunoprecipitation assays, AT1002 decreased ZO-1-occludin and ZO-1-claudin 1 interactions coincident with PKCα-dependent ZO-1 serine/threonine phosphorylation. Further, AT1002 increased serine phosphorylation of myosin 1C and, at the same time, transiently diminished its association with ZO-1. The COOH-terminal domain of ZO-1 was required for its association with myosin 1C. These data indicate that the NH(2)-terminal portion of active Zot contains a PAR(2)-activating motif, FCIGRL, that increases PKCα-dependent ZO-1 and myosin 1C serine/threonine phosphorylation. These modifications provoke selective disengagement of ZO-1 from its binding partners, occludin, claudin 1, and myosin 1C, coincident with opening of tjs.
Keywords: Amino Acid Sequence; Animals; Caco-2 Cells; Cell Line; Cells, Cultured; Cholera Toxin; Epithelial Cells; Humans; Immunoblotting; Male; Membrane Proteins; Mice; Mice, Inbred BALB C; Molecular Sequence Data; Myosins; Oligopeptides; Phosphoproteins; Phosphorylation; Protein Binding; Protein Kinase C-alpha; Rats; Rats, Wistar; Receptor, PAR-2; RNA Interference; Serine; Threonine; Tight Junctions; Zonula Occludens-1 Protein

Anti-α-enolase Antibodies in Serum from Pediatric Patients Affected by Inflammatory Diseases: Diagnostic and Pathogenetic Insights. - Pontillo, Alessandra; Di Toro, Nicola; Edomi, Paolo; Shadlow, A; Ammadeo, A; Gattorno, M; Not, T; Lepore, L; Crovella, S (Int J Rheumatol, 2011)
Human glycolytic enzyme α-enolase was associated with human diseases and with inflammation. An ELISA test was developed to measure anti-α-enolase AAE IgG and AAE IgA in the serum from patients affected by inflammatory diseases with the purpose to evaluate it as a novel diagnostic marker. 80 healthy blood donors and 194 paediatric patients affected by Juvenile idiopathic arthritis (JIA), celiac disease (CD), Crohn's Disease (CrD), hereditary periodic fever (HPF), and PFAPA syndrome were included in the study. HPF patients showed high levels of AAE antibodies, whereas JIA, CD, and CrD presented only partial results. Benign fevers such as PFAPA were almost negative for AAE Abs. These findings suggested that the genetic dysfunction of inflammasome associated with HPF could lead to the formation of AAE Abs that could be used for an early and easy diagnosis.

Association of a variant in the CHRNA5-A3-B4 gene cluster region to heavy smoking in the Italian population. - Sorice, Rossella; Bione, Silvia; Sansanelli, Serena; Ulivi, Sheila; Athanasakis, Emmanouil; Lanzara, Carmela; Nutile, Teresa; Sala, Cinzia; Camaschella, Clara; d'Adamo, Pio; Gasparini, Paolo; Ciullo, Marina; et al. (Eur J Hum Genet, 2011)
Large-scale population studies have established that genetic factors contribute to individual differences in smoking behavior. Linkage and genome-wide association studies have shown many chromosomal regions and genes associated with different smoking behaviors. One study was the association of single-nucleotide polymorphisms (SNPs) in the CHRNA5-A3-B4 gene cluster to nicotine addiction. Here, we report a replication of this association in the Italian population represented by three genetically isolated populations. One, the Val Borbera, is a genetic isolate from North-Western Italy; the Cilento population, is located in South-Western Italy; and the Carlantino village is located in South-Eastern Italy. Owing to their position and their isolation, the three populations have a different environment, different history and genetic structure. The variant A of the rs1051730 SNP was significantly associated with smoking quantity in two populations, Val Borbera and Cilento, no association was found in Carlantino population probably because difference in LD pattern in the variant region.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Italy; Multigene Family; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Nicotinic; Smoking; Tobacco Use Disorder

Association of tumor necrosis factor-related apoptosis-inducing ligand with total and cardiovascular mortality in older adults. - Volpato, Stefano; Ferrucci, Luigi; Secchiero, Paola; Corallini, Federica; Zuliani, Giovanni; Fellin, Renato; Guralnik, Jack M; Bandinelli, Stefania; Zauli, Giorgio (Atherosclerosis, 2011)
OBJECTIVE: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) exhibits biological activity on vascular cells in vitro. Rapid variation of circulating TRAIL levels occurs during acute coronary ischemia, suggesting that biological pathways involving TRAIL may be activated during ischemic heart disease. However, whether differential levels of soluble TRAIL in normal individuals are associated with adverse health outcomes has not been investigated. We tested the hypothesis that TRAIL levels predict mortality in a population based sample of community dwelling men and women. METHODS: Plasma TRAIL level was measured by ELISA at baseline in 1282 adults (mean age 68 years) enrolled in the InCHIANTI study. Vital status was ascertained over the six-year follow-up. RESULTS: In multivariable Cox regression analysis adjusted for potential confounders including prevalent cardiovascular diseases (CVD), ankle-brachial index, electrocardiogram abnormalities, and inflammatory markers, baseline TRAIL levels were inversely related to all-cause mortality (p=0.008). In stratified analyses, the prognostic effect of TRAIL level was strong and highly significant in participants with prevalent CVD (N=321), (lowest versus highest quartile: HR 3.1; 95% CI 1.5-6.5) while it was negligible in those free of CVD (p value for the interaction term between CVD status and TRAIL levels=0.038). Similar findings were obtained when CVD mortality was considered as the outcome of interest. CONCLUSIONS: In older patients with CVD, low levels of TRAIL were associated with increased risk of death over a period of 6 years. Lower concentration of circulating TRAIL may be related to the clinical evolution of older adults with CVD.
Keywords: Adult; Aged; Ankle Brachial Index; Cardiovascular Diseases; Female; Follow-Up Studies; Humans; Italy; Male; Middle Aged; TNF-Related Apoptosis-Inducing Ligand

Atlanto-axial joint involvement as exclusive manifestation of juvenile idiopathic arthritis (JIA). - Taddio, A; Pellegrin, M C; Gregori, M; Wientroub, S; Padeh, S; Lepore, L (Clin Exp Rheumatol, 2011)
Keywords: Antirheumatic Agents; Arthritis, Juvenile; Atlanto-Axial Joint; Child; Dislocations; Female; Glucocorticoids; Humans; Magnetic Resonance Imaging; Pulse Therapy, Drug; Torticollis; Treatment Outcome; Uveitis

Clinical heterogeneity and diagnostic delay of autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy syndrome. - Mazza, Cinzia; Buzi, Fabio; Ortolani, Federica; Vitali, Alberto; Notarangelo, Lucia D; Weber, Giovanna; Bacchetta, Rosa; Soresina, Annarosa; Lougaris, Vassilios; Greggio, Nella A; Taddio, Andrea; Pasic, Srdjan; et al. (Clin Immunol, 2011)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare autosomal recessive organ-specific autoimmune disorder that is characterized by a variable combination of (i) chronic mucocutaneous candidiasis, (ii) polyendocrinopathy and/or hepatitis and (iii) dystrophy of the dental enamel and nails. We analyzed the AIRE (autoimmune regulator) gene in subjects who presented any symptom that has been associated with APECED, including candidiasis and autoimmune endocrinopathy. We observed that 83.3% of patients presented at least two of the three typical manifestations of APECED, while the remaining 16.7% of patients showed other signs of the disease. Analysis of the genetic diagnosis of these subjects revealed that a considerable delay occurs in the majority of patients between the appearance of symptoms and the diagnosis. Overall, the mean diagnostic delay in our patients was 10.2 years. These results suggest that molecular analysis of AIRE should be performed in patients with relapsing mucocutaneous candidiasis for early identification of APECED.
Keywords: Adolescent; Adult; Child; Child, Preschool; Heterozygote; Homozygote; Humans; Middle Aged; Mutation; Polyendocrinopathies, Autoimmune; Time Factors; Young Adult

Consensus on diagnosis and empiric antibiotic therapy of febrile neutropenia. - Giurici, Nagua; Zanazzo, Giulio A (Pediatr Rep, 2011)
Controversial issues on the management of empiric therapy and diagnosis of febrile neutropenia (FN) were faced by a Consensus Group of the Italian Association of Pediatric Hematology-Oncology (AIEOP). In this paper we report the suggestions of the consensus process regarding the role of aminoglycosides, glycopeptides and oral antibiotics in empiric therapy of FN, the rules for changing or discontinuing the therapy as well as the timing of the blood cultures.

Epidemiological and molecular assessment of a measles outbreak in a highly vaccinated population of northeast Italy. - D'Agaro, P; Molin, G Dal; Gallo, T; Rossi, T; Santon, D; Busetti, M; Comar, M; Campello, C (Epidemiol Infect, 2011)
Two distinct measles outbreaks, unrelated from the epidemiological point of view but caused by genetically related strains, occurred in the Friuli Venezia Giulia region of northeastern Italy. Forty-two cases were reported during the period April-May 2008. In the first outbreak the index case was a teacher who introduced the virus into the Pordenone area, involving eight adolescents and young adults. The other concomitant outbreak occurred in the city of Trieste with 33 cases. The containment of the epidemics can be explained by the high MMR vaccine coverage in an area where the first dose was delivered to 93·4% and the second dose to 88·3% of the target children. Phylogenetic analysis of 14 measles virus strains showed that they belonged to a unique D4 genotype indistinguishable from the MVs/Enfield.GBR/14.07 strain, probably introduced from areas (i.e. Piedmont and Germany) where this genotype was present or had recently caused a large epidemic.
Keywords: Adolescent; Adult; Chi-Square Distribution; Child; Child, Preschool; Community-Acquired Infections; Disease Outbreaks; Female; Humans; Immunization Schedule; Infant; Italy; Male; Measles; Measles Vaccine; Measles virus; Middle Aged; Molecular Epidemiology; Phylogeny

Forkhead box protein 3 (FOXP3) mutations lead to increased TH17 cell numbers and regulatory T-cell instability. - Passerini, Laura; Olek, Sven; Di Nunzio, Sara; Barzaghi, Federica; Hambleton, Sophie; Abinun, Mario; Tommasini, Alberto; Vignola, Silvia; Cipolli, Marco; Amendola, Mario; Naldini, Luigi; Guidi, Luisa; et al. (J Allergy Clin Immunol, 2011)
Keywords: Forkhead Transcription Factors; Gene Expression Regulation; Genetic Diseases, X-Linked; Humans; Immunologic Deficiency Syndromes; Intestinal Diseases; Male; Mutation; Polyendocrinopathies, Autoimmune

Frequency distribution of HLA DQ2 and DQ8 in celiac patients and first-degree relatives in Recife, northeastern Brazil. - Castro-Antunes, Margarida Maria; Crovella, Sergio; Brandão, Lucas André Cavalcanti; Guimarães, Rafael Lima; Motta, Maria Eugênia Farias Almeida; Silva, Giselia Alves Pontes da (Clinics (Sao Paulo), 2011)
AIMS: The aim of this study was to evaluate the frequencies of the HLA genotypes DQ2 and DQ8 and the alleles A1*05, A1*0201, B1*0201 and B1*0302 in individuals with celiac disease in Recife, northeastern Brazil. METHODS: HLA DQ2 and DQ8 genotyping was performed for 73 individuals with celiac disease and 126 first-degree relatives with negative transglutaminase serology. The alleles DQA1*05, DQA1*0201, DQB1*02 and DQB1*0302 were identified by sequencing using specific primers and the EU-DQ kit from the Eurospital Laboratory, Trieste, Italy and double-checked by the All Set SPP kit (Dynal). RESULTS: Among the 73 cases, 50 (68.5%) had the genotype DQ2, 13 (17.8%) had DQ8, 5 (6.8%) had DQ2 and DQ8, and 5 did not have any of these genotypes. Among the 5 negative individuals, four had the B1*02 allele and one did not have any of the alleles studied. B1*02 was the most frequent allele in both groups (94% in the patients and 89% in the control relatives). CONCLUSIONS: In this study, celiac disease was associated with the genotypes DQ2 and DQ8. DQ2 predominated, but the distribution of the frequencies was different from what has been found in European populations and was closer to what has been found in the Americas. The high frequencies of the HLA genotypes DQ2 and DQ8 that were found in first-degree relatives would make it difficult to use these HLA genotypes for routine diagnosis of celiac disease in this group.
Keywords: Adolescent; Adult; Brazil; Celiac Disease; Chi-Square Distribution; Child; Child, Preschool; Cross-Sectional Studies; Europe; Family; Female; Gene Frequency; Genetic Predisposition to Disease; HLA-DQ Antigens; Humans; Infant; Male; Middle Aged; Young Adult

Frequency of HLA B*5701 allele carriers in abacavir treated-HIV infected patients and controls from northeastern Brazil. - Crovella, Sergio; Biller, Lara; Santos, Sergio; Salustiano, Ana; Brandão, Lucas; Guimarães, Rafael; Segat, Ludovica; Lima Filho, Jose Luiz de; Arraes, Luiz Claudio (Clinics (Sao Paulo), 2011)
Keywords: Adolescent; Adult; Anti-HIV Agents; Brazil; Case-Control Studies; Dideoxynucleosides; Drug Hypersensitivity; Female; Gene Frequency; Genotype; HIV Infections; HLA-B Antigens; Humans; Male; Middle Aged; Real-Time Polymerase Chain Reaction; Young Adult

Functional type 1 regulatory T cells develop regardless of FOXP3 mutations in patients with IPEX syndrome. - Passerini, Laura; Di Nunzio, Sara; Gregori, Silvia; Gambineri, Eleonora; Cecconi, Massimiliano; Seidel, Markus G; Cazzola, Giantonio; Perroni, Lucia; Tommasini, Alberto; Vignola, Silvia; Guidi, Luisa; Roncarolo, Maria G; et al. (Eur J Immunol, 2011)
Mutations of forkhead box p3 (FOXP3), the master gene for naturally occurring regulatory T cells (nTregs), are responsible for the impaired function of nTregs, resulting in an autoimmune disease known as the immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. The relevance of other peripheral tolerance mechanisms, such as the presence and function of type 1 regulatory T (Tr1) cells, the major adaptive IL-10-producing Treg subset, in patients with IPEX syndrome remains to be clarified. FOXP3(mutated) Tr1-polarized cells, differentiated in vitro from CD4(+) T cells of four IPEX patients, were enriched in IL-10(+) IL-4(-) IFN-γ(+) T cells, a cytokine production profile specific for Tr1 cells, and expressed low levels of FOXP3 and high levels of Granzyme-B. IPEX Tr1 cells were hypoproliferative and suppressive, thus indicating that FOXP3 mutations did not impair their function. Furthermore, we isolated Tr1 cell clones from the peripheral blood of one FOXP3(null) patient, demonstrating that Tr1 cells are present in vivo and they can be expanded in vitro in the absence of WT FOXP3. Overall, our results (i) show that functional Tr1 cells differentiate independently of FOXP3, (ii) confirm that human Tr1 and nTregs are distinct T-cell lineages, and (iii) suggest that under favorable conditions Tr1 cells could exert regulatory functions in IPEX patients.
Keywords: Cell Differentiation; Cell Lineage; Cells, Cultured; Enteritis; Forkhead Transcription Factors; Genetic Diseases, X-Linked; Humans; Immunity, Innate; Interleukin-2 Receptor alpha Subunit; Mutation; Polyendocrinopathies, Autoimmune; Syndrome; T-Lymphocytes, Regulatory

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

"GINEXMAL RCT: Induction of labour versus expectant management in gestational diabetes pregnancies". - Maso, Gianpaolo; Alberico, Salvatore; Wiesenfeld, Uri; Ronfani, Luca; Erenbourg, Anna; Hadar, Eran; Yogev, Yariv; Hod, Moshe (BMC Pregnancy Childbirth, 2011)
BACKGROUND: Gestational diabetes (GDM) is one of the most common complications of pregnancies affecting around 7% of women. This clinical condition is associated with an increased risk of developing fetal macrosomia and is related to a higher incidence of caesarean section in comparison to the general population. Strong evidence indicating the best management between induction of labour at term and expectant monitoring are missing. METHODS/DESIGN: Pregnant women with singleton pregnancy in vertex presentation previously diagnosed with gestational diabetes will be asked to participate in a multicenter open-label randomized controlled trial between 38+0 and 39+0 gestational weeks. Women will be recruited in the third trimester in the outpatient clinic or in the Day Assessment Unit according to local protocols. Women who opt to take part will be randomized according to induction of labour or expectant management for spontaneous delivery. Patients allocated to the induction group will be admitted to the obstetric ward and offered induction of labour via use of prostaglandins, Foley catheter or oxytocin (depending on clinical conditions). Women assigned to the expectant arm will be sent to their domicile where they will be followed up until delivery, through maternal and fetal wellbeing monitoring twice weekly. The primary study outcome is the Caesarean section (C-section) rate, whilst secondary measurements are maternal and neonatal outcomes. A total sample of 1760 women (880 each arm) will be recruited to identify a relative difference between the two arms equal to 20% in favour of induction, with concerns to C-section rate. Data will be collected until mothers and newborns discharge from the hospital. Analysis of the outcome measures will be carried out by intention to treat. DISCUSSION: The present trial will provide evidence as to whether or not, in women affected by gestational diabetes, induction of labour between 38+0 and 39+0 weeks is an effective management to ameliorate maternal and neonatal outcomes. The primary objective is to determine whether caesarean section rate could be reduced among women undergoing induction of labour, in comparison to patients allocated to expectant monitoring. The secondary objective consists of the assessment and comparison of maternal and neonatal outcomes in the two study arms. .
Keywords: Adolescent; Adult; Cesarean Section; Diabetes, Gestational; Female; Gestational Age; Humans; Intention to Treat Analysis; Labor, Induced; Patient Selection; Pregnancy; Pregnancy Outcome; Research Design; Watchful Waiting; Young Adult

Hearing function and thresholds: a genome-wide association study in European isolated populations identifies new loci and pathways. - Girotto, Giorgia; Pirastu, Nicola; Sorice, Rossella; Biino, Ginevra; Campbell, Harry; d'Adamo, Adamo P; Hastie, Nicholas D; Nutile, Teresa; Polasek, Ozren; Portas, Laura; Rudan, Igor; Ulivi, Sheila; et al. (J Med Genet, 2011)
BACKGROUND: Hearing is a complex trait, but until now only a few genes are known to contribute to variability of this process. In order to discover genes and pathways that underlie auditory function, a genome-wide association study was carried out within the International Consortium G-EAR. METHODS: Meta-analysis of genome-wide association study's data from six isolated populations of European ancestry for an overall number of 3417 individuals. RESULTS: Eight suggestive significant loci (p<10(-7)) were detected with a series of genes expressed within the inner ear such as: DCLK1, PTPRD, GRM8, CMIP. Additional biological candidates marked by a single nucleotide polymorphism (SNP) with a suggestive association (p<10(-6)) were identified, as well as loci encompassing 'gene desert regions'-genes of unknown function or genes whose function has not be linked to hearing so far. Some of these new loci map to already known hereditary hearing loss loci whose genes still need to be identified. Data have also been used to construct a highly significant 'in silico' pathway for hearing function characterised by a network of 49 genes, 34 of which are certainly expressed in the ear. CONCLUSION: These results provide new insights into the molecular basis of hearing function and may suggest new targets for hearing impairment treatment and prevention.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Auditory Threshold; Carrier Proteins; Databases, Genetic; Europe; European Continental Ancestry Group; Female; Founder Effect; Genetic Linkage; Genome-Wide Association Study; Hearing; Hearing Loss; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice; Phenotype; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases; Receptor-Like Protein Tyrosine Phosphatases, Class 2; Receptors, Metabotropic Glutamate

High incidence of NLRP3 somatic mosaicism in patients with chronic infantile neurologic, cutaneous, articular syndrome: results of an International Multicenter Collaborative Study. - Tanaka, Naoko; Izawa, Kazushi; Saito, Megumu K; Sakuma, Mio; Oshima, Koichi; Ohara, Osamu; Nishikomori, Ryuta; Morimoto, Takeshi; Kambe, Naotomo; Goldbach-Mansky, Raphaela; Aksentijevich, Ivona; de Saint Basile, Geneviève; et al. (Arthritis Rheum, 2011)
OBJECTIVE: Chronic infantile neurologic, cutaneous, articular (CINCA) syndrome, also known as neonatal-onset multisystem inflammatory disease (NOMID), is a dominantly inherited systemic autoinflammatory disease. Although heterozygous germline gain-of-function NLRP3 mutations are a known cause of this disease, conventional genetic analyses fail to detect disease-causing mutations in ∼40% of patients. Since somatic NLRP3 mosaicism has been detected in several mutation-negative NOMID/CINCA syndrome patients, we undertook this study to determine the precise contribution of somatic NLRP3 mosaicism to the etiology of NOMID/CINCA syndrome. METHODS: An international case-control study was performed to detect somatic NLRP3 mosaicism in NOMID/CINCA syndrome patients who had shown no mutation during conventional sequencing. Subcloning and sequencing of NLRP3 was performed in these mutation-negative NOMID/CINCA syndrome patients and their healthy relatives. Clinical features were analyzed to identify potential genotype-phenotype associations. RESULTS: Somatic NLRP3 mosaicism was identified in 18 of the 26 patients (69.2%). Estimates of the level of mosaicism ranged from 4.2% to 35.8% (mean ± SD 12.1 ± 7.9%). Mosaicism was not detected in any of the 19 healthy relatives (18 of 26 patients versus 0 of 19 relatives; P < 0.0001). In vitro functional assays indicated that the detected somatic NLRP3 mutations had disease-causing functional effects. No differences in NLRP3 mosaicism were detected between different cell lineages. Among nondescript clinical features, a lower incidence of mental retardation was noted in patients with somatic mosaicism. Genotype-matched comparison confirmed that patients with somatic NLRP3 mosaicism presented with milder neurologic symptoms. CONCLUSION: Somatic NLRP3 mutations were identified in 69.2% of patients with mutation-negative NOMID/CINCA syndrome. This indicates that somatic NLRP3 mosaicism is a major cause of NOMID/CINCA syndrome.
Keywords: Adolescent; Adult; Carrier Proteins; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Genetic Association Studies; Humans; Infant; Male; Mosaicism

Horizontal gaze palsy and progressive scoliosis without ROBO3 mutations. - Abu-Amero, Khaled K; Faletra, Flavio; Gasparini, Paolo; Parentin, Fulvio; Pensiero, Stefano; Alorainy, Ibrahim A; Hellani, Ali M; Catalano, Dario; Bosley, Thomas M (Ophthalmic Genet, 2011)
BACKGROUND: To describe clinical and genetic observations in a patient with horizontal gaze palsy and progressive scoliosis (HGPPS) without identified mutations in the ROBO3 gene. MATERIALS AND METHODS: Neurologic and orthopedic evaluation of the proband; sequencing all exons, exon-intron boundaries, and promoter region of ROBO3 in the proband and his mother. Array CGH was also carried out in the proband and his mother to evaluate possible chromosomal deletion(s) and/or duplication(s). RESULTS: The proband had complete horizontal gaze restriction with full vertical gaze and small amplitude horizontal pendular nystagmus. He also had severe scoliosis and brainstem hypoplasia pathognomonic of HGPPS. However, complete sequencing of ROBO3 twice in both forward and reverse directions did not reveal any mutations. Array CGH investigation revealed no chromosomal abnormalities. CONCLUSIONS: This patient had clinical and neuroimaging characteristics considered pathognomonic of HGPPS and yet did not have ROBO3 mutations. A clinical misdiagnosis is unlikely in the absence of facial weakness (typical of Moebius syndrome), deafness (typical of the HOXA1 spectrum), or mental retardation (typical of other central decussation abnormalities). It is perhaps more likely that a phenotype identical to HGPPS can be caused by abnormalities in ROBO3 splice variant expression, by mutations of a gene other than ROBO3, or by some environmental or epigenetic factor(s) inhibiting the action of ROBO3 or its protein product in the developing brainstem.
Keywords: Child; Humans; Kyphosis; Magnetic Resonance Imaging; Male; Mutation; Ocular Motility Disorders; Oculomotor Nerve Diseases; Pedigree; Receptors, Immunologic; Scoliosis

In vivo distribution of β2 glycoprotein I under various pathophysiologic conditions. - Agostinis, Chiara; Biffi, Stefania; Garrovo, Chiara; Durigutto, Paolo; Lorenzon, Andrea; Bek, Alpan; Bulla, Roberta; Grossi, Claudia; Borghi, Maria O; Meroni, Pierluigi; Tedesco, Francesco (Blood, 2011)
In vitro studies have documented β2 glycoprotein I (β2GPI) binding to endothelial cells (ECs) and trophoblast using antiphospholipid antibodies. The in vivo binding of β2GPI to these cells and the conditions that favor their interaction have not been investigated. We analyzed the in vivo distribution of cyanine 5.5-labeled β2GPI in mice and evaluated the effect of pregnancy and circulating antibodies on its tissue localization. The signal was detected in the liver by whole body scan and ex vivo analysis. The β2GPI failed to bind to the vascular endothelium and reacted only with the ECs of uterine vessels. In pregnant mice the protein was localized on ECs and trophoblast at the embryo implantation sites. Immunized mice showed a similar β2GPI biodistribution to naive mice but the immunized pregnant animals exhibited a significant increase in fetal loss associated with C3 and C9 deposition at the implantation sites. Treatment of mice with LPS after β2GPI-Cy5.5 injection promoted protein localization on gut and brain ECs associated with IgG, C1q, and C9 deposition in immunized mice. These findings indicate that β2GPI binding to EC requires priming with pro-inflammatory factors which is not needed for uterine and placental localization probably dependent on hormonal changes.
Keywords: Animals; beta 2-Glycoprotein I; Complement C1q; Complement C3; Complement C9; Endothelial Cells; Endothelium, Vascular; Female; Fetal Death; Humans; Mice; Mice, Inbred BALB C; Pregnancy; Trophoblasts; Uterus

Long-term clinical profile of children with the low-penetrance R92Q mutation of the TNFRSF1A gene. - Pelagatti, M A; Meini, A; Caorsi, R; Cattalini, M; Federici, S; Zulian, F; Calcagno, G; Tommasini, A; Bossi, G; Sormani, M P; Caroli, F; Plebani, A; et al. (Arthritis Rheum, 2011)
OBJECTIVE: To analyze the long-term impact of the R92Q mutation of TNFRSF1A in children with periodic fever, in comparison with children with tumor necrosis factor receptor-associated periodic syndrome (TRAPS) with TNFRSF1A structural mutations and children with periodic fever of unknown origin fulfilling the criteria for periodic fever, aphthosis, pharyngitis, and adenitis syndrome (PFAPA). METHODS: The extracellular region of TNFRSF1A was analyzed in 720 consecutive children with periodic fever, using denaturing high-performance liquid chromatography and DNA sequencing. Followup data on 11 pediatric patients with TNFRSF1A structural mutations (cysteine or T50M), 23 pediatric patients with an R92Q substitution, and 64 pediatric patients with PFAPA were collected during routine clinic visits. The 50-item Child Health Questionnaire was used to assess health-related quality of life (HRQOL). RESULTS: The frequency of typical TRAPS-related clinical manifestations was significantly lower and the impact of the disease on HRQOL was significantly reduced in patients with the R92Q mutation compared with TRAPS patients carrying structural mutations of TNFRSF1A. Followup data on 11 TRAPS patients with TNFRSF1A structural mutations (mean followup 7.9 years), 16 patients with theR92Q substitution (mean followup 7.3 years), and 64 patients with PFAPA (mean followup 5.2 years) were available. Patients with R92Q mutations and patients with PFAPA displayed a higher rate of self-resolution or amelioration of the fever episodes than did TRAPS patients with structural mutations. CONCLUSION: Although some cases may progress to a more chronic disease course, the majority of children with an R92Q mutation of the TNFRSFA1 gene show a milder disease course than that in children with TNFRSFA1 structural mutations and have a high rate of spontaneous resolution and amelioration of the recurrent fever episodes.
Keywords: Adolescent; Antirheumatic Agents; Biological Therapy; Child; Child, Preschool; Familial Mediterranean Fever; Female; Fever; Follow-Up Studies; Genotype; Health Surveys; Humans; Infant; Interleukin 1 Receptor Antagonist Protein; Longitudinal Studies; Lymphadenitis; Male; Mutation; Pharyngitis; Quality of Life; Receptors, Tumor Necrosis Factor; Receptors, Tumor Necrosis Factor, Type I; Recurrence; Retrospective Studies; Steroids; Syndrome

Mannose binding lectin gene (MBL2) functional polymorphisms are associated with systemic lupus erythematosus in southern Brazilians. - Sandrin-Garcia, Paula; Brandão, Lucas André Cavalcanti; Coelho, Antônio Victor Campos; Guimarães, Rafael Lima; Pancoto, João Alexandre Trés; Segat, Ludovica; Donadi, Eduardo Antônio; de Lima-Filho, José Luiz; Crovella, Sergio (Hum Immunol, 2011)
Susceptibility to systemic lupus erythematosus (SLE) has been associated with immunologic, environmental, and genetic factors. To uncover a possible association between MBL2 gene polymorphisms and SLE, we analyzed functional polymorphisms in the promoter and first exon of the MBL2 gene in 134 Brazilian SLE patients and 101 healthy controls. Genotype and allele frequencies of MBL2 A/O polymorphism were significantly different between patients and controls, and the O allele was associated with an increased risk of SLE. An association between low mannose binding lectin (MBL) producer combined genotypes and increased risk for SLE was also reported. Furthermore, when stratifying SLE patients according to clinical and laboratory data, an association between the A/O genotype and nephritic disorders and between the X/Y genotype and antiphospholipid syndrome was evident. Combined genotypes responsible for low MBL production were more frequently observed in SLE patients with nephritis. Our results indicate MBL2 polymorphisms as possible risk factors for SLE development and disease-related clinical manifestations.
Keywords: Adolescent; Adult; Aged; Brazil; DNA Mutational Analysis; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Lupus Erythematosus, Systemic; Male; Mannose-Binding Lectin; Middle Aged; Polymorphism, Genetic; Population Groups; Promoter Regions, Genetic

Mannose-binding lectin gene (MBL-2) polymorphism in oral lichen planus. - Barkokebas, Andreza; de Albuquerque T Carvalho, Alessandra; de Souza, Paulo Roberto Eleutério; Gomez, Ricardo Santiago; Xavier, Guilherme Machado; Ribeiro, Camila Maria Beder; Crovella, Sergio; Porter, Stephen Ross; Leão, Jair Carneiro (Clin Oral Investig, 2011)
TNF-α may be associated with the etiopathogenesis of oral lichen planus (OLP), and it has been suggested that polymorphism of mannose-binding lectin (MBL) increases the in vitro production of TNF- α. The aim of the present study was to assess the relevance of genetic diversity of MBL in OLP. The study sample comprised 90 individuals, 45 OLP patients and 45 healthy volunteers. MBL-2 gene was amplified using real-time PCR. Frequency of A/A genotype was 55.6% in OLP and 53.3% in healthy volunteers. Likewise, A/0 heterozygote genotype was found in 42.2% and 35.6%; 2.2% and 11.1%, had the recessive 0/0 genotype respectively. Frequencies of the "A" and "0" alleles were 77% and 23% in the OLP group and 71.2% in control group. There were no statistically significant differences regarding genotype frequency (p = 0.546) or allele frequency (p = 0.497). In conclusion, no significant association was found between polymorphism of MBL-2 gene and OLP.
Keywords: Adolescent; Adult; Aged; Female; Gene Expression Regulation; Gene Frequency; Genes, Recessive; Genetic Variation; Genotype; Heterozygote; Homozygote; Humans; Lichen Planus, Oral; Male; Mannose-Binding Lectin; Middle Aged; Mutation; Polymorphism, Genetic; Real-Time Polymerase Chain Reaction; Tumor Necrosis Factor-alpha; Young Adult

Multiple loci are associated with white blood cell phenotypes. - Nalls, Michael A; Couper, David J; Tanaka, Toshiko; van Rooij, Frank J A; Chen, Ming-Huei; Smith, Albert V; Toniolo, Daniela; Zakai, Neil A; Yang, Qiong; Greinacher, Andreas; Wood, Andrew R; Garcia, Melissa; et al. (PLoS Genet, 2011)
White blood cell (WBC) count is a common clinical measure from complete blood count assays, and it varies widely among healthy individuals. Total WBC count and its constituent subtypes have been shown to be moderately heritable, with the heritability estimates varying across cell types. We studied 19,509 subjects from seven cohorts in a discovery analysis, and 11,823 subjects from ten cohorts for replication analyses, to determine genetic factors influencing variability within the normal hematological range for total WBC count and five WBC subtype measures. Cohort specific data was supplied by the CHARGE, HeamGen, and INGI consortia, as well as independent collaborative studies. We identified and replicated ten associations with total WBC count and five WBC subtypes at seven different genomic loci (total WBC count-6p21 in the HLA region, 17q21 near ORMDL3, and CSF3; neutrophil count-17q21; basophil count- 3p21 near RPN1 and C3orf27; lymphocyte count-6p21, 19p13 at EPS15L1; monocyte count-2q31 at ITGA4, 3q21, 8q24 an intergenic region, 9q31 near EDG2), including three previously reported associations and seven novel associations. To investigate functional relationships among variants contributing to variability in the six WBC traits, we utilized gene expression- and pathways-based analyses. We implemented gene-clustering algorithms to evaluate functional connectivity among implicated loci and showed functional relationships across cell types. Gene expression data from whole blood was utilized to show that significant biological consequences can be extracted from our genome-wide analyses, with effect estimates for significant loci from the meta-analyses being highly corellated with the proximal gene expression. In addition, collaborative efforts between the groups contributing to this study and related studies conducted by the COGENT and RIKEN groups allowed for the examination of effect homogeneity for genome-wide significant associations across populations of diverse ancestral backgrounds.
Keywords: Genetic Loci; Genome-Wide Association Study; Humans; Leukocyte Count; Leukocytes; Molecular Epidemiology; Multigene Family; Phenotype; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Mutations in ANKRD26 are responsible for a frequent form of inherited thrombocytopenia: analysis of 78 patients from 21 families. - Noris, Patrizia; Perrotta, Silverio; Seri, Marco; Pecci, Alessandro; Gnan, Chiara; Loffredo, Giuseppe; Pujol-Moix, Núria; Zecca, Marco; Scognamiglio, Francesca; De Rocco, Daniela; Punzo, Francesca; Melazzini, Federica; et al. (Blood, 2011)
Until recently, thrombocytopenia 2 (THC2) was considered an exceedingly rare form of autosomal dominant thrombocytopenia and only 2 families were known. However, we recently identified mutations in the 5'-untranslated region of the ANKRD26 gene in 9 THC2 families. Here we report on 12 additional pedigrees with ANKRD26 mutations, 6 of which are new. Because THC2 affected 21 of the 210 families in our database, it has to be considered one of the less rare forms of inherited thrombocytopenia. Analysis of all 21 families with ANKRD26 mutations identified to date revealed that thrombocytopenia and bleeding tendency were usually mild. Nearly all patients had no platelet macrocytosis, and this characteristic distinguishes THC2 from most other forms of inherited thrombocytopenia. In the majority of cases, platelets were deficient in glycoprotein Ia and α-granules, whereas in vitro platelet aggregation was normal. Bone marrow examination and serum thrombopoietin levels suggested that thrombocytopenia was derived from dysmegakaryopoiesis. Unexplained high values of hemoglobin and leukocytes were observed in a few cases. An unexpected finding that warrants further investigation was a high incidence of acute leukemia. Given the scarcity of distinctive characteristics, the ANKRD26-related thrombocytopenia has to be taken into consideration in the differential diagnosis of isolated thrombocytopenias.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Ankyrin Repeat; Child; Cohort Studies; Family; Female; Gene Frequency; Humans; Inheritance Patterns; Male; Middle Aged; Mutation; Pedigree; Thrombocytopenia; Transcription Factors; Young Adult

Mutations in the 5' UTR of ANKRD26, the ankirin repeat domain 26 gene, cause an autosomal-dominant form of inherited thrombocytopenia, THC2. - Pippucci, Tommaso; Savoia, Anna; Perrotta, Silverio; Pujol-Moix, Núria; Noris, Patrizia; Castegnaro, Giovanni; Pecci, Alessandro; Gnan, Chiara; Punzo, Francesca; Marconi, Caterina; Gherardi, Samuele; Loffredo, Giuseppe; et al. (Am J Hum Genet, 2011)
THC2, an autosomal-dominant thrombocytopenia described so far in only two families, has been ascribed to mutations in MASTL or ACBD5. Here, we show that ANKRD26, another gene within the THC2 locus, and neither MASTL nor ACBD5, is mutated in eight unrelated families. ANKRD26 was also found to be mutated in the family previously reported to have an ACBD5 mutation. We identified six different ANKRD26 mutations, which were clustered in a highly conserved 19 bp sequence located in the 5' untranslated region. Mutations were not detected in 500 controls and are absent from the 1000 Genomes database. Available data from an animal model and Dr. Watson's genome give evidence against haploinsufficiency as the pathogenetic mechanism for ANKRD26-mediated thrombocytopenia. The luciferase reporter assay suggests that these 5' UTR mutations might enhance ANKRD26 expression. ANKRD26 is the ancestor of a family of primate-specific genes termed POTE, which have been recently identified as a family of proapoptotic proteins. Dysregulation of apoptosis might therefore be the pathogenetic mechanism, as demonstrated for another thrombocytopenia, THC4. Further investigation is needed to provide evidence supporting this hypothesis.
Keywords: Ankyrin Repeat; Base Sequence; Chromosome Breakage; Chromosome Disorders; Conserved Sequence; Female; Genes, Dominant; Genetic Loci; Haploinsufficiency; Humans; Male; Molecular Sequence Data; Mutation; Pedigree; Thrombocytopenia

Mutations in TTC19 cause mitochondrial complex III deficiency and neurological impairment in humans and flies. - Ghezzi, Daniele; Arzuffi, Paola; Zordan, Mauro; Da Re, Caterina; Lamperti, Costanza; Benna, Clara; d'Adamo, Pio; Diodato, Daria; Costa, Rodolfo; Mariotti, Caterina; Uziel, Graziella; Smiderle, Cristina; et al. (Nat Genet, 2011)
Although mutations in CYTB (cytochrome b) or BCS1L have been reported in isolated defects of mitochondrial respiratory chain complex III (cIII), most cIII-defective individuals remain genetically undefined. We identified a homozygous nonsense mutation in the gene encoding tetratricopeptide 19 (TTC19) in individuals from two families affected by progressive encephalopathy associated with profound cIII deficiency and accumulation of cIII-specific assembly intermediates. We later found a second homozygous nonsense mutation in a fourth affected individual. We demonstrated that TTC19 is embedded in the inner mitochondrial membrane as part of two high-molecular-weight complexes, one of which coincides with cIII. We then showed a physical interaction between TTC19 and cIII by coimmunoprecipitation. We also investigated a Drosophila melanogaster knockout model for TTC19 that showed low fertility, adult-onset locomotor impairment and bang sensitivity, associated with cIII deficiency. TTC19 is a putative cIII assembly factor whose disruption is associated with severe neurological abnormalities in humans and flies.
Keywords: Adult; Animals; Brain; Codon, Nonsense; Drosophila melanogaster; Electron Transport Complex III; Female; Gene Knockdown Techniques; Humans; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Nervous System Diseases

Neonatal necrotizing tracheobronchitis. - Bua, Jenny; Trappan, Antonella; Demarini, Sergio; Grasso, Domenico; Schleef, Jurgen; Zennaro, Floriana (J Pediatr, 2011)
Keywords: Bronchitis; Bronchoscopy; High-Frequency Ventilation; Humans; Infant, Newborn; Male; Necrosis; Respiratory Insufficiency; Respiratory Mucosa; Tracheitis

A new case of duplication of the MDS region identified by high-density SNP arrays and a review of the literature. - Faletra, Flavio; Devescovi, Raffaella; Pecile, Vanna; Fabretto, Antonella; Carrozzi, Marco; Gasparini, Paolo (J Appl Genet, 2011)
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Child; Female; Gene Duplication; Humans; Microtubule-Associated Proteins; Myelodysplastic Syndromes; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Prognosis

Non-invasive assessment of hemispheric language dominance by optical topography during a brief passive listening test: a pilot study. - Bembich, Stefano; Demarini, Sergio; Clarici, Andrea; Massaccesi, Stefano; Grasso, Domenico Loenardo (Med Sci Monit, 2011)
BACKGROUND: The Wada test is usually used for pre-surgical assessment of language lateralization. Considering its invasiveness and risk of complications, alternative methods have been proposed but they are not always applicable to non-cooperative patients. In this study we explored the possibility of using optical topography (OT)--a multichannel near-infrared system--for non-invasive assessment of hemispheric language dominance during passive listening. MATERIAL/METHODS: Cortical activity was monitored in a sample of healthy, adult Italian native speakers, all right-handed. We assessed changes in oxy-haemoglobin concentration in temporal, parietal and posterior frontal lobes during a passive listening of bi-syllabic words and vowel-consonant-vowel syllables lasting less then 3 minutes. Activated channels were identified by t tests. RESULTS: Left hemisphere showed significant activity only during the passive listening of bi-syllabic words. Specifically, the superior temporal gyrus, the supramarginal gyrus and the posterior inferior parietal lobe were activated. CONCLUSIONS: During passive listening of bi-syllabic words, right handed healthy adults showed a significant activation in areas already known to be involved in speech comprehension. Although more research is needed, OT proved to be a promising alternative to the Wada test for non-invasive assessment of hemispheric language lateralization, even if using a particularly brief trial, which has been designed for future applications with non-cooperative subjects.
Keywords: Acoustic Stimulation; Adult; Cerebrum; Diagnostic Techniques and Procedures; Dominance, Cerebral; Female; Humans; Language; Male; Middle Aged; Oxyhemoglobins; Pilot Projects; Spectroscopy, Near-Infrared

Phospholipase C-β3 is a key modulator of IL-8 expression in cystic fibrosis bronchial epithelial cells. - Bezzerri, Valentino; d'Adamo, Pio; Rimessi, Alessandro; Lanzara, Carmen; Crovella, Sergio; Nicolis, Elena; Tamanini, Anna; Athanasakis, Emmanouil; Tebon, Maela; Bisoffi, Giulia; Drumm, Mitchell L; Knowles, Michael R; et al. (J Immunol, 2011)
Respiratory insufficiency is the major cause of morbidity and mortality in patients affected by cystic fibrosis (CF). An excessive neutrophilic inflammation, mainly orchestrated by the release of IL-8 from bronchial epithelial cells and amplified by chronic bacterial infection with Pseudomonas aeruginosa, leads to progressive tissue destruction. The anti-inflammatory drugs presently used in CF patients have several limitations, indicating the need for identifying novel molecular targets. To address this issue, we preliminarily studied the association of 721 single nucleotide polymorphisms from 135 genes potentially involved in signal transduction implicated in neutrophil recruitment in a cohort of F508del homozygous CF patients with either severe or mild progression of lung disease. The top ranking association was found for a nonsynonymous polymorphism of the phospholipase C-β3 (PLCB3) gene. Studies in bronchial epithelial cells exposed to P. aeruginosa revealed that PLCB3 is implicated in extracellular nucleotide-dependent intracellular calcium signaling, leading to activation of the protein kinase Cα and Cβ and of the nuclear transcription factor NF-κB p65. The proinflammatory pathway regulated by PLCB3 acts by potentiating the Toll-like Receptors' signaling cascade and represents an interesting molecular target to attenuate the excessive recruitment of neutrophils without completely abolishing the inflammatory response.
Keywords: Adenosine Triphosphate; Calcium; Cell Line, Transformed; Cystic Fibrosis; Enzyme Activation; Epithelial Cells; Gene Expression; Gene Frequency; Genotype; Green Fluorescent Proteins; Host-Pathogen Interactions; Humans; Interleukin-8; Isoenzymes; Lung Diseases; Microscopy, Fluorescence; Phospholipase C beta; Polymorphism, Single Nucleotide; Protein Kinase C; Protein Kinase C beta; Pseudomonas aeruginosa; RNA Interference; Toll-Like Receptors; Transcription Factor RelA

A polymorphism in the 5' UTR of the DEFB1 gene is associated with the lung phenotype in F508del homozygous Italian cystic fibrosis patients. - Crovella, Sergio; Segat, Ludovica; Amato, Annalisa; Athanasakis, Emmanouil; Bezzerri, Valentino; Braggion, Cesare; Casciaro, Rosaria; Castaldo, Giuseppe; Colombo, Carla; Covone, Angela Elvira; De Rose, Virginia; Gagliardini, Rolando; et al. (Clin Chem Lab Med, 2011)
BACKGROUND: The identification of cystic fibrosis (CF) patients who are at greater risk of lung damage could be clinically valuable. Thus, we attempted to replicate previous findings and verify the possible association between three single nucleotide polymorphisms (SNPs c.-52G>A, c.-44C>G and c.-20G>A) in the 5' untranslated region (5' UTR) of the β defensin 1 (DEFB1) gene and the CF pulmonary phenotype. METHODS: Genomic DNA from 92 Italian CF patients enrolled in different regional CF centres was extracted from peripheral blood and genotyped for DEFB1 SNPs using TaqMan(®) allele specific probes. In order to avoid genetic confounding causes that can account for CF phenotype variability, all patients were homozygous for the F508del CFTR mutation, and were then classified on the basis of clinical and functional data as mild lung phenotype (Mp, n=50) or severe lung phenotype patients (Sp, n=42). RESULTS: For the c.-20G>A SNP, the frequency of the A allele, as well as the AA genotype, were significantly more frequent in Mp than in Sp patients, and thus this was associated with a protective effect against severe pulmonary disease (OR=0.48 and 0.28, respectively). The effect of the c.-20G>A A allele is consistent with a recessive model, and the protective effect against Sp is exerted only when it is present in homozygosis. For the other two SNPs, no differences were observed as allelic and genotypic frequency in the two subgroups of CF patients. CONCLUSIONS: Our results, although necessary to be confirmed in larger and multiethnic populations, reinforce DEFB1 as a candidate modifier gene of the CF pulmonary phenotype.
Keywords: 5' Untranslated Regions; Adult; beta-Defensins; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Female; Genotype; Homozygote; Humans; Italy; Male; Mutation; Phenotype; Polymorphism, Genetic; Young Adult

[Proteomic applications in gynecology-obstetrics]. - De Seta, F; Banco, R; Guaschino, S; De Santo, D; Turrisi, A; Piva, C (Minerva Ginecol, 2011)
Proteomics has recently emerged as a powerful approach both for discovering biomarkers as well as for understanding the physiopathology of unclear gynecological-obstetrical disorders. Currently, several biological fluids and fetal tissues were successfully tested, including maternal plasma, amniotic fluid, cervical-vaginal fluid, urine, saliva, placental trophoblast, amnio-chorionic membranes and cord blood. The potential of proteomics on the polycystic ovary syndrome (PCOS) involves biomarkers discovery for a more accurate diagnosis of the syndrome and identification, within the patients with PCOS, those who respond more easily to treatment and those who will be at increased risk for future metabolic complications. The proteomic approach applied to patients with endometriosis would allow not only a non-invasive early diagnosis, but also a staging of the disease and a prediction of infertility risk. Proteomics also involves oncological field, in order to discover biomarkers that allow early diagnosis and prognosis of female genital malignancies. In addition to this, proteomics could be used to understand and predict obstetrical complications such as recurrent spontaneous abortion, preterm birth and preeclampsia. However, further studies are needed on a larger cohort of patients to introduce these biomarkers in clinical practice.
Keywords: Endometriosis; Female; Genital Diseases, Female; Genital Neoplasms, Female; Humans; Polycystic Ovary Syndrome; Pregnancy; Pregnancy Complications; Proteomics

The role of mannose-binding lectin gene polymorphisms in susceptibility to HIV-1 infection in Southern Brazilian patients. - da Silva, Gabriela Kniphoff; Guimarães, Rafael; Mattevi, Vanessa Suñé; Lazzaretti, Rosmeri Kuhmmer; Sprinz, Eduardo; Kuhmmer, Regina; Brandão, Lucas; Crovella, Sergio; Chies, José Artur Bogo (AIDS, 2011)
OBJECTIVE: This study investigates the role of mannose-binding lectin (MBL) in the susceptibility to HIV-1 infection analyzing polymorphisms located at the MBL2 promoter and exon 1 regions. MATERIALS AND METHODS: The prevalence of MBL2 variant alleles was investigated in 410 HIV-1-infected patients from the South Brazilian HIV cohort and in 345 unexposed uninfected healthy individuals. The promoter variants were genotyped using polymerase chain reaction with sequence-specific primers (PCR-SSP) and exon 1 variants were analyzed by real-time PCR using a melting temperature assay and were confirmed by PCR-restriction fragment length polymorphism (RFLP). MBL2 genotypic and allelic frequencies were compared between HIV-1-infected patients and controls using the chi-squared tests. RESULTS: The analyses were performed subdividing the individuals according to their ethnic origin. Among Euro-derived individuals a higher frequency of the LX/LX genotype was observed in patients when compared to controls (P < 0.001). The haplotypic analysis also showed a higher frequency of the haplotypes associated with lower MBL levels among HIV-1-infected patients (P = 0.0001). Among Afro-derived individuals the frequencies of LY/LY and HY/HY genotypes were higher in patients when compared to controls (P = 0.009 and P = 0.02). CONCLUSIONS: An increased frequency of MBL2 genotypes associated with low MBL levels was observed in Euro-derived patients, suggesting a potential role for MBL in the susceptibility to HIV-1 infection in Euro-derived individuals.
Keywords: Adult; Aged; Brazil; Female; Genetic Predisposition to Disease; HIV Infections; HIV-1; Humans; Lectins, C-Type; Male; Mannose-Binding Lectin; Mannose-Binding Lectins; Middle Aged; Polymorphism, Genetic; Promoter Regions, Genetic; Receptors, Cell Surface; Young Adult

Rubella susceptibility profile in pregnant women with HIV. - Floridia, Marco; Pinnetti, Carmela; Ravizza, Marina; Tibaldi, Cecilia; Sansone, Matilde; Fiscon, Marta; Guaraldi, Giovanni; Guerra, Brunella; Alberico, Salvatore; Spinillo, Arsenio; Castelli, Paula; Dalzero, Serena; et al. (Clin Infect Dis, 2011)
Keywords: Female; HIV Infections; Humans; Pregnancy; Pregnancy Complications, Infectious; Rubella

Shwachman-Diamond syndrome and type 1 diabetes mellitus: more than a chance association? - Gana, S; Sainati, L; Frau, M R; Monciotti, C; Poli, F; Cannioto, Z; Comelli, M; Danesino, C; Minelli, A (Exp Clin Endocrinol Diabetes, 2011)
Shwachman-Diamond syndrome is a rare clinical condition consisting of exocrine pancreatic dysfunction, various degree of pancytopenia, and metaphyseal dysplasia. The majority of Shwachman-Diamond syndrome cases result from mutations in the Shwachman-Bodian-Diamond Syndrome gene. To date, type 1 diabetes mellitus has only been reported in 4 independent cases presenting with Shwachman-Diamond syndrome, 3 of them with molecular confirmation of the diagnosis. We describe 2 unrelated patients with clinical and molecular features typical of Shwachman-Diamond syndrome and type 1 diabetes mellitus. In addition, we report the occurrence rate of type 1 diabetes mellitus in the Italian registry for Shwachman-Diamond syndrome, which is low (3.23%) but increased at least 30-fold over the type 1 diabetes mellitus occurrence rate in the general population. No evidence of a direct correlation between Shwachman-Diamond syndrome and type 1 diabetes mellitus have been reported, therefore the presence of both diseases in the same patient might be a chance association, however we suggest that the defects in immune regulation of Shwachman-Diamond syndrome might play a role in the development of type 1 diabetes mellitus.
Keywords: Bone Marrow Diseases; CD4-CD8 Ratio; Diabetes Mellitus, Type 1; Exocrine Pancreatic Insufficiency; Female; Heterozygote; Humans; Immune System; Infant; Italy; Lipomatosis; Male; Mutation; Prevalence; Proteins; Registries

Somatic mosaic IDH1 and IDH2 mutations are associated with enchondroma and spindle cell hemangioma in Ollier disease and Maffucci syndrome. - Pansuriya, Twinkal C; van Eijk, Ronald; d'Adamo, Pio; van Ruler, Maayke A J H; Kuijjer, Marieke L; Oosting, Jan; Cleton-Jansen, Anne-Marie; van Oosterwijk, Jolieke G; Verbeke, Sofie L J; Meijer, Daniëlle; van Wezel, Tom; Nord, Karolin H; et al. (Nat Genet, 2011)
Ollier disease and Maffucci syndrome are non-hereditary skeletal disorders characterized by multiple enchondromas (Ollier disease) combined with spindle cell hemangiomas (Maffucci syndrome). We report somatic heterozygous mutations in IDH1 (c.394C>T encoding an R132C substitution and c.395G>A encoding an R132H substitution) or IDH2 (c.516G>C encoding R172S) in 87% of enchondromas (benign cartilage tumors) and in 70% of spindle cell hemangiomas (benign vascular lesions). In total, 35 of 43 (81%) subjects with Ollier disease and 10 of 13 (77%) with Maffucci syndrome carried IDH1 (98%) or IDH2 (2%) mutations in their tumors. Fourteen of 16 subjects had identical mutations in separate lesions. Immunohistochemistry to detect mutant IDH1 R132H protein suggested intraneoplastic and somatic mosaicism. IDH1 mutations in cartilage tumors were associated with hypermethylation and downregulated expression of several genes. Mutations were also found in 40% of solitary central cartilaginous tumors and in four chondrosarcoma cell lines, which will enable functional studies to assess the role of IDH1 and IDH2 mutations in tumor formation.
Keywords: Adult; Case-Control Studies; Cell Line, Tumor; DNA Methylation; Enchondromatosis; Female; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Humans; Isocitrate Dehydrogenase; Male; Middle Aged; Mosaicism; Mutation, Missense; Sequence Analysis, DNA; Transcription, Genetic; Young Adult

Therapeutic approaches in the treatment of juvenile dermatomyositis in patients with recent-onset disease and in those experiencing disease flare: an international multicenter PRINTO study. - Hasija, Rachana; Pistorio, Angela; Ravelli, Angelo; Demirkaya, Erkan; Khubchandani, Raju; Guseinova, Dinara; Malattia, Clara; Canhao, Helena; Harel, Liora; Foell, Dirk; Wouters, Carine; De Cunto, Carmen; et al. (Arthritis Rheum, 2011)
OBJECTIVE: To evaluate response to therapy over a 24-month period in a large prospective international cohort of patients with juvenile dermatomyositis (DM). METHODS: The study included 145 patients with recent-onset juvenile DM and 130 juvenile DM patients experiencing disease flare, all of whom were <18 years old. Disease activity parameters and therapeutic approaches in 4 geographic areas were analyzed at baseline and at 6, 12, and 24 months. Response was assessed according to the Pediatric Rheumatology International Trials Organization (PRINTO) juvenile DM response criteria, and data were reported "as observed" and in the intent-to-treat (ITT) population. RESULTS: Patients with recent-onset juvenile DM at baseline had higher baseline disease activity and greater improvement over 24 months when compared to juvenile DM patients experiencing disease flare at baseline. Methotrexate (MTX) or high-dose corticosteroids were administered more frequently to patients with recent-onset juvenile DM, compared to juvenile DM patients experiencing disease flare, who were more likely to receive cyclosporine. Compared to patients from Western and Eastern Europe, a higher proportion of patients from South and Central America and North America received pulse steroids, and the average steroid dosage was higher in the North American and South and Central American patients. The use of MTX was similar in all 4 regions, while cyclosporin A was more frequently used in Western Europe. In the "as observed" analysis, 57.9% of the patients with recent-onset juvenile DM and 36.4% of the patients experiencing disease flare (P<0.001) reached at least a 70% response by PRINTO criteria at 6 months; these proportions had increased at month 24 to 78.4% and 51.2%, respectively (P<0.001). Corresponding results of the ITT analysis were much lower, with only one-third of the patients able to maintain the initial assigned therapy over 24 months. CONCLUSION: Patients with recent-onset juvenile DM are more likely to achieve significant clinical improvement over 24 months, when compared to patients experiencing flares of juvenile DM. Internationally, various therapeutic approaches are used to treat this disease.
Keywords: Adolescent; Adrenal Cortex Hormones; Child; Dermatologic Agents; Dermatomyositis; Female; Humans; Longitudinal Studies; Male; Methotrexate; Prospective Studies; Treatment Outcome

Trail down-regulates the release of osteoprotegerin (OPG) by primary stromal cells. - Corallini, Federica; Celeghini, Claudio; Rimondi, Erika; di Iasio, Maria Grazia; Gonelli, Arianna; Secchiero, Paola; Zauli, Giorgio (J Cell Physiol, 2011)
The soluble member of the TNF-R superfamily osteoprotegerin (OPG) is abundantly released under basal conditions by both mesenchymal stem cells (MSC) and fibroblasts and by endothelial cells upon stimulation with inflammatory cytokines. Since MSC, fibroblasts and endothelial cells represent key elements of the normal and tumor microenvironment and express detectable levels of surface TRAIL receptors, we investigated the effect of TRAIL on OPG release. Unexpectedly, recombinant TRAIL decreased the spontaneous OPG release in all cell types examined. Moreover, TRAIL decreased OPG release also in stromal cells co-cultured with lymphoma cells and counteracted the OPG induction by TN-alpha in HUVEC and MSC. Such down-regulation was not due to a masking effect in the ELISA quantification of the OPG released in the culture supernatants due to binding of OPG to its ligands (TRAIL and RANKL), as demonstrated by competition experiments with recombinant TRAIL and by the lack of RANKL release/induction. In addition, OPG down-regulation was not due to induction of cytotoxic effects by TRAIL, since the degree of apoptosis in response to TRAIL was negligible in all primary cell types. With regards to the possible molecular mechanism accounting for the down-regulation of OPG release by TRAIL, we found that treatment of MSC with TRAIL significantly decreased the phosphorylation levels of p38/MAPK. There is a suggestion that this pathway is involved in the stabilization of OPG mRNA. In this respect, the ability of TRAIL to decrease the release of OPG, in the absence of cell cytotoxicity, was mimicked by the p38/MAPK inhibitor SB203580.
Keywords: Bone Marrow Cells; Cell Death; Cells, Cultured; Coculture Techniques; Down-Regulation; Endothelial Cells; Enzyme Activation; Enzyme-Linked Immunosorbent Assay; Fibroblasts; Humans; MAP Kinase Signaling System; Mesenchymal Stromal Cells; Osteoprotegerin; p38 Mitogen-Activated Protein Kinases; Protein Binding; Recombinant Proteins; Stromal Cells; TNF-Related Apoptosis-Inducing Ligand; Tumor Necrosis Factor-alpha

Two lumens, one diagnosis. - Pastore, Serena; Gortani, Giulia; Maschio, Massimo; Di Leo, Grazia; Ventura, Alessandro (J Pediatr, 2011)
Keywords: Capsule Endoscopy; Child, Preschool; Gastrointestinal Hemorrhage; Humans; Male; Meckel Diverticulum; Recurrence

Vertebral defects in patients with Peters plus syndrome and mutations in B3GALTL. - Faletra, Flavio; Athanasakis, Emmanouil; Minen, Federico; Fornasier, Federico; Marchetti, Federico; Gasparini, Paolo (Ophthalmic Genet, 2011)
Keywords: Abnormalities, Multiple; Alternative Splicing; Child, Preschool; Cleft Lip; Consanguinity; Cornea; Female; Galactosyltransferases; Glucosyltransferases; Growth Disorders; Humans; Limb Deformities, Congenital; Point Mutation; Spine

A 3'UTR SNP in NLRP3 gene is associated with susceptibility to HIV-1 infection. - Pontillo, Alessandra; Brandão, Lucas A; Guimarães, Rafael L; Segat, Ludovica; Athanasakis, Emmanouil; Crovella, Sergio (J Acquir Immune Defic Syndr, 2010)
OBJECTIVES: Innate immunity genes polymorphisms are known to be involved in the multifactorial susceptibility to HIV-1 infection. Recently it has been hypothesized that inflammasomes could play an important role in the host response to viruses. The aim of our study is to verify if single-nucleotide polymorphisms (SNPs) in genes encoding for NALPs-innate immune receptors that form molecular complexes leading to the production of IL-1beta and the activation of immune response-could influence the individual susceptibility to HIV-1. DESIGN: We performed an association study analyzing 2 NLRP1 and NLRP3 SNPs in HIV-1 vertically infected Brazilian children (n = 135), HIV-1-infected Brazilain adults (n = 192) and HIV-1-positive Italian seropositive subjects (n = 192). RESULTS: The 3'UTR NLRP3 rs10754558 SNP was associated with HIV-1 infection in all the studied groups. The frequency of rs10754558 G allele was differently distributed within seropositive subjects (HIV+) and controls, and in particular the GG genotype was less frequent in HIV+. CONCLUSIONS: susceptibility to HIV-1 infection is associated with a 3'UTR NLRP3 polymorphism. This is the first report linking SNPs in the NALPs with HIV-1 infection, and further epidemiologic and functional studies are needed to deeper investigate the role of inflammasome in the susceptibility to HIV-1 infection.
Keywords: Adult; Brazil; Carrier Proteins; Case-Control Studies; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genotype; HIV Infections; HIV-1; Humans; Infant; Infectious Disease Transmission, Vertical; Male; Middle Aged; Polymorphism, Single Nucleotide; Pregnancy; Young Adult

Abatacept improves health-related quality of life, pain, sleep quality, and daily participation in subjects with juvenile idiopathic arthritis. - Ruperto, Nicolino; Lovell, Daniel J; Li, Tracy; Sztajnbok, Flavio; Goldenstein-Schainberg, Claudia; Scheinberg, Morton; Penades, Inmaculada Calvo; Fischbach, Michael; Alcala, Javier Orozco; Hashkes, Philip J; Hom, Christine; Jung, Lawrence; et al. (Arthritis Care Res (Hoboken), 2010)
OBJECTIVE: To assess health-related quality of life (HRQOL) in abatacept-treated children/adolescents with juvenile idiopathic arthritis (JIA). METHODS: In this phase III, double-blind, placebo-controlled trial, subjects with active polyarticular course JIA and an inadequate response/intolerance to ≥1 disease-modifying antirheumatic drug (including biologics) received abatacept 10 mg/kg plus methotrexate (MTX) during the 4-month open-label period (period A). Subjects achieving the American College of Rheumatology Pediatric 30 criteria for improvement (defined "responders") were randomized to abatacept or placebo (plus MTX) in the 6-month double-blind withdrawal period (period B). HRQOL assessments included 15 Child Health Questionnaire (CHQ) health concepts plus the physical (PhS) and psychosocial summary scores (PsS), pain (100-mm visual analog scale), the Children's Sleep Habits Questionnaire, and a daily activity participation questionnaire. RESULTS: A total of 190 subjects from period A and 122 from period B were eligible for analysis. In period A, there were substantial improvements across all of the CHQ domains (greatest improvement was in pain/discomfort) and the PhS (8.3 units) and PsS (4.3 units) with abatacept. At the end of period B, abatacept-treated subjects had greater improvements versus placebo in all domains (except behavior) and both summary scores. Similar improvement patterns were seen with pain and sleep. For participation in daily activities, an additional 2.6 school days/month and 2.3 parents' usual activity days/month were gained in period A responders with abatacept, and further gains were made in period B (1.9 versus 0.9 [P = 0.033] and 0.2 versus -1.3 [P = 0.109] school days/month and parents' usual activity days/month, respectively, in abatacept- versus placebo-treated subjects). CONCLUSION: Improvements in HRQOL were observed with abatacept, providing real-life tangible benefits to children with JIA and their parents/caregivers.
Keywords: Adolescent; Arthritis, Juvenile; Child; Double-Blind Method; Female; Health Status; Humans; Immunoconjugates; Male; Pain; Quality of Life; Questionnaires; Sleep Stages

An alternative role of C1q in cell migration and tissue remodeling: contribution to trophoblast invasion and placental development. - Agostinis, Chiara; Bulla, Roberta; Tripodo, Claudio; Gismondi, Angela; Stabile, Helena; Bossi, Fleur; Guarnotta, Carla; Garlanda, Cecilia; De Seta, Francesco; Spessotto, Paola; Santoni, Angela; Ghebrehiwet, Berhane; et al. (J Immunol, 2010)
Fetal trophoblast cells invading the decidua in the early phase of pregnancy establish complex interaction with the maternal extracellular matrix. We discovered that C1q was widely distributed in human decidual stroma in the absence of C4 and C3 and was actively synthesized by migrating extravillous trophoblasts. The cells expressed the messages for the three chains of C1q and secreted this complement component that interacted with the proteins of the decidual extracellular matrix. Solid phase-bound C1q promoted trophoblast adhesion and migration, and cell binding to C1q resulted in activation of ERK1/2 MAPKs. Ab inhibition experiments showed that the receptors for the globular head of C1q/p33 and α(4)β(1) integrin were both involved in this process and were colocalized on the cell surface following binding of C1q to trophoblasts. We also found that C1q(-/-) mice manifested increased frequency of fetal resorption, reduced fetal weight, and smaller litter sizes compared with wild-type mice. C1q deficiency was associated with impaired labyrinth development and decidual vessel remodeling. Collectively, these data suggest that C1q plays an important role in promoting trophoblast invasion of decidua and that defective local production of C1q may be involved in pregnancy disorders, such as pre-eclampsia, characterized by poor trophoblast invasion.
Keywords: Animals; Cell Adhesion; Chemotaxis, Leukocyte; Complement C1q; Female; Humans; Immunoblotting; Immunohistochemistry; Immunoprecipitation; Mice; Mice, Inbred C57BL; Microscopy, Confocal; Placentation; Pre-Eclampsia; Pregnancy; Reverse Transcriptase Polymerase Chain Reaction; Trophoblasts

Beta defensin-1 gene (DEFB1) polymorphisms are not associated with atopic dermatitis in children and adolescents from northeast Brazil (Recife, Pernambuco). - Segat, Ludovica; Guimarães, Rafael L; Brandão, Lucas A C; Rocha, Cintia R C; Zanin, Valentina; Trevisiol, Chiara; de Lima Filho, José Luiz; Crovella, Sergio (Int J Dermatol, 2010)
BACKGROUND: Atopic dermatitis (AD) is a common inflammatory skin disease resulting from the interplay between environmental, immunological and genetic factors. In our study, we investigated the role of three single nucleotide polymorphisms (SNPs) at 5'-UTR of DEFB1 gene, encoding for the human beta defensin-1, on the susceptibility to develop AD in a group of Brazilian children and adolescents. METHODS: Three SNPs, -20 G/A (rs11362), -44 C/G (rs1800972), and -52 G/A (rs1799946) at 5'-UTR of DEFB1 gene were genotyped in two groups of children and adolescents, one affected by AD (96 subjects), the other healthy (191 individuals), from northeast Brazil. RESULTS: -44 C/G frequencies were comparable between the two groups. The -20 GG genotype was more frequent in AD subjects than in healthy controls; the -52 GG, conversely, was more frequent in healthy controls than in AD. However, both these differences did not reach statistical significance. Also, association between SNPs and AD severity has been shown. The analysis of DEFB1 haplotypes did not highlight any association of the three SNPs with AD development or disease severity. CONCLUSIONS: Our results seem to exclude a role for the -44 C/G DEFB1 SNPs on the pathogenesis and severity of AD, while for the -20 C/G and -52 G/A, even if not statistically significant, we evidenced a slight trend for susceptibility (-20 GG) and protection (-52 GG) for the development of AD. However, as controversial findings have been reported in the literature, the role of DEFB1 in the development of AD and in the severity of the phenotype deserves further investigation.
Keywords: Adolescent; beta-Defensins; Brazil; Child; Child, Preschool; Dermatitis, Atopic; Female; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; Humans; Infant; Male; Polymorphism, Single Nucleotide; Risk Factors

A case of lymphedema-distichiasis syndrome carrying a new de novo frameshift FOXC2 mutation. - Fabretto, Antonella; Shardlow, Alison; Faletra, Flavio; Lepore, Loredana; Hladnik, Uros; Gasparini, Paolo (Ophthalmic Genet, 2010)
PURPOSE: Lymphedema-Distichiasis (LD, OMIM 153400) is an autosomal dominant disorder with variable expression. The mutated gene implicated is FOXC2, which encodes for a forkhead transcription factor involved in the development of the lymphatic and vascular system. LD is characterized by late childhood or pubertal onset lymphedema of the limbs and distichiasis. Other associations have been reported, including congenital heart disease, ptosis, scoliosis. CONCLUSIONS: Here we describe a case of LD carrying a de novo frameshift mutation of FOXC2 who presented a prepubertal onset of lower limbs lymphedema and mild distichiasis associated with other anomalies such as webbing neck and ptosis.
Keywords: Abnormalities, Multiple; Adolescent; Eye Abnormalities; Eyelashes; Face; Forkhead Transcription Factors; Frameshift Mutation; Humans; Lymphedema; Male; Syndrome

Declining HCV seroprevalence in pregnant women with HIV. - Floridia, M; Tamburrini, E; Anzidei, G; Tibaldi, C; Muggiasca, M L; Guaraldi, G; Fiscon, M; Vimercati, A; Martinelli, P; Donisi, A; Dalzero, S; Ravizza, M (Epidemiol Infect, 2010)
We assessed recent trends in hepatitis C virus (HCV) prevalence in pregnant women with HIV using data from a large national study. Based on 1240 pregnancies, we observed a 3.4-fold decline in HCV seroprevalence in pregnant women with HIV between 2001 (29.3%) and 2008 (8.6%). This decline was the net result of two components: a progressively declining HCV seroprevalence in non-African women (from 35.7% in 2001 to 16.7% in 2008), sustained by a parallel reduction in history of injecting drug use (IDU) in this population, and a significantly growing presence (from 21.2% in 2001 to 48.6% in 2008) of women of African origin, at very low risk of being HCV-infected [average HCV prevalence 1%, adjusted odds ratio (aOR) for HCV 0.09, 95% CI 0.03-0.29]. Previous IDU was the stronger determinant of HCV co-infection in pregnant women with HIV (aOR 30.9, 95% CI 18.8-51.1). The observed trend is expected to translate into a reduced number of cases of vertical HCV transmission.
Keywords: Chi-Square Distribution; Female; Hepatitis C; HIV Infections; Humans; Italy; Logistic Models; Pregnancy; Risk Factors; Seroepidemiologic Studies

Defective FOXP3 expression in patients with acute Kawasaki disease and restoration by intravenous immunoglobulin therapy. - Olivito, Biagio; Taddio, Andrea; Simonini, Gabriele; Massai, Cristina; Ciullini, Sara; Gambineri, Eleonora; de Martino, Maurizio; Azzari, Chiara; Cimaz, Rolando (Clin Exp Rheumatol, 2010)
OBJECTIVES: The aims of this study were: 1) to investigate forkhead box P3 (FOXP3) expression in patients with Kawasaki disease (KD), exploring possible differences during the acute phase and after defervescence; 2) to evaluate a possible association of the FOXP3 single nucleotide polymorphism (SNP) 543 (SNP ID: rs2232367) with KD. METHODS: FOXP3 expression was evaluated on 8 children with KD and 15 healthy children by flow cytometry and Real-Time polymerase chain reaction (RT-PCR). FOXP3 SNP 543 was genotyped by denaturing high-performance liquid chromatography (DHPLC) and sequencing on DNA samples from 58 additional children with KD and 114 healthy donors. RESULTS: The frequencies of CD4+CD25 +FOXP3+ regulatory T cells were significantly (p=0.0002) lower during the acute phase of KD than in sex- and age-matched healthy donors (median % + SD: 4.8+/-1.3 vs. 7.7+/-1.7) and a similar tendency was revealed for FOXP3 mRNA transcripts (p<0.0001). FOXP3 expression increased significantly, at both protein and mRNA levels, after intravenous immunoglobulin (IVIG) therapy treatment and achieving complete remission of disease (at least 48 hrs; median 9.5 days, range 2-30). Of the 58 patients screened, only one female subject (1.7%) carried the presence of 543 SNP in heterozygosis (C>T; for a total of 1 allele out of 88), with no difference between KD patients and controls (0.0%, 0/203 alleles). CONCLUSIONS: Our data reinforce the notion of an impaired immunoregulation in KD, suggesting also a role of IVIG treatment in modifying the Treg compartment. FOXP3 SNP 543 does not seem to be involved in susceptibility to KD in Italian children.
Keywords: Acute Disease; Child; Child, Preschool; Female; Flow Cytometry; Forkhead Transcription Factors; Genotype; Humans; Immunoglobulins, Intravenous; Infant; Italy; Male; Mucocutaneous Lymph Node Syndrome; Polymorphism, Single Nucleotide; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; T-Lymphocytes, Regulatory

Eltrombopag for the treatment of the inherited thrombocytopenia deriving from MYH9 mutations. - Pecci, Alessandro; Gresele, Paolo; Klersy, Catherine; Savoia, Anna; Noris, Patrizia; Fierro, Tiziana; Bozzi, Valeria; Mezzasoma, Anna Maria; Melazzini, Federica; Balduini, Carlo L (Blood, 2010)
Platelet transfusion is currently the primary medical treatment for reducing thrombocytopenia in patients with inherited thrombocytopenias. To evaluate whether stimulating megakaryopoiesis could increase platelet count in these conditions, we treated patients with a severe thrombocytopenia induced by MYH9 mutations (MYH9-related disease) with a nonpeptide thrombopoietin receptor agonist, eltrombopag. Twelve adult patients with MYH9-RD and platelet counts of less than 50 × 10(9)/L received 50 mg of eltrombopag orally per day for 3 weeks. Patients who achieved a platelet count higher than 150 × 10(9)/L stopped therapy, those with 100 to 150 platelets × 10(9)/L continued treatment at the same eltrombopag dose for 3 additional weeks, while those with less than 100 platelets × 10(9)/L increased the eltrombopag dose to 75 mg for 3 weeks. Major responses (platelet count of at least 100 × 10(9)/L or 3 times the baseline value) were obtained in 8 patients, minor responses (platelet counts at least twice the baseline value) in 3. One patient did not respond. Bleeding tendency disappeared in 8 of 10 patients with bleeding symptoms at baseline. Mild adverse events were reported in 2 patients. The availability of thrombopoietin mimetics opened new prospects in the treatment of inherited thrombocytopenias. This study is registered at www.clinicaltrials.gov as NCT01133860 (European Union Drug Regulating Authorities Clinical Trials number 2008-001903-42).
Keywords: Administration, Oral; Adolescent; Adult; Benzoates; Dose-Response Relationship, Drug; Female; Genetic Predisposition to Disease; Humans; Hydrazines; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Platelet Aggregation; Platelet Count; Pyrazoles; Receptors, Thrombopoietin; Survival Rate; Thrombocytopenia; Treatment Outcome; Young Adult

Emx2 and Foxg1 inhibit gliogenesis and promote neuronogenesis. - Brancaccio, Marco; Pivetta, Chiara; Granzotto, Marilena; Filippis, Carol; Mallamaci, Antonello (Stem Cells, 2010)
Neural stem cells (NSCs) give rise to all cell types forming the cortex: neurons, astrocytes, and oligodendrocytes. The transition from the former to the latter ones takes place via lineage-restricted progenitors in a highly regulated way. This process is mastered by large sets of genes, among which some implicated in central nervous system pattern formation. The aim of this study was to disentangle the kinetic and histogenetic roles exerted by two of these genes, Emx2 and Foxg1, in cortico-cerebral precursors. For this purpose, we set up a new integrated in vitro assay design. Embryonic cortical progenitors were transduced with lentiviral vectors driving overexpression of Emx2 and Foxg1 in NSCs and neuronal progenitors. Cells belonging to different neuronogenic and gliogenic compartments were labeled by spectrally distinguishable fluoroproteins driven by cell type-specific promoters and by cell type-specific antibodies and were scored via multiplex cytofluorometry and immunocytofluorescence. A detailed picture of Emx2 and Foxg1 activities in cortico-cerebral histogenesis resulted from this study. Unexpectedly, we found that both genes inhibit gliogenesis and promote neuronogenesis, through distinct mechanisms, and Foxg1 also dramatically stimulates neurite outgrowth. Remarkably, such activities, alone or combined, may be exploited to ameliorate the neuronal output obtainable from neural cultures, for purposes of cell-based brain repair.
Keywords: Animals; Cell Differentiation; Cell Enlargement; Cells, Cultured; Female; Forkhead Transcription Factors; Homeodomain Proteins; Mice; Nerve Tissue Proteins; Neurogenesis; Neuroglia; Neurons; Stem Cells; Transcription Factors

EULAR/PRINTO/PRES criteria for Henoch-Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part I: Overall methodology and clinical characterisation. - Ruperto, Nicolino; Ozen, Seza; Pistorio, Angela; Dolezalova, Pavla; Brogan, Paul; Cabral, David A; Cuttica, Ruben; Khubchandani, Raju; Lovell, Daniel J; O'Neil, Kathleen M; Quartier, Pierre; Ravelli, Angelo; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To report methodology and overall clinical, laboratory and radiographic characteristics for Henoch-Schönlein purpura (HSP), childhood polyarteritis nodosa (c-PAN), c-Wegener granulomatosis (c-WG) and c-Takayasu arteritis (c-TA) classification criteria. METHODS: The preliminary Vienna 2005 consensus conference, which proposed preliminary criteria for paediatric vasculitides, was followed by a EULAR/PRINTO/PRES - supported validation project divided into three main steps. Step 1: retrospective/prospective web-data collection for HSP, c-PAN, c-WG and c-TA, with age at diagnosis <or=18 years. Step 2: blinded classification by consensus panel of a subgroup of 280 cases (128 difficult cases, 152 randomly selected) enabling expert diagnostic verification. Step 3: Ankara 2008 Consensus Conference and statistical evaluation (sensitivity, specificity, area under the curve, kappa-agreement) using as 'gold standard' the final consensus classification or original treating physician diagnosis. RESULTS: A total of 1183/1398 (85%) samples collected were available for analysis: 827 HSP, 150 c-PAN, 60 c-WG, 87 c-TA and 59 c-other. Prevalence, signs/symptoms, laboratory, biopsy and imaging reports were consistent with the clinical picture of the four c-vasculitides. A representative subgroup of 280 patients was blinded to the treating physician diagnosis and classified by a consensus panel, with a kappa-agreement of 0.96 for HSP (95% CI 0.84 to 1), 0.88 for c-WG (95% CI 0.76 to 0.99), 0.84 for c-TA (95% CI 0.73 to 0.96) and 0.73 for c-PAN (95% CI 0.62 to 0.84), with an overall kappa of 0.79 (95% CI 0.73 to 0.84). CONCLUSION: EULAR/PRINTO/PRES propose validated classification criteria for HSP, c-PAN, c-WG and c-TA, with substantial/almost perfect agreement with the final consensus classification or original treating physician diagnosis.
Keywords: Adolescent; Biopsy; Child; Delphi Technique; Granulomatosis with Polyangiitis; Humans; International Cooperation; Internet; Polyarteritis Nodosa; Purpura, Schoenlein-Henoch; Reproducibility of Results; Takayasu Arteritis

Expression and association data strongly support JARID2 involvement in nonsyndromic cleft lip with or without cleft palate. - Scapoli, Luca; Martinelli, Marcella; Pezzetti, Furio; Palmieri, Annalisa; Girardi, Ambra; Savoia, Anna; Bianco, Anna Monica; Carinci, Francesco (Hum Mutat, 2010)
Nonsyndromic cleft lip with or without cleft palate (CL/P) affects approximately 1 in 1,000 births. Genetic studies have provided evidence for the role of several genes and candidate loci in clefting; however, conflicting results have frequently been obtained and much have to be done to unravel the complex genetics of CL/P. In the present investigation we have focused on the candidate region in 6p23, a region that have been found linked to CL/P in several investigations, in the attempt to find out the susceptibility gene provisionally named OFC1. Gene expression experiments in mice embryo of positional candidate genes revealed that JARID2 was highly and specifically expressed in epithelial cells in merging palatal shelves. A family-based linkage disequilibrium study confirmed the pivotal role of JARID2 in orofacial development and strongly supports a role for this gene in CL/P etiology (multiallelic haplotype test P=6 x 10(-5)). Understanding the molecular role of JARID2 within facial development may offer additional information to further unravel the complex genetics of CL/P.
Keywords: Animals; Cleft Lip; Cleft Palate; DNA Mutational Analysis; Family Health; Female; Gene Expression; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Haplotypes; Humans; In Situ Hybridization; Linkage Disequilibrium; Male; Mice; Mice, Inbred C57BL; Mutation; Nerve Tissue Proteins; Palate; Polycomb Repressive Complex 2; Polymorphism, Single Nucleotide; Pregnancy; Reverse Transcriptase Polymerase Chain Reaction

Five new OTOF gene mutations and auditory neuropathy. - Zadro, Cristina; Ciorba, Andrea; Fabris, Annalisa; Morgutti, Marcello; Trevisi, Patrizia; Gasparini, Paolo; Martini, Alessandro (Int J Pediatr Otorhinolaryngol, 2010)
OBJECTIVE: Purpose of this paper is to analyse OTOF gene in a series of subjects affected by auditory neuropathy. METHODS: Four children showing mild to profound prelingual deafness, confirmed by the absence of a clear and detectable responses at auditory brainstem responses (ABR), associated with the presence of bilateral OAE, were enrolled in the study. RESULTS AND CONCLUSIONS: Genetic analysis identified five new mutations (a nonsense, a small and a large deletion and two splicing site mutations), and one missense mutation (F1795C) previously described. These results further confirm the role of OTOF gene in auditory neuropathy. In the absence of a context of neurological syndrome, the combination of absent ABR and positive OAE responses should lead to an auditory neuropathy diagnosis and to a mutational screening in OTOF.
Keywords: Auditory Diseases, Central; Deafness; Evoked Potentials, Auditory, Brain Stem; Female; Humans; Male; Membrane Proteins; Mutation; Otoacoustic Emissions, Spontaneous; Polymerase Chain Reaction

Follow-up and quality of life of patients with cryopyrin-associated periodic syndromes treated with Anakinra. - Lepore, Loredana; Paloni, Giulia; Caorsi, Roberta; Alessio, Maria; Rigante, Donato; Ruperto, Nicola; Cattalini, Marco; Tommasini, Alberto; Zulian, Francesco; Ventura, Alessando; Martini, Alberto; Gattorno, Marco (J Pediatr, 2010)
OBJECTIVE: To evaluate the quality of life and long-term follow-up of patients enrolled in the Italian registry of cryopyrin-associated periodic syndromes (CAPS). STUDY DESIGN: Since 2004, 20 patients with CAPS were enrolled in a common registry from different Italian Centers of Pediatric Rheumatology; 14 patients were treated with Anakinra in an open fashion. Both treated and untreated patients were routinely followed according to standard of care. The Child Health Questionnaire (CHQ-PF 50) was used to assess the health-related quality of life. RESULTS: The mean duration of follow-up was 37.5 months. In all treated patients, a complete and persistent control of the inflammatory manifestations was observed with no further progression of the disease. At enrollment in the registry, patients showed a poorer health-related quality of life than healthy children in both physical and the psychosocial summary scores. Treatment was associated with a dramatic and sustained amelioration of a variety of measures of poor quality of life, particularly in those concerning the global health perception, bodily pain-discomfort, and other physical domains. CONCLUSIONS: Long-term IL-1 blockade produces a significant and persistent improvement in the clinical manifestations associated with the disease and on the overall quality of life.
Keywords: Adolescent; Adult; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Follow-Up Studies; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-1; Male; Phenotype; Quality of Health Care; Quality of Life; Questionnaires; Syndrome; Treatment Outcome

A G to C transversion at the last nucleotide of exon 25 of the MYH9 gene results in a missense mutation rather than in a splicing defect. - Vettore, Silvia; De Rocco, Daniela; Gerber, Bernhard; Scandellari, Raffaella; Bianco, Anna Monica; Balduini, Carlo L; Pecci, Alessandro; Fabris, Fabrizio; Savoia, Anna (Eur J Med Genet, 2010)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant disorder caused by mutations in MYH9, the gene encoding the heavy chain of non-muscle myosin IIA. Patients present with congenital macrothrombocytopenia and inclusion bodies in neutrophils and might develop sensorineural deafness, presenile cataract, and/or progressive nephropathy leading to end-stage renal failure. In two families with macrothrombocytopenia we identified a novel c.3485G > C mutation in the last nucleotide of exon 25. Bioinformatic tools for splice site prediction and minigene functional test predicted splicing anomalies of exon 25. However, analysis of RNA purified from patient's peripheral blood did not allowed us to detect any anomalies, suggesting that RNA processing is correct at least in this tissue. Therefore, we concluded that c.3485G > C leads to a novel missense mutation (p.Arg1162Thr) of myosin-9, which resulted to be slightly degraded in patient platelets. A precise definition of the effect of mutations is fundamental to improve our knowledge into the pathogenetic mechanisms responsible for the disease.
Keywords: Adolescent; Adult; Blood Platelets; Computational Biology; Exons; Female; Humans; Inclusion Bodies; Kidney Failure, Chronic; Molecular Motor Proteins; Mutation, Missense; Myosin Heavy Chains; Neutrophils; Nonmuscle Myosin Type IIA; Nucleotides; RNA Splicing; Thrombocytopenia

Hot water and preparation of infant formula: how hot does it have to be to be safe? - Davanzo, Riccardo; Giurici, Nagua; Demarini, Sergio (J Pediatr Gastroenterol Nutr, 2010)
Keywords: Guidelines as Topic; Hot Temperature; Humans; Infant; Infant Formula; Water; World Health Organization

[Human papillomavirus cervical infection: viral genotyping and risk factors for high-grade squamous intraepithelial lesion and cervix cancer]. - de Mendonça, Vilma Guimarães; Guimarães, Maria José Bezerra; de Lima Filho, José Luiz; de Mendonça, Carolina Guimarães; Martins, Danyelly Bruneska Gondim; Crovella, Sergio; de Alencar, Luiz Cláudio Arraes (Rev Bras Ginecol Obstet, 2010)
PURPOSE: to analyze the characteristics of viral infection and the risk factors for high-grade squamous intraepithelial lesion and cervical carcinoma in women with cervical HPV infection. METHODS: a case-control study was conducted on women with cervical HPV at a Gynecology reference service enrolled at the Public Health System, located in Recife, Northeastern Brazil. The groups of cases (72 women with high-grade squamous intraepithelial lesion or cervical cancer) and controls (176 women with normal Pap smear or benign alterations) were investigated for six viral genotypes (HPV 16, 18, 31, 33, 6, 11) in ecto- and endocervical material using MY09/MY11 primers. The independent variables were ranked in three levels of determination: distal (sociodemographic), intermediate (behavioral) and proximal (previous Pap smear). The homogeneity of proportions was tested (χ2), unadjusted Odds Ratios (OR) were obtained and hierarchical logistic regression was applied to the final model, with adjustment of the effect of each variable to the outcome based on the variables in the same and previous levels of causality. RESULTS: the viral genotype of cervical infection was identified in 76.6% of the 248 women participating in the study. High-risk HPV genotypes (83.4% of cases and 67.1% of controls) were predominant, especially HPV 16 and 31. The distal risk factors identified were: living in a rural area (OR=2.71, 95%CI: 1.18-6.23), less than three years of study (OR=3.97, 95%CI: 2.09-7.54) and family income below two minimum wages (OR=3.30, 95%CI: 1.04-10.51); intermediate: four or more pregnancies (OR=2.00, 95%CI: 1.06-3.76); and proximal: absence of a previous Pap smear (OR=9.74, 95%CI: 2.48-38.28). CONCLUSIONS: genotypes 16 and 31 of cervical HPV infection are predominant among women assisted by the Public Health System in Northeastern Brazil. Socioeconomic and reproductive factors, as well as the absence of cytological screening, represent risk factors for the progression of infection to high-grade squamous intraepithelial lesion and cervical cancer.
Keywords: Adult; Carcinoma in Situ; Case-Control Studies; Female; Genotype; Humans; Papillomaviridae; Papillomavirus Infections; Risk Factors; Socioeconomic Factors; Uterine Cervical Neoplasms

Incidence of bacteremias and invasive mycoses in children with acute non-lymphoblastic leukemia: results from a multi-center Italian study. - Castagnola, Elio; Rossi, Mario R; Cesaro, Simone; Livadiotti, Susanna; Giacchino, Mareva; Zanazzo, Giulio; Fioredda, Francesca; Beretta, Chiara; Ciocchello, Francesca; Carli, Modesto; Putti, Maria Caterina; Pansini, Valeria; et al. (Pediatr Blood Cancer, 2010)
BACKGROUND: Data on the epidemiology of bacteremias and invasive fungal diseases (IFD) in children with acute myeloid leukemia (AML) are scarce. DESIGN AND METHODS: In a multi-center, retrospective study, we analyzed proportion, rate per 1,000 person-days at risk, and cumulative risk of bacteremias and IFD in children with AML. RESULTS: Between January 1998 and December 2005, 240 children were treated for AML at 8 Italian Centers, for a total of 521 treatment courses and 63,232 person-days at risk. Bacteremia was observed in 32% of treatment courses and IFD was seen in 10% (P < 0.0001), with rates of 2.62 and 0.84, respectively (P < 0.001). There was a significantly higher frequency of IFD during relapse treatment: proportion 15% versus 9% (P = 0.05), rate 2.10 versus 0.64 (P = 0.008) and cumulative risk 32% versus 12% (P = 0.007), while there were no differences in the proportion, rate and cumulative risk of bacteremia during front-line or relapse treatment. The epidemiology of bacteremias and IFD was different during front-line therapy for M3 as compared to other types of AML, but the differences were not statistically significant. CONCLUSIONS: Severe infectious complications are frequent during the treatment of pediatric AML, especially during relapse treatment, and bacteremias are more frequent than IFD.
Keywords: Antineoplastic Combined Chemotherapy Protocols; Bacteremia; Child; Female; Follow-Up Studies; Humans; Incidence; Italy; Leukemia, Myeloid, Acute; Male; Mycoses; Neoplasm Recurrence, Local; Retrospective Studies

Individual differences in prefrontal cortex activity during perception of bitter taste using fNIRS methodology. - Bembich, Stefano; Lanzara, Carmela; Clarici, Andrea; Demarini, Sergio; Tepper, Beverly J; Gasparini, Paolo; Grasso, Domenico L (Chem Senses, 2010)
Although bitter taste has a crucial role in nutrition by preventing the ingestion of toxic foods, there are few studies on bitter taste neuroimaging. To identify cortical areas involved in bitter taste perception and to determine if individual differences in taste sensitivity to 6-n-propylthiouracil (PROP) are represented in the brain by different cortical activation patterns, we examined 48 healthy volunteers using functional near-infrared spectroscopy. Participants rated the perceived intensity of filter paper disks impregnated with PROP and NaCl during the imaging procedure and were then classified as PROP tasters and nontasters. We monitored cortical activity in both the anterior and posterior regions of the dorsolateral prefrontal cortex (DLPFC) and in the ventrolateral prefrontal cortex (VLPFC). No activity was detected in the anterior DLPFC in any of the participants. However, during the administration of PROP, significant cortical activation was detected in the more posterior regions of the left DLPFC and in the left and right VLPFC but only in PROP tasters. PROP nontasters showed no cortical activity in these areas. These data suggest that the prefrontal cortex is involved in the conscious perception of the bitter taste of PROP and that the pattern of activity is consistent with individual differences in the ability to taste this compound. Thus, the PROP phenotype is associated with fundamental differences in cortical taste processing.
Keywords: Adult; Eating; Female; Food Preferences; Humans; Individuality; Male; Perception; Phenotype; Prefrontal Cortex; Propylthiouracil; Sodium Chloride; Spectroscopy, Near-Infrared; Taste; Taste Threshold; Young Adult

Insights into the binding of Phenyltiocarbamide (PTC) agonist to its target human TAS2R38 bitter receptor. - Biarnés, Xevi; Marchiori, Alessandro; Giorgetti, Alejandro; Lanzara, Carmela; Gasparini, Paolo; Carloni, Paolo; Born, Stephan; Brockhoff, Anne; Behrens, Maik; Meyerhof, Wolfgang (PLoS One, 2010)
Humans' bitter taste perception is mediated by the hTAS2R subfamily of the G protein-coupled membrane receptors (GPCRs). Structural information on these receptors is currently limited. Here we identify residues involved in the binding of phenylthiocarbamide (PTC) and in receptor activation in one of the most widely studied hTAS2Rs (hTAS2R38) by means of structural bioinformatics and molecular docking. The predictions are validated by site-directed mutagenesis experiments that involve specific residues located in the putative binding site and trans-membrane (TM) helices 6 and 7 putatively involved in receptor activation. Based on our measurements, we suggest that (i) residue N103 participates actively in PTC binding, in line with previous computational studies. (ii) W99, M100 and S259 contribute to define the size and shape of the binding cavity. (iii) W99 and M100, along with F255 and V296, play a key role for receptor activation, providing insights on bitter taste receptor activation not emerging from the previously reported computational models.
Keywords: Amino Acid Sequence; Calcium; Cell Line; Computational Biology; Dose-Response Relationship, Drug; Humans; Intracellular Space; Ligands; Models, Molecular; Molecular Sequence Data; Mutagenesis, Site-Directed; Phenylthiourea; Protein Binding; Protein Structure, Secondary; Receptors, G-Protein-Coupled

Methotrexate withdrawal at 6 vs 12 months in juvenile idiopathic arthritis in remission: a randomized clinical trial. - Foell, Dirk; Wulffraat, Nico; Wedderburn, Lucy R; Wittkowski, Helmut; Frosch, Michael; Gerss, Joachim; Stanevicha, Valda; Mihaylova, Dimitrina; Ferriani, Virginia; Tsakalidou, Florence Kanakoudi; Foeldvari, Ivan; Cuttica, Ruben; et al. (JAMA, 2010)
CONTEXT: Novel therapies have improved the remission rate in chronic inflammatory disorders including juvenile idiopathic arthritis (JIA). Therefore, strategies of tapering therapy and reliable parameters for detecting subclinical inflammation have now become challenging questions. OBJECTIVES: To analyze whether longer methotrexate treatment during remission of JIA prevents flares after withdrawal of medication and whether specific biomarkers identify patients at risk for flares. DESIGN, SETTING, AND PATIENTS: Prospective, open, multicenter, medication-withdrawal randomized clinical trial including 364 patients (median age, 11.0 years) with JIA recruited in 61 centers from 29 countries between February 2005 and June 2006. Patients were included at first confirmation of clinical remission while continuing medication. At the time of therapy withdrawal, levels of the phagocyte activation marker myeloid-related proteins 8 and 14 heterocomplex (MRP8/14) were determined. INTERVENTION: Patients were randomly assigned to continue with methotrexate therapy for either 6 months (group 1 [n = 183]) or 12 months (group 2 [n = 181]) after induction of disease remission. MAIN OUTCOME MEASURES: Primary outcome was relapse rate in the 2 treatment groups; secondary outcome was time to relapse. In a prespecified cohort analysis, the prognostic accuracy of MRP8/14 concentrations for the risk of flares was assessed. RESULTS: Intention-to-treat analysis of the primary outcome revealed relapse within 24 months after the inclusion into the study in 98 of 183 patients (relapse rate, 56.7%) in group 1 and 94 of 181 (55.6%) in group 2. The odds ratio for group 1 vs group 2 was 1.02 (95% CI, 0.82-1.27; P = .86). The median relapse-free interval after inclusion was 21.0 months in group 1 and 23.0 months in group 2. The hazard ratio for group 1 vs group 2 was 1.07 (95% CI, 0.82-1.41; P = .61). Median follow-up duration after inclusion was 34.2 and 34.3 months in groups 1 and 2, respectively. Levels of MRP8/14 during remission were significantly higher in patients who subsequently developed flares (median, 715 [IQR, 320-1 110] ng/mL) compared with patients maintaining stable remission (400 [IQR, 220-800] ng/mL; P = .003). Low MRP8/14 levels indicated a low risk of flares within the next 3 months following the biomarker test (area under the receiver operating characteristic curve, 0.76; 95% CI, 0.62-0.90). CONCLUSIONS: In patients with JIA in remission, a 12-month vs 6-month withdrawal of methotrexate did not reduce the relapse rate. Higher MRP8/14 concentrations were associated with risk of relapse after discontinuing methotrexate. TRIAL REGISTRATION: isrctn.org Identifier: ISRCTN18186313.
Keywords: Adolescent; Antirheumatic Agents; Arthritis, Juvenile; ATP-Binding Cassette Transporters; Calgranulin B; Child; Child, Preschool; Female; Humans; Infant; Male; Methotrexate; Predictive Value of Tests; Prospective Studies; Recurrence; Remission Induction

Mode of delivery in HIV-infected pregnant women and prevention of mother-to-child transmission: changing practices in Western Europe. - Boer, K; England, K; Godfried, M H; Thorne, C (HIV Med, 2010)
OBJECTIVES: The aim of the study was to examine temporal and geographical patterns of mode of delivery in the European Collaborative Study (ECS), identify factors associated with elective caesarean section (CS) delivery in the highly active antiretroviral therapy (HAART) era and explore associations between mode of delivery and mother-to-child transmission (MTCT). METHODS: The ECS is a cohort study in which HIV-infected pregnant women are enrolled and their infants prospectively followed. Data on 5238 mother-child pairs (MCPs) enrolled in Western European ECS sites between 1985 and 2007 were analysed. RESULTS: The elective CS rate increased from 16% in 1985-1993 to 67% in 1999-2001, declining to 51% by 2005-2007. In 2002-2004, 10% of infants were delivered vaginally, increasing to 34% by 2005-2007. During the HAART era, women in Belgium, the United Kingdom and the Netherlands were less likely to deliver by elective CS than those in Italy and Spain [adjusted odds ratio (AOR) 0.07; 95% confidence interval (CI) 0.04-0.12]. The MTCT rate in 2005-2007 was 1%. Among MCPs with maternal HIV RNA<400 HIV-1 RNA copies/mL (n=960), elective CS was associated with 80% decreased MTCT risk (AOR 0.20; 95% CI 0.05-0.65) adjusting for HAART and prematurity. Two infants born to 559 women with viral loads <50 copies/mL were infected, one of whom was delivered by elective CS (MTCT rate 0.4%; 95% CI 0.04-1.29). CONCLUSIONS: Our findings suggest that elective CS prevents MTCT even at low maternal viral loads, but the study was insufficiently powered to enable a conclusion to be drawn as to whether this applies for viral loads <50 copies/mL. Diverging mode of delivery patterns in Europe reflect uncertainties regarding the risk-benefit balance of elective CS for women on successful HAART.
Keywords: Adult; Antiretroviral Therapy, Highly Active; Cesarean Section; Delivery, Obstetric; Epidemiologic Methods; Europe; Female; HIV Infections; Humans; Infant; Infant, Newborn; Infectious Disease Transmission, Vertical; Pregnancy; Pregnancy Complications, Infectious; Premature Birth; Prenatal Care; Reverse Transcriptase Inhibitors; Substance Abuse, Intravenous; Viral Load; Young Adult; Zidovudine

MYH9-related disease: Report on five German families and description of a novel mutation. - Savoia, Anna; Germeshausen, Manuela; De Rocco, Daniela; Henschel, Bettina; Kratz, Christian P; Kuhlen, Michaela; Rath, Bettina; Steuhl, Klaus-Peter; Wermes, Cornelia; Ballmaier, Matthias (Ann Hematol, 2010)
Keywords: Adult; Aged; Child; Chromosome Disorders; DNA Mutational Analysis; Germany; Humans; Infant; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Young Adult

Oxidative stress-based cytotoxicity of delphinidin and cyanidin in colon cancer cells. - Cvorovic, Jovana; Tramer, Federica; Granzotto, Marilena; Candussio, Luigi; Decorti, Giuliana; Passamonti, Sabina (Arch Biochem Biophys, 2010)
Colorectal cancer is the second most frequent cause of cancer death in the western world. Although the prognosis has improved after the introduction of newer anticancer drugs, the treatment of metastatic colorectal cancer still remains a challenge due to a high percentage of drug-resistant tumor forms. We aimed at testing whether anthocyanidins exerted cytotoxicity in primary (Caco-2) and metastatic (LoVo and LoVo/ADR) colorectal cancer cell lines. Both cyanidin and delphinidin, though neither pelargonidin nor malvidin, were cytotoxic in metastatic cells only. The cell line most sensitive to anthocyanidins was the drug-resistant LoVo/ADR. There, cellular ROS accumulation, inhibition of glutathione reductase, and depletion of glutathione could be observed. This suggests that anthocyanidins may be used as sensitizing agents in metastatic colorectal cancer therapy.
Keywords: Anthocyanins; Antioxidants; Apoptosis; Caco-2 Cells; Camptothecin; Cell Line, Tumor; Colonic Neoplasms; Drug Resistance, Neoplasm; Glutathione; Glutathione Reductase; Humans; Oxidants; Oxidative Stress

Predictors of poor response to methotrexate in polyarticular-course juvenile idiopathic arthritis: analysis of the PRINTO methotrexate trial. - Vilca, Iris; Munitis, Pablo Garcia; Pistorio, Angela; Ravelli, Angelo; Buoncompagni, Antonella; Bica, Blanca; Campos, Lucia; Häfner, Renate; Hofer, Michael; Ozen, Seza; Huemer, Christian; Bae, Sang Cheol; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To determine whether baseline demographic, clinical, articular and laboratory variables predict methotrexate (MTX) poor response in polyarticular-course juvenile idiopathic arthritis. METHODS: Patients newly treated for 6 months with MTX enrolled in the Paediatric Rheumatology International Trials Organization (PRINTO) MTX trial. Bivariate and logistic regression analyses were used to identify baseline predictors of poor response according to the American College of Rheumatology pediatric (ACR-ped) 30 and 70 criteria. RESULTS: In all, 405/563 (71.9%) of patients were women; median age at onset and disease duration were 4.3 and 1.4 years, respectively, with anti-nuclear antibody (ANA) detected in 259/537 (48.2%) patients. With multivariate logistic regression analysis, the most important determinants of ACR-ped 70 non-responders were: disease duration > 1.3 years (OR 1.93), ANA negativity (OR 1.77), Childhood Health Assessment Questionnaire (CHAQ) disability index > 1.125 (OR 1.65) and the presence of right and left wrist activity (OR 1.55). Predictors of ACR-ped 30 non-responders were: ANA negativity (OR 1.92), CHAQ disability index > 1.14 (OR 2.18) and a parent's evaluation of child's overall well-being < or = 4.69 (OR 2.2). CONCLUSION: The subgroup of patients with longer disease duration, ANA negativity, higher disability and presence of wrist activity were significantly associated with a poorer response to a 6-month MTX course.
Keywords: Adolescent; Antibodies, Antinuclear; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Disability Evaluation; Female; Follow-Up Studies; Humans; Immunosuppressive Agents; Male; Methotrexate; Prognosis; Treatment Outcome

Prepregnancy BMI influences maternal and fetal outcomes in women with isolated gestational hyperglycaemia: a multicentre study. - Lapolla, A; Bonomo, M; Dalfrà, M G; Parretti, E; Mannino, D; Mello, G; Di Cianni, G (Diabetes Metab, 2010)
AIM: This multicentre study analyzed the maternal and fetal outcomes of women who had one elevated 3-h oral glucose tolerance test (isolated gestational hyperglycaemia [IGH]). METHODS: From 1999 to 2003, data were collected for 606 IGH women from 31 Italian obstetric or diabetic centres, including time and mode of delivery, gestational hypertension, preeclampsia, eclampsia, congenital malformations, and neonatal mortality and morbidity, to compare them with the general pregnant Italian population. A prognostic model for the outcome of pregnancy was constructed, and the concurrence of certain specified conditions was considered a positive outcome, whereas pregnancies that failed to meet one or more of the stated conditions were classified as "complicated". RESULTS: Macrosomia was significantly more frequent in women with IGH than in the normal pregnant population (10.7 vs 7.4%, respectively; P=0.003). Stillbirth and neonatal mortality rates did not differ from those in normal pregnancies, while a slight rise in the frequency of major malformations was not statistically significant (1.48 vs 0.89%, respectively; P<0.11). Multivariate logistic analyses confirmed that the prepregnancy body mass index (BMI) was an independent predictor of a complicated pregnancy. As for fetal growth, multivariate logistic analyses according to BMI showed that being overweight or obese were strong predictors of macrosomia. CONCLUSION: These findings in a large cohort of Italian women with IGH confirm the detrimental effect of even minimally altered glucose tolerance on fetal outcome. Also, prepregnancy obesity plays an important role in raising the risk of adverse perinatal outcomes in such patients.
Keywords: Adult; Blood Glucose; Body Mass Index; Female; Fetal Macrosomia; Glucose Tolerance Test; Humans; Hyperglycemia; Italy; Models, Statistical; Obesity; Pregnancy; Pregnancy Complications; Pregnancy Outcome; Prognosis; Retrospective Studies; Risk Factors; Time Factors

Progress towards the achievement of MDG4 in the Commonwealth of Independent States: uncertain data, clear priorities. - Cattaneo, Adriano; Gafurov, Ilkhom; Bomestar, Tamara; Bacci, Marianna; Kumar, Sanjiv; Popovic, Dragoslav; Tamburlini, Giorgio (Health Res Policy Syst, 2010)
Data on under five mortality in the twelve countries of the Commonwealth of Independent States show important fluctuations over time due to variations in quality of data, definitions of neonatal deaths and methods of mortality estimation. Despite the uncertainties regarding mortality trends, the analysis of health and social information from different sources offers clues to identify priority areas and key strategic directions for accelerating the achievement of the 4th Millennium Development Goal. Neonatal deaths represent from 40% to over 50% of under five deaths in all these countries. Maternal mortality was above 50 per 100,000 in 2005, despite the good coverage with antenatal care and births assisted by skilled birth attendants. The scanty information on quality of perinatal care indicates widespread substandard care at all levels. Stunting in children under five is above 10% in ten out of twelve countries and coexists with emerging overweight. Exclusivity and duration of breastfeeding fall short of what is recommended. There are important inequalities in child and maternal mortality, malnutrition and access and use of health services within countries. Taken as a whole, the available information clearly indicates that priority should be given to improvement of the health of women in reproductive age and of the quality of perinatal care, including the establishment of reliable data collection systems. To achieve this, action will need to focus on strengthening the capacity of the health system to improve the technical content of service provision, and on improving access and appropriate use of services by the most disadvantaged groups. The involvement of other sectors will be necessary to improve reproductive health and nutrition at community level and to tackle inequity. Comparisons between countries with similar socioeconomic background but different health policies seem to indicate that gradual progression towards universal coverage with essential health care through a national health insurance system is associated with larger reduction of child mortality than troubled transition towards a privatized and unregulated health system.

Screening for GJB2 and GJB6 gene mutations in patients from Campania region with sensorineural hearing loss. - Chinetti, Viviana; Iossa, Sandra; Auletta, Gennaro; Laria, Carla; De Luca, Maria; Di Leva, Francesca; Riccardi, Pasquale; Giannini, Pasquale; Gasparini, Paolo; Ciccodicola, Alfredo; Marciano, Elio; Franzè, Annamaria (Int J Audiol, 2010)
The aim of this study was to screen 349 patients affected by sensorineural hearing loss (SNHL), mostly from the Campania region (southern Italy), for GJB2 gene mutations and for two deletions of the GJB6 gene (del GJB6 -D13S1830 and del GJB6 -D13S1854). We identified pathogenetic GJB2 mutations in 51 cases (15% of patients). No GJB6 mutation was found. We also examined the audiologic features of the patients for whom we had an etiologic diagnosis, in order to identify correlations between the severity of hearing loss and the type of mutation.
Keywords: Acoustic Stimulation; Adolescent; Adult; Audiometry; Auditory Perception; Child; Child, Preschool; Connexins; Genetic Predisposition to Disease; Genetic Testing; Hearing Loss, Sensorineural; Heterozygote; Homozygote; Humans; Italy; Mass Screening; Middle Aged; Mutation; Phenotype; Risk Factors; Severity of Illness Index; Young Adult

Severe X-linked mitochondrial encephalomyopathy associated with a mutation in apoptosis-inducing factor. - Ghezzi, Daniele; Sevrioukova, Irina; Invernizzi, Federica; Lamperti, Costanza; Mora, Marina; d'Adamo, Pio; Novara, Francesca; Zuffardi, Orsetta; Uziel, Graziella; Zeviani, Massimo (Am J Hum Genet, 2010)
We investigated two male infant patients who were given a diagnosis of progressive mitochondrial encephalomyopathy on the basis of clinical, biochemical, and morphological features. These patients were born from monozygotic twin sisters and unrelated fathers, suggesting an X-linked trait. Fibroblasts from both showed reduction of respiratory chain (RC) cIII and cIV, but not of cI activities. We found a disease-segregating mutation in the X-linked AIFM1 gene, encoding the Apoptosis-Inducing Factor (AIF) mitochondrion-associated 1 precursor that deletes arginine 201 (R201 del). Under normal conditions, mature AIF is a FAD-dependent NADH oxidase of unknown function and is targeted to the mitochondrial intermembrane space (this form is called AIF(mit)). Upon apoptogenic stimuli, a soluble form (AIF(sol)) is released by proteolytic cleavage and migrates to the nucleus, where it induces "parthanatos," i.e., caspase-independent fragmentation of chromosomal DNA. In vitro, the AIF(R201 del) mutation decreases stability of both AIF(mit) and AIF(sol) and increases the AIF(sol) DNA binding affinity, a prerequisite for nuclear apoptosis. In AIF(R201 del) fibroblasts, staurosporine-induced parthanatos was markedly increased, whereas re-expression of AIF(wt) induced recovery of RC activities. Numerous TUNEL-positive, caspase 3-negative nuclei were visualized in patient #1's muscle, again indicating markedly increased parthanatos in the AIF(R201 del) critical tissues. We conclude that AIF(R201 del) is an unstable mutant variant associated with increased parthanatos-linked cell death. Our data suggest a role for AIF in RC integrity and mtDNA maintenance, at least in some tissues. Interestingly, riboflavin supplementation was associated with prolonged improvement of patient #1's neurological conditions, as well as correction of RC defects in mutant fibroblasts, suggesting that stabilization of the FAD binding in AIF(mit) is beneficial.
Keywords: Apoptosis; Apoptosis Inducing Factor; Caspase 3; Computer Simulation; Dietary Supplements; DNA Primers; DNA, Mitochondrial; Electron Transport; Female; Fibroblasts; Flavin-Adenine Dinucleotide; Genes, X-Linked; Humans; In Situ Nick-End Labeling; Infant, Newborn; Magnetic Resonance Imaging; Male; Mitochondrial Encephalomyopathies; Muscle, Skeletal; Mutation; Nervous System Diseases; Pedigree; Poly(ADP-ribose) Polymerases; Protein Conformation; Riboflavin; Staurosporine; Twins, Monozygotic

Splenomegaly as presentation of a wandering spleen. - Maschio, Massimo; Cozzi, Giorgio; Sanabor, Daniela; Zennaro, Floriana; Gloria, Pelizzo; Barbi, Egidio (J Pediatr, 2010)
Keywords: Child; Female; Humans; Splenomegaly; Wandering Spleen

[Strategies for cardiovascular prevention in children]. - Spinelli, Angela; Nardone, Paola; Lamberti, Anna; Baglio, Giovanni (G Ital Cardiol (Rome), 2010)
Keywords: Body Mass Index; Cardiovascular Diseases; Child; Diet, Mediterranean; Food Habits; Humans; Life Style; Motor Activity; Obesity; Overweight; Patient Education as Topic; Population Surveillance; Questionnaires; Risk Factors

Therapeutic strategy in p47-phox deficient chronic granulomatous disease presenting as inflammatory bowel disease. - Freudenberg, Folke; Wintergerst, Uwe; Roesen-Wolff, Angela; Albert, Michael H; Prell, Christine; Strahm, Brigitte; Koletzko, Sibylle; Ehl, Stephan; Roos, Dirk; Tommasini, Alberto; Ventura, Alessandro; Belohradsky, Bernd H; et al. (J Allergy Clin Immunol, 2010)
Keywords: Age of Onset; Anti-Bacterial Agents; Antibodies, Monoclonal; Child; Drug Therapy, Combination; Gene Deletion; Granulomatous Disease, Chronic; Humans; Inflammatory Bowel Diseases; Male; NADPH Oxidase; Steroids; Treatment Outcome; Vidarabine

Thirty new loci for age at menarche identified by a meta-analysis of genome-wide association studies. - Elks, Cathy E; Perry, John R B; Sulem, Patrick; Chasman, Daniel I; Franceschini, Nora; He, Chunyan; Lunetta, Kathryn L; Visser, Jenny A; Byrne, Enda M; Cousminer, Diana L; Gudbjartsson, Daniel F; Esko, Tõnu; et al. (Nat Genet, 2010)
To identify loci for age at menarche, we performed a meta-analysis of 32 genome-wide association studies in 87,802 women of European descent, with replication in up to 14,731 women. In addition to the known loci at LIN28B (P = 5.4 × 10⁻⁶⁰) and 9q31.2 (P = 2.2 × 10⁻³³), we identified 30 new menarche loci (all P < 5 × 10⁻⁸) and found suggestive evidence for a further 10 loci (P < 1.9 × 10⁻⁶). The new loci included four previously associated with body mass index (in or near FTO, SEC16B, TRA2B and TMEM18), three in or near other genes implicated in energy homeostasis (BSX, CRTC1 and MCHR2) and three in or near genes implicated in hormonal regulation (INHBA, PCSK2 and RXRG). Ingenuity and gene-set enrichment pathway analyses identified coenzyme A and fatty acid biosynthesis as biological processes related to menarche timing.
Keywords: Adolescent; Aging; Body Height; Body Size; Child; DNA Copy Number Variations; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inheritance Patterns; Menarche; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Time Factors

Two cases of Noonan syndrome with severe respiratory and gastroenteral involvement and the SOS1 mutation F623I. - Fabretto, Antonella; Kutsche, Kerstin; Harmsen, May-Britt; Demarini, Sergio; Gasparini, Paolo; Fertz, Maria Cristina; Zenker, Martin (Eur J Med Genet, 2010)
Noonan syndrome (NS) is an autosomal dominant, inherited disorder characterized by facial dysmorphism, congenital heart defects, and reduced postnatal growth. Dysregulated RAS-MAPK signalling is the common molecular basis for NS, a genetically heterogeneous disease. Germline mutations in genes encoding small GTPases of the RAS family (KRAS and NRAS), modulators of RAS function (PTPN11, SOS1 and SHOC2) or downstream signal transducers (RAF1) are causative for NS. SOS1 is the second major gene for NS after PTPN11. Compared to patients with mutations in other genes, SOS1 mutation-positive individuals in general tend to have a more favorable outcome, with less short stature and cognitive impairment. We describe two unrelated patients with NS carrying the same heterozygous SOS1 missense mutation (c.1867T > A/p.F623I). The phenotype of both patients is remarkable as they show uncommon clinical features such as pulmonary lymphangiectasis, congenital pleural effusions, severe feeding problems, and laryngomalacia. These findings may be related to the specific mutation present in our two patients, or be part of the SOS1 phenotype. Detailed clinical assessment of large cohorts of patients with NS and SOS1 mutation is required to clarify this initial observation.
Keywords: Child, Preschool; Genes, ras; Germ-Line Mutation; Heterozygote; Humans; Infant; Infant, Newborn; Male; Mutation, Missense; Noonan Syndrome; Phenotype; SOS1 Protein

Wired to be social: the ontogeny of human interaction. - Castiello, Umberto; Becchio, Cristina; Zoia, Stefania; Nelini, Cristian; Sartori, Luisa; Blason, Laura; D'Ottavio, Giuseppina; Bulgheroni, Maria; Gallese, Vittorio (PLoS One, 2010)
BACKGROUND: Newborns come into the world wired to socially interact. Is a propensity to socially oriented action already present before birth? Twin pregnancies provide a unique opportunity to investigate the social pre-wiring hypothesis. Although various types of inter-twins contact have been demonstrated starting from the 11(th) week of gestation, no study has so far investigated the critical question whether intra-pair contact is the result of motor planning rather then the accidental outcome of spatial proximity. METHODOLOGY/PRINCIPAL FINDINGS: Kinematic profiles of movements in five pairs of twin foetuses were studied by using four-dimensional ultrasonography during two separate recording sessions carried out at the 14(th) and 18(th) week of gestation. We demonstrate that by the 14th week of gestation twin foetuses do not only display movements directed towards the uterine wall and self-directed movements, but also movements specifically aimed at the co-twin, the proportion of which increases between the 14(th) and 18(th) gestational week. Kinematic analysis revealed that movement duration was longer and deceleration time was prolonged for other-directed movements compared to movements directed towards the uterine wall. Similar kinematic profiles were observed for movements directed towards the co-twin and self-directed movements aimed at the eye-region, i.e. the most delicate region of the body. CONCLUSIONS/SIGNIFICANCE: We conclude that performance of movements towards the co-twin is not accidental: already starting from the 14th week of gestation twin foetuses execute movements specifically aimed at the co-twin.
Keywords: Female; Fetus; Humans; Pregnancy; Social Behavior; Ultrasonography, Prenatal